Constrained Optimization of Charged Particle Tracking with Multi-Agent Reinforcement Learning - Tobias Kortus; Ralf Keidel; Nicolas R. Gauger; Jan Kieseler

Investigating Λ baryon production in p-Pb collisions in jets and the underlying event using angular correlations - Collaboration ALICE; S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Physical Review C, 2025)

Measurement of HΛ3 production in Pb-Pb collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; I. Ahuja; A. Akindinov; et al. (Physics Letters B, 2025)

Measurement of the inclusive isolated-photon production cross section in pp collisions at s=13 TeV - S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (The European Physical Journal C, 2025)

Particle production as a function of charged-particle flattenicity in pp collisions at s=13 TeV - Collaboration ALICE; S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Physical Review D, 2025)

Probing Strangeness Hadronization with Event-by-Event Production of Multistrange Hadrons - Collaboration ALICE; S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Physical Review Letters, 2025)

Rapidity dependence of antideuteron coalescence in pp collisions at s=13 TeV with ALICE - S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; I. Ahuja; A. Akindinov; et al. (Physics Letters B, 2025)

Addendum: Dielectron production in proton-proton and proton-lead collisions at s_NN = 5.02 TeV - Collaboration ALICE; S. Acharya; D. Adamová; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al.

Charm fragmentation fractions and cc cross section in p-Pb collisions at √sNN = 5.02TeV - S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (The European Physical Journal C, 2024)

Development of the trigger-controlling system for the proton computed tomography prototype - N. Ritjoho; P. Phumara; Y. Buanill; P. Boontueng; A. Songmoolnak; N. Laojamnongwong; L. Charoonratana; T. Sanghangthum; D. Röhrich; A. Schilling; M. Aehle; J. Alme; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2024)

Exclusive four pion photoproduction in ultraperipheral Pb-Pb collisions at s_NN = 5.02 TeV - Shreyasi Acharya; Dagmar Adamova; Apar Agarwal; Gianluca Aglieri Rinella; Luca Aglietta; Michelangelo Agnello; Neelima Agrawal; Zubayer Ahammed; Shakeel Ahmad; Sang Un Ahn; Ishaan Ahuja; Alexander Akindinov; et al. (CERN, 2024)

Exploring End-to-end Differentiable Neural Charged Particle Tracking: A Loss Landscape Perspective - Tobias Kortus; Ralf Keidel; Nicolas R. Gauger (arXiv, 2024)

Exploring nuclear structure with multiparticle azimuthal correlations at the LHC - S. Acharya; D. Adamová; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; M. Al-Turany; et al. (arXiv, 2024)

Higher-order symmetry plane correlations in Pb−Pb collisions at √sNN = 5.02 TeV - Collaboration ALICE; S. Acharya; D. Adamová; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (arXiv, 2024)

Investigating strangeness enhancement in jet and medium via φ(1020) production in p-Pb collisions at s_NN=5.020.16em0exTeV - Collaboration ALICE; S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Physical Review C, 2024)

Investigating strangeness enhancement with multiplicity in pp collisions using angular correlations - S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2024)

J/ψ-hadron correlations at midrapidity in pp collisions at s√ = 13 TeV - S. Acharya; D. Adamová; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; M. Al-Turany; et al. (arXiv, 2024)

Measurement of ω meson production in pp collisions at s = 13 TeV - S. Acharya; D. Adamová; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; M. Al-Turany; et al. (2024)

Measurement of beauty production via non-prompt charm hadrons in p-Pb collisions at s_NN = 5.02 TeV - S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2024)

Measurement of f1(1285) production in pp collisions at s√ = 13 TeV - Collaboration ALICE; S. Acharya; D. Adamová; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (ArXiv, 2024)

Measurement of the impact-parameter dependent azimuthal anisotropy in coherent ρ0 photoproduction in Pb-Pb collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; I. Ahuja; A. Akindinov; et al. (Physics Letters B, 2024)

Measurement of the production and elliptic flow of (anti)nuclei in Xe-Xe collisions at s_NN=5.44 TeV - Collaboration ALICE; S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Physical Review C, 2024)

Measurement of Ω0 c baryon production and branching-fraction ratio BR⁡(Ω0 c →Ω−⁢e+⁢𝜈e)/BR⁡(Ω0 c →Ω−⁢𝜋+) in 𝑝⁢𝑝 collisions at √𝑠 =13 Te - Collaboration ALICE; S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Physical Review D, 2024)

Systematic study of flow vector fluctuations in s_NN=5.02 TeV Pb-Pb collisions - Collaboration ALICE; S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Physical Review C, 2024)

Σ (1385)^± resonance production in Pb-Pb collisions at s_NN=5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (The European Physical Journal C, 2023)
Hadronic resonances are used to probe the hadron gas produced in the late stage of heavy-ion collisions since they decay on the same timescale, of the order of 1-10 fm/c, as the decoupling time of the system. In the hadron gas, (pseudo)elastic scatterings among the products of resonances that decayed before the kinetic freeze-out and regeneration processes counteract each other, the net effect depending on the resonance lifetime, the duration of the hadronic phase, and the hadronic cross sections at play. In this context, the Σ(1385)± particle is of particular interest as models predict that regeneration dominates over rescattering despite its relatively short lifetime of about 5.5 fm/c. The first measurement of the Σ(1385)± resonance production at midrapidity in Pb-Pb collisions at 𝑠NN‾‾‾‾√=5.02 TeV with the ALICE detector is presented in this Letter. The resonances are reconstructed via their hadronic decay channel, Λ𝜋, as a function of the transverse momentum (𝑝T) and the collision centrality. The results are discussed in comparison with the measured yield of pions and with expectations from the statistical hadronization model as well as commonly employed event generators, including PYTHIA8/Angantyr and EPOS3 coupled to the UrQMD hadronic cascade afterburner. None of the models can describe the data. For Σ(1385)±, a similar behaviour as K∗(892)0 is observed in data unlike the predictions of EPOS3 with afterburner.

Anisotropic flow and flow fluctuations of identified hadrons in Pb-Pb collisions at s_NN = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2023)
The first measurements of elliptic flow of π±, K±, p+p⎯⎯⎯, K0S, Λ+Λ⎯⎯⎯⎯, ϕ, Ξ−+Ξ⎯⎯⎯⎯+, and Ω−+Ω⎯⎯⎯⎯⎯+ using multiparticle cumulants in Pb-Pb collisions at 𝑠NN‾‾‾‾√ = 5.02 TeV are resented. Results obtained with two- (v22) and four-particle cumulants (v24) are shown as a function of transverse momentum, pT, for various collision centrality intervals. Combining the data for both v22 and v24 also allows us to report the first measurements of the mean elliptic flow, elliptic flow fluctuations, and relative elliptic flow fluctuations for various hadron species. These observables probe the event-by-event eccentricity fluctuations in the initial state and the contributions from the dynamic evolution of the expanding quark-gluon plasma. The characteristic features observed in previous pT-differential anisotropic flow measurements for identified hadrons with two-particle correlations, namely the mass ordering at low pT and the approximate scaling with the number of constituent quarks at intermediate pT, are similarly present in the four-particle correlations and the combinations of v22 and v24. In addition, a particle species dependence of flow fluctuations is observed that could indicate a significant contribution from final state hadronic interactions. The comparison between experimental measurements and CoLBT model calculations, which combine the various physics processes of hydrodynamics, quark coalescence, and jet fragmentation, illustrates their importance over a wide pT range.

Azimuthal correlations of heavy-flavor hadron decay electrons with charged particles in pp and p-Pb collisions at √sNN = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (The European Physical Journal C, 2023)
The azimuthal (Δφ) correlation distributions between heavy-flavor decay electrons and associated charged particles are measured in pp and p-Pb collisions at 𝑠NN‾‾‾‾√=5.02 TeV. Results are reported for electrons with transverse momentum 4<𝑝T<16 GeV/𝑐 and pseudorapidity |𝜂|<0.6. The associated charged particles are selected with transverse momentum 1<𝑝T<7 GeV/𝑐, and relative pseudorapidity separation with the leading electron |Δ𝜂|<1. The correlation measurements are performed to study and characterize the fragmentation and hadronization of heavy quarks. The correlation structures are fitted with a constant and two von Mises functions to obtain the baseline and the near- and away-side peaks, respectively. The results from p-Pb collisions are compared with those from pp collisions to study the effects of cold nuclear matter. In the measured trigger electron and associated particle kinematic regions, the two collision systems give consistent results. The Δφ distribution and the peak observables in pp and p-Pb collisions are compared with calculations from various Monte Carlo event generators.

Constraining the KN coupled channel dynamics using femtoscopic correlations at the LHC - S. Acharya; D. Adamová; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; R. Keidel; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (The European Physical Journal C, 2023)
The interaction of K−with protons is characterised by the presence of several coupled channels, systems like K⎯⎯⎯⎯0n and πΣ with a similar mass and the same quantum numbers as the K−p state. The strengths of these couplings to the K−p system are of crucial importance for the understanding of the nature of the Λ(1405) resonance and of the attractive K−p strong interaction. In this article, we present measurements of the K−p correlation functions in relative momentum space obtained in pp collisions at 𝑠√ = 13 Te, in p-Pb collisions at 𝑠NN‾‾‾‾√ = 5.02 Te, and (semi)peripheral Pb-Pb collisions at 𝑠NN‾‾‾‾√ = 5.02 Te. The emitting source size, composed of a core radius anchored to the K+p correlation and of a resonance halo specific to each particle pair, varies between 1 and 2 fm in these collision systems. The strength and the effects of the K⎯⎯⎯⎯0n and πΣ inelastic channels on the measured K−p correlation function are investigated in the different colliding systems by comparing the data with state-of-the-art models of chiral potentials. A novel approach to determine the conversion weights 𝜔, necessary to quantify the amount of produced inelastic channels in the correlation function, is presented. In this method, particle yields are estimated from thermal model predictions, and their kinematic distribution from blast-wave fits to measured data. The comparison of chiral potentials to the measured K−p interaction indicates that, while the πΣ-K−p dynamics is well reproduced by the model, the coupling to the K⎯⎯⎯⎯0n channel in the model is currently underestimated.

Data-driven precision determination of the material budget in ALICE - R. Keidel; S. Acharya; D. Adamová (2023)
The knowledge of the material budget with a high precision is fundamental for measurements of direct photon production using the photon conversion method due to its direct impact on the total systematic uncertainty. Moreover, it influences many aspects of the charged-particle reconstruction performance. In this article, two procedures to determine data-driven corrections to the material-budget description in ALICE simulation software are developed. One is based on the precise knowledge of the gas composition in the Time Projection Chamber. The other is based on the robustness of the ratio between the produced number of photons and charged particles, to a large extent due to the approximate isospin symmetry in the number of produced neutral and charged pions. Both methods are applied to ALICE data allowing for a reduction of the overall material budget systematic uncertainty from 4.5% down to 2.5%. Using these methods, a locally correct material budget is also achieved. The two proposed methods are generic and can be applied to any experiment in a similar fashion.

Dielectron production at midrapidity at low transverse momentum in peripheral and semi-peripheral Pb-Pb collisions at s_NN = 5.02 TeV - S. Acharya; D. Adamová; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; M. Al-Turany; et al. (Journal of High Energy Physics, 2023)
The first measurement of the e+e− pair production at low lepton pair transverse momentum (pT,ee) and low invariant mass (mee) in non-central Pb-Pb collisions at 𝑠√NN = 5.02 TeV at the LHC is presented. The dielectron production is studied with the ALICE detector at midrapidity (|ηe| < 0.8) as a function of invariant mass (0.4 ≤ mee < 2.7 GeV/c2) in the 50-70% and 70-90% centrality classes for pT,ee < 0.1 GeV/c, and as a function of pT,ee in three mee intervals in the most peripheral Pb-Pb collisions. Below a pT,ee of 0.1 GeV/c, a clear excess of e+e− pairs is found compared to the expectations from known hadronic sources and predictions of thermal radiation from the medium. The mee excess spectra are reproduced, within uncertainties, by different predictions of the photon-photon production of dielectrons, where the photons originate from the extremely strong electromagnetic fields generated by the highly Lorentz-contracted Pb nuclei. Lowest-order quantum electrodynamic (QED) calculations, as well as a model that takes into account the impact-parameter dependence of the average transverse momentum of the photons, also provide a good description of the pT,ee spectra. The measured ⟨𝑝2T,ee⟩‾‾‾‾‾‾‾√ of the excess pT,ee spectrum in peripheral Pb-Pb collisions is found to be comparable to the values observed previously at RHIC in a similar phase-space region.

Dielectron production in central Pb−Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel (2023)
The first measurement of the e+e− pair production at midrapidity and low invariant mass in central Pb−Pb collisions at sNN‾‾‾‾√=5.02 TeV at the LHC is presented. The yield of e+e− pairs is compared with a cocktail of expected hadronic decay contributions in the invariant mass (mee) and pair transverse momentum (pT,ee) ranges mee<3.5 GeV/c2 and pT,ee<8 GeV/c. For 0.18<mee<0.5 GeV/c2 the ratio of data to the cocktail of hadronic contributions without ρ mesons amounts to 1.42±0.12 (stat.)±0.17 (syst.)±0.12 (cocktail) and 1.44±0.12 (stat.)±0.17 (syst.)+0.17−0.21 (cocktail), including or not including medium effects in the estimation of the heavy-flavor background, respectively. It is consistent with predictions from two different models for an additional contribution of thermal e+e− pairs from the hadronic and partonic phases. In the intermediate-mass range (1.2<mee<2.6 GeV/c2), the pair transverse impact parameter of the e+e− pairs (DCAee) is used for the first time in Pb−Pb collisions to separate displaced dielectrons from heavy-flavor hadron decays from a possible (thermal) contribution produced at the interaction point. The data are consistent with a suppression of e+e− pairs from cc⎯⎯⎯ and an additional prompt component. Finally, the first direct-photon measurement in the 10% most central Pb−Pb collisions at sNN‾‾‾‾√=5.02 TeV is reported via the study of virtual direct photons in the transverse momentum range 1<pT<5 GeV/c. A model including prompt photons, as well as photons from the pre-equilibrium and fluid-dynamic phases, can reproduce the result, while being at the upper edge of the data uncertainties.

Elliptic flow of charged particles at midrapidity relative to the spectator plane in Pb-Pb and Xe-Xe collisions - R. Keidel; S. Acharya; D. Adamová; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; I. Ahuja; A. Akindinov; et al. (Physics Letters B, 2023)
Measurements of the elliptic flow coefficient relative to the collision plane defined by the spectator neutrons v2 SPin collisions of Pb ions at center-of-mass energy per nucleon-nucleon pair √sNN=2.76TeVand Xe ions at √sNN=5.44TeVare reported. The results are presented for charged particles produced at midrapidity as a function of centrality and transverse momentum for the 5-70% and 0.2-6GeV/cranges, respectively. The ratio between v2 SPand the elliptic flow coefficient relative to the participant plane v24, estimated using four-particle correlations, deviates by up to 20% from unity depending on centrality. This observation differs strongly from the magnitude of the corresponding eccentricity ratios predicted by the TRENTo and the elliptic power models of initial state fluctuations that are tuned to describe the participant plane anisotropies. The differences can be interpreted as a decorrelation of the neutron spectator plane and the reaction plane because of fragmentation of the remnants from the colliding nuclei, which points to an incompleteness of current models describing the initial state fluctuations. A significant transverse momentum dependence of the ratio v2 SP/v24is observed in all but the most central collisions, which may help to understand whether momentum anisotropies at low and intermediate transverse momentum have a common origin in initial state fluctuations. The ratios of v2 SPand v24to the corresponding initial state eccentricities for Xe-Xe and Pb-Pb collisions at similar initial entropy density show a difference of (7.0 ±0.9)%with an additional variation of +1.8%when including RHIC data in the TRENTo parameter extraction. These observations provide new experimental constraints for viscous effects in the hydrodynamic modeling of the expanding quark-gluon plasma produced in heavy-ion collisions at the LHC.

Enhanced Deuteron Coalescence Probability in Jets - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Physical Review Letters, 2023)
The transverse-momentum (pT) spectra and coalescence parameters B2 of (anti)deuterons are measured in p-p collisions at √s=13 TeV for the first time in and out of jets. In this measurement, the direction of the leading particle with the highest pT in the event (pleadT>5 GeV/c) is used as an approximation for the jet axis. The event is consequently divided into three azimuthal regions, and the jet signal is obtained as the difference between the toward region, that contains jet fragmentation products in addition to the underlying event (UE), and the transverse region, which is dominated by the UE. The coalescence parameter in the jet is found to be approximately a factor of 10 larger than that in the underlying event. This experimental observation is consistent with the coalescence picture and can be attributed to the smaller average phase-space distance between nucleons in the jet cone as compared with the underlying event. The results presented in this Letter are compared to predictions from a simple nucleon coalescence model, where the phase-space distributions of nucleons are generated using pythia8 with the Monash 2013 tuning, and to predictions from a deuteron production model based on ordinary nuclear reactions with parametrized energy-dependent cross sections tuned on data. The latter model is implemented in pythia8.3. Both models reproduce the observed large difference between in-jet and out-of-jet coalescence parameters, although the almost flat trend of the BJet2 is not reproduced by the models, which instead give a decreasing trend.

Exploiting Differentiable Programming for the End-to-end Optimization of Detectors - Max Aehle; Mateusz Bawaj; Ralf Keidel (HAL science ouverte, 2023)
The coming of age of differentiable programming makes possible today to create complete computer models of experimental apparatus that include the stochastic data-generation processes, the full modeling of the reconstruction and inference procedures, and a suitably defined objective function, along with the cost of any given detector configuration, geometry and materials. This enables the end-to-end optimization of the instruments, by using techniques developed within computer science that are currently vastly exploited in fields such as fluid dynamics. The MODE Collaboration has started to consider the problem in its generality, to provide software architectures that may be useful for the optimization of experimental design. These models may be useful in a ”human in the middle” system as they provide information on the relative merit of different configurations as a continuous function of the design choices. In this short contribution we summarize the plan of studies that has been laid out, and its potential in the long term for the future of experimental studies in fundamental physics.

First Measurement of Antideuteron Number Fluctuations at Energies Available at the Large Hadron Collider - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Physical Review Letters, 2023)
The first measurement of event-by-event antideuteron number fluctuations in high energy heavy-ion collisions is presented. The measurements are carried out at midrapidity (|η|<0.8) as a function of collision centrality in Pb-Pb collisions at √sNN=5.02 TeV using the ALICE detector. A significant negative correlation between the produced antiprotons and antideuterons is observed in all collision centralities. The results are compared with a state-of-the-art coalescence calculation. While it describes the ratio of higher order cumulants of the antideuteron multiplicity distribution, it fails to describe quantitatively the magnitude of the correlation between antiproton and antideuteron production. On the other hand, thermal-statistical model calculations describe all the measured observables within uncertainties only for correlation volumes that are different with respect to those describing proton yields and a similar measurement of net-proton number fluctuations.

First measurement of Λc+ production down to pT=0 in pp and p-Pb collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; M. Al-Turany; et al. (Physical Review C, 2023)
The production of prompt Λ+c baryons has been measured at midrapidity in the transverse momentum interval 0<pT<1 GeV/c for the first time, in pp and p-Pb collisions at a center-of-mass energy per nucleon-nucleon collision √sNN=5.02TeV. The measurement was performed in the decay channel Λ+c→pK0S by applying new decay reconstruction techniques using a Kalman-Filter vertexing algorithm and adopting a machine-learning approach for the candidate selection. The pT-integrated Λ+c production cross sections in both collision systems were determined and used along with the measured yields in Pb-Pb collisions to compute the pT-integrated nuclear modification factors RpPb and RAA of Λ+c baryons, which are compared to model calculations that consider nuclear modification of the parton distribution functions. The Λ+c/D0 baryon-to-meson yield ratio is reported for pp and p-Pb collisions. Comparisons with models that include modified hadronization processes are presented, and the implications of the results on the understanding of charm hadronization in hadronic collisions are discussed. A significant (3.7σ) modification of the mean transverse momentum of Λ+c baryons is seen in p-Pb collisions with respect to pp collisions, while the pT-integrated Λ+c/D0 yield ratio was found to be consistent between the two collision systems within the uncertainties.

Inclusive photon production at forward rapidities in pp and p-Pb collisions at s_NN=5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (The European Physical Journal C, 2023)
A study of multiplicity and pseudorapidity distributions of inclusive photons measured in pp and p-Pb collisions at a center-of-mass energy per nucleon-nucleon collision of 𝑠NN‾‾‾‾√ = 5.02 TeV using the ALICE detector in the forward pseudorapidity region 2.3 < 𝜂lab < 3.9 is presented. Measurements in p-Pb collisions are reported for two beam configurations in which the directions of the proton and lead ion beam were reversed. The pseudorapidity distributions in p-Pb collisions are obtained for seven centrality classes which are defined based on different event activity estimators, i.e., the charged-particle multiplicity measured at midrapidity as well as the energy deposited in a calorimeter at beam rapidity. The inclusive photon multiplicity distributions for both pp and p-Pb collisions are described by double negative binomial distributions. The pseudorapidity distributions of inclusive photons are compared to those of charged particles at midrapidity in pp collisions and for different centrality classes in p-Pb collisions. The results are compared to predictions from various Monte Carlo event generators. None of the generators considered in this paper reproduces the inclusive photon multiplicity distributions in the reported multiplicity range. The pseudorapidity distributions are, however, better described by the same generators.

Investigation of K+K− interactions via femtoscopy in Pb-Pb collisions at sNN=2.76 TeV at the CERN Large Hadron Collider - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Physical Review C, 2023)
Femtoscopic correlations of nonidentical charged kaons (K+K−) are studied in Pb-Pb collisions at a center-of-mass energy per nucleon-nucleon collision √sNN=2.76 TeV by ALICE at the CERN Large Hadron Collider. One-dimensional K+K− correlation functions are analyzed in three centrality classes and eight intervals of particle-pair transverse momentum. The Lednický and Luboshitz interaction model used in the K+K− analysis includes the final-state Coulomb interactions between kaons and the final-state interaction through a0(980) and f0(980) resonances. The mass of f0(980) and coupling were extracted from the fit to K+K− correlation functions using the femtoscopic technique. The measured mass and width of the f0(980) resonance are consistent with other published measurements. The height of the ϕ(1020) meson peak present in the K+K− correlation function rapidly decreases with increasing source radius, qualitatively in agreement with an inverse volume dependence. A phenomenological fit to this trend suggests that the ϕ(1020) meson yield is dominated by particles produced directly from the hadronization of the system. The small fraction subsequently produced by final-state interactions could not be precisely quantified with data presented in this paper and will be assessed in future work.

J/ψ production at midrapidity in p-Pb collisions at s_NN = 8.16 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2023)
The production of inclusive, prompt and non-prompt J/ψ was studied for the first time at midrapidity (−1.37 < ycms < 0.43) in p-Pb collisions at 𝑠NN‾‾‾‾√ = 8.16 TeV with the ALICE detector at the LHC. The inclusive J/ψ mesons were reconstructed in the dielectron decay channel in the transverse momentum (pT) interval 0 < pT < 14 GeV/c and the prompt and non-prompt contributions were separated on a statistical basis for pT > 2 GeV/c. The study of the J/ψ mesons in the dielectron channel used for the first time in ALICE online single-electron triggers from the Transition Radiation Detector, providing a data sample corresponding to an integrated luminosity of 689 ± 13 μb−1. The proton-proton reference cross section for inclusive J/ψ was obtained based on interpolations of measured data at different centre-of-mass energies and a universal function describing the pT-differential J/ψ production cross sections. The pT-differential nuclear modification factors RpPb of inclusive, prompt, and non-prompt J/ψ are consistent with unity and described by theoretical models implementing only nuclear shadowing.

Jet-like correlations with respect to K^0_S and Λ (Λ ) in pp and central Pb-Pb collisions at s_NN = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (The European Physical Journal C, 2023)
Two-particle correlations with K0S, Λ/Λ⎯⎯⎯⎯, and charged hadrons as trigger particles in the transverse momentum range 8<𝑝T,trig<16 GeV/𝑐, and associated charged particles within 1<𝑝T,assoc<8 GeV/𝑐, are studied at midrapidity in pp and central Pb-Pb collisions at a centre-of-mass energy per nucleon-nucleon collision 𝑠NN‾‾‾‾√ = 5.02 TeV with the ALICE detector at the LHC. After subtracting the contributions of the flow background, the per-trigger yields are extracted on both the near and away sides, and the ratio in Pb-Pb collisions with respect to pp collisions (𝐼AA) is computed. The per-trigger yield in Pb-Pb collisions on the away side is strongly suppressed to the level of 𝐼AA ≈0.6 for 𝑝T,assoc>3 GeV/𝑐 as expected from strong in-medium energy loss, while an enhancement develops at low 𝑝T,assoc on both the near and away sides, reaching 𝐼AA ≈1.8 and 2.7 respectively. These findings are in good agreement with previous ALICE measurements from two-particle correlations triggered by neutral pions (𝜋0-h) and charged hadrons (h-h) in Pb-Pb collisions at 𝑠NN‾‾‾‾√ = 2.76 TeV. Moreover, the correlations with K0S mesons and Λ/Λ⎯⎯⎯⎯ baryons as trigger particles are compared to those of inclusive charged hadrons. The results are compared with the predictions of Monte Carlo models.

Light (anti)nuclei production in Pb-Pb collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Physical Review C, 2023)
The measurement of the production of deuterons, tritons and 3He and their antiparticles in Pb-Pb collisions at √sNN=5.02TeV is presented in this article. The measurements are carried out at midrapidity (|y|< 0.5) as a function of collision centrality using the ALICE detector. The pT-integrated yields, the coalescence parameters and the ratios to protons and antiprotons are reported and compared with nucleosynthesis models. The comparison of these results in different collision systems at different center-of-mass collision energies reveals a suppression of nucleus production in small systems. In the Statistical Hadronisation Model framework, this can be explained by a small correlation volume where the baryon number is conserved, as already shown in previous fluctuation analyses. However, a different size of the correlation volume is required to describe the proton yields in the same data sets. The coalescence model can describe this suppression by the fact that the wave functions of the nuclei are large and the fireball size starts to become comparable and even much smaller than the actual nucleus at low multiplicities.

Measurement of electrons from beauty-hadron decays in pp and Pb-Pb collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Physical Review C, 2023)
The production of electrons from beauty-hadron decays was measured at midrapidity in proton-proton (pp) and central Pb-Pb collisions at center-of-mass energy per nucleon-nucleon pair √sNN = 5.02 TeV, using the ALICE detector at the LHC. The cross section measured in pp collisions in the transverse momentum interval 2<pT<8GeV/c was compared with models based on perturbative quantum chromodynamics calculations. The yield in the 10% most central Pb-Pb collisions, measured in the interval 2<pT<26GeV/c, was used to compute the nuclear modification factor RAA, extrapolating the pp reference cross section to pT larger than 8 GeV/c. The measured RAA shows significant suppression of the yield of electrons from beauty-hadron decays at high pT and does not show a significant dependence above 8GeV/c within uncertainties. The results are described by several theoretical models based on different implementations of the interaction of heavy quarks with a quark-gluon plasma, which predict a smaller energy loss for beauty quarks compared to light and charm quarks.

Measurement of inclusive and leading subjet fragmentation in pp and Pb-Pb collisions at s_NN = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2023)
This article presents new measurements of the fragmentation properties of jets in both proton-proton (pp) and heavy-ion collisions with the ALICE experiment at the Large Hadron Collider (LHC). We report distributions of the fraction zr of transverse momentum carried by subjets of radius r within jets of radius R. Charged-particle jets are reconstructed at midrapidity using the anti-kT algorithm with jet radius R = 0.4, and subjets are reconstructed by reclustering the jet constituents using the anti-kT algorithm with radii r = 0.1 and r = 0.2. In proton-proton collisions, we measure both the inclusive and leading subjet distributions. We compare these measurements to perturbative calculations at next-to-leading logarithmic accuracy, which suggest a large impact of threshold resummation and hadronization effects on the zr distribution. In heavy-ion collisions, we measure the leading subjet distributions, which allow access to a region of harder jet frag- mentation than has been probed by previous measurements of jet quenching via hadron fragmentation distributions. The zr distributions enable extraction of the parton-to-subjet fragmentation function and allow for tests of the universality of jet fragmentation functions in the quark-gluon plasma (QGP). We find no significant modification of zr distributions in Pb-Pb compared to pp collisions. However, the distributions are also consistent with a hardening trend for zr < 0.95, as predicted by several jet quenching models. As zr → 1 our results indicate that any such hardening effects cease, exposing qualitatively new possibilities to disentangle competing jet quenching mechanisms. By comparing our results to theoretical calculations based on an independent extraction of the parton-to-jet fragmentation function, we find consistency with the universality of jet fragmentation and no indication of factorization breaking in the QGP.

Measurement of inclusive charged-particle jet production in pp and p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; D. Adamová; R. Keidel (2023)
Measurements of inclusive charged-particle jet production in pp and p-Pb collisions at center-of-mass energy per nucleon-nucleon collision sNN‾‾‾‾√=5.02 TeV and the corresponding nuclear modification factor RchjetpPb are presented, using data collected with the ALICE detector at the LHC. Jets are reconstructed in the central rapidity region |ηjet|<0.5 from charged particles using the anti-kT algorithm with resolution parameters R=0.2, 0.3, and 0.4. The pT-differential inclusive production cross section of charged-particle jets, as well as the corresponding cross-section ratios, are reported for pp and p-Pb collisions in the transverse momentum range 10<pchT,jet<140 GeV/c and 10<pchT,jet<160 GeV/c, respectively, together with the nuclear modification factor RchjetpPb in the range 10<pchT,jet<140 GeV/c. The analysis extends the pT range of the previously-reported charged-particle jet measurements by the ALICE Collaboration. The nuclear modification factor is found to be consistent with one and independent of the jet resolution parameter with the improved precision of this study, indicating that the possible influence of cold nuclear matter effects on the production cross section of charged-particle jets in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV is smaller than the current precision. The obtained results are in agreement with other minimum bias jet measurements available for RHIC and LHC energies, and are well reproduced by the NLO perturbative QCD POWHEG calculations with parton shower provided by PYTHIA8 as well as by JETSCAPE simulations.

Measurement of the angle between jet axes in pp collisions at s = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2023)
This article reports measurements of the angle between differently defined jet axes in pp collisions at 𝑠√ = 5.02 TeV carried out by the ALICE Collaboration. Charged particles at midrapidity are clustered into jets with resolution parameters R = 0.2 and 0.4. The jet axis, before and after Soft Drop grooming, is compared to the jet axis from the Winner-Takes-All (WTA) recombination scheme. The angle between these axes, ∆Raxis, probes a wide phase space of the jet formation and evolution, ranging from the initial high-momentum-transfer scattering to the hadronization process. The ∆Raxis observable is presented for 20 < 𝑝ch jetT < 100 GeV/c, and compared to predictions from the PYTHIA 8 and Herwig 7 event generators. The distributions can also be calculated analytically with a leading hadronization correction related to the non-perturbative component of the Collins-Soper-Sterman (CSS) evolution kernel. Comparisons to analytical predictions at next-to-leading-logarithmic accuracy with leading hadronization correction implemented from experimental extractions of the CSS kernel in Drell-Yan measurements are presented. The analytical predictions describe the measured data within 20% in the perturbative regime, with surprising agreement in the non-perturbative regime as well. These results are compatible with the universality of the CSS kernel in the context of jet substructure.

Measurement of the J/ψ Polarization with Respect to the Event Plane in Pb-Pb Collisions at the LHC - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Physical Review Letters, 2023)
We study the polarization of inclusive J/ψ produced in Pb-Pb collisions at √sNN=5.02 TeV at the LHC in the dimuon channel, via the measurement of the angular distribution of its decay products. We perform the study in the rapidity region 2.5<y<4, for three transverse momentum intervals (2<pT<4, 4<pT<6, 6<pT<10 GeV/c) and as a function of the centrality of the collision for 2<pT<6 GeV/c. For the first time, the polarization is measured with respect to the event plane of the collision, by considering the angle between the positive-charge decay muon in the J/ψ rest frame and the axis perpendicular to the event-plane vector in the laboratory system. A small transverse polarization is measured, with a significance reaching 3.9σ at low pT and for intermediate centrality values. The polarization could be connected with the behavior of the quark-gluon plasma, formed in Pb-Pb collisions, as a rotating fluid with large vorticity, as well as with the existence of a strong magnetic field in the early stage of its formation.

Measurement of the Lifetime and Λ Separation Energy of HΛ3 - S. Acharya; D. Adamová; A. Adler; R. Keidel; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Physical Review Letters, 2023)
The most precise measurements to date of the 3ΛH lifetime τ and Λ separation energy BΛ are obtained using the data sample of Pb-Pb collisions at √sNN=5.02 TeV collected by ALICE at the LHC. The 3ΛH is reconstructed via its charged two-body mesonic decay channel (3ΛH→3He+π− and the charge-conjugate process). The measured values τ=[253±11(stat)±6(syst)] ps and BΛ=[102±63(stat)±67(syst)] keV are compatible with predictions from effective field theories and confirm that the 3ΛH structure is consistent with a weakly bound system.

Measurement of the production of charm jets tagged with D0 mesons in pp collisions at s = 5.02 and 13 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2023)
The measurement of the production of charm jets, identified by the presence of a D0 meson in the jet constituents, is presented in proton-proton collisions at centre-of-mass energies of 𝑠√ = 5.02 and 13 TeV with the ALICE detector at the CERN LHC. The D0 mesons were reconstructed from their hadronic decay D0 → K−π+ and the respective charge conjugate. Jets were reconstructed from D0-meson candidates and charged particles using the anti-kT algorithm, in the jet transverse momentum range 5 < pT,chjet < 50 GeV/c, pseudorapidity |ηjet| < 0.9 − R, and with the jet resolution parameters R = 0.2, 0.4, 0.6. The distribution of the jet momentum fraction carried by a D0 meson along the jet axis ⎛⎝⎜⎜𝑧ch‖‖‖⎞⎠⎟⎟ was measured in the range 0.4 < 𝑧ch‖‖‖ < 1.0 in four ranges of the jet transverse momentum. Comparisons of results for different collision energies and jet resolution parameters are also presented. The measurements are compared to predictions from Monte Carlo event generators based on leading-order and next-to-leading-order perturbative quantum chromodynamics calculations. A generally good description of the main features of the data is obtained in spite of a few discrepancies at low pT,chjet. Measurements were also done for R = 0.3 at 𝑠√ = 5.02 and are shown along with their comparisons to theoretical predictions in an appendix to this paper.

Measurement of ψ (2S) production as a function of charged-particle pseudorapidity density in pp collisions at s = 13 TeV and p-Pb collisions at s_NN = 8.16 TeV with ALICE at the LHC - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2023)
Production of inclusive charmonia in pp collisions at center-of-mass energy of 𝑠√ = 13 TeV and p-Pb collisions at center-of-mass energy per nucleon pair of 𝑠NN‾‾‾‾√ = 8.16 TeV is studied as a function of charged-particle pseudorapidity density with ALICE. Ground and excited charmonium states (J/ψ, ψ(2S)) are measured from their dimuon decays in the interval of rapidity in the center-of-mass frame 2.5 < ycms < 4.0 for pp collisions, and 2.03 < ycms < 3.53 and −4.46 < ycms < −2.96 for p-Pb collisions. The charged-particle pseudorapidity density is measured around midrapidity (|η| < 1.0). In pp collisions, the measured charged-particle multiplicity extends to about six times the average value, while in p-Pb collisions at forward (backward) rapidity a multiplicity corresponding to about three (four) times the average is reached. The ψ(2S) yield increases with the charged-particle pseudorapidity density. The ratio of ψ(2S) over J/ψ yield does not show a significant multiplicity dependence in either colliding system, suggesting a similar behavior of J/ψ and ψ(2S) yields with respect to charged-particle pseudorapidity density. Results for the ψ(2S) yield and its ratio with respect to J/ψ agree with available model calculations.

Measurements of jet quenching using semi-inclusive hadron+jet distributions in pp and central Pb−Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; D. Adamová; R. Keidel (2023)
The ALICE Collaboration reports measurements of the semi-inclusive distribution of charged-particle jets recoiling from a high transverse momentum (high pT) charged hadron, in pp and central Pb−Pb collisions at center of mass energy per nucleon−nucleon collision sNN‾‾‾‾√=5.02 TeV. The large uncorrelated background in central Pb−Pb collisions is corrected using a data-driven statistical approach, which enables precise measurement of recoil jet distributions over a broad range in pT,chjet and jet resolution parameter R. Recoil jet yields are reported for R=0.2, 0.4, and 0.5 in the range 7<pT,chjet<140 GeV/c and π/2<Δφ<π, where Δφ is the azimuthal angular separation between hadron trigger and recoil jet. The low pT,chjet reach of the measurement explores unique phase space for studying jet quenching, the interaction of jets with the quark-gluonnplasma generated in high-energy nuclear collisions. Comparison of pT,chjet distributions from pp and central Pb−Pb collisions probes medium-induced jet energy loss and intra-jet broadening, while comparison of their acoplanarity distributions explores in-medium jet scattering and medium response. The measurements are compared to theoretical calculations incorporating jet quenching.

Measurements of the groomed jet radius and momentum splitting fraction with the soft drop and dynamical grooming algorithms in pp collisions at s = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2023)
This article presents measurements of the groomed jet radius and momentum splitting fraction in pp collisions at 𝑠√ = 5.02 TeV with the ALICE detector at the Large Hadron Collider. Inclusive charged-particle jets are reconstructed at midrapidity using the anti-kT algorithm for transverse momentum 60<𝑝chjetT<80 GeV/c. We report results using two different grooming algorithms: soft drop and, for the first time, dynamical grooming. For each grooming algorithm, a variety of grooming settings are used in order to explore the impact of collinear radiation on these jet substructure observables. These results are compared to perturbative calculations that include resummation of large logarithms at all orders in the strong coupling constant. We find good agreement of the theoretical predictions with the data for all grooming settings considered.

Modification of charged-particle jets in event-shape engineered Pb−Pb collisions at sNN‾‾‾‾√=5 TeV - S. Acharya; D. Adamová; R. Keidel (2023)
Charged-particle jet yields have been measured in semicentral Pb−Pb collisions at center-of-mass energy per nucleon-nucleon collision sNN‾‾‾‾√=5 TeV with the ALICE detector at the LHC. These yields are reported as a function of the jet transverse momentum, and further classified by their angle with respect to the event plane and the event shape, characterized by ellipticity, in an effort to study the path-length dependence of jet quenching. Jets were reconstructed at midrapidity from charged-particle tracks using the anti-kT algorithm with resolution parameters R= 0.2 and 0.4, with event-plane angle and event-shape values determined using information from forward scintillating detectors. The results presented in this letter show that, in semicentral Pb−Pb collisions, there is no significant difference between jet yields in predominantly isotropic and elliptical events. However, out-of-plane jets are observed to be more suppressed than in-plane jets. Further, this relative suppression is greater for low transverse momentum (< 50 GeV/c) R= 0.2 jets produced in elliptical events, with out-of-plane to in-plane jet-yield ratios varying up to 5.2σ between different event-shape classes. These results agree with previous studies indicating that jets experience azimuthally anisotropic suppression when traversing the QGP medium, and can provide additional constraints on the path-length dependence of jet energy loss.

Multiplicity and rapidity dependence of K^*(892)^0 and φ (1020) production in p-Pb collisions at s_NN = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (The European Physical Journal C, 2023)
The transverse-momentum (𝑝T) spectra of K∗(892)0 and 𝜙(1020) measured with the ALICE detector up to 𝑝T = 16 GeV/c in the rapidity range −1.2<𝑦<0.3, in p-Pb collisions at the center-of-mass energy per nucleon-nucleon collision 𝑠NN‾‾‾‾√=5.02 TeV are presented as a function of charged particle multiplicity and rapidity. The measured 𝑝T distributions show a dependence on both multiplicity and rapidity at low 𝑝T whereas no significant dependence is observed at high 𝑝T. A rapidity dependence is observed in the 𝑝T-integrated yield (dN/dy), whereas the mean transverse momentum (⟨𝑝T⟩) shows a flat behavior as a function of rapidity. The rapidity asymmetry (𝑌asym) at low 𝑝T (< 5 GeV/c) is more significant for higher multiplicity classes. At high 𝑝T, no significant rapidity asymmetry is observed in any of the multiplicity classes. Both K∗(892)0 and 𝜙(1020) show similar 𝑌asym. The nuclear modification factor (𝑄CP) as a function of 𝑝T shows a Cronin-like enhancement at intermediate 𝑝T, which is more prominent at higher rapidities (Pb-going direction) and in higher multiplicity classes. At high 𝑝T (> 5 GeV/𝑐), the 𝑄CP values are greater than unity and no significant rapidity dependence is observed.

Neutron emission in ultraperipheral Pb-Pb collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Physical Review C, 2023)
In ultraperipheral collisions (UPCs) of relativistic nuclei without overlap of nuclear densities, the two nuclei are excited by the Lorentz-contracted Coulomb fields of their collision partners. In these UPCs, the typical nuclear excitation energy is below a few tens of MeV, and a small number of nucleons are emitted in electromagnetic dissociation (EMD) of primary nuclei, in contrast to complete nuclear fragmentation in hadronic interactions. The cross sections of emission of given numbers of neutrons in UPCs of 208Pb nuclei at √sNN=5.02 TeV were measured with the neutron zero degree calorimeters (ZDCs) of the ALICE detector at the LHC, exploiting a similar technique to that used in previous studies performed at √sNN=2.76 TeV. In addition, the cross sections for the exclusive emission of one, two, three, four, and five forward neutrons in the EMD, not accompanied by the emission of forward protons, and thus mostly corresponding to the production of 207,206,205,204,203Pb, respectively, were measured for the first time. The predictions from the available models describe the measured cross sections well. These cross sections can be used for evaluating the impact of secondary nuclei on the LHC components, in particular, on superconducting magnets, and also provide useful input for the design of the Future Circular Collider (FCC-hh).

Observation of flow angle and flow magnitude fluctuations in Pb-Pb collisions at sNN=5.02TeV at the CERN Large Hadron Collider - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Physical Review C, 2023)
This Letter reports on the first measurements of transverse momentum dependent flow angle Ψn and flow magnitude vn fluctuations determined using new four-particle correlators. The measurements are performed for various centralities in Pb-Pb collisions at a center-of-mass energy per nucleon pair of √sNN = 5.02 TeV with ALICE at the CERN Large Hadron Collider. Both flow angle and flow magnitude fluctuations are observed in the presented centrality ranges and are strongest in the most central collisions and for a transverse momentum pT>2GeV/c. Comparison with theoretical models, including iEBE-VISHNU, MUSIC, and AMPT, show that the measurements exhibit unique sensitivities to the initial state of heavy-ion collisions.

Observation of medium-induced yield enhancement and acoplanarity broadening of low-pT jets from measurements in pp and central Pb−Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; D. Adamová; R. Keidel (2023)
The ALICE Collaboration reports the measurement of semi-inclusive distributions of charged-particle jets recoiling from a high transverse momentum (high pT) hadron trigger in proton−proton and central Pb−Pb collisions at sNN‾‾‾‾√=5.02 TeV. A data-driven statistical method is used to mitigate the large uncorrelated background in central Pb−Pb collisions. Recoil jet distributions are reported for jet resolution parameter R=0.2, 0.4, and 0.5 in the range 7<pT,jet<140 GeV/c and trigger−recoil jet azimuthal separation π/2<Δφ<π. The measurements exhibit a marked medium-induced jet yield enhancement at low pT and at large azimuthal deviation from Δφ∼π. The enhancement is characterized by its dependence on Δφ, which has a slope that differs from zero by 4.7σ. Comparisons to model calculations incorporating different formulations of jet quenching are reported. These comparisons indicate that the observed yield enhancement arises from the response of the QGP medium to jet propagation.

Performance of the ALICE Electromagnetic Calorimeter - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; I. Ahuja; S. Aiola; et al. (Journal of Instrumentation, 2023)
The performance of the electromagnetic calorimeter of the ALICE experiment during operation in 2010-2018 at the Large Hadron Collider is presented. After a short introduction into the design, readout, and trigger capabilities of the detector, the procedures for data taking, reconstruction, and validation are explained. The methods used for the calibration and various derived corrections are presented in detail. Subsequently, the capabilities of the calorimeter to reconstruct and measure photons, light mesons, electrons and jets are discussed. The performance of the calorimeter is illustrated mainly with data obtained with test beams at the Proton Synchrotron and Super Proton Synchrotron or in proton-proton collisions at √s = 13 TeV, and compared to simulations.

Production of K_S^0 , Λ ( Λ ), Ξ±, and Ω± in jets and in the underlying event in pp and p-Pb collisions - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2023)
The production of strange hadrons (K0S, Λ, Ξ±, and Ω±), baryon-to-meson ratios (Λ/K0S, Ξ/K0S, and Ω/K0S), and baryon-to-baryon ratios (Ξ/Λ, Ω/Λ, and Ω/Ξ) associated with jets and the underlying event were measured as a function of transverse momentum (pT) in pp collisions at 𝑠√ = 13 TeV and p Pb collisions at 𝑠NN‾‾‾‾√ = 5.02 TeV with the ALICE detector at the LHC. The inclusive production of the same particle species and the corresponding ratios are also reported. The production of multi-strange hadrons, Ξ± and Ω±, and their associated particle ratios in jets and in the underlying event are measured for the first time. In both pp and p-Pb collisions, the baryon-to-meson and baryon-to-baryon yield ratios measured in jets differ from the inclusive particle production for low and intermediate hadron pT (0.6-6 GeV/c). Ratios measured in the underlying event are in turn similar to those measured for inclusive particle production. In pp collisions, the particle production in jets is compared with Pythia 8 predictions with three colour-reconnection implementation modes. None of them fully reproduces the data in the measured hadron pT region. The maximum deviation is observed for Ξ± and Ω± which reaches a factor of about six. The event multiplicity dependence is further investigated in p−Pb collisions. In contrast to what is observed in the underlying event, there is no significant event-multiplicity dependence for particle production in jets. The presented measurements provide novel constraints on hadronisation and its Monte Carlo description. In particular, they demonstrate that the fragmentation of jets alone is insufficient to describe the strange and multi-strange particle production in hadronic collisions at LHC energies.

Production of pions, kaons, and protons as a function of the relative transverse activity classifier in pp collisions at s = 13 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2023)
The production of π±, K±, and (p⎯⎯⎯)p is measured in pp collisions at 𝑠√ = 13 TeV in different topological regions of the events. Particle transverse momentum (pT) spectra are measured in the “toward”, “transverse”, and “away” angular regions defined with respect to the direction of the leading particle in the event. While the toward and away regions contain the fragmentation products of the near-side and away-side jets, respectively, the transverse region is dominated by particles from the Underlying Event (UE). The relative transverse activity classifier, RT = NT/〈NT〉, is used to group events according to their UE activity, where NT is the measured charged-particle multiplicity per event in the transverse region and 〈NT〉 is the mean value over all the analysed events. The first measurements of identified particle pT spectra as a function of RT in the three topological regions are reported. It is found that the yield of high transverse momentum particles relative to the RT-integrated measurement decreases with increasing RT in both the toward and the away regions, indicating that the softer UE dominates particle production as RT increases and validating that RT can be used to control the magnitude of the UE. Conversely, the spectral shapes in the transverse region harden significantly with increasing RT. This hardening follows a mass ordering, being more significant for heavier particles. Finally, it is observed that the pT-differential particle ratios (p+p⎯⎯⎯)/(π++π−) and (K+ + K−)/(π+ + π−) in the low UE limit (RT → 0) approach expectations from Monte Carlo generators such as PYTHIA 8 with Monash 2013 tune and EPOS LHC, where the jet-fragmentation models have been tuned to reproduce e+e− results.

Study of charged particle production at high pT using event topology in pp, p-Pb and Pb-Pb collisions at sNN=5.02TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; I. Ahuja; A. Akindinov; et al. (Physics Letters B, 2023)
This letter reports measurements which characterize the underlying event associated with hard scatterings at mid-pseudorapidity () in pp, p-Pb and Pb-Pb collisions at centre-of-mass energy per nucleon pair, TeV. The measurements are performed with ALICE at the LHC. Different multiplicity classes are defined based on the event activity measured at forward rapidities. The hard scatterings are identified by the leading particle defined as the charged particle with the largest transverse momentum () in the collision and having 8 GeV/c. The spectra of associated particles (0.5 GeV/c) are measured in different azimuthal regions defined with respect to the leading particle direction: toward, transverse, and away. The associated charged particle yields in the transverse region are subtracted from those of the away and toward regions. The remaining jet-like yields are reported as a function of the multiplicity measured in the transverse region. The measurements show a suppression of the jet-like yield in the away region and an enhancement of high- associated particles in the toward region in central Pb-Pb collisions, as compared to minimum-bias pp collisions. These observations are consistent with previous measurements that used two-particle correlations, and with an interpretation in terms of parton energy loss in a high-density quark gluon plasma. These yield modifications vanish in peripheral Pb-Pb collisions and are not observed in either high-multiplicity pp or p-Pb collisions.

Symmetry plane correlations in Pb-Pb collisions at s_NN =2.76 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (The European Physical Journal C, 2023)
A newly developed observable for correlations between symmetry planes, which characterize the direction of the anisotropic emission of produced particles, is measured in Pb-Pb collisions at 𝑠NN‾‾‾‾√ = 2.76 TeV with ALICE. This so-called Gaussian Estimator allows for the first time the study of these quantities without the influence of correlations between different flow amplitudes. The centrality dependence of various correlations between two, three and four symmetry planes is presented. The ordering of magnitude between these symmetry plane correlations is discussed and the results of the Gaussian Estimator are compared with measurements of previously used estimators. The results utilizing the new estimator lead to significantly smaller correlations than reported by studies using the Scalar Product method. Furthermore, the obtained symmetry plane correlations are compared to state-of-the-art hydrodynamic model calculations for the evolution of heavy-ion collisions. While the model predictions provide a qualitative description of the data, quantitative agreement is not always observed, particularly for correlators with significant non-linear response of the medium to initial state anisotropies of the collision system. As these results provide unique and independent information, their usage in future Bayesian analysis can further constrain our knowledge on the properties of the QCD matter produced in ultrarelativistic heavy-ion collisions.

System size dependence of hadronic rescattering effect at LHC energies - S. Acharya; D. Adamová; R. Keidel (2023)
The first measurements of K∗(892)0K∗(892)0 resonance production as a function of charged-particle multiplicity in Xe−−Xe collisions at sNN=sNN​ ​= 5.44 TeV and pp collisions at s=s ​= 5.02 TeV using the ALICE detector are presented. The resonance is reconstructed at midrapidity (∣y∣<0.5∣y∣<0.5) using the hadronic decay channel K∗0→K±π∓K∗0→K±π∓. Measurements of transverse-momentum integrated yield, mean transverse-momentum, nuclear modification factor of K∗0K∗0, and yield ratios of resonance to stable hadron (K∗0K∗0/K) are compared across different collision systems (pp, p−−Pb, Xe−−Xe, and Pb−−Pb) at similar collision energies to investigate how the production of K∗0K∗0 resonances depends on the size of the system formed in these collisions. The hadronic rescattering effect is found to be independent of the size of colliding systems and mainly driven by the produced charged-particle multiplicity, which is a proxy of the volume of produced matter at the chemical freeze-out. In addition, the production yields of K∗0K∗0 in Xe−−Xe collisions are utilized to constrain the dependence of the kinetic freeze-out temperature on the system size using HRG-PCE model.

System-size dependence of the charged-particle pseudorapidity density at sNN=5.02TeV for pp, p Pb, and Pb Pb collisions - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; I. Ahuja; A. Akindinov; et al. (Physics Letters B, 2023)
We present the first systematic comparison of the charged-particle pseudorapidity densities for three widely different collision systems, pp, p-Pb, and Pb-Pb, at the top energy of the Large Hadron Collider (√sNN=5.02 TeV) measured over a wide pseudorapidity range (−3.5<η<5), the widest possible among the four experiments at that facility. The systematic uncertainties are minimised since the measurements are recorded by the same experimental apparatus (ALICE). The distributions for p-Pb and Pb-Pb collisions are determined as a function of the centrality of the collisions, while results from pp collisions are reported for inelastic events with at least one charged particle at midrapidity. The charged-particle pseudorapidity densities are, under simple and robust assumptions, transformed to charged-particle rapidity densities. This allows for the calculation and the presentation of the evolution of the width of the rapidity distributions and of a lower bound on the Bjorken energy density, as a function of the number of participants in all three collision systems. We find a decreasing width of the particle production, and roughly a smooth ten fold increase in the energy density, as the system size grows, which is consistent with a gradually higher dense phase of matter.

The Bergen proton CT system - M. Aehle; J. Alme; G.G. Barnaföldi; T. Bodova; V. Borshchov; A. van den Brink; M. Chaar; V. Eikeland; G. Feofilov; C. Garth; N.R. Gauger; G. Genov; et al. (Journal of Instrumentation, 2023)

Towards Neural Charged Particle Tracking in Digital Tracking Calorimeters with Reinforcement Learning - Tobias Kortus; Ralf Keidel; Nicolas R. Gauger (Transactions on Pattern Analysis and Machine Intelligence, 2023)

Towards the understanding of the genuine three-body interaction for p-p-p and p-p-Λ - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (The European Physical Journal A, 2023)
Three-body nuclear forces play an important role in the structure of nuclei and hypernuclei and are also incorporated in models to describe the dynamics of dense baryonic matter, such as in neutron stars. So far, only indirect measurements anchored to the binding energies of nuclei can be used to constrain the three-nucleon force, and if hyperons are considered, the scarce data on hypernuclei impose only weak constraints on the three-body forces. In this work, we present the first direct measurement of the p-p-p and p-p-Λ systems in terms of three-particle correlation functions carried out for pp collisions at 𝑠√=13 TeV. Three-particle cumulants are extracted from the correlation functions by applying the Kubo formalism, where the three-particle interaction contribution to these correlations can be isolated after subtracting the known two-body interaction terms. A negative cumulant is found for the p-p-p system, hinting to the presence of a residual three-body effect while for p-p-Λ the cumulant is consistent with zero. This measurement demonstrates the accessibility of three-baryon correlations at the LHC.

Two-particle transverse momentum correlations in pp and p-Pb collisions at energies available at the CERN Large Hadron Collider - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Physical Review C, 2023)
Two-particle transverse momentum differential correlators, recently measured in Pb-Pb collisions at energies available at the CERN Large Hadron Collider (LHC), provide an additional tool to gain insights into particle production mechanisms and infer transport properties, such as the ratio of shear viscosity to entropy density, of the medium created in Pb-Pb collisions. The longitudinal long-range correlations and the large azimuthal anisotropy measured at low transverse momenta in small collision systems, namely pp and p-Pb, at LHC energies resemble manifestations of collective behavior. This suggests that locally equilibrated matter may be produced in these small collision systems, similar to what is observed in Pb-Pb collisions. In this work, the same two-particle transverse momentum differential correlators are exploited in pp and p-Pb collisions at √s=7TeV and √sNN=5.02TeV, respectively, to seek evidence for viscous effects. Specifically, the strength and shape of the correlators are studied as a function of the produced particle multiplicity to identify evidence for longitudinal broadening that might reveal the presence of viscous effects in these smaller systems. The measured correlators and their evolution from pp and p-Pb to Pb-Pb collisions are additionally compared to predictions from Monte Carlo event generators, and the potential presence of viscous effects is discussed.

Uncertainty-aware spot rejection rate as quality metric for proton therapy using a digital tracking calorimeter - Alexander Schilling; Max Aehle; Johan Alme; Gergely Gábor Barnaföldi; Tea Bodova; Vyacheslav Borshchov; Anthony van den Brink; Viljar Eikeland; Gregory Feofilov; Christoph Garth; Nicolas R Gauger; Ola Grøttvik; et al. (Physics in Medicine & Biology, 2023)

Underlying-event properties in pp and p-Pb collisions at s_NN = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2023)
We report about the properties of the underlying event measured with ALICE at the LHC in pp and p-Pb collisions at 𝑠NN‾‾‾‾√ = 5.02 TeV. The event activity, quantified by charged-particle number and summed-pT densities, is measured as a function of the leading-particle transverse momentum (𝑝trigT). These quantities are studied in three azimuthal-angle regions relative to the leading particle in the event: toward, away, and transverse. Results are presented for three different pT thresholds (0.15, 0.5 and 1 GeV/c) at mid-pseudorapidity (|η| < 0.8). The event activity in the transverse region, which is the most sensitive to the underlying event, exhibits similar behaviour in both pp and p-Pb collisions, namely, a steep increase with 𝑝trigT for low 𝑝trigT, followed by a saturation at 𝑝trigT≈5 GeV/c. The results from pp collisions are compared with existing measurements at other centre-of-mass energies. The quantities in the toward and away regions are also analyzed after the subtraction of the contribution measured in the transverse region. The remaining jet-like particle densities are consistent in pp and p-Pb collisions for 𝑝trigT>10 GeV/c, whereas for lower 𝑝trigT values the event activity is slightly higher in p-Pb than in pp collisions. The measurements are compared with predictions from the PYTHIA 8 and EPOS LHC Monte Carlo event generators.

W±-boson production in p-Pb collisions at s_NN = 8.16 TeV and Pb-Pb collisions at s_NN = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2023)
The production of the W± bosons measured in p-Pb collisions at a centre-of-mass energy per nucleon-nucleon collision 𝑠NN‾‾‾‾√ = 8.16 TeV and Pb-Pb collisions at 𝑠NN‾‾‾‾√ = 5.02 TeV with ALICE at the LHC is presented. The W± bosons are measured via their muonic decay channel, with the muon reconstructed in the pseudorapidity region −4 < 𝜂𝜇lab < −2.5 with transverse momentum 𝑝𝜇T > 10 GeV/c. While in Pb-Pb collisions the measurements are performed in the forward (2.5 < 𝑦𝜇cms < 4) rapidity region, in p-Pb collisions, where the centre-of-mass frame is boosted with respect to the laboratory frame, the measurements are performed in the backward (−4.46 < 𝑦𝜇cms < −2.96) and forward (2.03 < 𝑦𝜇cms < 3.53) rapidity regions. The W− and W+ production cross sections, lepton-charge asymmetry, and nuclear modification factors are evaluated as a function of the muon rapidity. In order to study the production as a function of the p-Pb collision centrality, the production cross sections of the W− and W+ bosons are combined and normalised to the average number of binary nucleon-nucleon collision 〈Ncoll〉. In Pb-Pb collisions, the same measurements are presented as a function of the collision centrality. Study of the binary scaling of the W±-boson cross sections in p-Pb and Pb-Pb collisions is also reported. The results are compared with perturbative QCD calculations, with and without nuclear modifications of the Parton Distribution Functions (PDFs), as well as with available data at the LHC. Significant deviations from the theory expectations are found in the two collision systems, indicating that the measurements can provide additional constraints for the determination of nuclear PDFs and in particular of the light-quark distributions.

Charm-quark fragmentation fractions and production cross section at midrapidity in pp collisions at the LHC - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Physical Review D, 2022)
Recent pT-integrated cross section measurements of the ground-state charm mesons and baryons, D0, D+, D+s, Λ+c, and Ξ0c, are used to evaluate the charm fragmentation fractions and production cross section per unit of rapidity at midrapidity (|y|<0.5), in pp collisions at s√=5.02 TeV at the LHC. The latter is dσcc⎯⎯⎯/dy||y|<0.5 =1165 ±44(stat)+134−101(syst) μb. These measurements were obtained for the first time in hadronic collisions at the LHC including the charm baryon states, recently measured by ALICE at midrapidity. The charm fragmentation fractions differ significantly from the values measured in e+e− and ep collisions, providing evidence of the dependence of the parton-to-hadron fragmentation fractions on the collision system, indicating that the assumption of their universality is not supported by the measured cross sections. An increase of a factor of about 3.3 for the fragmentation fraction for the Λ+c with a significance of 5σ between the values obtained in pp collisions and those obtained in e+e− (ep) collisions is reported. The fragmentation fraction for the Ξ0c was obtained for the first time in any collision system. The measured fragmentation fractions were used to update the cc⎯⎯⎯ cross sections per unit of rapidity at |y|<0.5 at s√=2.76 and 7 TeV, which are about 40% higher than the previously published results. The data were compared with perturbative-QCD calculations and lie at the upper edge of the theoretical bands.

Derivatives in Proton CT - Max Aehle; Johan Alme; Ralf Keidel; Gergely Gábor Barnaföldi (2022)
Algorithmic derivatives can be useful to quantify uncertainties and optimize parameters using computer simulations. Whether they actually are, depends on how "well-linearizable" the program is. Proton computed tomography (pCT) is a medical imaging technology with the potential to increase the spatial accuracy of the dose delivered in proton-beam radiotherapy. The Bergen pCT collaboration is developing and constructing a digital tracking calorimeter (DTC) to measure the position, direction and energy of protons after they passed through a patient, and a software pipeline to process these data into a pCT image. We revisit the software pipeline from the perspective of algorithmic differentiation (AD). In the early subprocedures, several obstacles such as discrete variables or frequent discontinuities were identified, and are probably tackled best by using surrogate models. The model-based iterative reconstruction (MBIR) subprocedure in the end seems to be AD-ready, and we propose changes in the AD workflow that can reduce the memory consumption in reverse mode.

First measurement of the absorption of 3He nuclei in matter and impact on their propagation in the galaxy - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2022)
Antimatter particles such as positrons and antiprotons abound in the cosmos. Much less common are light antinuclei, composed of antiprotons and antineutrons, which can be produced in our galaxy via high-energy cosmic-ray collisions with the interstellar medium or could also originate from the annihilation of the still undiscovered dark-matter particles. On Earth, the only way to produce and study antinuclei with high precision is to create them at high-energy particle accelerators like the Large Hadron Collider (LHC). Though the properties of elementary antiparticles have been studied in detail, knowledge of the interaction of light antinuclei with matter is rather limited. This work focuses on the determination of the disappearance probability of when it encounters matter particles and annihilates or disintegrates. The material of the ALICE detector at the LHC serves as a target to extract the inelastic cross section for in the momentum range of 1.17≤p<10 GeV/c. This inelastic cross section is measured for the first time and is used as an essential input to calculations of the transparency of our galaxy to the propagation of 3He stemming from dark-matter decays and cosmic-ray interactions within the interstellar medium. A transparency of about 50% is estimated using the GALPROP program for a specific dark-matter profile and a standard set of propagation parameters. For cosmic-ray sources, the obtained transparency with the same propagation scheme varies with increasing 3He momentum from 25% to 90%. The absolute uncertainties associated to the 3He inelastic cross section measurements are of the order of 10%−15%. The reported results indicate that 3He nuclei can travel long distances in the galaxy, and can be used to study cosmic-ray interactions and dark-matter decays.

First study of the two-body scattering involving charm hadrons - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2022)
This Letter presents the first measurement of the interaction between charm hadrons and nucleons. The two-particle momentum correlations of pD− and pD+ pairs are measured by the ALICE Collaboration in high-multiplicity pp collisions at s√=13 TeV. The data are compatible with the Coulomb-only interaction hypothesis within (1.1-1.5)σ. Considering an attractive nucleon(N)D strong interaction, in contrast to most model predictions which suggest an overall repulsive interaction, slightly improves the level of agreement. This measurement allows for the first time an estimation of the 68% confidence level interval for the isospin I=0 inverse scattering length of the ND state f−10, I=0∈[−0.4,0.9] fm−1, assuming negligible interaction for the isospin I=1 channel.

Investigating charm production and fragmentation via azimuthal correlations of prompt D mesons with charged particles in pp collisions at s = 13 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (The European Physical Journal C, 2022)
Angular correlations of heavy-flavour and charged particles in high-energy proton-proton collisions are sensitive to the production mechanisms of heavy quarks and to their fragmentation as well as hadronisation processes. The measurement of the azimuthal-correlation function of prompt D mesons with charged particles in proton-proton collisions at a centre-of-mass energy of 𝑠√=13TeV with the ALICE detector is reported, considering D0, D+, and D∗+mesons in the transverse-momentum interval 3<𝑝T<36 GeV/𝑐at midrapidity 𝑦|<0.5), and charged particles with 𝑝T>0.3 GeV/𝑐 and pseudorapidity |𝜂|<0.8. This measurement has an improved precision and provides an extended transverse-momentum coverage compared to previous ALICE measurements at lower energies. The study is also performed as a function of the charged-particle multiplicity, showing no modifications of the correlation function with multiplicity within uncertainties. The properties and the transverse-momentum evolution of the near- and away-side correlation peaks are studied and compared with predictions from various Monte Carlo event generators. Among those considered, PYTHIA8 and POWHEG+PYTHIA8 provide the best description of the measured observables. The obtained results can provide guidance on tuning the generators.

Measurement of beauty production in Pb-Pb collisions at √sNN‾ = 5.02 TeV via non-prompt Ds+ mesons - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2022)
The production of non-prompt D0 mesons from beauty-hadron decays was measured at midrapidity (∣∣y∣∣<0.5) in Pb-Pb collisions at a nucleon-nucleon center-of-mass energy of sNN‾‾√=5.02 TeV with the ALICE experiment at the LHC. Their nuclear modification factor (RAA), measured for the first time down to pT=1 GeV/c in the 0−10% and 30−50% centrality classes, indicates a significant suppression, up to a factor of about three, for pT>5 GeV/c in the 0−10% central Pb-Pb collisions. The data are described by models that include both collisional and radiative processes in the calculation of beauty-quark energy loss in the quark-gluon plasma, and quark recombination in addition to fragmentation as a hadronization mechanism. The ratio of the non-prompt to prompt D0 meson RAA is larger than unity for pT>4 GeV/c in the 0−10% central Pb-Pb collisions, as predicted by models in which beauty quarks lose less energy than charm quarks in the quark-gluon plasma because of their larger mass.

Measurement of inclusive charged-particle b-jet production in pp and p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Journal of High Energy Physics, 2022)
A measurement of the inclusive b-jet production cross section is presented in pp and p-Pb collisions at sNN‾‾‾‾√=5.02 TeV, using data collected with the ALICE detector at the LHC. The jets were reconstructed in the central rapidity region |η|<0.5 from charged particles using the anti-kT algorithm with resolution parameter R=0.4. Identification of b jets exploits the long lifetime of b-hadrons, using the properties of secondary vertices and impact parameter distributions. The pT-differential inclusive production cross section of b jets, as well as the corresponding inclusive b-jet fraction, are reported for pp and p-Pb collisions in the jet transverse momentum range 10≤pT, ch jet≤100 GeV/c, together with the nuclear modification factor, Rb-jetpPb. The analysis thus extends the lower pT limit of b-jet measurements at the LHC. The nuclear modification factor is found to be consistent with unity, indicating that the production of b jets in p–Pb at sNN‾‾‾‾√=5.02 TeV is not affected by cold nuclear matter effects within the current precision. The measurements are well reproduced by POWHEG NLO pQCD calculations with PYTHIA fragmentation.

Measurement of Prompt D0, Λc+, and Σc0,++(2455) Production in Proton-Proton Collisions at s=13 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Physical Review Letters, 2022)
The pT-differential production cross sections of prompt D0, Λ+c, and Σ0,++c(2455) charmed hadrons are measured at midrapidity (|y|<0.5) in pp collisions at s√=13 TeV. This is the first measurement of Σ0,++c production in hadronic collisions. Assuming the same production yield for the three Σ0,+,++c isospin states, the baryon-to-meson cross section ratios Σ0,+,++c/D0 and Λ+c/D0 are calculated in the transverse momentum (pT) intervals 2<pT<12 GeV/c and 1<pT<24 GeV/c. Values significantly larger than in e+e− collisions are observed, indicating for the first time that baryon enhancement in hadronic collisions also extends to the Σc. The feed-down contribution to Λ+c production from Σ0,+,++c is also reported and is found to be larger than in e+e− collisions. The data are compared with predictions from event generators and other phenomenological models, providing a sensitive test of the different charm-hadronisation mechanisms implemented in the models.

Multiplicity dependence of charged-particle jet production in pp collisions at √s=13 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2022)
The multiplicity dependence of jet production in pp collisions at the centre-of-mass energy of √s=13 TeV is studied for the first time. Jets are reconstructed from charged particles using the anti-kT algorithm with resolution parameters R varying from 0.2 to 0.7. The jets are measured in the pseudorapidity range |ηjet|<0.9−R and in the transverse momentum range 5<pchT,jet<140 GeV/c. The multiplicity intervals are categorised by the ALICE forward detector V0. The pT differential cross section of charged-particle jets are compared to leading order (LO) and next-to-leading order (NLO) perturbative quantum chromodynamics (pQCD) calculations. It is found that the data are better described by the NLO calculation, although the NLO prediction overestimates the jet cross section below 20 GeV/c. The cross section ratios for different R are also measured and compared to model calculations. These measurements provide insights into the angular dependence of jet fragmentation. The jet yield increases with increasing self-normalised charged-particle multiplicity. This increase shows only a weak dependence on jet transverse momentum and resolution parameter at the highest multiplicity. While such behaviour is qualitatively described by the present version of PYTHIA, quantitative description may require implementing new mechanisms for multi-particle production in hadronic collisions.

Nuclear modification factor of light neutral-meson spectra up to high transverse momentum in p-Pb collisions at sNN=8.16 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; I. Ahuja; et al. (Physics Letters B, 2022)
Neutral pion and η meson production cross sections were measured up to unprecedentedly high transverse momenta (pT) in p-Pb collisions at sNN‾‾‾‾√ = 8.16 TeV. The mesons were reconstructed via their two-photon decay channel in the rapidity interval −1.3<y<0.3 in the ranges of 0.4<pT<200 GeV/c and 1.0<pT<50 GeV/c, respectively. The respective nuclear modification factor (RpPb) is presented for pT up to of 200 and 30 GeV/c, where the former was achieved extending the π0 measurement in pp collisions at s√ = 8 TeV. The values of RpPb are below unity for pT<10 GeV/c, while they are consistent with unity for pT>10 GeV/c. The new data provide constraints for nuclear parton distribution and fragmentation functions over a broad kinematic range and are compared to model predictions as well as previous results at sNN‾‾‾‾√ = 5.02 TeV.

Production of K*(892)0 and ϕ(1020) in pp and Pb−Pb collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; Z. Akbar; et al. (Physical Review C, 2022)
The production of K∗(892)0 and ϕ(1020) mesons in proton-proton (pp) and lead-lead (Pb-Pb) collisions at sNN‾‾‾‾√=5.02 TeV has been measured using the ALICE detector at the Large Hadron Collider (LHC). The transverse momentum (pT) distributions of K∗(892)0 and ϕ(1020) mesons have been measured at midrapidity (|y|<0.5) up to pT=20 GeV/c in inelastic pp collisions and for several Pb-Pb collision centralities. The collision centrality and collision energy dependence of the average transverse momenta agree with the radial flow scenario observed with stable hadrons, showing that the effect is stronger for more central collisions and higher collision energies. The K∗0/K ratio is found to be suppressed in Pb-Pb collisions relative to pp collisions: this indicates a loss of the measured K∗(892)0 signal due to rescattering of its decay products in the hadronic phase. In contrast, for the longer-lived ϕ(1020) mesons, no such suppression is observed. The nuclear modification factors (RAA) of K∗(892)0 and ϕ(1020) mesons are calculated using pp reference spectra at the same collision energy. In central Pb-Pb collisions for pT>8 GeV/c, the RAA values of K∗(892)0 and ϕ(1020) are below unity and observed to be similar to those of pions, kaons, and (anti)protons. The RAA values at high pT (>8 GeV/c) for K∗(892)0 and ϕ(1020) mesons are in agreement within uncertainties for sNN‾‾‾‾√=5.02 and 2.76 TeV.

Prompt D0, D+, and D∗+ production in Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Journal of High Energy Physics, 2022)
The production of prompt D0, D+, and D∗+ mesons was measured at midrapidity (|y|< 0.5) in Pb-Pb collisions at the centre-of-mass energy per nucleon-nucleon pair sNN‾‾‾‾√ = 5.02 TeV with the ALICE detector at the LHC. The D mesons were reconstructed via their hadronic decay channels and their production yields were measured in central (0-10%) and semicentral (30-50%) collisions. The measurement was performed up to a transverse momentum (pT) of 36 or 50 GeV/c depending on the D meson species and the centrality interval. For the first time in Pb-Pb collisions at the LHC, the yield of D0 mesons was measured down to pT = 0, which allowed a model-independent determination of the pT-integrated yield per unit of rapidity (dN/dy). A maximum suppression by a factor 5 and 2.5 was observed with the nuclear modification factor (RAA) of prompt D mesons at pT = 6-8 GeV/c for the 0-10% and 30-50% centrality classes, respectively. The D-meson RAA is compared with that of charged pions, charged hadrons, and J/ψ mesons as well as with theoretical predictions. The analysis of the agreement between the measured RAA, elliptic (v2) and triangular (v3) flow, and the model predictions allowed us to constrain the charm spatial diffusion coefficient Ds. Furthermore the comparison of RAA and v2 with different implementations of the same models provides an important insight into the role of radiative energy loss as well as charm quark recombination in the hadronisation mechanisms.

Semi-Automatic Particle Tracking for and Visualization of Particle Detector Data - Robin Eschbach; Kai Messerschmidt; Ralf Keidel; Alexander Wiebel (The Eurographics Association, 2022)
In high energy physics, tracking particles in point-based particle detector data is important to reconstruct the particles’ trajectories. As the numbers of particles can be in the hundreds or over a thousand, automatic algorithmic tracking is usually preferred over manual tracking. However, in some cases, manual tracking is needed as a baseline to assess the quality of the algorithmic tracking. Tracking particle locations manually is time-consuming and challenging when dealing with thousands of particles in the same data frame. In this paper, we describe Semi-Automatic Particle Tracking (SAPT), a collection of methods that aid manual particle tracking and visualization. These methods aim to make related particle hits easier to recognize by stretching the data and hiding likely irrelevant hits based on an angle criterion. They also help with finding the most likely track among a set of intuitively selected detector hits. These methods, together with a prediction of the most probable continuation of a track that can simply be accepted by the human user, accelerate the manual tracking process tremendously. We demonstrate the usefulness and efficiency of our methods by applying them to simulation data of a detector for proton computed tomography (pCT).

Toward the End-to-End Optimization of Particle Physics Instruments with Differentiable Programming: a White Paper - Tommaso Dorigo; Andrea Giammanco; Ralf Keidel; Pietro Vischia (2022)
The full optimization of the design and operation of instruments whose functioning relies on the interaction of radiation with matter is a super-human task, given the large dimensionality of the space of possible choices for geometry, detection technology, materials, data-acquisition, and information-extraction techniques, and the interdependence of the related parameters. On the other hand, massive potential gains in performance over standard, "experience-driven" layouts are in principle within our reach if an objective function fully aligned with the final goals of the instrument is maximized by means of a systematic search of the configuration space. The stochastic nature of the involved quantum processes make the modeling of these systems an intractable problem from a classical statistics point of view, yet the construction of a fully differentiable pipeline and the use of deep learning techniques may allow the simultaneous optimization of all design parameters. In this document we lay down our plans for the design of a modular and versatile modeling tool for the end-to-end optimization of complex instruments for particle physics experiments as well as industrial and medical applications that share the detection of radiation as their basic ingredient. We consider a selected set of use cases to highlight the specific needs of different applications.

Towards Neural Charged Particle Tracking in Proton Computed Tomography with Reinforcement Learning - Tobias Kortus; Ralf Keidel; Nicolas R. Gauger (2022)
Proton computed tomography (pCT) is an emerging imaging modality, receiving increasing importance for treatment planning in hadron therapy. One of the core challenges in the reconstruction pipeline for the high-granularity Bergen pCT Digital Tracking Calorimeter (DTC) prototype is the efficient reconstruction of high-multiplicity proton traces throughout the scanner which, in contrast to X-rays used in conventional CT, do not travel in a straight line. For this application, we propose a novel sequential tracking scheme based on model-free reinforcement learning working on graph-structured data, allowing for ground-truth free training of deep neural network architectures. For optimization, we consider only partial-information in terms of a scalar reward function, modeled based on the Gaussian approximation of the underlying theory of multiple Coulomb scattering. Given this information, we aim to find a policy that maximizes the plausibility of reconstructed tracks. We demonstrate on Monte Carlo simulated data the high potential as well as the current limitations of this approach. Primary

Tracking of Proton Traces in a Digital Tracking Calorimeter using Reinforcement Learning - Tobias Kortus; Ralf Keidel; Nicolas R. Gauger (2022)
Particle therapy using protons or heavy ions is a relatively new cancer treatment modality which has acquired increasing popularity in the last decade, due to its potential in reducing undesired dose to the nearby healthy tissues, with respect to conventional radiotherapy. However, current clinical treatment planning based on computed tomography suffers from modest range uncertainties due to inaccurate conversions of Hounsfield units (HU) to relative stopping power (RSP). Proton computed tomography (pCT) poses an alternative imaging technique promising accurate pre-imaging of patients for treatment planning reducing uncertainties in dose distribution calculations. In contrast to X-rays used in conventional CT, protons do not travel on a straight line throughout patient and detector due to interactions with the traversed matter and thus require a reconstruction of the taken path prior to image reconstruction. We propose a novel track following technique based on deep reinforcement learning (RL) for recovering proton traces inside the DTC where we formalize the task at hand as a Markov decision process (MDP) on a graph. Here we aim to learn a deterministic policy parametrized by a deep neural network optimizing the physical plausibility of sequential transitions between nodes, describing proton hit centroids. In a proof of principle study on Monte Carlo simulated data, we show that modeling of elastic nuclear interactions is a sufficient metric for a dense reward function allowing the optimization of proton traces in homogeneous detector configurations without knowledge of the ground truth. Moreover, with reinforcement learning we can reconstruct at the current stage trajectories originating from a variety of phantoms and particle densities with accuracies in the 50-98% range while being able to relocate the optimization steps to an initial training phase and thus avoid performing recursive or iterative optimization of proton tracks during inference. Currently this approach is limited to homogeneous detectors lacking the ability to efficiently trace protons over tracking layers. Finally, at the moment we rely on ground-truth seeding for finding initial track seeds in order to avoid unwanted behavior on the reinforcement learning approach.

Anisotropic flow of identified hadrons in Xe-Xe collisions at sNN‾‾‾‾√ = 5.44TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; Z. Akbar; et al. (Journal of High Energy Physics, 2021)
Measurements of elliptic (v2) and triangular (v3) flow coefficients of π±, K±, p+p⎯⎯⎯, K0S, and Λ+Λ⎯⎯⎯⎯ obtained with the scalar product method in Xe-Xe collisions at sNN‾‾‾‾√ = 5.44 TeV are presented. The results are obtained in the rapidity range ∣∣y∣∣<0.5 and reported as a function of transverse momentum, pT, for several collision centrality classes. The flow coefficients exhibit a particle mass dependence for pT<3 GeV/c, while a grouping according to particle type (i.e., meson and baryon) is found at intermediate transverse momenta (3< pT <8 GeV/c). The magnitude of the baryon v2 is larger than that of mesons up to pT = 6 GeV/c. The centrality dependence of the shape evolution of the pT-differential v2 is studied for the various hadron species. The v2 coefficients of π±, K±, and p+p⎯⎯⎯ are reproduced by MUSIC hydrodynamic calculations coupled to a hadronic cascade model (UrQMD) for pT<1 GeV/c. A comparison with vn measurements in the corresponding centrality intervals in Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV yields an enhanced v2 in central collisions and diminished value in semicentral collisions.

Characterizing the initial conditions of heavy-ion collisions at the LHC with mean transverse momentum and anisotropic flow correlations - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (arXiv, 2021)
Correlations between mean transverse momentum [pT] and anisotropic flow coefficients v2 or v3 are measured as a function of centrality in Pb-Pb and Xe-Xe collisions at sNN‾‾‾‾√=5.02 TeV and 5.44 TeV, respectively, with ALICE. In addition, the recently proposed higher-order correlation between [pT], v2, and v3 is measured for the first time, which shows an anticorrelation for the presented centrality ranges. These measurements are compared with hydrodynamic calculations using IP-Glasma and TRENTo initial-state shapes, the former based on the Color Glass Condensate effective theory with gluon saturation, and the latter a parameterized model with nucleons as the relevant degrees of freedom. The data are better described by the IP-Glasma rather than the TRENTo based calculations. In particular, Trajectum and JETSCAPE predictions, both based on the TRENTo initial state model but with different parameter settings, fail to describe the measurements. As the correlations between [pT] and vn are mainly driven by the correlations of the size and the shape of the system in the initial state, these new studies pave a novel way to characterize the initial state in relativistic heavy-ion collisions.

Charged-particle multiplicity fluctuations in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (The European Physical Journal C, 2021)
Measurements of event-by-event fluctuations of charged-particle multiplicities in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV using the ALICE detector at the CERN Large Hadron Collider (LHC) are presented in the pseudorapidity range |η|<0.8 and transverse momentum 0.2<pT<2.0 GeV/c. The amplitude of the fluctuations is expressed in terms of the variance normalized by the mean of the multiplicity distribution. The η and pT dependences of the fluctuations and their evolution with respect to collision centrality are investigated. The multiplicity fluctuations tend to decrease from peripheral to central collisions. The results are compared to those obtained from HIJING and AMPT Monte Carlo event generators as well as to experimental data at lower collision energies. Additionally, the measured multiplicity fluctuations are discussed in the context of the isothermal compressibility of the high-density strongly-interacting system formed in central Pb-Pb collisions.

Coherent J/ψ and ψ′ photoproduction at midrapidity in ultra-peripheral Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; Z. Akbar; et al. (The European Physical Journal C, 2021)
The coherent photoproduction of J/ψ and ψ′ mesons was measured in ultra-peripheral Pb-Pb collisions at a center-of-mass energy sNN‾‾‾‾√ = 5.02 TeV with the ALICE detector. Charmonia are detected in the central rapidity region for events where the hadronic interactions are strongly suppressed. The J/ψ is reconstructed using the dilepton (l+l−) and proton-antiproton decay channels, while for the ψ′, the dilepton and the l+l−π+π− decay channels are studied. The analysis is based on an event sample corresponding to an integrated luminosity of about 233 μb−1. The results are compared with theoretical models for coherent J/ψ and ψ′ photoproduction. The coherent cross section is found to be in a good agreement with models incorporating moderate nuclear gluon shadowing of about 0.65 at a Bjorken-x of around 6×10−4, such as the EPS09 parametrization, however none of the models is able to fully describe the rapidity dependence of the coherent J/ψ cross section including ALICE measurements at forward rapidity. The ratio of ψ′ to J/ψ coherent photoproduction cross sections was also measured and found to be consistent with the one for photoproduction off protons.

Constraining hadronization mechanisms with Λ+c/D0 production ratios in Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (arXiv, 2021)
The production of prompt Λ+c baryons at midrapidity (|y|<0.5) was measured in central (0-10%) and mid-central (30-50%) Pb-Pb collisions at the center-of-mass energy per nucleon-nucleon pair sNN‾‾‾‾√=5.02 TeV with the ALICE detector. The Λ+c production yield, the Λ+c/D0 production ratio, and the Λ+c nuclear modification factor RAA are reported. The results are more precise and more differential in transverse momentum (pT) and centrality with respect to previous measurements. The Λ+c/D0 ratio, which is enhanced with respect to the pp measurement for 4<pT<8 GeV/c, is described by theoretical calculations that model the charm-quark transport in the quark-gluon plasma and include hadronization via both coalescence and fragmentation mechanisms.

Direct observation of the dead-cone effect in QCD - S. Acharya; D. Adamová; Ralf Keidel; A. Adler (arXiv, 2021)
At particle collider experiments, elementary particle interactions with large momentum transfer produce quarks and gluons (known as partons) whose evolution is governed by the strong force, as described by the theory of quantum chromodynamics (QCD). The vacuum is not transparent to the partons and induces gluon radiation and quark pair production in a process that can be described as a parton shower. Studying the pattern of the parton shower is one of the key experimental tools in understanding the properties of QCD. This pattern is expected to depend on the mass of the initiating parton, through a phenomenon known as the dead-cone effect, which predicts a suppression of the gluon spectrum emitted by a heavy quark of mass m and energy E, within a cone of angular size m/E around the emitter. A direct observation of the dead-cone effect in QCD has not been possible until now, due to the challenge of reconstructing the cascading quarks and gluons from the experimentally accessible bound hadronic states. We report the first direct observation of the QCD dead-cone by using new iterative declustering techniques to reconstruct the parton shower of charm quarks. This result confirms a fundamental feature of QCD, which is derived more generally from its origin as a gauge quantum field theory. Furthermore, the measurement of a dead-cone angle constitutes a direct experimental observation of the non-zero mass of the charm quark, which is a fundamental constant in the standard model of particle physics.

Energy dependence of ϕ meson production at forward rapidity in pp collisions at the LHC - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (The European Physical Journal C, 2021)
The production of ϕ mesons has been studied in pp collisions at LHC energies with the ALICE detector via the dimuon decay channel in the rapidity region 2.5<y<4. Measurements of the differential cross section d2σ/dydpT are presented as a function of the transverse momentum (pT) at the center-of-mass energies s√=5.02, 8 and 13 TeV and compared with the ALICE results at midrapidity. The differential cross sections at s√=5.02 and 13 TeV are also studied in several rapidity intervals as a function of pT, and as a function of rapidity in three pT intervals. A hardening of the pT-differential cross section with the collision energy is observed, while, for a given energy, pT spectra soften with increasing rapidity and, conversely, rapidity distributions get slightly narrower at increasing pT. The new results, complementing the published measurements at s√=2.76 and 7 TeV, allow one to establish the energy dependence of ϕ meson production and to compare the measured cross sections with phenomenological models.

Experimental Evidence for an Attractive p−ϕ Interaction - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Physical Review Letters, 2021)
This Letter presents the first experimental evidence of the attractive strong interaction between a proton and a ϕ meson. The result is obtained from two-particle correlations of combined p-ϕ⊕p⎯⎯⎯-ϕ pairs measured in high-multiplicity pp collisions at s√ = 13 TeV by the ALICE collaboration. The spin-averaged scattering length and effective range of the p-ϕ interaction are extracted from the fully corrected correlation function employing the Lednický-Lyuboshits approach. In particular, the imaginary part of the scattering length vanishes within uncertainties, indicating that inelastic processes do not play a prominent role for the p-ϕ interaction. These data demonstrate that the interaction is dominated by elastic p-ϕ scattering. Furthermore, an analysis employing phenomenological Gaussian- and Yukawa-type potentials is conducted. Under the assumption of the latter, the N-ϕ coupling constant is found to be gN−ϕ=0.14±0.03(stat.)±0.02(syst.). This work provides valuable experimental input to accomplish a self-consistent description of the N-ϕ interaction, which is particularly relevant for the more fundamental studies on partial restoration of chiral symmetry in nuclear medium.

Exploring the NΛ-NΣ coupled system with high precision correlation techniques at the LHC - S. Acharya; D. Adamová; Ralf Keidel; A. Adler (arXiv, 2021)
The interaction of Λ and Σ hyperons (Y) with nucleons (N) is strongly influenced by the coupled-channel dynamics. Due to the small mass difference of the NΛ and NΣ systems, the coupling strength of the NΣ↔NΛ processes is non-negligible and constitutes a crucial element in the determination of the NΛ interaction. In this letter we present the most precise measurements on the interaction of pΛ pairs, from zero relative momentum up to the opening of the NΣ channel. The correlation function in the relative momentum space for pΛ⊕p⎯⎯⎯Λ⎯⎯⎯⎯ pairs measured in high-multiplicity triggered pp collisions at s√ = 13 TeV at the LHC is reported. The opening of the inelastic NΣ channels is visible in the extracted correlation function as a cusp-like structure occurring at relative momentum k∗ = 289 MeV/c. This represents the first direct experimental observation of the NΣ→NΛ coupled channel in the pΛ system. The correlation function is compared with recent chiral effective field theory calculations, based on different strengths of the NΣ↔NΛ transition potential. A weaker coupling, as possibly supported by the present measurement, would require a more repulsive three-body NNΛ interaction for a proper description of the Λ in-medium properties, which has implications on the nuclear equation of state and for the presence of hyperons inside neutron stars.

First measurement of coherent ρ0 photoproduction in ultra-peripheral Xe-Xe collisions at sNN=5.44 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; Z. Akbar; et al. (Physics Letters B, 2021)
The first measurement of the coherent photoproduction of ρ0 vector mesons in ultra-peripheral Xe-Xe collisions at sNN‾‾‾‾√=5.44 TeV is presented. This result, together with previous HERA γp data and γ-Pb measurements from ALICE, describes the atomic number (A) dependence of this process, which is particularly sensitive to nuclear shadowing effects and to the approach to the black-disc limit of QCD at a semi-hard scale. The cross section of the Xe+Xe→ρ0+Xe+Xe process, measured at midrapidity through the decay channel ρ0→π+π−, is found to be dσ/dy=131.5±5.6(stat.)+17.5−16.9(syst.) mb. The ratio of the continuum to resonant contributions for the production of pion pairs is also measured. In addition, the fraction of events accompanied by electromagnetic dissociation of either one or both colliding nuclei is reported. The dependence on A of cross section for the coherent ρ0 photoproduction at a centre-of-mass energy per nucleon of the γA system of WγA,n=65 GeV is found to be consistent with a power-law behaviour σ(γA→ρ0A)∝Aα with a slope α=0.96±0.02(syst.). This slope signals important shadowing effects, but it is still far from the behaviour expected in the black-disc limit.

First measurement of the |t|-dependence of coherent J/ψ photonuclear production - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; Z. Akbar; et al. (Physics Letters B, 2021)
The first measurement of the cross section for coherent J/ψ photoproduction as a function of |t|, the square of the momentum transferred between the incoming and outgoing target nucleus, is presented. The data were measured with the ALICE detector in ultra-peripheral Pb-Pb collisions at a centre-of-mass energy per nucleon pair sNN‾‾‾‾√=5.02 TeV with the J/ψ produced in the central rapidity region |y|<0.8, which corresponds to the small Bjorken-x range (0.3−1.4)×10−3. The measured |t|-dependence is not described by computations based only on the Pb nuclear form factor, while the photonuclear cross section is better reproduced by models including shadowing according to the leading-twist approximation, or gluon-saturation effects from the impact-parameter dependent Balitsky-Kovchegov equation. These new results are therefore a valid tool to constrain the relevant model parameters and to investigate the transverse gluonic structure at very low Bjorken-x.

First measurements of N-subjettiness in central Pb−Pb collisions at sNN‾‾‾‾√=2.76 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Journal of High Energy Physics, 2021)
The ALICE Collaboration reports the first fully-corrected measurements of the N-subjettiness observable for track-based jets in heavy-ion collisions. This study is performed using data recorded in pp and Pb−Pb collisions at centre-of-mass energies of s√=7 TeV and sNN‾‾‾‾√=2.76 TeV, respectively. In particular the ratio of 2-subjettiness to 1-subjettiness, τ2/τ1, which is sensitive to the rate of two-pronged jet substructure, is presented. Energy loss of jets traversing the strongly interacting medium in heavy-ion collisions is expected to change the rate of two-pronged substructure relative to vacuum. The results are presented for jets with a resolution parameter of R=0.4 and charged jet transverse momentum of 40≤pT,jet≤60 GeV/c, which constitute a larger jet resolution and lower jet transverse momentum interval than previous measurements in heavy-ion collisions. This has been achieved by utilising a semi-inclusive hadron-jet coincidence technique to suppress the larger jet combinatorial background in this kinematic region. No significant modification of the τ2/τ1 observable for track-based jets in Pb–Pb collisions is observed relative to vacuum PYTHIA6 and PYTHIA8 references at the same collision energy. The measurements of τ2/τ1, together with the splitting aperture angle ΔR, are also performed in pp collisions at s√=7 TeV for inclusive jets. These results are compared with PYTHIA calculations at s√=7 TeV, in order to validate the model as a vacuum reference for the Pb−Pb centre-of-mass energy. The PYTHIA references for τ2/τ1 are shifted to larger values compared to the measurement in pp collisions. This hints at a reduction in the rate of two-pronged jets in Pb–Pb collisions compared to pp collisions.

Forward rapidity J/ψ production as a function of charged-particle multiplicity in pp collisions at s√= 5.02 and 13 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2021)
The production of J/ψ is measured as a function of charged-particle multiplicity at forward rapidity in proton−proton (pp) collisions at center-of-mass energies s√= 5.02 and 13 TeV. The J/ψ mesons are reconstructed via their decay into dimuons in the rapidity interval (2.5 <y< 4.0), whereas the charged-particle multiplicity density () is measured at midrapidity (|η|<1). The production rate as a function of multiplicity is reported as the ratio of the yield in a given multiplicity interval to the multiplicity-integrated one. This observable shows a linear increase with charged-particle multiplicity normalized to the corresponding average value for inelastic events (dNch/dη/⟨dNch/dη⟩), at both the colliding energies. Measurements are compared with available ALICE results at midrapidity and theoretical model calculations. First measurement of the mean transverse momentum (⟨pT⟩) of J/ψ in pp collisions exhibits an increasing trend as a function of dNch/dη/⟨dNch/dη⟩ showing a saturation towards high charged-particle multiplicities.

General balance functions of identified charged hadron pairs of (π,K,p) in Pb−Pb collisions at sNN‾‾‾‾√=2.76 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (arXiv, 2021)
First measurements of balance functions (BFs) of all combinations of identified charged hadron (π,K,p) pairs in Pb−Pb collisions at sNN‾‾‾‾√=2.76 TeV recorded by the ALICE detector are presented. The BF measurements are carried out as two-dimensional differential correlators versus the relative rapidity (Δy) and azimuthal angle (Δφ) of hadron pairs, and studied as a function of collision centrality. The Δφ dependence of BFs is expected to be sensitive to the light quark diffusivity in the quark−gluon plasma. While the BF azimuthal widths of all pairs substantially decrease from peripheral to central collisions, the longitudinal widths exhibit mixed behaviors: BFs of ππ and cross-species pairs narrow significantly in more central collisions, whereas those of KK and pp are found to be independent of collision centrality. This dichotomy is qualitatively consistent with the presence of strong radial flow effects and the existence of two stages of quark production in relativistic heavy-ion collisions. Finally, the first measurements of the collision centrality evolution of BF integrals are presented, with the observation that charge balancing fractions are nearly independent of collision centrality in Pb−Pb collisions. Overall, the results presented provide new and challenging constraints for theoretical models of hadron production and transport in relativistic heavy-ion collisions.

Hypertriton production in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - S. Acharya; D. Adamová; Ralf Keidel; A. Adler (arXiv, 2021)
The study of nuclei and antinuclei production has proven to be a powerful tool to investigate the formation mechanism of loosely bound states in high-energy hadronic collisions. The first measurement of the production of 3ΛH in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV is presented in this Letter. Its production yield measured in the rapidity interval −1<y<0 for the 40% highest multiplicity p-Pb collisions is dN/dy=[6.3±1.8(stat.)±1.2(syst.)]×10−7. The measurement is compared with the expectations of statistical hadronisation and coalescence models, which describe the nucleosynthesis in hadronic collisions. These two models predict very different yields of the hypertriton in small collision systems such as p-Pb and therefore the measurement of dN/dy is crucial to distinguish between them. The precision of this measurement leads to the exclusion with a significance larger than 6σ of some configurations of the statistical hadronisation, thus constraining the production mechanism of loosely bound states.

Inclusive J/ψ production at midrapidity in pp collisions at s√ = 13 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; Z. Akbar; et al. (The European Physical Journal C, 2021)
We report on the inclusive J/ψ production cross section measured at the CERN Large Hadron Collider in proton-proton collisions at a centre-of-mass energy s√ = 13 TeV. The J/ψ mesons are reconstructed in the e+e− decay channel and the measurements are performed at midrapidity (|y|<0.9) in the transverse-momentum interval 0<pT<40 GeV/c, using a minimum-bias data sample corresponding to an integrated luminosity Lint=32.2 nb−1 and an Electromagnetic Calorimeter triggered data sample with Lint=8.3 pb−1. The pT-integrated J/ψ production cross section at midrapidity, computed using the minimum-bias data sample, is dσ/dy|y=0=8.97±0.24 (stat)±0.48 (syst)±0.15 (lumi) μb. An approximate logarithmic dependence with the collision energy is suggested by these results and available world data, in agreement with model predictions. The integrated and pT-differential measurements are compared with measurements in pp collisions at lower energies and with several recent phenomenological calculations based on the non-relativistic QCD and Color Evaporation models.

Inclusive quarkonium production in pp collisions at s√=5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (arXiv, 2021)
This article reports on the inclusive production cross section of several quarkonium states, J/ψ, ψ(2S), Υ(1S), Υ(2S), and Υ(3S), measured with the ALICE detector at the LHC, in collisions at s√=5.02 TeV. The analysis is performed in the dimuon decay channel at forward rapidity (2.5<y<4). The measured cross sections, assuming unpolarized quarkonia, are: σJ/ψ=5.88±0.03±0.34 μb, σψ(2S)=0.87±0.06±0.10 μb, σΥ(1S)=45.5±3.9±3.5 nb, σΥ(2S)=22.4±3.2±2.7 nb, and σΥ(3S)=4.9±2.2±1.0 nb, where the first (second) uncertainty is the statistical (systematic) one. The transverse-momentum (pT) and rapidity (y) differential cross sections for J/ψ, ψ(2S), Υ(1S), and the ψ(2S)-to-J/ψ cross section ratios are presented. For the first time, the cross sections of the three Υ states, as well as the ψ(2S) one as a function of pT and y, are measured at s√=5.02 TeV at forward rapidity. These measurements also significantly extend the J/ψ pT reach with respect to previously published results. A comparison with ALICE measurements in pp collisions at s√=2.76, 7, 8, and 13 TeV is presented and the energy dependence of quarkonium production cross sections is discussed. Finally, the results are compared with the predictions from several production models.

Inclusive, prompt and non-prompt J/ψ production at midrapidity in p−Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; D. Adamová; Ralf Keidel; A. Adler (arXiv, 2021)
A measurement of inclusive, prompt, and non-prompt J/ψ production in p−Pb collisions at a nucleon–nucleon centre-of-mass energy sNN‾‾‾‾√=5.02 TeV is presented. The J/ψ mesons are reconstructed in the dielectron decay channel at midrapidity down to a transverse momentum pT=0. The inclusive J/ψ nuclear modification factor RpPb is calculated by comparing the results in p−Pb collisions to a measured proton−proton reference at the same centre-of-mass energy. Non-prompt J/ψ mesons, which originate from the decay of beauty hadrons, are separated from promptly produced J/ψ on a statistical basis for pT larger than 1.0 GeV/c. These results are based on the data sample collected by the ALICE detector during the 2016 LHC p−Pb run, corresponding to an integrated luminosity int=292±11μb−1, which is six times larger than the previous publications. The total uncertainty on the pT-integrated inclusive J/ψ and non-prompt J/ψ cross section are reduced by a factor 1.7 and 2.2, respectively. The measured cross sections and RpPb are compared with theoretical models that include various combinations of cold nuclear matter effects. From the non-prompt J/ψ production cross section, the bb⎯⎯⎯ production cross section at midrapidity, dσbb⎯⎯⎯/dy, and the total cross section extrapolated over full phase space, σbb⎯⎯⎯, are derived.

Investigating particle track topology for range telescopes in particle radiography using convolutional neural networks - Helge Egil Seime Pettersen; Max Aehle; Johan Alme; Gergely Gábor Barnaföldi; Vyacheslav Borshchov; Anthony van den Brink; Mamdouh Chaar; Viljar Eikeland; Grigory Feofilov; Christoph Garth; Nicolas R. Gauger; Georgi Genov; et al. (Acta Oncologica, 2021)
Background Proton computed tomography (pCT) and radiography (pRad) are proposed modalities for improved treatment plan accuracy and in situ treatment validation in proton therapy. The pCT system of the Bergen pCT collaboration is able to handle very high particle intensities by means of track reconstruction. However, incorrectly reconstructed and secondary tracks degrade the image quality. We have investigated whether a convolutional neural network (CNN)-based filter is able to improve the image quality. Material and methods The CNN was trained by simulation and reconstruction of tens of millions of proton and helium tracks. The CNN filter was then compared to simple energy loss threshold methods using the Area Under the Receiver Operating Characteristics curve (AUROC), and by comparing the image quality and Water Equivalent Path Length (WEPL) error of proton and helium radiographs filtered with the same methods. Results The CNN method led to a considerable improvement of the AUROC, from 74.3% to 97.5% with protons and from 94.2% to 99.5% with helium. The CNN filtering reduced the WEPL error in the helium radiograph from 1.03 mm to 0.93 mm while no improvement was seen in the CNN filtered pRads. Conclusion The CNN improved the filtering of proton and helium tracks. Only in the helium radiograph did this lead to improved image quality.

Investigating the role of strangeness in baryon−antibaryon annihilation at the LHC - S. Acharya; D. Adamová; Ralf Keidel; A. Adler (arXiv, 2021)
Annihilation dynamics plays a fundamental role in the baryon−antibaryon interaction (B−B⎯⎯⎯⎯) at low-energy and its strength and range are crucial in the assessment of possible baryon bound states. Experimental data on annihilation cross sections are available for the p−p⎯⎯⎯ system but not in the low relative momentum region. Data regarding the BB⎯⎯⎯⎯ interaction with strange degrees of freedom are extremely scarce or absent, hence the modeling of the annihilation contributions is mainly based on nucleon−antinucleon (N−N⎯⎯⎯⎯) results, when available. In this letter we present a measurement of the p−p⎯⎯⎯, p−Λ⎯⎯⎯⎯⊕p⎯⎯⎯−Λ and Λ−Λ⎯⎯⎯⎯ interaction using correlation functions in the relative momentum space in high-multiplicity triggered pp collisions at s√=13 TeV recorded by ALICE at the LHC. In the p−p⎯⎯⎯ system the couplings to the mesonic channels in different partial waves are extracted by adopting a coupled-channel approach with recent χEFT potentials. The inclusion of these inelastic channels provides good agreement with the data, showing a significant presence of the annihilation term down to zero momentum. Predictions obtained using the Lednický−Lyuboshits formula and scattering parameters obtained from heavy-ion collisions, hence mainly sensitive to elastic processes, are compared with the experimental p−Λ⎯⎯⎯⎯⊕p⎯⎯⎯−Λ and Λ−Λ⎯⎯⎯⎯ correlations. The model describes the Λ−Λ⎯⎯⎯⎯ data and underestimates the p−Λ⎯⎯⎯⎯⊕p⎯⎯⎯−Λ data in the region of momenta below 200 MeV/c. The observed deviation indicates a different contribution of annihilation channels to the two systems containing strange hadrons.

K∗(892)0 and ϕ(1020) production in p-Pb collisions at sNN‾‾‾‾√ = 8.16 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (arXiv, 2021)
The production of K∗(892)0 and ϕ(1020) resonances has been measured in p-Pb collisions at sNN‾‾‾‾√ = 8.16 TeV using the ALICE detector. Resonances are reconstructed via their hadronic decay channels in the rapidity interval −0.5 < y < 0 and the transverse momentum spectra are measured for various multiplicity classes up to pT = 20 GeV/c for K∗(892)0 and pT = 16 GeV/c for ϕ(1020). The pT -integrated yields and mean transverse momenta are reported and compared with previous results in pp, p-Pb and Pb-Pb collisions. The xT scaling for K∗(892)0 and ϕ(1020) resonance production is newly tested in p-Pb collisions and found to hold in the high-pT region at LHC energies. The nuclear modification factors (RpPb) as a function of pT for K∗0 and ϕ at sNN‾‾‾‾√ = 8.16 TeV are presented along with the new RpPb measurements of K∗0, ϕ , Ξ, and Ω at sNN‾‾‾‾√ = 5.02 TeV. At intermediate pT (2-8 GeV/c), RpPb of Ξ, Ω show a Cronin-like enhancement, while K∗0 and ϕ show no or little nuclear modification. At high pT (> 8 GeV/c), the RpPb values of all hadrons are consistent with unity within uncertainties. The RpPb of K∗(892)0 and ϕ(1020) at sNN‾‾‾‾√ = 8.16 and 5.02 TeV show no significant energy dependence.

K0S- and (anti-)Λ-hadron correlations in pp collisions at s√=13 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; Z. Akbar; et al. (The European Physical Journal C, 2021)
Two-particle azimuthal correlations are measured with the ALICE apparatus in pp collisions at s√=13 TeV to explore strangeness- and multiplicity-related effects in the fragmentation of jets and the transition regime between bulk and hard production, probed with the condition that a strange meson (K0S) or a baryon (Λ) with transverse momentum pT>3 GeV/c is produced. Azimuthal correlations between kaons or Λ hyperons with other hadrons are presented at midrapidity for a broad range of the trigger (3<ptriggT<20 GeV/c) and associated particle pT (1 GeV/c <passocT<ptriggT), for minimum-bias events and as a function of the event multiplicity. The near- and away-side peak yields are compared for the case of either K0S or Λ(Λ⎯⎯⎯⎯) being the trigger particle with that of inclusive hadrons (a sample dominated by pions). In addition, the measurements are compared with predictions from PYTHIA 8 and EPOS LHC event generators.

K0SK0S and K0SK± femtoscopy in pp collisions at s√= 5.02 and 13 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (arXiv, 2021)
Femtoscopic correlations with the particle pair combinations K0SK0S and K0SK± are studied in pp collisions at s√=5.02 and 13 TeV by the ALICE experiment. At both energies, boson source parameters are extracted for both pair combinations, by fitting models based on Gaussian size distributions of the sources, to the measured two-particle correlation functions. The interaction model used for the K0SK0S analysis includes quantum statistics and strong final-state interactions through the f0(980) and a0(980) resonances. The model used for the K0SK± analysis includes only the final-state interaction through the a0 resonance. Source parameters extracted in the present work are compared with published values from pp collisions at s√= 7 TeV and the different pair combinations are found to be consistent. From the finding that the strength of the K0SK0S correlations is significantly greater than the strength of the K0SK± correlations, the new results are compatible with the a0 resonance being a tetraquark state of the form (q1,q2⎯⎯⎯⎯⎯⎯,s,s⎯⎯), where q1 and q2 are u or d quarks.

Kaon-proton strong interaction at low relative momentum via femtoscopy in Pb-Pb collisions at the LHC - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; I. Ahuja; et al. (Physics Letters B, 2021)
In quantum scattering processes between two particles, aspects characterizing the strong and Coulomb forces can be observed in kinematic distributions of the particle pairs. The sensitivity to the interaction potential reaches a maximum at low relative momentum and vanishing distance between the two particles. Ultrarelativistic heavy-ion collisions at the LHC provide an abundant source of many hadron species and can be employed as a measurement method of scattering parameters that is complementary to scattering experiments. This study confirms that momentum correlations of particles produced in Pb-Pb collisions at the LHC provide an accurate measurement of kaon-proton scattering parameters at low relative momentum, allowing precise access to the K−p→K−p process. This work also validates the femtoscopic measurement in ultrarelativistic heavy-ion collisions as an alternative to scattering experiments and a complementary tool to the study of exotic atoms with comparable precision. In this work, the first femtoscopic measurement of momentum correlations of K−p (K+p⎯⎯⎯) and K+p(K−p⎯⎯⎯) pairs in Pb-Pb collisions at centre-of-mass energy per nucleon pair of sNN‾‾‾‾√=5.02 TeV registered by the ALICE experiment is reported. The components of the K−p complex scattering length are extracted and found to be ℜf0=−0.91± 0.03(stat)+0.17−0.03(syst) and ℑf0=0.92± 0.05(stat)+0.12−0.33(syst). The results are compared with chiral effective field theory predictions as well as with existing data from dedicated scattering and exotic kaonic atom experiments.

Long- and short-range correlations and their event-scale dependence in high-multiplicity pp collisions at s√=13 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (Journal of High Energy Physics, 2021)
Two-particle angular correlations are measured in high-multiplicity proton-proton collisions at s√=13 TeV by the ALICE Collaboration. The yields of particle pairs at short-(Δη ∼ 0) and long-range (1.6<|Δη|<1.8) in pseudorapidity are extracted on the near-side (Δφ ∼ 0). They are reported as a function of transverse momentum (pT) in the range 1<pT<4 GeV/c. Furthermore, the event-scale dependence is studied for the first time by requiring the presence of high-pT leading particles and jets for varying pT thresholds. The results demonstrate that the long-range "ridge" yield, possibly related to the collective behavior of the system, is present in events with high-pT processes. The magnitudes of the short- and long-range yields are found to grow with the event scale. The results are compared to EPOS LHC and PYTHIA 8 calculations, with and without string-shoving interactions. It is found that while both models describe the qualitative trends in the data, calculations from EPOS LHC show a better quantitative agreement, in particular for the pT and event-scale dependencies.

Measurement of beauty and charm production in pp collisions at s√=5.02 TeV via non-prompt and prompt D mesons - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; Z. Akbar; et al. (Journal of High Energy Physics, 2021)
The pT-differential production cross sections of prompt and non-prompt (produced in beauty-hadron decays) D mesons were measured by the ALICE experiment at midrapidity (|y|<0.5) in proton–proton collisions at s√=5.02 TeV. The data sample used in the analysis corresponds to an integrated luminosity of (19.3±0.4) nb−1. D mesons were reconstructed from their decays D0→K−π+, D+→K−π+π+, and D+s→ϕπ+→K−K+π+ and their charge conjugates. Compared to previous measurements in the same rapidity region, the cross sections of prompt D+ and D+s mesons have an extended pT coverage and total uncertainties reduced by a factor ranging from 1.05 to 1.6, depending on pT, allowing for a more precise determination of their pT-integrated cross sections. The results are well described by perturbative QCD calculations. The fragmentation fraction of heavy quarks to strange mesons divided by the one to non-strange mesons, fs/(fu+fd), is compatible for charm and beauty quarks and with previous measurements at different centre-of-mass energies and collision systems. The bb⎯⎯⎯ production cross section per rapidity unit at midrapidity, estimated from non-prompt D-meson measurements, is dσbb⎯⎯⎯/dy||y|<0.5=34.5±2.4(stat.)+4.7−2.9(tot.syst.) μb. It is compatible with previous measurements at the same centre-of-mass energy and with the cross section predicted by perturbative QCD calculations.

Measurement of K∗(892)± production in inelastic pp collisions at the LHC - S. Acharya; D. Adamová; Ralf Keidel; A. Adler (arXiv, 2021)
The first results on K∗(892)± resonance production in inelastic pp collisions at LHC energies of s√=5.02, 8, and 13 TeV are presented. The K∗(892)± has been reconstructed via its hadronic decay channel K∗(892)± → K0S + π± with the ALICE detector. Measurements of transverse momentum distributions, integrated yields, and mean transverse momenta for charged K∗(892) are found to be consistent with previous ALICE measurements for neutral K∗(892) within uncertainties. For pT>1 GeV/c the K∗(892)± transverse momentum spectra become harder with increasing centre-of-mass energy from 5.02 to 13 TeV, similar to what previously observed for charged kaons and pions. For pT<1 GeV/c the K∗(892)± yield does not evolve significantly and the abundance of K∗(892)± relative to K is rather independent of the collision energy. The transverse momentum spectra, measured for K∗(892)± at midrapidity in the interval 0<pT<15 GeV/c, are not well described by predictions of different versions of PYTHIA 6, PYTHIA 8 and EPOS-LHC event generators. These generators reproduce the measured pT-integrated K∗±/K ratios and describe well the momentum dependence for pT<2 GeV/c.

Measurement of prompt D+s-meson production and azimuthal anisotropy in Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (arXiv, 2021)
The production yield and angular anisotropy of prompt D+s mesons were measured as a function of transverse momentum (pT) in Pb-Pb collisions at a centre-of-mass energy per nucleon pair sNN‾‾‾‾√=5.02 TeV collected with the ALICE detector at the LHC. D+s mesons and their charge conjugates were reconstructed at midrapidity (|y|<0.5) from their hadronic decay channel D+s→ϕπ+, with ϕ→K−K+, in the pT intervals 2<pT<50 GeV/c and 2<pT<36 GeV/c for the 0-10% and 30-50% centrality intervals. For pT>10 GeV/c, the measured D+s-meson nuclear modification factor RAA is consistent with the one of non-strange D mesons within uncertainties, while at lower pT a hint for a D+s-meson RAA larger than that of non-strange D mesons is seen. The enhanced production of D+s relative to non-strange D mesons is also studied by comparing the pT-dependent D+s/D0 production yield ratios in Pb-Pb and in pp collisions. The ratio measured in Pb-Pb collisions is found to be on average higher than that in pp collisions in the interval 2<pT<8 GeV/c with a significance of 2.3σ and 2.4σ for the 0-10% and 30-50% centrality intervals. The azimuthal anisotropy coefficient v2 of prompt D+s mesons was measured in Pb-Pb collisions in the 30-50% centrality interval and is found to be compatible with that of non-strange D mesons. The main features of the measured RAA, D+s/D0 ratio, and v2 as a function of pT are described by theoretical calculations of charm-quark transport in a hydrodynamically expanding quark-gluon plasma including hadronisation via charm-quark recombination with light quarks from the medium. The pT-integrated production yield of D+s mesons is compatible with the prediction of the statistical hadronisation model.

Measurement of the Cross Sections of Ξc0 and Ξc+ Baryons and of the Branching-Fraction Ratio BR(Ξc0→Ξ−e+νe)/BR(Ξc0→Ξ−π+) in pp Collisions at s=13 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Physical Review Letters, 2021)
The pT-differential cross sections of prompt charm-strange baryons Ξ0c and Ξ+c were measured at midrapidity (|y|<0.5) in proton−proton (pp) collisions at a centre-of-mass energy s√=13 TeV with the ALICE detector at the LHC. The Ξ0c baryon was reconstructed via both the semileptonic decay (Ξ−e+νe) and the hadronic decay (Ξ−π+) channels. The Ξ+c baryon was reconstructed via the hadronic decay (Ξ−π+π+) channel. The branching-fraction ratio BR(Ξ0c→Ξ−e+νe)/BR(Ξ0c→Ξ−π+)= 1.38 ± 0.14 (stat) ± 0.22 (syst) was measured with a total uncertainty reduced by a factor of about 3 with respect to the current world average reported by the Particle Data Group. The transverse momentum (pT) dependence of the Ξ0c- and Ξ+c-baryon production relative to the D0-meson and to the Σ0,+,++c- and Λ+c-baryon production are reported. The baryon-to-meson ratio increases towards low pT up to a value of approximately 0.3. The measurements are compared with various models that take different hadronisation mechanisms into consideration. The results provide stringent constraints to these theoretical calculations and additional evidence that different processes are involved in charm hadronisation in electron−positron (e+e−) and hadronic collisions.

Measurement of the production cross section of prompt Ξ0c baryons at midrapidity in pp collisions at s√ = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Journal of High Energy Physics, 2021)
The transverse momentum (pT) differential cross section of the charm-strange baryon Ξ0c is measured at midrapidity (|y|< 0.5) via its semileptonic decay into e+Ξ−νe in pp collisions at s√ = 5.02 TeV with the ALICE detector at the LHC. The ratio of the pT-differential Ξ0c-baryon and D0-meson production cross sections is also reported. The measurements are compared with simulations with different tunes of the PYTHIA 8 event generator, with predictions from a statistical hadronisation model (SHM) with a largely augmented set of charm-baryon states beyond the current lists of the Particle Data Group, and with models including hadronisation via quark coalescence. The pT-integrated cross section of prompt Ξ0c-baryon production at midrapidity is also reported, which is used to calculate the baryon-to-meson ratio Ξ0c/D0=0.20±0.04 (stat.)+0.08−0.07 (syst.). These results provide an additional indication of a modification of the charm fragmentation from e+e− and e−p collisions to pp collisions.

Measurement of very forward energy and particle production at midrapidity in pp and p-Pb collisions at the LHC - S. Acharya; D. Adamová; Ralf Keidel; A. Adler (arXiv, 2021)
The very forward energy is a powerful tool for characterising the proton fragmentation in pp and p-Pb collisions and, studied in correlation with particle production at midrapidity, provides direct insightsinto the initial stages and the subsequent evolution of the collision. Furthermore, the correlation between the forward energy and the production of particles with large transverse momenta at midrapidity provides information complementary to the measurements of the underlying event, which are usually interpreted in the framework of models implementing centrality-dependent multiple parton interaction. Results about the very forward energy, measured by the ALICE zero degree calorimeters (ZDC), and its dependence on the activity measured at midrapidity in pp collisions at s√=13 TeV and in p-Pb collisions at sNN‾‾‾‾√=8.16 TeV are presented and discussed. The measurements performed in pp collisions are compared with the expectations of three hadronic interaction event generators: PYTHIA 6 (Perugia 2011 tune), PYTHIA 8 (Monash tune), and EPOS LHC. These results provide new constraints on the validity of models in describing the beam remnants at very forward rapidities, where perturbative QCD cannot be used.

Measurements of mixed harmonic cumulants in Pb-Pb collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; Z. Akbar; et al. (Physics Letters B, 2021)
Correlations between moments of different flow coefficients are measured in Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV recorded with the ALICE detector. These new measurements are based on multiparticle mixed harmonic cumulants calculated using charged particles in the pseudorapidity region |η|<0.8 with the transverse momentum range 0.2<pT<5.0 GeV/c. The centrality dependence of correlations between two flow coefficients as well as the correlations between three flow coefficients, both in terms of their second moments, are shown. In addition, a collection of mixed harmonic cumulants involving higher moments of v2 and v3 is measured for the first time, where the characteristic signature of negative, positive and negative signs of four-, six- and eight-particle cumulants are observed, respectively. The measurements are compared to the hydrodynamic calculations using iEBE-VISHNU with AMPT and TRENTo initial conditions. It is shown that the measurements carried out using the LHC Run 2 data in 2015 have the precision to explore the details of initial-state fluctuations and probe the nonlinear hydrodynamic response of v2 and v3 to their corresponding initial anisotropy coefficients ε2 and ε3. These new studies on correlations between three flow coefficients as well as correlations between higher moments of two different flow coefficients will pave the way to tighten constraints on initial-state models and help to extract precise information on the dynamic evolution of the hot and dense matter created in heavy-ion collisions at the LHC.

Multiharmonic Correlations of Different Flow Amplitudes in Pb-Pb Collisions at sNN=2.76 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; Z. Akbar; et al. (Physical Review Letters, 2021)
The event-by-event correlations between three flow amplitudes are measured for the first time in Pb-Pb collisions, using higher-order symmetric cumulants. We find that different three-harmonic correlations develop during the collective evolution of the medium when compared to correlations that exist in the initial state. These new results cannot be interpreted in terms of previous lower-order flow measurements since contributions from two-harmonic correlations are explicitly removed in the new observables. A comparison to Monte Carlo simulations provides new and independent constraints for the initial conditions and system properties of nuclear matter created in heavy-ion collisions.

Neutral to charged kaon yield fluctuations in Pb−Pb collisions at sNN‾‾‾‾√ = 2.76TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (arXiv, 2021)
We present the first measurement of event-by-event fluctuations in the kaon sector in Pb-Pb collisions at sNN‾‾‾‾√= 2.76 TeV with the ALICE detector at the LHC. The robust fluctuation correlator νdyn is used to evaluate the magnitude of fluctuations of the relative yields of neutral and charged kaons, as well as the relative yields of charged kaons, as a function of collision centrality and selected kinematic ranges. While the correlator νdyn[K+,K−] exhibits a scaling approximately in inverse proportion of the charged particle multiplicity, νdyn[K0S,K±] features a significant deviation from such scaling. Within uncertainties, the value of νdyn[K0S,K±] is independent of the selected transverse momentum interval, while it exhibits a pseudorapidity dependence. The results are compared with HIJING, AMPT and EPOS-LHC predictions, and are further discussed in the context of the possible production of disoriented chiral condensates in central Pb-Pb collisions.

Observation of a multiplicity dependence in the pT-differential charm baryon-to-meson ratios in proton-proton collisions at s√=13 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (arXiv, 2021)
The production of prompt D0, D+s, and Λ+c hadrons, and their ratios, D+s/D0 and Λ+c/D0, are measured in proton-proton collisions at s√ = 13 TeV at midrapidity (|y|<0.5) with the ALICE detector at the LHC. The measurements are performed as a function of the charm-hadron transverse momentum (pT) in intervals of charged-particle multiplicity, measured with two multiplicity estimators covering different pseudorapidity regions. While the strange to non-strange D+s/D0 ratio indicates no significant multiplicity dependence, the baryon-to-meson pT-differential Λ+c/D0 ratio shows a multiplicity-dependent enhancement, with a significance of 5.3σ for 1<pT<12 GeV/c, comparing the highest multiplicity interval with respect to the lowest one. The measurements are compared with a theoretical model that explains the multiplicity dependence by a canonical treatment of quantum charges in the statistical hadronisation approach, and with predictions from event generators that implement colour reconnection mechanisms beyond the leading colour approximation to model the hadronisation process. The Λ+c/D0 ratios as a function of pT present a similar shape and magnitude as the Λ/K0s ratios in comparable multiplicity intervals, suggesting a potential common mechanism for light- and charm-hadron formation, with analogous multiplicity dependence. The pT-integrated ratios, extrapolated down to pT=0, do not show a significant dependence on multiplicity within the uncertainties.

Pion-kaon femtoscopy and the lifetime of the hadronic phase in Pb−Pb collisions at sNN=2.76 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; M.M. Aggarwal; S. Agha; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; et al. (Physics Letters B, 2021)
In this paper, the first femtoscopic analysis of pion-kaon correlations at the LHC is reported. The analysis was performed on the Pb-Pb collision data at sNN‾‾‾‾√ = 2.76 TeV recorded with the ALICE detector. The non-identical particle correlations probe the spatio-temporal separation between sources of different particle species as well as the average source size of the emitting system. The sizes of the pion and kaon sources increase with centrality, and pions are emitted closer to the centre of the system and/or later than kaons. This is naturally expected in a system with strong radial flow and is qualitatively reproduced by hydrodynamic models. ALICE data on pion-kaon emission asymmetry are consistent with (3+1)-dimensional viscous hydrodynamics coupled to a statistical hadronization model, resonance propagation, and decay code THERMINATOR 2 calculation, with an additional time delay between 1 and 2 fm/c for kaons. The delay can be interpreted as evidence for a significant hadronic rescattering phase in heavy-ion collisions at the LHC.

Polarization of Λ and Λ⎯⎯⎯⎯ hyperons along the beam direction in Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - D. Adamová; S. Acharya; Ralf Keidel; A. Adler (arXiv, 2021)
The polarization of the Λ and Λ⎯⎯⎯⎯ hyperons along the beam (z) direction, Pz, has been measured in Pb-Pb collisions at sNN‾‾‾‾√ = 5.02TeV recorded with ALICE at the Large Hadron Collider (LHC). The largest contribution to Pz comes from elliptic flow induced vorticity and can be characterized by the second Fourier sine coefficient Pz,s2=⟨Pzsin(2φ−2Ψ2)⟩, where φ is the hyperon azimuthal emission angle, and Ψ2 is the elliptic flow plane angle. We report the measurement of Pz,s2 for different collision centralities, and in the 30-50% centrality interval as a function of the hyperon transverse momentum and rapidity. The Pz,s2 is positive similarly as measured by the STAR Collaboration in Au-Au collisions at sNN‾‾‾‾√ = 200 GeV, with somewhat smaller amplitude in the semi-central collisions. This is the first experimental evidence of a non-zero hyperon Pz in Pb-Pb collisions at the LHC. The comparison of the measured Pz,s2 with the hydrodynamic model calculations shows sensitivity to the competing contributions from thermal and the recently found shear induced vorticity, as well as to whether the polarization is acquired at the quark-gluon plasma or the hadronic phase.

Production of light (anti)nuclei in pp collisions at s√ = 5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (arXiv, 2021)
The study of the production of nuclei and antinuclei in pp collisions has proven to be a powerful tool to investigate the formation mechanism of loosely bound states in high-energy hadronic collisions. In this paper, the production of protons, deuterons and 3He and their charge conjugates at midrapidity is studied as a function of the charged-particle multiplicity in inelastic pp collisions at s√=5.02 TeV using the ALICE detector. Within the uncertainties, the yields of nuclei in pp collisions at s√=5.02 TeV are compatible with those in pp collisions at different energies and to those in p-Pb collisions when compared at similar multiplicities. The measurements are compared with the expectations of coalescence and Statistical Hadronisation Models. The results suggest a common formation mechanism behind the production of light nuclei in hadronic interactions and confirm that they do not depend on the collision energy but on the number of produced particles.

Production of pions, kaons, (anti-)protons and φ mesons in Xe-Xe collisions at s_NN = 5.44 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; Z. Akbar; et al. (The European Physical Journal C, 2021)
The first measurement of the production of pions, kaons, (anti-)protons and 𝜙 mesons at midrapidity in Xe-Xe collisions at 𝑠NN‾‾‾‾√=5.44 TeV is presented. Transverse momentum (𝑝T) spectra and 𝑝T-integrated yields are extracted in several centrality intervals bridging from p-Pb to mid-central Pb-Pb collisions in terms of final-state multiplicity. The study of Xe-Xe and Pb-Pb collisions allows systems at similar charged-particle multiplicities but with different initial geometrical eccentricities to be investigated. A detailed comparison of the spectral shapes in the two systems reveals an opposite behaviour for radial and elliptic flow. In particular, this study shows that the radial flow does not depend on the colliding system when compared at similar charged-particle multiplicity. In terms of hadron chemistry, the previously observed smooth evolution of particle ratios with multiplicity from small to large collision systems is also found to hold in Xe-Xe. In addition, our results confirm that two remarkable features of particle production at LHC energies are also valid in the collision of medium-sized nuclei: the lower proton-to-pion ratio with respect to the thermal model expectations and the increase of the 𝜙-to-pion ratio with increasing final-state multiplicity.

Production of Λ and K0S in jets in p-Pb collisions at sNN‾‾‾‾√=5 TeV and pp collisions at s√=7 TeV - S. Acharya; D. Adamová; Ralf Keidel; A. Adler (arXiv, 2021)
The production of Λ baryons and K0S mesons (V0 particles) was measured in p-Pb collisions at sNN‾‾‾‾√=5 TeV and pp collisions at s√=7 TeV with ALICE at the LHC. The production of these strange particles is studied separately for particles associated with hard scatterings and the underlying event to shed light on the baryon-to-meson ratio enhancement observed at intermediate transverse momentum (pT) in high multiplicity pp and p-Pb collisions. Hard scatterings are selected on an event-by-event basis with jets reconstructed with the anti-kT algorithm using charged particles. The production of strange particles associated with jets pchT,jet>10 GeV/c is reported as a function of pT in both systems; and its dependence on pT with jets pchT,jet>20 GeV/c and on angular distance from the jet axis, R(V0,jet), for jets with pchT,jet>10 GeV/c are reported in p-Pb collisions. The results are compared with the strange particle production in the underlying event. The Λ/K0S ratio associated with jets in p-Pb collisions for R(V0,jet)<0.4 is consistent with the ratio measured in pp collisions and with the expectation of jets fragmenting in vacuum given by the PYTHIA event generator.

(Anti-)Deuteron production in pp collisions at s√=13 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
The study of (anti-)deuteron production in pp collisions has proven to be a powerful tool to investigate the formation mechanism of loosely bound states in high energy hadronic collisions. In this paper the production of (anti-)deuterons is studied as a function of the charged particle multiplicity in inelastic pp collisions at s√=13 TeV using the ALICE experiment. Thanks to the large accumulated integrated luminosity, it has been possible to measure (anti-)deuteron production in pp collisions up to the same charged particle multiplicity (dNch/dη∼26) as measured in p-Pb collisions at similar centre-of-mass energies. Within the uncertainties, the deuteron yield in pp collisions resembles the one in p-Pb interactions, suggesting a common formation mechanism behind the production of light nuclei in hadronic interactions. In this context the measurements are compared with the expectations of coalescence and Statistical Hadronisation Models (SHM).

A High-Granularity Digital Tracking Calorimeter Optimized for Proton CT - Johan Alme; Gergely Gábor Barnaföldi; Ralf Keidel; Rene Barthel; Vyacheslav Borshchov; Tea Bodova; Anthony van den Brink; Stephan Brons; Mamdouh Chaar; Viljar Eikeland; Grigory Feofilov; Georgi Genov; et al. (Frontiers in Physics, 2020)
A typical proton CT (pCT) detector comprises a tracking system, used to measure the proton position before and after the imaged object, and an energy/range detector to measure the residual proton range after crossing the object. The Bergen pCT collaboration was established to design and build a prototype pCT scanner with a high granularity digital tracking calorimeter used as both tracking and energy/range detector. In this work the conceptual design and the layout of the mechanical and electronics implementation, along with Monte Carlo simulations of the new pCT system are reported. The digital tracking calorimeter is a multilayer structure with a lateral aperture of 27 cm × 16.6 cm, made of 41 detector/absorber sandwich layers (calorimeter), with aluminum (3.5 mm) used both as absorber and carrier, and two additional layers used as tracking system (rear trackers) positioned downstream of the imaged object; no tracking upstream the object is included. The rear tracker’s structure only differs from the calorimeter layers for the carrier made of ∼200 μm carbon fleece and carbon paper (carbon-epoxy sandwich), to minimize scattering. Each sensitive layer consists of 108 ALICE pixel detector (ALPIDE) chip sensors (developed for ALICE, CERN) bonded on a polyimide flex and subsequently bonded to a larger flexible printed circuit board. Beam tests tailored to the pCT operation have been performed using high-energetic (50-220 MeV/u) proton and ion beams at the Heidelberg Ion-Beam Therapy Center (HIT) in Germany. These tests proved the ALPIDE response independent of occupancy and proportional to the particle energy deposition, making the distinction of different ion tracks possible. The read-out electronics is able to handle enough data to acquire a single 2D image in few seconds making the system fast enough to be used in a clinical environment. For the reconstructed images in the modeled Monte Carlo simulation, the water equivalent path length error is lower than 2 mm, and the relative stopping power accuracy is better than 0.4%. Thanks to its ability to detect different types of radiation and its specific design, the pCT scanner can be employed for additional online applications during the treatment, such as in-situ proton range verification.

Centrality and transverse momentum dependence of inclusive J/ψ production at midrapidity in Pb-Pb collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; et al. (Physics Letters B, 2020)
The inclusive J/ψ meson production in Pb-Pb collisions at a center-of-mass energy per nucleon-nucleon collision of sNN‾‾‾‾√ = 5.02 TeV at midrapidity (|y| < 0.9) is reported by the ALICE Collaboration. The measurements are performed in the dielectron decay channel, as a function of event centrality and J/ψ transverse momentum pT, down to pT = 0 GeV/c. The J/ψ mean transverse momentum ⟨pT⟩ and rAA ratio, defined as ⟨p2T⟩PbPb/⟨p2T⟩pp, are evaluated. Both observables show a centrality dependence decreasing towards central (head-on) collisions. The J/ψ nuclear modification factor RAA exhibits a strong pT dependence with a large suppression at high pT and an increase to unity for decreasing pT. When integrating over the measured momentum range pT < 10 GeV/c, the J/ψ RAA shows a weak centrality dependence. Each measurement is compared with results at lower center-of-mass energies and with ALICE measurements at forward rapidity, as well as to theory calculations. All reported features of the J/ψ production at low pT are consistent with a dominant contribution to the J/ψ yield originating from charm quark (re)combination.

Centrality dependence of J/ψ and ψ(2S) production and nuclear modification in p-Pb collisions at sNN√= 8.16 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
The inclusive production of the J/ψ and ψ(2S) charmonium states is studied as a function of centrality in p-Pb collisions at a centre-of-mass energy per nucleon pair sNN‾‾‾‾√=8.16 TeV at the LHC. The measurement is performed in the dimuon decay channel with the ALICE apparatus in the centre-of-mass rapidity intervals −4.46<ycms<−2.96 (Pb-going direction) and 2.03<ycms<3.53 (p-going direction), down to zero transverse momentum (pT). The J/ψ and ψ(2S) production cross sections are evaluated as a function of the collision centrality, estimated through the energy deposited in the zero degree calorimeter located in the Pb-going direction. The pT-differential J/ψ production cross section is measured at backward and forward rapidity for several centrality classes, together with the corresponding average ⟨pT⟩ and ⟨p2T⟩ values. The nuclear effects affecting the production of both charmonium states are studied using the nuclear modification factor. In the p-going direction, a suppression of the production of both charmonium states is observed, which seems to increase from peripheral to central collisions. In the Pb-going direction, however, the centrality dependence is different for the two states: the nuclear modification factor of the J/ψ increases from below unity in peripheral collisions to above unity in central collisions, while for the ψ(2S) it stays below or consistent with unity for all centralities with no significant centrality dependence. The results are compared with measurements in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV and no significant dependence on the energy of the collision is observed. Finally, the results are compared with theoretical models implementing various nuclear matter effects.

Coherent photoproduction of ρ0 vector mesons in ultra-peripheral Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (Journal of High Energy Physics, 2020)
Cross sections for the coherent photoproduction of ρ0 vector mesons in ultra-peripheral Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV are reported. The measurements, which rely on the π+π− decay channel, are presented in three regions of rapidity covering the range |y| < 0.8. For each rapidity interval, cross sections are shown for different nuclear-breakup classes defined according to the presence of neutrons measured in the zero-degree calorimeters. The results are compared with predictions based on different models of nuclear shadowing. Finally, the observation of a coherently produced resonance-like structure with a mass around 1.7 GeV/c2 and a width of about 140 MeV/c2 is reported and compared with similar observations from other experiments.

Constraining the Chiral Magnetic Effect with charge-dependent azimuthal correlations in Pb-Pb collisions at sNN√ = 2.76 and 5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
Systematic studies of charge-dependent two- and three-particle correlations in Pb–Pb collisions at sNN‾‾‾‾√= 2.76and 5.02TeV used to probe the Chiral Magnetic Effect (CME) are presented. These measurements are performed for charged particles in the pseudorapidity (η) and transverse momentum (pT) ranges ∣∣η∣∣<0.8 and 0.2<pT<5GeV/c. A significant charge-dependent signal that becomes more pronounced for peripheral collisions is reported for the CME-sensitive correlators γ1,1=⟨cos(φα+φβ−2Ψ2)⟩ and γ1,−3=⟨cos(φα−3φβ+2Ψ2)⟩. The results are used to estimate the contribution of background effects, associated with local charge conservation coupled to anisotropic flow modulations, to measurements of the CME. A blast-wave parametrisation that incorporates local charge conservation tuned to reproduce the centrality dependent background effects is not able to fully describe the measured γ1,1. Finally, the charge and centrality dependence of mixed-harmonics three-particle correlations, of the form γ1,2=⟨cos(φα+φβ−3Ψ3)⟩, which are insensitive to the CME signal, verify again that background contributions dominate the measurement of γ1,1.

Dielectron production in proton-proton and proton-lead collisions at 𝑠NN√= 5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
The first measurements of dielectron production at midrapidity (|𝜂𝑐|<0.8) in proton-proton and proton-lead collisions at 𝑠NN‾‾‾‾√ = 5.02 TeV at the LHC are presented. The dielectron cross section is measured with the ALICE detector as a function of the invariant mass 𝑚T,ee and the pair transverse momentum 𝑝T,ee in the ranges 𝑚T,ee < 3.5 GeV/𝑐2 and 𝑚T,ee < 8.0 GeV/𝑐2, in both collision systems. In proton-proton collisions, the charm and beauty cross sections are determined at midrapidity from a fit to the data with two different event generators. This complements the existing dielectron measurements performed at 𝑠√ = 7 and 13 TeV. The slope of the 𝑠√ dependence of the three measurements is described by FONLL calculations. The dielectron cross section measured in proton-lead collisions is in agreement, within the current precision, with the expected dielectron production without any nuclear matter effects for e+e− pairs from open heavy-flavor hadron decays. For the first time at LHC energies, the dielectron production in proton-lead and proton-proton collisions are directly compared at the same 𝑠NN‾‾‾‾√ via the dielectron nuclear modification factor 𝑅pPb. The measurements are compared to model calculations including cold nuclear matter effects, or additional sources of dielectrons from thermal radiation.

Elliptic and triangular flow of (anti)deuterons in Pb-Pb collisions at 𝑠NN√= 5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
The measurements of the (anti)deuterons elliptic flow (𝑣2) and the first measurements of triangular flow (𝑣3) in Pb-Pb collisions at a center-of-mass energy per nucleon-nucleon collisions 𝑠NN√ = 5.02 TeV are presented. A mass ordering at low transverse momentum (𝑝T) is observed when comparing these measurements with those of other identified hadrons, as expected from relativistic hydrodynamics. The measured (anti)deuterons 𝑣2 lies between the predictions from the simple coalescence and blast-wave models, which provide a good description of the data only for more peripheral and for more central collisions, respectively. The mass number scaling, which is violated for 𝑣2, is approximately valid for the (anti)deuterons 𝑣3. The measured 𝑣2 and 𝑣3 are also compared with the predictions from a coalescence approach with phase-space distributions of nucleons generated by iEBE-VISHNU with AMPT initial conditions coupled with UrQMD, and from a dynamical model based on relativistic hydrodynamics coupled to the hadronic afterburner SMASH. The model predictions are consistent with the data within the uncertainties in mid-central collisions, while a deviation is observed in central centrality intervals.

Elliptic flow of electrons from beauty-hadron decays in Pb-Pb collisions at 𝑠NN√ = 5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
The elliptic flow of electrons from beauty hadron decays at midrapidity (|𝑦| < 0.8) is measured in Pb-Pb collisions at 𝑠NN√ = 5.02 TeV with the ALICE detector at the LHC. The azimuthal distribution of the particles produced in the collisions can be parameterized with a Fourier expansion, in which the second harmonic coefficient represents the elliptic flow, 𝑣2. The 𝑣2 coefficient is measured for the first time in transverse momentum (𝑝T) range 1.3-6 GeV/𝑐 in the centrality class 30-50%. The measurement of electrons from beauty-hadron decays exploits their larger mean proper decay length 𝑐𝜏≈ 500 𝜇m compared to that of charm hadrons and most of the other background sources. The 𝑣2 of electrons from beauty hadron decays at midrapidity is found to be positive with a significance of 3.75𝜎. The results provide insights on the degree of thermalization of beauty quarks in the medium. A model assuming full thermalization of beauty quarks is strongly disfavoured by the measurement at high 𝑝T, but is in agreement with the results at low 𝑝T. Transport models including substantial interactions of beauty quarks with an expanding strongly-interacting medium describe the measurement.

Evidence of rescattering effect in Pb-Pb collisions at the LHC through production of K(892)0⁎ and ϕ(1020) mesons - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; et al. (Physics Letters B, 2020)
Measurements of K∗(892)0 and ϕ(1020) resonance production in Pb-Pb and pp collisions at sNN‾‾‾‾√ = 5.02 TeV with the ALICE detector at the Large Hadron Collider are reported. The resonances are measured at midrapidity (|y| < 0.5) via their hadronic decay channels and the transverse momentum (pT) distributions are obtained for various collision centrality classes up to pT = 20 GeV/c. The pT-integrated yield ratio K∗(892)0/K in Pb-Pb collisions shows significant suppression relative to pp collisions and decreases towards more central collisions. In contrast, the ϕ(1020)/K ratio does not show any suppression. Furthermore, the measured K∗(892)0/K ratio in central Pb-Pb collisions is significantly suppressed with respect to the expectations based on a thermal model calculation, while the ϕ(1020)/K ratio agrees with the model prediction. These measurements are an experimental demonstration of rescattering of K∗(892)0 decay products in the hadronic phase of the collisions. The K∗(892)0/K yield ratios in Pb-Pb and pp collisions are used to estimate the time duration between chemical and kinetic freeze-out, which is found to be ∼ 4-7 fm/c for central collisions. The pT-differential ratios of K∗(892)0/K, ϕ(1020)/K, K∗(892)0/π, ϕ(1020)/π, p/K∗(892)0 and p/ϕ(1020) are also presented for Pb-Pb and pp collisions at sNN‾‾‾‾√ = 5.02 TeV. These ratios show that the rescattering effect is predominantly a low-pT phenomenon.

Evidence of Spin-Orbital Angular Momentum Interactions in Relativistic Heavy-Ion Collisions - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; et al. (Physical Review Letters, 2020)

First measurement of quarkonium polarization in nuclear collisions at the LHC - D. Adamova; S. Acharya; Ralf Keidel; A. Adler (2020)
The polarization of inclusive J/ψ and Υ(1S) produced in Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV at the LHC is measured with the ALICE detector. The study is carried out by reconstructing the quarkonium through its decay to muon pairs in the rapidity region 2.5<y<4 and measuring the polar and azimuthal angular distributions of the muons. The polarization parameters λθ, λϕ and λθϕ are measured in the helicity and Collins-Soper reference frames, in the transverse momentum interval 2<pT<10 GeV/c and pT<15 GeV/c for the J/ψ and Υ(1S), respectively. The polarization parameters for the J/ψ are found to be compatible with zero, with a maximum deviation at low pT of about 2σ, for both reference frames and over the whole pT range. The values are compared with the corresponding results obtained for pp collisions at s√=7 and 8 TeV in a similar kinematic region by the ALICE and LHCb experiments. Although with much larger uncertainties, the polarization parameters for Υ(1S) production in Pb-Pb collisions are also consistent with zero.

Global polarization of Λ and Λ hyperons in Pb-Pb collisions at the LHC - S. Acharya; D. Adamová; R. Keidel; S. P. Adhya; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; et al. (Physical Review C, 2020)
The global polarization of the Λ and Λ⎯⎯⎯⎯ hyperons is measured for Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 and 5.02 TeV recorded with the ALICE at the LHC. The results are reported differentially as a function of collision centrality and hyperon's transverse momentum (pT) for the range of centrality 5-50%, 0.5<pT<5 GeV/c, and rapidity |y|<0.5. The hyperon global polarization averaged for Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 and 5.02 TeV is found to be consistent with zero, ⟨PH⟩ (%) ≈ 0.01 ± 0.06 (stat.) ± 0.03 (syst.) in the collision centrality range 15-50%, where the largest signal is expected. The results are compatible with expectations based on an extrapolation from measurements at lower collision energies at RHIC, hydrodynamical model calculations, and empirical estimates based on collision energy dependence of directed flow, all of which predict the global polarization values at LHC energies of the order of 0.01%.

Higher harmonic non-linear flow modes of charged hadrons in Pb-Pb collisions at 𝑠NN‾‾‾‾√ = 5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (Journal of High Energy Physics JHEP05, 2020)
Anisotropic flow coefficients, v𝑛, non-linear flow mode coefficients, χ𝑛,𝑚𝑘, and correlations among different symmetry planes, ρ𝑛,𝑚𝑘 are measured in Pb-Pb collisions at 𝑠NN‾‾‾‾√ = 5.02 TeV. Results obtained with multi-particle correlations are reported for the transverse momentum interval 0.2 < p𝑇< 5.0 GeV/c within the pseudorapidity interval 0.4 < |η| < 0.8 as a function of collision centrality. The v𝑛 coefficients and χ𝑛,𝑚𝑘 and ρ𝑛,𝑚𝑘 are presented up to the ninth and seventh harmonic order, respectively. Calculations suggest that the correlations measured in different symmetry planes and the non-linear flow mode coefficients are dependent on the shear and bulk viscosity to entropy ratios of the medium created in heavy-ion collisions. The comparison between these measurements and those at lower energies and calculations from hydrodynamic models places strong constraints on the initial conditions and transport properties of the system.

Inclusive heavy-flavour production at central and forward rapidity in Xe-Xe collisions at sNN√=5.44 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
The first measurements of the production of muons and electrons from heavy-flavour hadron decays in Xe-Xe collisions at sNN‾‾‾‾√ = 5.44 TeV, using the ALICE detector at the LHC, are reported. The measurement of the nuclear modification factor RAA is performed as a function of transverse momentum pT in several centrality classes at forward rapidity (2.5<y<4) and midrapidity (|y|<0.8) for muons and electrons from heavy-flavour hadron decays, respectively. A suppression by a factor up to about 2.5 compared to the binary-scaled pp reference is observed in central collisions at both central and forward rapidities. The RAA of muons from heavy-flavour hadron decays is compared to previous measurements in Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV. A similar suppression, with RAA∼0.4 in the pT interval 4<pT<8 GeV/c, is observed in Pb-Pb and Xe-Xe collisions when the nuclear modification factors are compared in event classes with similar charged-particle multiplicity density. The comparison of the measured RAA values in the two collision systems brings new insights on the properties of the quark-gluon plasma by investigating the system-size and path-length dependence of medium-induced parton energy loss. The results of muons and electrons from heavy-flavour hadron decays provide new constraints to model calculations.

Investigation of the p-Σ0 interaction via femtoscopy in pp collisions - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; et al. (Physics Letters B, 2020)
This Letter presents the first direct investigation of the p-Σ0 interaction, using the femtoscopy technique in high-multiplicity pp collisions at s√ = 13 TeV measured by the ALICE detector. The Σ0 is reconstructed via the decay channel to Λγ, and the subsequent decay of Λ to pπ−. The photon is detected via the conversion in material to e+e− pairs exploiting the unique capability of the ALICE detector to measure electrons at low transverse momenta. The measured p-Σ0 correlation indicates a shallow strong interaction. The comparison of the data to several theoretical predictions obtained employing the Correlation Analysis Tool using the Schrödinger Equation (CATS) and the Lednický-Lyuboshits approach shows that the current experimental precision does not yet allow to discriminate between different models, as it is the case for the available scattering and hypernuclei data. Nevertheless, the p-Σ0 correlation function is found to be sensitive to the strong interaction, and driven by the interplay of the different spin and isospin channels. This pioneering study demonstrates the feasibility of a femtoscopic measurement in the p-Σ0 channel and with the expected larger data samples in LHC Run 3 and Run 4, the p-Σ0 interaction will be constrained with high precision.

J/ψ elliptic and triangular flow in Pb-Pb collisions at sNN√ = 5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
The inclusive J/ψ elliptic (v2) and triangular (v3) flow coefficients are measured at forward rapidity (2.5 < y < 4) and the v2 at midrapidity (|y| < 0.9) in PbPb collisions at sNN‾‾‾‾√ = 5.02 TeV using the ALICE detector at the LHC. The entire Pb-Pb data sample collected during Run 2 is employed, amounting to integrated luminosities of about 750 μb−1 at forward rapidity and 93 μb−1 at midrapidity. The results are obtained with the scalar product method and are reported as a function of transverse momentum pT and collision centrality. At forward rapidity, an ordering is observed for the v2 and v3 coefficients up to 5 GeV/c when comparing pions, D mesons, and inclusive J/ψ. The midrapidity J/ψ v2 is in agreement with the forward rapidity results. At pT > 5 GeV/c, the J/ψ v2 exhibits the same behavior as D mesons and charged pions. The J/ψ v3 in the 0-50% centrality interval is found to be positive for 2 < pT < 5 GeV/c with a significance of 5.1σ while the v3/v2 ratio is lower than the one observed for D mesons and light flavored particles. The ratio of π± v2 over the pT-integrated J/ψ v2 for pT < 5 GeV/c reveals an increasing trend from central to peripheral collisions. Using a simplistic extension of the quark scaling approach involving both light and charm quark flow components, it is shown that the D-meson vn measurements can be described based on those for charged pions and J/ψ flow.

J/ψ production as a function of charged-particle multiplicity in p-Pb collisions at sNN√ = 8.16 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
Inclusive J/ψ yields and average transverse momenta in p-Pb collisions at a center-of-mass energy per nucleon pair sNN√ = 8.16 TeV are measured as a function of the charged-particle pseudorapidity density with ALICE. The J/ψ mesons are reconstructed at forward (2.03<ycms<3.53) and backward (−4.46<ycms<−2.96) center-of-mass rapidity in their dimuon decay channel while the charged-particle pseudorapidity density is measured around midrapidity. The J/ψ yields at forward and backward rapidity normalized to their respective average values increase with the normalized charged-particle pseudorapidity density, the former showing a weaker increase than the latter. The normalized average transverse momenta at forward and backward rapidity manifest a steady increase from low to high charged-particle pseudorapidity density with a saturation beyond the average value.

Jet fragmentation transverse momentum distributions in pp and p-Pb collisions at sNN√ = 5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
Jet fragmentation transverse momentum (jT) distributions are measured in proton-proton (pp) and proton-lead (p-Pb) collisions at sNN‾‾‾‾√ = 5.02 TeV with the ALICE experiment at the LHC. Jets are reconstructed with the ALICE tracking detectors and electromagnetic calorimeter using the anti-kT algorithm with resolution parameter R=0.4 in the pseudorapidity range |η|<0.25. The jT values are calculated for charged particles inside a fixed cone with a radius R=0.4 around the reconstructed jet axis. The measured jT distributions are compared with a variety of parton-shower models. Herwig and PYTHIA 8 based models describe the data well for the higher jT region, while they underestimate the lower jT region. The jT distributions are further characterised by fitting them with a function composed of an inverse gamma function for higher jT values (called the "wide component"), related to the perturbative component of the fragmentation process, and with a Gaussian for lower jT values (called the "narrow component"), predominantly connected to the hadronisation process. The width of the Gaussian has only a weak dependence on jet transverse momentum, while that of the inverse gamma function increases with increasing jet transverse momentum. For the narrow component, the measured trends are successfully described by all models except for Herwig. For the wide component, Herwig and PYTHIA 8 based models slightly underestimate the data for the higher jet transverse momentum region. These measurements set constraints on models of jet fragmentation and hadronisation.

Jet-associated deuteron production in pp collisions at s√=13 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
Deuteron production in high-energy collisions is sensitive to the space-time evolution of the collision system, and is typically described by a coalescence mechanism. For the first time, we present results on jet-associated deuteron production in collisions at s√=13 TeV, providing an opportunity to test the established picture for deuteron production in events with a hard scattering. Using a trigger particle with high transverse-momentum (pT>5 GeV/c) as a proxy for the presence of a jet at midrapidity, we observe a measurable population of deuterons being produced around the jet proxy. The associated deuteron yield measured in a narrow angular range around the trigger particle differs by 2.4-4.8 standard deviations from the uncorrelated background. The data are described by PYTHIA model calculations featuring baryon coalescence.

Jet-hadron correlations measured relative to the second order event plane in Pb-Pb collisions at sNN=2.76TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; et al. (Physical Review C, 2020)
The Quark Gluon Plasma (QGP) produced in ultra relativistic heavy-ion collisions at the Large Hadron Collider (LHC) can be studied by measuring the modifications of jets formed by hard scattered partons which interact with the medium. We studied these modifications via angular correlations of jets with charged hadrons for jets with momenta 20 < pjetT < 40 GeV/c as a function of the associated particle momentum. The reaction plane fit (RPF) method is used in this analysis to remove the flow modulated background. The analysis of angular correlations for different orientations of the jet relative to the second order event plane allows for the study of the path length dependence of medium modifications to jets. We present the dependence of azimuthal angular correlations of charged hadrons with respect to the angle of the axis of a reconstructed jet relative to the event plane in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV. The dependence of particle yields associated with jets on the angle of the jet with respect to the event plane is presented. Correlations at different angles relative to the event plane are compared through ratios and differences of the yield. No dependence of the results on the angle of the jet with respect to the event plane is observed within uncertainties, which is consistent with no significant path length dependence of the medium modifications for this observable.

Longitudinal and azimuthal evolution of two-particle transverse momentum correlations in Pb-Pb collisions at sNN=2.76TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; et al. (Physics Letters B, 2020)
This paper presents the first measurements of the charge independent (CI) and charge dependent (CD) two-particle transverse momentum correlators GCI2 and GCD2 in Pb–Pb collisions at sNN‾‾‾‾√=2.76by the ALICE collaboration. The two-particle transverse momentum correlator G2 was introduced as a measure of the momentum current transfer between neighbouring system cells. The correlators are measured as a function of pair separation in pseudorapidity (Δη) and azimuth (Δφ) and as a function of collision centrality. From peripheral to central collisions, the correlator GCI2 exhibits a longitudinal broadening while undergoing a monotonic azimuthal narrowing. By contrast, GCD2 exhibits a narrowing along both dimensions. These features are not reproduced by models such as HIJING and AMPT. However, the observed narrowing of the correlators from peripheral to central collisions is expected to result from the stronger transverse flow profiles produced in more central collisions and the longitudinal broadening is predicted to be sensitive to momentum currents and the shear viscosity per unit of entropy density η/s of the matter produced in the collisions. The observed broadening is found to be consistent with the hypothesized lower bound of η/s and is in qualitative agreement with values obtained from anisotropic flow measurements.

Measurement of electrons from heavy-flavour hadron decays as a function of multiplicity in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; S. P. Adhya; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; et al. (Journal of High Energy Physics, 2020)
The multiplicity dependence of electron production from heavy-flavour hadron decays as a function of transverse momentum was measured in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV using the ALICE detector at the LHC. The measurement was performed in the centre-of-mass rapidity interval −1.07<ycms<0.14 and transverse momentum interval 2 <pT< 16 GeV/c. The multiplicity dependence of the production of electrons from heavy-flavour hadron decays was studied by comparing the pT spectra measured for different multiplicity classes with those measured in pp collisions (QpPb) and in peripheral p-Pb collisions (QCP). The QpPb results obtained are consistent with unity within uncertainties in the measured pT interval and event classes. This indicates that heavy-flavour decay electron production is consistent with binary scaling and independent of the geometry of the collision system. Additionally, the results suggest that cold nuclear matter effects are negligible within uncertainties, in the production of heavy-flavour decay electrons at midrapidity in p-Pb collisions.

Measurement of electrons from semileptonic heavy-flavour hadron decays at midrapidity in pp and Pb-Pb collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; R. Keidel; S.P. Adhya; A. Adler; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; et al. (Physics Letters B, 2020)
The differential invariant yield as a function of transverse momentum (pT) of electrons from semileptonic heavy-flavour hadron decays was measured at midrapidity in central (0-10%), semi-central (30-50%) and peripheral (60-80%) lead-lead (Pb-Pb) collisions at sNN‾‾‾‾√=5.02 TeV in the pT intervals 0.5-26 GeV/c (0-10% and 30-50%) and 0.5-10 GeV/c (60-80%). The production cross section in proton-proton (pp) collisions at s√=5.02 TeV was measured as well in 0.5<pT<10 GeV/c and it lies close to the upper band of perturbative QCD calculation uncertainties up to pT=5 GeV/c and close to the mean value for larger pT. The modification of the electron yield with respect to what is expected for an incoherent superposition of nucleon-nucleon collisions is evaluated by measuring the nuclear modification factor RAA. The measurement of the RAA in different centrality classes allows in-medium energy loss of charm and beauty quarks to be investigated. The RAA shows a suppression with respect to unity at intermediate pT, which increases while moving towards more central collisions. Moreover, the measured RAA is sensitive to the modification of the parton distribution functions (PDF) in nuclei, like nuclear shadowing, which causes a suppression of the heavy-quark production at low pT in heavy-ion collisions at LHC.

Measurement of isolated photon-hadron correlations in 5 TeV pp and pPb data - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
This paper presents isolated photon-hadron correlations using pp and p-Pb data collected by the ALICE detector at the LHC. For photons with |η| < 0.67 and 12 < pT < 40 GeV/c, the associated yield of charged particles in the range |η| < 0.80 and 0.5 < pT < 10 GeV/c is presented. These momenta are much lower than previous measurements at the LHC. No significant difference between pp and p-Pb is observed, with PYTHIA 8.2 describing both data sets within uncertainties. This measurement constrains nuclear effects on the parton fragmentation in p-Pb collisions, and provides a benchmark for future studies of Pb-Pb collisions.

Measurement of nuclear effects on ψ(2S) production in p-Pb collisions at sNN√=8.16 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
Inclusive ψ(2S) production is measured in p-Pb collisions at the centre-of-mass energy per nucleon-nucleon pair sNN√=8.16 TeV, using the ALICE detector at the CERN LHC. The production of ψ(2S) is studied at forward (2.03<ycms<3.53) and backward (−4.46<ycms<−2.96) centre-of-mass rapidity and for transverse momentum pT < 12 GeV/c via the decay to muon pairs. In this paper, we report the integrated as well as the ycms- and pT-differential inclusive production cross sections. Nuclear effects on ψ(2S) production are studied via the determination of the nuclear modification factor that shows a strong suppression at both forward and backward centre-of-mass rapidities. Comparisons with corresponding results for inclusive J/ψ show a similar suppression for the two states at forward rapidity (p-going direction), but a stronger suppression for ψ(2S) at backward rapidity (Pb-going direction). As a function of pT, no clear dependence of the nuclear modification factor is found. The relative size of nuclear effects on ψ(2S) production compared to J/ψ is also studied via the double ratio of production cross sections [σψ(2S)/σJ/ψ]pPb/[σψ(2S)/σJ/ψ]pp between p-Pb and pp collisions. The results are compared with theoretical models that include various effects related to the initial and final state of the collision system and also with previous measurements at sNN√ = 5.02 TeV.

Measurement of the (anti-)3He elliptic flow in Pb-Pb collisions at sNN=5.02TeV - S. Acharya; D. Adamová; R. Keidel; S.P. Adhya; A. Adler; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; et al. (Physics Letters B, 2020)
The elliptic flow (v2) of (anti-)3He is measured in Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV in the transverse-momentum (pT) range of 2-6 GeV/c for the centrality classes 0-20%, 20-40%, and 40-60% using the event-plane method. This measurement is compared to that of pions, kaons, and protons at the same center-of-mass energy. A clear mass ordering is observed at low pT, as expected from relativistic hydrodynamics. The violation of the scaling of v2 with the number of constituent quarks at low pT, already observed for identified hadrons and deuterons at LHC energies, is confirmed also for (anti-)3He. The elliptic flow of (anti-)3He is underestimated by the Blast-Wave model and overestimated by a simple coalescence approach based on nucleon scaling. The elliptic flow of (anti-)3He measured in the centrality classes 0-20% and 20-40% is well described by a more sophisticated coalescence model where the phase-space distributions of protons and neutrons are generated using the iEBE-VISHNU hybrid model with AMPT initial conditions.

Measurement of the low-energy antideuteron inelastic cross section - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
In this Letter, we report the first measurement of the antideuteron inelastic cross section at low particle momenta, covering a range of 0.3≤p<4 GeV/c. The measurement is carried out using p-Pb collisions at a center-of-mass energy per nucleon-nucleon pair of sNN‾‾‾‾√ = 5.02 TeV, recorded with the ALICE detector at the CERN LHC and utilizing the detector material as an absorber for antideuterons and antiprotons. The extracted raw primary antiparticle-to-particle ratios are compared to the results from detailed ALICE simulations based on the GEANT4 toolkit for the propagation of antiparticles through the detector material. The analysis of the raw primary (anti)proton spectra serves as a benchmark for this study, since their hadronic interaction cross sections are well constrained experimentally. The first measurement of the antideuteron inelastic cross section averaged over the ALICE detector material with atomic mass numbers ⟨A⟩ = 17.4 and 31.8 is obtained. The measured inelastic cross section points to a possible excess with respect to the Glauber model parameterization in the lowest momentum interval of 0.3≤p<0.47 GeV/c up to a factor 2.1. This result is relevant for the understanding of antimatter propagation and the contributions to antinuclei production from cosmic ray interactions within the interstellar medium. In addition, the momentum range covered by this measurement is of particular importance to evaluate signal predictions for indirect dark-matter searches.

Measurement of Λ(1520) production in pp collisions at s√ = 7 TeV and p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; S. P. Adhya; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; et al. (The European Physical Journal C, 2020)
The production of the Λ(1520) baryonic resonance has been measured at midrapidity in inelastic pp collisions at s√ = 7 TeV and in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV for non-single diffractive events and in multiplicity classes. The resonance is reconstructed through its hadronic decay channel Λ(1520) → pK− and the charge conjugate with the ALICE detector. The integrated yields and mean transverse momenta are calculated from the measured transverse momentum distributions in pp and p-Pb collisions. The mean transverse momenta follow mass ordering as previously observed for other hyperons in the same collision systems. A Blast-Wave function constrained by other light hadrons (π, K, K0S, p, Λ) describes the shape of the Λ(1520) transverse momentum distribution up to 3.5 GeV/c in p-Pb collisions. In the framework of this model, this observation suggests that the Λ(1520) resonance participates in the same collective radial flow as other light hadrons. The ratio of the yield of Λ(1520) to the yield of the ground state particle Λ remains constant as a function of charged-particle multiplicity, suggesting that there is no net effect of the hadronic phase in p-Pb collisions on the Λ(1520) yield.

Measurements of inclusive jet spectra in pp and central Pb-Pb collisions at sNN=5.02TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; et al. (Physical Review C, 2020)
This article reports measurements of the pT-differential inclusive jet cross-section in pp collisions at s√ = 5.02 TeV and the pT-differential inclusive jet yield in Pb-Pb 0-10% central collisions at sNN‾‾‾‾√ = 5.02 TeV. Jets were reconstructed at mid-rapidity with the ALICE tracking detectors and electromagnetic calorimeter using the anti-kT algorithm. For pp collisions, we report jet cross-sections for jet resolution parameters R=0.1−0.6 over the range 20<pT,jet<140 GeV/c, as well as the jet cross-section ratios of different R, and comparisons to two next-to-leading-order (NLO)-based theoretical predictions. For Pb-Pb collisions, we report the R=0.2 and R=0.4 jet spectra for 40<pT,jet<140 GeV/c and 60<pT,jet<140 GeV/c, respectively. The scaled ratio of jet yields observed in Pb-Pb to pp collisions, RAA, is constructed, and exhibits strong jet quenching and a clear pT-dependence for R=0.2. No significant R-dependence of the jet RAA is observed within the uncertainties of the measurement. These results are compared to several theoretical predictions.

Multiplicity dependence of (multi-)strange hadron production in proton-proton collisions at s√ = 13 TeV - S. Acharya; D. Adamová; R. Keidel; S. P. Adhya; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; et al. (The European Physical Journal C, 2020)
The production rates and the transverse momentum distribution of strange hadrons at mid-rapidity ( |y |<0.5) are measured in proton-proton collisions at s√ = 13 TeV as a function of the charged particle multiplicity, using the ALICE detector at the LHC. The production rates of K0S, Λ, Ξ, and Ω increase with the multiplicity faster than what is reported for inclusive charged particles. The increase is found to be more pronounced for hadrons with a larger strangeness content. Possible auto-correlations between the charged particles and the strange hadrons are evaluated by measuring the event-activity with charged particle multiplicity estimators covering different pseudorapidity regions. When comparing to lower energy results, the yields of strange hadrons are found to depend only on the mid-rapidity charged particle multiplicity. Several features of the data are reproduced qualitatively by general purpose QCD Monte Carlo models that take into account the effect of densely-packed QCD strings in high multiplicity collisions. However, none of the tested models reproduce the data quantitatively. This work corroborates and extends the ALICE findings on strangeness production in proton-proton collisions at 7 TeV.

Multiplicity dependence of J/ψ production at midrapidity in pp collisions at s√ = 13 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
Measurements of the inclusive J/ψ yield as a function of charged-particle pseudorapidity density dNch/dη in pp collisions at s√ = 13 TeV with ALICE at the LHC are reported. The J/ψ meson yield is measured at midrapidity (|y|<0.9) in the dielectron channel, for events selected based on the charged-particle multiplicity at midrapidity (|η|<1) and at forward rapidity (−3.7<η<−1.7 and 2.8<η<5.1); both observables are normalized to their corresponding averages in minimum bias events. The increase of the normalized J/ψ yield with normalized dN/dη is significantly stronger than linear and dependent on the transverse momentum. The data are compared to theoretical predictions, which describe the observed trends well, albeit not always quantitatively.

Multiplicity dependence of π, K, and p production in pp collisions at s√=13 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
This paper presents the measurements of π±, K±, p and p¯ transverse momentum (pT) spectra as a function of charged-particle multiplicity density in proton-proton (pp) collisions at s√ = 13 TeV with the ALICE detector at the LHC. Such study allows us to isolate the center-of-mass energy dependence of light-flavour particle production. The measurements reported here cover a pT range from 0.1 GeV/c to 20 GeV/c and are done in the rapidity interval |y|<0.5. The pT-differential particle ratios exhibit an evolution with multiplicity, similar to that observed in pp collisions at s√ = 7 TeV, which is qualitatively described by some of the hydrodynamical and pQCD-inspired models discussed in this paper. Furthermore, the pT-integrated hadron-to-pion yield ratios measured in pp collisions at two different center-of-mass energies are consistent when compared at similar multiplicities. This also extends to strange and multi-strange hadrons, suggesting that, at LHC energies, particle hadrochemistry scales with particle multiplicity the same way under different collision energies and colliding systems.

Non-linear flow modes of identified particles in Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; et al. (Journal of High Energy Physics JHEP06, 2020)
The pT-differential non-linear flow modes, v4,22, v5,32, v6,33 and v6,222 for π±, K± , K0S , p + p⎯⎯⎯, Λ + Λ⎯⎯⎯⎯ and ϕ-meson have been measured for the first time at sNN‾‾‾‾√ = 5.02 TeV in Pb-Pb collisions with the ALICE detector at the Large Hadron Collider. The results were obtained with a multi-particle technique, correlating the identified hadrons with reference charged particles from a different pseudorapidity region. These non-linear observables probe the contribution from the second and third order initial spatial anisotropy coefficients to higher flow harmonics. All the characteristic features observed in previous pT-differential anisotropic flow measurements for various particle species are also present in the non-linear flow modes, i.e. increase of magnitude with increasing centrality percentile, mass ordering at low pT and particle type grouping in the intermediate pT range. Hydrodynamical calculations (iEBE-VISHNU) that use different initial conditions and values of shear and bulk viscosity to entropy density ratios are confronted with the data at low transverse momenta. These calculations exhibit a better agreement with the anisotropic flow coefficients than the non-linear flow modes. These observations indicate that non-linear flow modes can provide additional discriminatory power in the study of initial conditions as well as new stringent constraints to hydrodynamical calculations.

Production of (anti-)He3 and (anti-)H3 in p-Pb collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; et al. (Physical Review C, 2020)
The transverse momentum (pT) differential yields of (anti-)3He and (anti-)3H measured in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV with ALICE at the Large Hadron Collider (LHC) are presented. The ratios of the pT-integrated yields of (anti-)3He and (anti-)3H to the proton yields are reported, as well as the pT dependence of the coalescence parameters B3 for (anti-)3He and (anti-)3H. For (anti-)3He, the results obtained in four classes of the mean charged-particle multiplicity density are also discussed. These results are compared to predictions from a canonical statistical hadronization model and coalescence approaches. An upper limit on the total yield of 4He¯ is determined.

Production of charged pions, kaons, and (anti-)protons in Pb-Pb and inelastic pp collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; R. Keidel; S. P. Adhya; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; et al. (Physical Review C, 2020)
Mid-rapidity production of π±, K± and (p¯)p measured by the ALICE experiment at the LHC, in Pb-Pb and inelastic pp collisions at sNN‾‾‾‾√ = 5.02 TeV, is presented. The invariant yields are measured over a wide transverse momentum (pT) range from hundreds of MeV/c up to 20 GeV/c. The results in Pb-Pb collisions are presented as a function of the collision centrality, in the range 0−90%. The comparison of the pT-integrated particle ratios, i.e. proton-to-pion (p/π) and kaon-to-pion (K/π) ratios, with similar measurements in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV show no significant energy dependence. Blast-wave fits of the pT spectra indicate that in the most central collisions radial flow is slightly larger at 5.02 TeV with respect to 2.76 TeV. Particle ratios (p/π, K/π) as a function of pT show pronounced maxima at pT ≈ 3 GeV/c in central Pb-Pb collisions. At high pT, particle ratios at 5.02 TeV are similar to those measured in pp collisions at the same energy and in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV. Using the pp reference spectra measured at the same collision energy of 5.02 TeV, the nuclear modification factors for the different particle species are derived. Within uncertainties, the nuclear modification factor is particle species independent for high pT and compatible with measurements at sNN‾‾‾‾√ = 2.76 TeV. The results are compared to state-of-the-art model calculations, which are found to describe the observed trends satisfactorily.

Production of light-flavor hadrons in pp collisions at s√ = 7 and s√ = 13 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
The production of π±, K±, K0S, K∗(892)0, p, ϕ(1020), Λ, Ξ−, Ω−, and their antiparticles was measured in inelastic proton-proton (pp) collisions at a center-of-mass energy of s√ = 13 TeV at midrapidity (|y|<0.5) as a function of transverse momentum (pT) using the ALICE detector at the CERN LHC. Furthermore, the single-particle pT distributions of K0S, Λ, and Λ⎯⎯⎯⎯ in inelastic pp collisions at s√ = 7 TeV are reported here for the first time. The pT distributions are studied at midrapidity within the transverse momentum range 0≤pT≤20 GeV/c, depending on the particle species. The pT spectra, integrated yields, and particle yield ratios are discussed as a function of collision energy and compared with measurements at lower s√ and with results from various general-purpose QCD-inspired Monte Carlo models. A hardening of the spectra at high pT with increasing collision energy is observed, which is similar for all particle species under study. The transverse mass and xT≡2pT/s√ scaling properties of hadron production are also studied. As the collision energy increases from s√ = 7 to 13 TeV, the yields of non- and single-strange hadrons normalized to the pion yields remain approximately constant as a function of s√, while ratios for multi-strange hadrons indicate enhancements. The pT-differential cross sections of π±, K± and p (p⎯⎯⎯) are compared with next-to-leading order perturbative QCD calculations, which are found to overestimate the cross sections for π± and p (p⎯⎯⎯) at high pT.

Production of muons from heavy-flavour hadron decays at high transverse momentum in Pb-Pb collisions at sNN√=5.02 and 2.76 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
Measurements of the production of muons from heavy-flavour hadron decays in Pb−Pb collisions at sNN‾‾‾‾√ = 5.02 and 2.76 TeV using the ALICE detector at the LHC are reported. The nuclear modification factor RAA at sNN‾‾‾‾√ = 5.02 TeV is measured at forward rapidity (2.5<y<4) as a function of transverse momentum pT in central, semi-central, and peripheral collisions over a wide pT interval, 3<pT<20 GeV/c, in which a significant contribution of muons from beauty-hadron decays is expected at high pT. With a significantly improved precision compared to the measurements at lower collision energy, the RAA shows an increase of the suppression of the yields of muons from heavy-flavour hadron decays with increasing centrality. A suppression by a factor of about three is observed in the 10% most central collisions. The RAA at sNN‾‾‾‾√ = 5.02 is similar to that reported at 2.76 TeV in a broader pT interval and with an improved accuracy with respect to previously published measurements. The precise RAA results have the potential to distinguish between model predictions implementing different mechanisms of parton energy loss in the high-density medium formed in heavy-ion collisions. The results place stringent constraints on the relative energy loss between charm and beauty quarks.

Production of ω mesons in pp collisions at s√ = 7 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; M. M. Aggarwal; S. Agha; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; et al. (The European Physical Journal C, 2020)
The invariant differential cross section of inclusive ω(782) meson production at midrapidity (|y|<0.5) in pp collisions at s√ = 7 TeV was measured with the ALICE detector at the LHC over a transverse momentum range of 2 < pT < 17 GeV/c. The ω meson was reconstructed via its ω→π+π−π0 decay channel. The measured ω production cross section is compared to various calculations: PYTHIA 8.2 Monash 2013 describes the data, while PYTHIA 8.2 Tune 4C overestimates the data by about 50%. A recent NLO calculation, which includes a model describing the fragmentation of the whole vector-meson nonet, describes the data within uncertainties below 6 GeV/c, while it overestimates the data by up to 50% for higher pT. The ω/π0 ratio is in agreement with previous measurements at lower collision energies and the PYTHIA calculations. In addition, the measurement is compatible with transverse mass scaling within the measured pT range and the ratio is constant with Cω/π0 = 0.67 ± 0.03 (stat) ± 0.04 (sys) above a transverse momentum of 2.5 GeV/c.

Pseudorapidity distributions of charged particles as a function of mid and forward rapidity mutiplicities in pp collisions at s√ = 5.02, 7 and 13 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
The multiplicity dependence of the pseudorapidity density of charged particles in proton-proton (pp) collisions at centre-of-mass energies s√ = 5.02, 7 and 13 TeV measured by ALICE is reported. The analysis relies on track segments measured in the midrapidity range (|η|<1.5). Results are presented for inelastic events having at least one charged particle produced in the pseudorapidity interval |η|<1 (INEL>0). The multiplicity dependence of the pseudorapidy density of charged particles is measured with mid and forward rapidity multiplicity estimators, the latter being less affected by autocorrelations. A detailed comparison with predictions from the PYTHIA 8 and EPOS LHC event generators is also presented. Both generators provide a good description of the data.

Search for a common baryon source in high-multiplicity pp collisions at the LHC - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
We report on the measurement of the size of the particle-emitting source from two-baryon correlations with ALICE in high-multiplicity pp collisions at s√ = 13 TeV. The source radius is studied with low relative momentum p-p, p¯-p¯, p-Λ and p¯-Λ¯ pairs as a function of the pair transverse mass mT considering for the first time in a quantitative way the effect of strong resonance decays. After correcting for this effect, the radii extracted for pairs of different particle species agree. This indicates that protons, antiprotons, Λ, and Λ¯ originate from the same source. Within the measured mT range (1.1-2.2) GeV/c2 the invariant radius of this common source varies between 0.85 and 1.3 fm. These results provide a precise reference for studies of the strong hadron-hadron interactions and for the investigation of collective properties in small colliding systems.

Soft-dielectron excess in proton-proton collisions at s√= 13 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
A measurement of dielectron production in proton-proton (pp) collisions at s√ = 13 TeV, recorded with the ALICE detector at the CERN LHC, is presented in this Letter. The data set was recorded with a reduced magnetic solenoid field. This enables the investigation of a kinematic domain at low dielectron invariant mass mee and pair transverse momentum pT,ee that was previously inaccessible at the LHC. The cross section for dielectron production is studied as a function of mee, pT,ee, and event multiplicity dNch/dη. The expected dielectron rate from hadron decays, called hadronic cocktail, utilizes a parametrization of the measured η/π0 ratio in pp and proton-nucleus (p-A) collisions, assuming that this ratio shows no strong dependence on collision energy at low transverse momentum. Comparison of the measured dielectron yield to the hadronic cocktail at 0.15 < mee < 0.6 GeV/c and for pT,ee < 0.4 GeV/c indicates an enhancement of soft dielectrons, reminiscent of the ’anomalous’ soft-photon and -dilepton excess in hadron-hadron collisions reported by several experiments under different experimental conditions. The enhancement factor over the hadronic cocktail amounts to 1.69 ± 0.14(stat.) ± 0.18(syst.,data) ± 0.36(syst., cocktail) in the ALICE acceptance. Acceptance-corrected excess spectra in mee and pT,ee are extracted and compared with calculations of dielectron production from hadronic bremsstrahlung and thermal radiation within a hadronic many-body approach.

Studies of J/ψ production at forward rapidity in Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - S. Acharya; D. Adamová; R. Keidel; S. P. Adhya; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; et al. (Journal of High Energy Physics, 2020)
The inclusive J/ψ production in Pb-Pb collisions at the center-of-mass energy per nucleon pair sNN‾‾‾‾√ = 5.02 TeV, measured with the ALICE detector at the CERN LHC, is reported. The J/ψ meson is reconstructed via the dimuon decay channel at forward rapidity (2.5<y<4) down to zero transverse momentum. The suppression of the J/ψ yield in Pb-Pb collisions with respect to binary-scaled pp collisions is quantified by the nuclear modification factor (RAA). The RAA at sNN‾‾‾‾√ = 5.02 TeV is presented and compared with previous measurements at sNN‾‾‾‾√ = 2.76 TeV as a function of the centrality of the collision, and of the J/ψ transverse momentum and rapidity. The inclusive J/ψ RAA shows a suppression increasing toward higher pT, with a steeper dependence for central collisions. The modification of the J/ψ average pT and p2T is also studied. Comparisons with the results of models based on a transport equation and on statistical hadronization are also carried out.

Transverse-momentum and event-shape dependence of D-meson flow harmonics in Pb-Pb collisions at sNN√=5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
The elliptic and triangular flow coefficients 𝑣2 and 𝑣3 of prompt 𝐷0, 𝐷+, and 𝐷∗+ mesons were measured at midrapidity (|𝑦|<0.8) in Pb-Pb collisions at the centre-of-mass energy per nucleon pair of 𝑠𝑁𝑁‾‾‾‾√=5.02 TeV with the ALICE detector at the LHC. The D mesons were reconstructed via their hadronic decays in the transverse momentum interval 1<𝑝T<36 GeV/𝑐 in central (0-10%) and semi-central (30-50%) collisions. Compared to pions, protons, and J/𝜓 mesons, the average D-meson 𝑣𝑛 harmonics are found to follow a mass ordering for 𝑝T<3 GeV/𝑐, and to be similar to those of charged pions for higher 𝑝T. The coupling of the charm quark to the light quarks in the underlying medium is further investigated with the application of the event-shape engineering (ESE) technique to the D-meson 𝑣2 and 𝑝T-differential yields. The D-meson 𝑣2 is correlated with average bulk elliptic flow in both central and semi-central collisions. Within the current precision, the ratios of per-event D-meson yields in the ESE-selected and unbiased samples are found to be compatible with unity. All the measurements are found to be reasonably well described by theoretical calculations including the effects of charm-quark transport and the recombination of charm quarks with light quarks in a hydrodynamically expanding medium.

Underlying Event properties in pp collisions at s√ = 13 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; et al. (Journal of High Energy Physics, 2020)
This article reports measurements characterizing the Underlying Event (UE) associated with hard scatterings at midrapidity in pp collisions at s√=13 TeV. The hard scatterings are identified by the leading particle, the charged particle with the highest transverse momentum (pleadingT) in the event. Charged-particle number and summed transverse-momentum densities are measured in different azimuthal regions defined with respect to the leading particle direction: Toward, Transverse, and Away. The Toward and Away regions contain the fragmentation products of the hard scatterings in addition to the UE contribution, whereas particles in the Transverse region are expected to originate predominantly from the UE. The study is performed as a function of pleadingT with three different pT thresholds for the associated particles, pminT> 0.15, 0.5, and 1.0 GeV/c. The charged-particle density in the Transverse region rises steeply for low values of pleadingT and reaches a plateau. The results confirm the trend that the charged-particle density in the Transverse region shows a stronger increase with s√ than the inclusive charged-particle density at midrapidity. The UE activity is increased by approximately 20% when going from 7 to 13 TeV. The plateau in the Transverse region (5<pleadingT< 40 GeV/c ) is further characterized by the probability distribution of its charged-particle multiplicity normalized to its average value (relative transverse activity, RT) and the mean transverse momentum as a function of RT. Experimental results are compared to model calculations using PYTHIA 8 and EPOS LHC. The overall agreement between models and data is within 30%. These measurements provide new insights on the interplay between hard scatterings and the associated UE in pp collisions.

Unveiling the strong interaction among hadrons at the LHC - D. Adamova; R. Keidel; A. Adler (Nature, 2020)
Correlations in momentum space between hadrons created by ultrarelativistic proton-proton collisions at the CERN Large Hadron Collider provide insights into the strong interaction, particularly the short-range dynamics of hyperons—baryons that contain strange quarks.

Z-boson production in p-Pb collisions at sNN√=8.16 TeV and Pb-Pb collisions at sNN√=5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
Measurement of Z-boson production in p-Pb collisions at sNN√=8.16 TeV and Pb-Pb collisions at sNN√=5.02 TeV is reported. It is performed in the dimuon decay channel, through the detection of muons with pseudorapidity −4<ημ<−2.5 and transverse momentum pμT>20 GeV/c in the laboratory frame. The invariant yield and nuclear modification factor are measured for opposite-sign dimuons with invariant mass 60<mμμ<120 GeVc2 and rapidity 2.5<yμμcms<4. They are presented as a function of rapidity and, for the Pb-Pb collisions, of centrality as well. The results are compared with theoretical calculations, both with and without nuclear modifications to the Parton Distribution Functions (PDFs). In p-Pb collisions the center-of-mass frame is boosted with respect to the laboratory frame, and the measurements cover the backward (−4.46<yμμcms<−2.96) and forward (2.03<yμμcms<3.53) rapidity regions. For the p-Pb collisions, the results are consistent within experimental and theoretical uncertainties with calculations that include both free-nucleon and nuclear-modified PDFs. For the Pb-Pb collisions, a 3.4σ deviation is seen in the integrated yield between the data and calculations based on the free-nucleon PDFs, while good agreement is found once nuclear modifications are considered.

Λ+c production and baryon-to-meson ratios in pp and p-Pb collisions at sNN√=5.02 TeV at the LHC - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
The prompt production of the charmed baryon Λ+c and the Λ+c/D0 production ratios were measured at midrapidity with the ALICE detector in pp and p-Pb collisions at sNN‾‾‾‾√=5.02TeV. These new measurements show a clear decrease of the Λ+c/D0 ratio with increasing transverse momentum (pT) in both collision systems in the range 2<pT<12 GeV/c, exhibiting similarities with the light-flavour baryon-to-meson ratios p/π and Λ/K0S. At low pT, predictions that include additional colour-reconnection mechanisms beyond the leading-colour approximation; assume the existence of additional higher-mass charmed-baryon states; or include hadronisation via coalescence can describe the data, while predictions driven by charm-quark fragmentation processes measured in e+e− and e−p collisions significantly underestimate the data. The results presented in this letter provide significant evidence that the established assumption of universality (colliding-system independence) of parton-to-hadron fragmentation is not sufficient to describe charmed-baryon production in hadronic collisions at LHC energies.

ΛK femtoscopy in Pb-Pb collisions at sNN√ = 2.76 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
The first measurements of the scattering parameters of ΛK pairs in all three charge combinations (ΛK+, ΛK−, and ΛK0S) are presented. The results are achieved through a femtoscopic analysis of ΛK correlations in Pb-Pb collisions at sNN√ = 2.76 TeV recorded by ALICE at the LHC. The femtoscopic correlations result from strong final-state interactions, and are fit with a parametrization allowing for both the characterization of the pair emission source and the measurement of the scattering parameters for the particle pairs. Extensive studies with the THERMINATOR 2 event generator provide a good description of the non-femtoscopic background, which results mainly from collective effects, with unprecedented precision. Furthermore, together with HIJING simulations, this model is used to account for contributions from residual correlations induced by feed-down from particle decays. The extracted scattering parameters indicate that the strong force is repulsive in the ΛK+ interaction and attractive in the ΛK− and ΛK0S interactions. The results suggest an effect arising either from different quark-antiquark interactions between the pairs (ss⎯⎯ in ΛK+ and uu⎯⎯⎯ in ΛK−) or from different net strangeness for each system (S = 0 for ΛK+, and S = −2 for ΛK−). Finally, the ΛK systems exhibit source radii larger than expected from extrapolation from identical particle femtoscopic studies. This effect is interpreted as resulting from the separation in space-time of the single-particle Λ and K source distributions.

Υ production and nuclear modification at forward rapidity in Pb-Pb collisions at sNN√=5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; A. Adler (2020)
The production of Υ mesons in Pb-Pb collisions at a centre-of-mass energy per nucleon pair sNN‾‾‾‾√ = 5 TeV is measured with the muon spectrometer of ALICE at the LHC. The yields as well as the nuclear modification factors are determined in the forward rapidity region 2.5<y<4.0, as a function of rapidity, transverse momentum and collision centrality. The results show that the production of Υ(1S) is suppressed by a factor of about three with respect to the production in proton-proton collisions. For the first time, a significant Υ(2S) signal is observed at forward rapidity, indicating a suppression stronger by about a factor 2-3 with respect to the ground state. The measurements are compared with transport, hydrodynamic, comover and statistical hadronisation model calculations.

ϒ production in p-Pb collisions at sNN=8.16 TeV - S. Acharya; D. Adamová; R. Keidel; A. Adler; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; et al. (Physics Letters B, 2020)
Υ production in p-Pb interactions is studied at the centre-of-mass energy per nucleon-nucleon collision sNN‾‾‾‾√ = 8.16 TeV with the ALICE detector at the CERN LHC. The measurement is performed reconstructing bottomonium resonances via their dimuon decay channel, in the centre-of-mass rapidity intervals 2.03<ycms<3.53 and −4.46<ycms<−2.96, down to zero transverse momentum. In this work, results on the inclusive Υ(1S) production cross section as a function of rapidity and transverse momentum are presented. The corresponding nuclear modification factor shows a suppression of the Υ(1S) yields with respect to pp collisions, both at forward and backward rapidity. This suppression is stronger in the low transverse momentum region and shows no significant dependence on the centrality of the interactions. Furthermore, the Υ(2S) nuclear modification factor is also evaluated, suggesting a suppression similar to that of the Υ(1S). A first measurement of the Υ(3S) has also been performed. Finally, results are compared with previous measurements performed by ALICE in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV and with theoretical calculations.

3ΛH and 3Λ¯H¯ lifetime measurement in Pb-Pb collisions at sNN‾‾‾‾√= 5.02 TeV via two-body decay - S. Acharya; D. Adamová; R. Keidel; S.P. Adhya; A. Adler; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; et al. (Physics Letters B, 2019)
An improved value for the lifetime of the (anti-)hypertriton has been obtained using the data sample of Pb-Pb collisions at sNN‾‾‾‾√= 5.02 TeV collected by the ALICE experiment at the LHC. The (anti-)hypertriton has been reconstructed via its charged two-body mesonic decay channel and the lifetime has been determined from an exponential fit to the dN/d(ct) spectrum. The measured value, τ = 242+34−38 (stat.) ± 17 (syst.) ps, is compatible with all the available theoretical predictions, thus contributing to the solution of the longstanding hypertriton lifetime puzzle.

A next-generation LHC heavy-ion experiment - D. Adamova; G. Aglieri Rinella; Ralf Keidel; M. Agnello (2019)
The present document discusses plans for a compact, next-generation multi-purpose detector at the LHC as a follow-up to the present ALICE experiment. The aim is to build a nearly massless barrel detector consisting of truly cylindrical layers based on curved wafer-scale ultra-thin silicon sensors with MAPS technology, featuring an unprecedented low material budget of 0.05% X_0 per layer, with the innermost layers possibly positioned inside the beam pipe. In addition to superior tracking and vertexing capabilities over a wide momentum range down to a few tens of MeV/c, the detector will provide particle identification via time-of-flight determination with about 20ps resolution. In addition, electron and photon identification will be performed in a separate shower detector. The proposed detector is conceived for studies of pp, pA and AA collisions at luminosities a factor of 20 to 50 times higher than possible with the upgraded ALICE detector, enabling a rich physics program ranging from measurements with electromagnetic probes at ultra-low transverse momenta to precision physics in the charm and beauty sector.

Azimuthal correlations of prompt D mesons with charged particles in pp and p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - S. Acharya; D. Adamova; R. Keidel; A. Adler (2019)
The measurement of the azimuthal-correlation function of prompt D mesons with charged particles in pp collisions at s√ = 5.02 TeV and p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV with the ALICE detector at the LHC is reported. The D0, D+, and D∗+ mesons, together with their charge conjugates, were reconstructed at midrapidity in the transverse momentum interval 3 < pT < 24 GeV/c and correlated with charged particles having pT > 0.3 GeV/c and pseudorapidity |η|< 0.8. The properties of the correlation peaks appearing in the near- and away-side regions (for Δφ≈ 0 and Δφ≈π, respectively) were extracted via a fit to the azimuthal correlation functions. The shape of the correlation functions and the near- and away-side peak features are found to be consistent in pp and p-Pb collisions, showing no modifications due to nuclear effects within uncertainties. The results are compared with predictions from Monte Carlo simulations performed with the PYTHIA, POWHEG+PYTHIA, HERWIG, and EPOS 3 event generators.

Calibration of the photon spectrometer PHOS of the ALICE experiment - S. Acharya; F.T.-. Acosta; R. Keidel; D. Adamová; S.P. Adhya; A. Adler; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; Z. Ahammed; S. Ahmad; et al. (Journal of Instrumentation, 2019)
The procedure for the energy calibration of the high granularity electromagnetic calorimeter PHOS of the ALICE experiment is presented. The methods used to perform the relative gain calibration, to evaluate the geometrical alignment and the corresponding correction of the absolute energy scale, to obtain the nonlinearity correction coefficients and finally, to calculate the time-dependent calibration corrections, are discussed and illustrated by the PHOS performance in proton-proton (pp) collisions at √s=13 TeV. After applying all corrections, the achieved mass resolutions for π0 and η mesons for pT > 1.7 GeV/c are σmπ0 = 4.56 ± 0.03 MeV/c2 and σmη = 15.3 ± 1.0 MeV/c2, respectively.

Charged-particle production as a function of multiplicity and transverse spherocity in pp collisions at s =5.02 and 13 TeV - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
We present a study of the inclusive charged-particle transverse momentum (p_T) spectra as a function of charged-particle multiplicity density at mid-pseudorapidity, dN_ch/dη, in pp collisions at s=5.02 and 13 TeV covering the kinematic range |η|<0.8 and 0.15<p_T<20 GeV/c. The results are presented for events with at least one charged particle in |η|<1 (INEL >0). The transverse momentum spectra are reported for two multiplicity estimators covering different pseudorapidity regions. While the p_T spectra exhibit a strong dependence on multiplicity and center-of-mass energy, they show little energy dependence when normalized to the p_T spectrum for INEL >0. The behavior of the multiplicity dependent spectra from intermediate to high transverse momentum (6<p_T<20 GeV/c) is parametrised by the exponent of a power-law function. Going from low to high average charged-particle density, the exponent decreases from 6 to 5. Moreover, the high-p_T yields of charged particles increase faster than the charged-particle multiplicity density. The average p_T as a function of multiplicity and transverse spherocity is reported for pp collisions at s=13 TeV. For low- (high-) spherocity events, corresponding to jet-like (isotropic) events, the average p_T is higher (smaller) than that measured in INEL >0 pp collisions. Within uncertainties, the functional form of p_T (N_ch) is not affected by the spherocity selection. While EPOS LHC gives a good description of many features of data, PYTHIA overestimates the average p_T in jet-like events. The observations are discussed in terms of multi-parton interactions with large momentum transfer and color reconnection.

Coherent J/ψ photoproduction at forward rapidity in ultra-peripheral Pb-Pb collisions at s_NN=5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
The coherent photoproduction of J/ψ was measured in ultra-peripheral Pb-Pb collisions at a center-of-mass energy s_NN=5.02 TeV with the ALICE detector. The J/ψ is detected via its dimuon decay in the forward rapidity region for events where the hadronic activity is required to be minimal. The analysis is based on an event sample corresponding to an integrated luminosity of about 750 μb^-1. The cross section for coherent J/ψ production is presented in six rapidity bins, covering the interval -4.0 < y < -2.5. The results are compared with theoretical models for coherent J/ψ photoproduction. The results indicate that gluon shadowing effects play a role in the photoproduction process. The ratio of ψ' to J/ψ coherent photoproduction cross sections was measured and found to be consistent with that measured for photoproduction off protons.

Event-shape and multiplicity dependence of freeze-out radii in pp collisions at s=7 TeV - D. Adamova; S. Acharya; Ralf Keidel; S. P. Adhya (2019)
Two-particle correlations in high-energy collision experiments enable the extraction of particle source radii by using the Bose-Einstein enhancement of pion production at low relative momentum q1/R. It was previously observed that in pp collisions at s=7 TeV the average pair transverse momentum k_T range of such analyses is limited due to large background correlations which were attributed to mini-jet phenomena. To investigate this further, an event-shape dependent analysis of Bose-Einstein correlations for pion pairs is performed in this work. By categorizing the events by their transverse sphericity S_T into spherical (S_T>0.7) and jet-like (S_T<0.3) events a method was developed that allows for the determination of source radii for much larger values of k_T for the first time. Spherical events demonstrate little or no background correlations while jet-like events are dominated by them. This observation agrees with the hypothesis of a mini-jet origin of the non-femtoscopic background correlations and gives new insight into the physics interpretation of the k_T dependence of the radii. The emission source size in spherical events shows a substantially diminished k_T dependence, while jet-like events show indications of a negative trend with respect to k_T in the highest multiplicity events. Regarding the emission source shape, the correlation functions for both event sphericity classes show good agreement with an exponential shape, rather than a Gaussian one.

Exploration of jet substructure using iterative declustering in pp and Pb-Pb collisions at LHC energies - S. Acharya; D. Adamova; Ralf Keidel; S. P Adhya (2019)
The ALICE collaboration at the CERN LHC reports novel measurements of jet substructure in pp collisions at s= 7 TeV and central Pb-Pb collisions at s_NN = 2.76 TeV. Jet substructure of track-based jets is explored via iterative declustering and grooming techniques. We present the measurement of the momentum sharing of two-prong substructure exposed via grooming, the z_g, and its dependence on the opening angle, in both pp and Pb-Pb collisions. We also present the first measurement of the distribution of the number of branches obtained in the iterative declustering of the jet, which is interpreted as the number of its hard splittings. In Pb-Pb collisions, we observe a suppression of symmetric splittings at large opening angles and an enhancement of splittings at small opening angles relative to pp collisions, with no significant modification of the number of splittings. The results are compared to predictions from various Monte Carlo event generators to test the role of important concepts in the evolution of the jet in the medium such as color coherence.

First observation of an attractive interaction between a proton and a multi-strange baryon - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
This work presents the first experimental observation of the attractive strong interaction between a proton and a multi-strange baryon (hyperon) Ξ^-. The result is extracted from two-particle correlations of combined p-Ξ^-p-Ξ^+ pairs measured in p-Pb collisions at s_NN=5.02 TeV at the LHC with ALICE. The measured correlation function is compared with the prediction obtained assuming only an attractive Coulomb interaction and a standard deviation in the range [3.6,5.3] is found. Since the measured p-Ξ^-p-Ξ^+ correlation is significantly enhanced with respect to the Coulomb prediction, the presence of an additional, strong, attractive interaction is evident. The data are compatible with recent lattice calculations by the HAL-QCD Collaboration, with a standard deviation in the range [1.8,3.7]. The lattice potential predicts a shallow repulsive Ξ^- interaction within pure neutron matter at saturation densities and this implies stiffer equations of state for neutron-rich matter including hyperons. Implications of the strong interaction for the modeling of neutron stars are discussed.

Global baryon number conservation encoded in net-proton fluctuations measured in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - S. Acharya; D. Adamova; R. Keidel; A. Adler (2019)
Experimental results are presented on event-by-event net-proton fluctuation measurements in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV, recorded by the ALICE detector at the CERN LHC. These measurements have as their ultimate goal an experimental test of Lattice QCD (LQCD) predictions on second and higher order cumulants of net-baryon distributions to search for critical behavior near the QCD phase boundary. Before confronting them with LQCD predictions, account has to be taken of correlations stemming from baryon number conservation as well as fluctuations of participating nucleons. Both effects influence the experimental measurements and are usually not considered in theoretical calculations. For the first time, it is shown that event-by-event baryon number conservation leads to subtle long-range correlations arising from very early interactions in the collisions.

Inclusive J/ψ production at mid-rapidity in pp collisions at s = 5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
Inclusive J/ψ production is studied in minimum-bias proton-proton collisions at a centre-of-mass energy of s = 5.02 TeV by ALICE at the CERN LHC. The measurement is performed at mid-rapidity (|y| < 0.9) in the dielectron decay channel down to zero transverse momentum p_T, using a data sample corresponding to an integrated luminosity of L_int = 19.4 ± 0.4 nb^-1. The measured p_T-integrated inclusive J/ψ production cross section is dσ/dy = 5.64 ± 0.22 (stat.) ± 0.33 (syst.) ± 0.12 (lumi.) μb. The p_T-differential cross section d^2 σ/dp_Tdy is measured in the p_T range 0-10 GeV/c and compared with state-of-the-art perturbative QCD calculations. The J/ψ p_T and p_T^2 are extracted and compared with results obtained at other collision energies.

Investigations of anisotropic flow using multi-particle azimuthal correlations in pp, p-Pb, Xe-Xe, and Pb-Pb collisions at the LHC - S. Acharya; D. Adamova; Ralf Keidel; S. Adhya (2019)
Measurements of anisotropic flow coefficients (v_n) and their cross-correlations using two- and multi-particle cumulant methods are reported in collisions of pp at s = 13 TeV, p-Pb at s__NN = 5.02 TeV, Xe-Xe at s__NN = 5.44 TeV, and Pb-Pb at s__NN = 5.02 TeV recorded with the ALICE detector. These measurements are performed as a function of multiplicity in the mid-rapidity region |η|<0.8 for the transverse momentum range 0.2 < p_T < 3.0 GeV/c. An ordering of the coefficients v_2 > v_3 > v_4 is found in pp and p-Pb collisions, similar to that seen in large collision systems, while a weak v_2 multiplicity dependence is observed relative to nucleus–nucleus collisions in the same multiplicity range. Using the novel subevent method, v_2 measured in pp and p-Pb collisions with four-particle cumulants is found to be compatible with that from six-particle cumulants. The symmetric cumulants SC(m,n) calculated with the subevent method which evaluate the correlation strength between v_n^2 and v_m^2 are also presented. The presented data, which add further support to the existence of long-range multi-particle azimuthal correlations in high multiplicity pp and p-Pb collisions, can neither be described by PYTHIA8 nor by IP-Glasma+MUSIC+UrQMD model calculations, and hence provide new insights into the understanding of collective effects in small collision systems.

K∗(892)0 and ϕ(1020) production at midrapidity in pp collisions at s√ = 8 TeV - S. Acharya; D. Adamova; R. Keidel; A. Adler (2019)
The production of K∗(892)0 and ϕ(1020) in pp collisions at s√ = 8 TeV were measured using Run 1 data collected by the ALICE collaboration at the LHC. The pT-differential yields d2N/dydpT in the range 0 < pT < 20 GeV/c for K∗0 and 0.4 < pT < 16 GeV/c for ϕ have been measured at midrapidity |y| < 0.5. Moreover, improved measurements of the K∗(892)0 and ϕ(1020) at s√ = 7 TeV are presented. The collision energy dependence of pT distributions, pT-integrated yields and particle ratios in inelastic pp collisions are examined. The results are also compared with different collision systems. The values of the particle ratios are measured to be similar to those found at other LHC energies. In pp collisions a hardening of the particle spectra is observed with increasing energy, but at the same time it is also observed that the relative particle abundances are independent of the collision energy. The pT-differential yields of K∗0 and ϕ in pp collisions at s√ = 8 TeV are compared with the expectations of different Monte Carlo event generators.

Measurement of pΛpΛ and ΛΛ interactions with femtoscopic correlations in Pb-Pb collisions at s_NN = 2.76 TeV and s_NN = 5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
Femtoscopic correlation functions were measured for pp, pΛpΛ, and ΛΛ pairs, as a function of collision centrality, in Pb-Pb collisions at s_NN=2.76 TeV and s_NN=5.02 TeV recorded by the ALICE experiment at the LHC. A simultaneous fit to all obtained correlation functions was performed, maximising the precision and sensitivity to the strong interaction parameters for the selected baryon pairs. Real and imaginary components of the scattering lengths, as well as the effective ranges, were extracted for combined pΛpΛ pairs and, for the first time, for ΛΛ pairs. Effective averaged scattering parameters for heavier baryon-anti-baryon pairs, not measured directly, are also provided. The results reveal similarly strong interaction between measured baryon-anti-baryon pairs, suggesting that they annihilate in the same manner as pp at the same pair relative momentum k^*. Moreover, the reported significant non-zero imaginary part and negative real part of the scattering length open up a possibility for future baryon-anti-baryon bound state searches.

Measurement of Υ(1S) elliptic flow at forward rapidity in Pb-Pb collisions at s_NN=5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
The first measurement of the Υ(1S) elliptic flow coefficient (v_2) is performed at forward rapidity (2.5 < y < 4) in Pb-Pb collisions at s_NN = 5.02 TeV with the ALICE detector at the LHC. The results are obtained with the scalar product method and are reported as a function of transverse momentum (p_T) up to 15 GeV/c in the 5-60% centrality interval. The measured Υ(1S) v_2 is consistent with zero and with the small positive values predicted by transport models within uncertainties. The v_2 coefficient in 2 < p_T < 15 GeV/c is lower than that of inclusive J/ψ mesons in the same p_T interval by 2.6 standard deviations. These results, combined with earlier suppression measurements, are in agreement with a scenario in which the Υ(1S) production in Pb-Pb collisions at LHC energies is dominated by dissociation limited to the early stage of the collision whereas in the J/ψ case there is substantial experimental evidence of an additional regeneration component.

Measurement of charged jet cross section in pp collisions at s=5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
The cross section of jets reconstructed from charged particles is measured in the transverse momentum range of 5<p_T<100 GeV/c in pp collisions at the center-of-mass energy of s = 5.02 TeV with the ALICE detector. The jets are reconstructed using the anti-k_T algorithm with resolution parameters R=0.2, 0.3, 0.4, and 0.6 in the pseudorapidity range |η|< 0.9-R. The charged jet cross sections are compared with the leading order (LO) and to next-to-leading order (NLO) perturbative Quantum ChromoDynamics (pQCD) calculations. It was found that the NLO calculations agree better with the measurements. The cross section ratios for different resolution parameters were also measured. These ratios increase from low p_T to high p_T and saturate at high p_T, indicating that jet collimation is larger at high p_T than at low p_T. These results provide a precision test of pQCD predictions and serve as a baseline for the measurement in Pb-Pb collisions at the same energy to quantify the effects of the hot and dense medium created in heavy-ion collisions at the LHC.

Measurement of D0 , D+ , D∗+ and D+s production in pp collisions at s√ = 5.02 TeV with ALICE - S. Acharya; D. Adamová; R. Keidel; S. P. Adhya; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; Z. Ahammed; S. Ahmad; S. U. Ahn; et al. (The European Physical Journal C, 2019)
The measurements of the production of prompt D0, D+, D∗+, and D+s mesons in proton–proton (pp) collisions at s√=5.02 TeV with the ALICE detector at the Large Hadron Collider (LHC) are reported. D mesons were reconstructed at mid-rapidity (|y|<0.5) via their hadronic decay channels D0→K−π+, D+→K−π+π+, D∗+→D0π+→K−π+π+, D+s→ϕπ+→K+K−π+, and their charge conjugates. The production cross sections were measured in the transverse momentum interval 0<pT<36 GeV/c for D0, 1<pT<36 GeV/c for D+ and D∗+, and in 2<pT<24 GeV/c for D+s mesons. Thanks to the higher integrated luminosity, an analysis in finer pT bins with respect to the previous measurements at s√=7 TeV was performed, allowing for a more detailed description of the cross-section pT shape. The measured pT-differential production cross sections are compared to the results at s√=7 TeV and to four different perturbative QCD calculations. Its rapidity dependence is also tested combining the ALICE and LHCb measurements in pp collisions at s√=5.02 TeV. This measurement will allow for a more accurate determination of the nuclear modification factor in p-Pb and Pb-Pb collisions performed at the same nucleon-nucleon centre-of-mass energy.

Measurement of jet radial profiles in Pb-Pb collisions at s_NN = 2.76 TeV - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
The jet radial structure and particle transverse momentum (p_T) composition within jets are presented in centrality-selected Pb-Pb collisions at s_NN = 2.76 TeV. Track-based jets, which are also called charged jets, were reconstructed with a resolution parameter of R=0.3 at midrapidity |η_ch jet|<0.6 for transverse momenta p_T, ch jet=30-120 GeV/c. Jet-hadron correlations in relative azimuth and pseudorapidity space (Δφ, Δη) are measured to study the distribution of the associated particles around the jet axis for different p_T, assoc-ranges between 1 and 20 GeV/c. The data in Pb-Pb collisions are compared to reference distributions for pp collisions, obtained using embedded PYTHIA simulations. The number of high-p_T associate particles (4<p_T, assoc<20 GeV/c) in Pb-Pb collisions is found to be suppressed compared to the reference by 30 to 10%, depending on centrality. The radial particle distribution relative to the jet axis shows a moderate modification in Pb-Pb collisions with respect to PYTHIA. High-p_T associate particles are slightly more collimated in Pb-Pb collisions compared to the reference, while low-p_T associate particle tend to be broadened. The results, which are compatible with both previous jet-hadron-related measurements from the CMS Collaboration and jet shape measurements from the ALICE Collaboration at higher p_T, support the currently established picture of in-medium parton energy loss.

Measurement of prompt D0,D+,D∗+, andD+s production in p-Pb collisions at √sNN=5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
The measurement of the production of prompt D0, D+, D∗+, and D+s mesons in proton−lead (p−Pb) collisions at the centre-of-mass energy per nucleon pair of sNN‾‾‾‾√ = 5.02 TeV, with an integrated luminosity of 292±11 μb−1, are reported. Differential production cross sections are measured at mid-rapidity (−0.96<ycms<0.04) as a function of transverse momentum (pT) in the intervals 0<pT<36 GeV/c for D0, 1<pT<36 GeV/c for D+ and D∗+, and 2<pT<24 GeV/c for D+s mesons. For each species, the nuclear modification factor RpPb is calculated as a function of pT using a proton-proton (pp) reference measured at the same collision energy. The results are compatible with unity in the whole pT range. The average of the non-strange D mesons RpPb is compared with theoretical model predictions that include initial-state effects and parton transport model predictions. The pT dependence of the D0, D+, and D∗+ nuclear modification factors is also reported in the interval 1<pT<36 GeV/c as a function of the collision centrality, and the central-to-peripheral ratios are computed from the D-meson yields measured in different centrality classes. The results are further compared with charged-particle measurements and a similar trend is observed in all the centrality classes. The ratios of the pT-differential cross sections of D0, D+, D∗+, and D+s mesons are also reported. The D+s and D+ yields are compared as a function of the charged-particle multiplicity for several pT intervals. No modification in the relative abundances of the four species is observed with respect to pp collisions within the statistical and systematic uncertainties.

Measurement of the inclusive isolated photon production cross section in pp collisions at s = 7 TeV - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
The production cross section of inclusive isolated photons has been measured by the ALICE experiment at the CERN LHC in pp collisions at a centre-of-momentum energy of s= 7 TeV. The measurement is performed with the electromagnetic calorimeter EMCal and the central tracking detectors, covering a range of |η|<0.27 in pseudorapidity and a transverse momentum range of 10 < p_T^γ < 60 GeV/c. The result extends the p_T coverage of previously published results of the ATLAS and CMS experiments at the same collision energy to smaller p_T. The measurement is compared to next-to-leading order perturbative QCD calculations and to the results from the ATLAS and CMS experiments. All measurements and theory predictions are in agreement with each other.

Measurement of the production of charm jets tagged with D^0 mesons in pp collisions at s= 7 TeV - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
The production of charm jets in proton-proton collisions at a center-of-mass energy of s=7 TeV was measured with the ALICE detector at the CERN Large Hadron Collider. The measurement is based on a data sample corresponding to a total integrated luminosity of 6.23 nb^-1, collected using a minimum-bias trigger. Charm jets are identified by the presence of a D^0 meson among their constituents. The D^0 mesons are reconstructed from their hadronic decay D^0→K^-π^+. The D^0-meson tagged jets are reconstructed using tracks of charged particles (track-based jets) with the anti-k_T algorithm in the jet transverse momentum range 5<p_T,jet^ch<30 GeV/c and pseudorapidity |η_jet|<0.5. The fraction of charged jets containing a D^0-meson increases with p_T,jet^ch from 0.042 ± 0.004 (stat) ± 0.006 (syst) to 0.080 ± 0.009 (stat) ± 0.008 (syst). The distribution of D^0-meson tagged jets as a function of the jet momentum fraction carried by the D^0 meson in the direction of the jet axis (z_||^ch) is reported for two ranges of jet transverse momenta, 5<p_T,jet^ch<15 GeV/c and 15<p_T,jet^ch<30 GeV/c in the intervals 0.2<z_||^ch<1.0 and 0.4<z_||^ch<1.0, respectively. The data are compared with results from Monte Carlo event generators (PYTHIA 6, PYTHIA 8 and Herwig 7) and with a Next-to-Leading-Order perturbative Quantum Chromodynamics calculation, obtained with the POWHEG method and interfaced with PYTHIA 6 for the generation of the parton shower, fragmentation, hadronisation and underlying event.

Multiplicity dependence of (anti-)deuteron production in pp collisions at s=7TeV - S. Acharya; F.T. Acosta; R. Keidel; D. Adamová; S.P. Adhya; A. Adler; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; Z. Ahammed; S. Ahmad; et al. (Physics Letters B, 2019)
In this letter, the production of deuterons and anti-deuterons in pp collisions at s=7 TeV is studied as a function of the charged-particle multiplicity density at mid-rapidity with the ALICE detector at the LHC. Production yields are measured at mid-rapidity in five multiplicity classes and as a function of the deuteron transverse momentum ( pT ). The measurements are discussed in the context of hadron-coalescence models. The coalescence parameter B2 , extracted from the measured spectra of (anti-)deuterons and primary (anti-)protons, exhibits no significant pT -dependence for pT<3 GeV/c , in agreement with the expectations of a simple coalescence picture. At fixed transverse momentum per nucleon, the B2 parameter is found to decrease smoothly from low multiplicity pp to Pb-Pb collisions, in qualitative agreement with more elaborate coalescence models. The measured mean transverse momentum of (anti-)deuterons in pp is not reproduced by the Blast-Wave model calculations that simultaneously describe pion, kaon and proton spectra, in contrast to central Pb-Pb collisions. The ratio between the pT -integrated yield of deuterons to protons, d/p, is found to increase with the charged-particle multiplicity, as observed in inelastic pp collisions at different centre-of-mass energies. The d/p ratios are reported in a wide range, from the lowest to the highest multiplicity values measured in pp collisions at the LHC.

Multiplicity dependence of K*(892)0 and ϕ(1020) production in pp collisions at s√ = 13 TeV - S. Acharya; D. Adamova; R. Keidel; A. Adler (2019)
Measurements of identified hadrons as a function of the charged-particle multiplicity in pp collisions enable a search for the onset of collective effects in small collision systems. With such measurements, it is possible to study the mechanisms that determine the shapes of hadron transverse momentum (pT) spectra, to search for possible modifications of the yields of short-lived hadronic resonances due to scattering effects in the hadron-gas phase, and to investigate different explanations for the multiplicity evolution of strangeness production provided by phenomenological models. In this paper, these topics are addressed through measurements of the K∗(892)0 and ϕ(1020) mesons at midrapidity in pp collisions at s√ = 13 TeV as a function of the charged-particle multiplicity. The results include the pT spectra, pT-integrated yields, mean transverse momenta, and the ratios of the yields of these resonances to those of longer-lived hadrons. Comparisons with results from other collision systems and energies, as well as predictions from phenomenological models, are also discussed.

Multiplicity dependence of light (anti-)nuclei production in p-Pb collisions at s_NN = 5.02 TeV - S. Acharya; D. Adamova; R. Keidel; S. P. Adhya (2019)
The measurement of the deuteron and anti-deuteron production in the rapidity range -1 < y < 0 as a function of transverse momentum and event multiplicity in p-Pb collisions at s_NN = 5.02 TeV is presented. (Anti-)deuterons are identified via their specific energy loss dE/dx and via their time-of-flight. Their production in p-Pb collisions is compared to pp and Pb-Pb collisions and is discussed within the context of thermal and coalescence models. The ratio of integrated yields of deuterons to protons (d/p) shows a significant increase as a function of the charged-particle multiplicity of the event starting from values similar to those observed in pp collisions at low multiplicities and approaching those observed in Pb-Pb collisions at high multiplicities. The mean transverse momenta are extracted from the deuteron spectra and the values are similar to those obtained for p and Λ particles. Thus, deuteron spectra do not follow mass ordering. This behaviour is in contrast to the trend observed for non-composite particles in p-Pb collisions. In addition, the production of the rare ^3He and ^3He nuclei has been studied. The spectrum corresponding to all non-single diffractive p-Pb collisions is obtained in the rapidity window -1 < y < 0 and the p_T-integrated yield dN/dy is extracted. It is found that the yields of protons, deuterons, and ^3He, normalised by the spin degeneracy factor, follow an exponential decrease with mass number.

One-dimensional charged kaon femtoscopy in p-Pb collisions at s_NN = 5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
The correlations of identical charged kaons were measured in p-Pb collisions at s_NN=5.02 TeV by the ALICE experiment at the LHC. The femtoscopic invariant radii and correlation strengths were extracted from one-dimensional kaon correlation functions and were compared with those obtained in pp and Pb-Pb collisions at s=7 TeV and s_NN=2.76 TeV, respectively. The presented results also complement the identical-pion femtoscopic data published by the ALICE collaboration. The extracted radii increase with increasing charged-particle multiplicity and decrease with increasing pair transverse momentum. At comparable multiplicities, the radii measured in p-Pb collisions are found to be close to those observed in pp collisions. The obtained femtoscopic parameters are reproduced by the EPOS hadronic interaction model and disfavor models with large initial size or strong collective expansion at low multiplicities.

Probing the effects of strong electromagnetic fields with charge-dependent directed flow in Pb-Pb collisions at the LHC - S. Acharya; D. Adamova; R. Keidel; A. Adler (2019)
The first measurement at the LHC of charge-dependent directed flow (v1) relative to the spectator plane is presented for Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV. Results are reported for charged hadrons and D0 mesons for the transverse momentum intervals pT>0.2 GeV/c and 3<pT< 6 GeV/c in the 5-40% and 10-40% centrality classes, respectively. The difference between the positively and negatively charged hadron v1 is found to have a positive slope as a function of pseudorapidity η, dΔv1/dη=[1.68 ± 0.49 (stat.) ± 0.41 (syst.)] ×10−4, with a 2.6σ significance. The same measurement for D0 and D¯0 mesons yields a positive value dΔv1/dη= [4.9 ± 1.7 (stat.) ± 0.6 (syst.)]×10−1, which is about three orders of magnitude larger than the one of the charged hadrons, and is larger than zero with significance of 2.7σ. These measurements can provide new insights into the effects of the strong electromagnetic field and the initial tilt of matter created in non-central heavy-ion collisions on the dynamics of light (u, d, and s) and heavy (c) quarks. The large difference between the observed Δv1 of charged hadrons and D0 mesons may reflect different sensitivity of the charm and light quarks to the early time dynamics of a heavy-ion collision. These observations challenge some of the recent theoretical calculations incorporating effects of the strong electromagnetic field, which predicted a negative and an order of magnitude smaller value of dΔv1/dη for both light-flavour and charmed hadrons.

Production of muons from heavy-flavour hadron decays in pp collisions at s=5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
Production cross sections of muons from semi-leptonic decays of charm and beauty hadrons were measured at forward rapidity (2.5<y<4) in proton–proton (pp) collisions at a centre-of-mass energy s=5.02 TeV with the ALICE detector at the CERN LHC. The results were obtained in an extended transverse momentum interval, 2 < p_T < 20 GeV/c, and with an improved precision compared to previous measurements performed in the same rapidity interval at centre-of-mass energies s= 2.76 and 7 TeV. The p_T- and y-differential production cross sections as well as the p_T-differential production cross section ratios between different centre-of-mass energies and different rapidity intervals are described, within experimental and theoretical uncertainties, by predictions based on perturbative QCD.

Scattering studies with low-energy kaon-proton femtoscopy in proton-proton collisions at the LHC - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
The study of the strength and behaviour of the antikaon-nucleon (KN) interaction constitutes one of the key focuses of the strangeness sector in low-energy Quantum Chromodynamics (QCD). In this letter a unique high-precision measurement of the strong interaction between kaons and protons, close and above the kinematic threshold, is presented. The femtoscopic measurements of the correlation function at low pair-frame relative momentum of (K^+ p K^- p) and (K^- p K^+ p) pairs measured in pp collisions at s = 5, 7 and 13 TeV are reported. A structure observed around a relative momentum of 58 MeV/c in the measured correlation function of (K^- p K^+ p) constitutes the first experimental evidence for the opening of the (K^0 n K^0 n) isospin breaking channel due to the mass difference between charged and neutral kaons. The measured correlation functions have been compared to several models. The high-precision data at low relative momenta presented in this work prove femtoscopy to be a powerful complementary tool to scattering experiments and provide new constraints above the KN threshold for low-energy QCD chiral models.

Study of the Λ-Λ interaction with femtoscopy correlations in pp and p-Pb collisions at the LHC - S. Acharya; D. Adamova; Ralf Keidel; S. P. Adhya (2019)
This work presents new constraints on the existence and the binding energy of a possible Λ-Λ bound state, the H-dibaryon, derived from Λ-Λ femtoscopic measurements by the ALICE collaboration. The results are obtained from a new measurement using the femtoscopy technique in pp collisions at s=13 TeV and p-Pb collisions at s_NN=5.02 TeV, combined with previously published results from p-Pb collisions at s=7 TeV. The Λ-Λ scattering parameter space, spanned by the inverse scattering length f_0^-1 and the effective range d_0, is constrained by comparing the measured Λ-Λ correlation function with calculations obtained within the Lednicky model. The data are compatible with hypernuclei results and lattice computations, both predicting a shallow attractive interaction, and permit to test different theoretical approaches describing the Λ-Λ interaction. The region in the (f_0^-1,d_0) plane which would accommodate a Λ-Λ bound state is substantially restricted compared to previous studies. The binding energy of the possible Λ-Λ bound state is estimated within an effective-range expansion approach and is found to be B_ΛΛ=3.2^+1.6_-2.4(stat)^+1.8_-1.0(syst) MeV.

Analysis of the apparent nuclear modification in peripheral Pb-Pb collisions at 5.02 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
Charged-particle spectra at midrapidity are measured in Pb-Pb collisions at the centre-of-mass energy per nucleon-nucleon pair sNN‾‾‾‾√ = 5.02 TeV and presented in centrality classes ranging from most central (0-5%) to most peripheral (95-100%) collisions. Possible medium effects are quantified using the nuclear modification factor (RAA) by comparing the measured spectra with those from proton-proton collisions, scaled by the number of independent nucleon-nucleon collisions obtained from a Glauber model. At large transverse momenta (8<pT<20 GeV/c), the average RAA is found to increase from about 0.15 in 0-5% central to a maximum value of about 0.8 in 75-85% peripheral collisions, beyond which it falls off strongly to below 0.2 for the most peripheral collisions. Furthermore, RAA initially exhibits a positive slope as a function of pT in the 8-20 GeV/c interval, while for collisions beyond the 80% class the slope is negative. To reduce uncertainties related to event selection and normalization, we also provide the ratio of RAA in adjacent centrality intervals. Our results in peripheral collisions are consistent with a PYTHIA-based model without nuclear modification, demonstrating that biases caused by the event selection and collision geometry can lead to the apparent suppression in peripheral collisions. This explains the unintuitive observation that RAA is below unity in peripheral Pb-Pb, but equal to unity in minimum-bias p-Pb collisions despite similar charged-particle multiplicities.

Anisotropic flow in Xe-Xe collisions at sNN=5.44 TeV - S. Acharya; F.T. Acosta; R. Keidel; D. Adamová; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S.U. Ahn; S. Aiola; et al. (Physics Letters B, 2018)
The first measurements of anisotropic flow coefficients vn for mid-rapidity charged particles in Xe-Xe collisions at sNN‾‾‾‾√=5.44 TeV are presented. Comparing these measurements to those from Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV, v2 is found to be suppressed for mid-central collisions at the same centrality, and enhanced for central collisions. The values of v3 are generally larger in Xe-Xe than in Pb-Pb at a given centrality. These observations are consistent with expectations from hydrodynamic predictions. When both v2 and v3 are divided by their corresponding eccentricities for a variety of initial state models, they generally scale with transverse density when comparing Xe-Xe and Pb-Pb, with some deviations observed in central Xe-Xe and Pb-Pb collisions. These results assist in placing strong constraints on both the initial state geometry and medium response for relativistic heavy-ion collisions.

Anisotropic flow of identified particles in Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
The elliptic (v2), triangular (v3), and quadrangular (v4) flow coefficients of π±, K±, p+p⎯⎯⎯, Λ+Λ⎯⎯⎯⎯, K0S, and the ϕ-meson are measured in Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV. Results obtained with the scalar product method are reported for the rapidity range |y|< 0.5 as a function of transverse momentum, pT, at different collision centrality intervals between 0-70%, including ultra-central (0-1%) collisions for π±, K±, and p+p⎯⎯⎯. For pT<3 GeV/c, the flow coefficients exhibit a particle mass dependence. At intermediate transverse momenta (3<pT<8-10 GeV/c), particles show an approximate grouping according to their type (i.e., mesons and baryons). The ϕ-meson v2, which tests both particle mass dependence and type scaling, follows p+p⎯⎯⎯ v2 at low pT and π± v2 at intermediate pT. The evolution of the shape of vn(pT) as a function of centrality and harmonic number n is studied for the various particle species. Flow coefficients of π±, K±, and p+p⎯⎯⎯ for pT<3 GeV/c are compared to iEBE-VISHNU and MUSIC hydrodynamical calculations coupled to a hadronic cascade model (UrQMD). The iEBE-VISHNU calculations describe the results fairly well for pT<2.5 GeV/c, while MUSIC calculations reproduce the measurements for pT<1 GeV/c. A comparison to vn coefficients measured in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV is also provided.

Azimuthal anisotropy of heavy-flavour decay electrons in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
Angular correlations between heavy-flavour decay electrons and charged particles at mid-rapidity (|η|<0.8) are measured in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV. The analysis is carried out for the 0-20% (high) and 60-100% (low) multiplicity ranges. The jet contribution in the correlation distribution from high-multiplicity events is removed by subtracting the distribution from low-multiplicity events. An azimuthal modulation remains after removing the jet contribution, similar to previous observations in two-particle angular correlation measurements for light-flavour hadrons. A Fourier decomposition of the modulation results in a positive second-order coefficient (v2) for heavy-flavour decay electrons in the transverse momentum interval 1.5<pT<4 GeV/c in high-multiplicity events, with a significance larger than 5σ. The results are compared with those of charged particles at mid-rapidity and of inclusive muons at forward rapidity. The v2 measurement of open heavy-flavour particles at mid-rapidity in small collision systems could provide crucial information to help interpret the anisotropies observed in such systems.

Azimuthally-differential pion femtoscopy relative to the third harmonic event plane in Pb-Pb collisions at sNN=2.76TeV - S. Acharya; F.T. Acosta; R. Keidel; D. Adamová; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S.U. Ahn; S. Aiola; et al. (Physics Letters B, 2018)
Azimuthally-differential femtoscopic measurements, being sensitive to spatio-temporal characteristics of the source as well as to the collective velocity fields at freeze out, provide very important information on the nature and dynamics of the system evolution. While the HBT radii oscillations relative to the second harmonic event plane measured recently reflect mostly the spatial geometry of the source, model studies have shown that the HBT radii oscillations relative to the third harmonic event plane are predominantly defined by the velocity fields. In this Letter, we present the first results on azimuthally-differential pion femtoscopy relative to the third harmonic event plane as a function of the pion pair transverse momentum for different collision centralities in Pb-Pb collisions at . We find that the and radii, which characterize the pion source size in the directions perpendicular and parallel to the pion transverse momentum, oscillate in phase relative to the third harmonic event plane, similar to the results from 3+1D hydrodynamical calculations. The observed radii oscillations unambiguously signal a collective expansion and anisotropy in the velocity fields. A comparison of the measured radii oscillations with the Blast-Wave model calculations indicate that the initial state triangularity is washed-out at freeze out.

Centrality and pseudorapidity dependence of the charged-particle multiplicity density in Xe-Xe collisions at sNN‾‾‾‾√ = 5.44 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
In this Letter, the ALICE Collaboration presents the first measurements of the charged-particle multiplicity density, dNch/dη, and total charged-particle multiplicity, Ntotch, in Xe-Xe collisions at a centre-of-mass energy per nucleon–nucleon pair of sNN‾‾‾‾√ = 5.44 TeV. The measurements are performed as a function of collision centrality over a wide pseudorapidity range of −3.5<η<5. The values of dNch/dη at mid-rapidity and Ntotch for central collisions, normalised to the number of nucleons participating in the collision (Npart) as a function of sNN‾‾‾‾√, follow the trends established in previous heavy-ion measurements. The same quantities are also found to increase as a function of Npart, and up to the 10% most central collisions the trends are the same as the ones observed in Pb-Pb at a similar energy. For more central collisions, the Xe-Xe scaled multiplicities exceed those in Pb-Pb for a similar Npart. The results are compared to phenomenological models and theoretical calculations based on different mechanisms for particle production in nuclear collisions. All considered models describe the data reasonably well within 20%.

Charged jet cross section and fragmentation in proton-proton collisions at s√ = 7 TeV - Fernando Torales Acosta; Shreyasi Acharya; Ralf Keidel; Dagmar Adamova (2018)
We report the differential charged jet cross section and jet fragmentation distributions measured with the ALICE detector in proton-proton collisions at a centre-of-mass energy s√= 7 TeV. Jets with pseudo-rapidity ∣∣η∣∣<0.5 are reconstructed from charged particles using the anti-kT jet finding algorithm with a resolution parameter R = 0.4. The jet cross section is measured in the transverse momentum interval 5 ≤pchjetT< 100 GeV/c. Jet fragmentation is studied measuring the scaled transverse momentum spectra of the charged constituents of jets in four intervals of jet transverse momentum between 5 GeV/c and 30 GeV/c. The measurements are compared to calculations from the PYTHIA model as well as next-to-leading order perturbative QCD calculations with POWHEG + PYTHIA8. The charged jet cross section is described by POWHEG for the entire measured range of pchjetT. For pchjetT > 40 GeV/c, the PYTHIA calculations also agree with the measured charged jet cross section. PYTHIA6 simulations describe the fragmentation distributions to 15%. Larger discrepancies are observed for PYTHIA8.

Charged-particle pseudorapidity density at mid-rapidity in p-Pb collisions at sNN‾‾‾‾√ = 8.16 TeV - Shreyasi Acharya; Fernando Torales Acosta; Ralf Keidel; Dagmar Adamova (2018)
The pseudorapidity density of charged particles, dNch/dη, in p-Pb collisions has been measured at a centre-of-mass energy per nucleon-nucleon pair of sNN‾‾‾‾√ = 8.16 TeV at mid-pseudorapidity for non-single-diffractive events. The results cover 3.6 units of pseudorapidity, |η|<1.8. The dNch/dη value is 19.1±0.7 at |η|<0.5. This quantity divided by ⟨Npart⟩/2, is 4.73±0.20, which is 9.5% higher than the corresponding value for p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV. Measurements are compared with models based on different mechanisms for particle production. All models agree within uncertainties with data in the Pb-going side, while HIJING overestimates, showing a symmetric behaviour, and EPOS underestimates the p-going side of the dNch/dη distribution. Saturation-based models reproduce the distributions well for η>−1.3. The dNch/dη is also measured for different centrality estimators, based both on the charged-particle multiplicity and on the energy deposited in the Zero-Degree Calorimeters. A study of the implications of the large multiplicity fluctuations due to the small number of participants for systems like p-Pb in the centrality calculation for multiplicity-based estimators is discussed, demonstrating the advantages of determining the centrality with energy deposited near beam rapidity.

Dielectron and heavy-quark production in inelastic and high-multiplicity proton-proton collisions at sNN‾‾‾‾√ = 13 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
The measurement of dielectron production is presented as a function of invariant mass and transverse momentum (pT) at midrapidity (|ye|<0.8) in proton-proton (pp) collisions at a centre-of-mass energy of s√=13 TeV. The contributions from light-hadron decays are calculated from their measured cross sections in pp collisions at s√=7 TeV or 13 TeV. The remaining continuum stems from correlated semileptonic decays of heavy-flavour hadrons. Fitting the data with templates from two different MC event generators, PYTHIA and POWHEG, the charm and beauty cross sections at midrapidity are extracted for the first time at this collision energy: dσcc¯/dy|y=0=974±138(stat.)±140(syst.) μb and dσbb¯/dy|y=0=79±14(stat.)±11(syst.) μb using PYTHIA simulations and dσcc¯/dy|y=0=1417±184(stat.)±204(syst.) μb and dσbb¯/dy|y=0=48±14(stat.)±7(syst.) μb for POWHEG. These values, whose uncertainties are fully correlated between the two generators, are consistent with extrapolations from lower energies. The different results obtained with POWHEG and PYTHIA imply different kinematic correlations of the heavy-quark pairs in these two generators. Furthermore, comparisons of dielectron spectra in inelastic events and in events collected with a trigger on high charged-particle multiplicities are presented in various pT intervals. The differences are consistent with the already measured scaling of light-hadron and open-charm production at high charged-particle multiplicity as a function of pT. Upper limits for the contribution of virtual direct photons are extracted at 90% confidence level and found to be in agreement with pQCD calculations.

Dielectron production in proton-proton collisions at s√ = 7 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
The first measurement of e+e− pair production at mid-rapidity (|ηe| < 0.8) in pp collisions at s√=7 TeV with ALICE at the LHC is presented. The dielectron production is studied as a function of the invariant mass (mee < 3.3 GeV/c2), the pair transverse momentum (pT,ee < 8 GeV/c), and the pair transverse impact parameter (DCAee), i.e., the average distance of closest approach of the reconstructed electron and positron tracks to the collision vertex, normalised to its resolution. The results are compared with the expectations from a cocktail of known hadronic sources and are well described when PYTHIA is used to generate the heavy-flavour contributions. In the low-mass region (0.14 < mee < 1.1 GeV/c2), prompt and non-prompt e+e− sources can be separated via the DCAee. In the intermediate-mass region (1.1 < mee < 2.7 GeV/c2), a double-differential fit to the data in mee and pT,ee and a fit of the DCAee distribution allow the total cc⎯⎯⎯ and bb⎯⎯⎯ cross sections to be extracted. Two different event generators, PYTHIA and POWHEG, can reproduce the shape of the two-dimensional mee and pT,ee spectra, as well as the shape of the DCAee distribution, reasonably well. However, differences in the cc⎯⎯⎯ and bb⎯⎯⎯ cross sections are observed when using the generators to extrapolate to full phase space. Finally, the ratio of inclusive to decay photons is studied via the measurement of virtual direct photons in the transverse-momentum range 1 < pT < 8 GeV/c. This is found to be unity within the statistical and systematic uncertainties and consistent with expectations from next-to-leading order perturbative quantum chromodynamic calculations.

Direct photon elliptic flow in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
The elliptic flow of inclusive and direct photons was measured at mid-rapidity in two centrality classes 0-20% and 20-40% in Pb-Pb collisions at sNN‾‾‾‾√ =2.76 TeV by ALICE. Photons were detected with the highly segmented electromagnetic calorimeter PHOS and via conversions in the detector material with the e+e− pairs reconstructed in the central tracking system. The results of the two methods were combined and the direct photon elliptic flow was extracted in the transverse momentum range 0.9<pT<6.2 GeV/c. We test the hypothesis vγ,dir2≡0 for 0.9<pT<2.1 GeV/c and obtain a significance of 1.4σ for the 0-20% class and 1.0σ for the 20-40% class. A comparison to RHIC data shows a similar magnitude of the measured elliptic flow, while hydrodynamic and transport model calculations predict a smaller flow than observed.

Direct photon production at low transverse momentum in proton-proton collisions at s√=2.76 and 8 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
Measurements of inclusive and direct photon production at mid-rapidity in pp collisions at s√=2.76 and 8 TeV are presented by the ALICE experiment at the LHC. The results are reported in transverse momentum ranges of 0.4<pT<10 GeV/c and 0.3<pT<16 GeV/c, respectively. Photons are detected with the electromagnetic calorimeter(EMCal) and via reconstruction of e+e− pairs from conversions in the ALICE detector material using the central tracking system. For the final measurement of the inclusive photon spectra the results are combined in the overlapping pT interval of both methods. Direct photon spectra, or their upper limits at 90% C.L. are extracted using the direct photon excess ratio Rγ, which quantifies the ratio of inclusive photons over decay photons generated with a decay-photon simulation. An additional hybrid method, combining photons reconstructed from conversions with those identified in the EMCal, is used for the combination of the direct photon excess ratio Rγ, as well as the extraction of direct photon spectra or their upper limits. While no significant signal of direct photons is seen over the full pT range, Rγ for pT>7 GeV/c is at least one σ above unity and consistent with expectations from next-to-leading order pQCD calculations.

Energy dependence and fluctuations of anisotropic flow in Pb-Pb collisions at sNN‾‾‾‾√=5.02 and 2.76 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
Measurements of anisotropic flow coefficients with two- and multi-particle cumulants for inclusive charged particles in Pb-Pb collisions at sNN‾‾‾‾√=5.02 and 2.76 TeV are reported in the pseudorapidity range |η|<0.8 and transverse momentum 0.2<pT<50 GeV/c. The full data sample collected by the ALICE detector in 2015 (2010), corresponding to an integrated luminosity of 12.7 (2.0) μb−1 in the centrality range 0-80%, is analysed. Flow coefficients up to the sixth flow harmonic (v6) are reported and a detailed comparison among results at the two energies is carried out. The pT dependence of anisotropic flow coefficients and its evolution with respect to centrality and harmonic number n are investigated. An approximate power-law scaling of the form vn(pT)∼pn/3T is observed for all flow harmonics at low pT (0.2<pT<3 GeV/c). At the same time, the ratios vn/vn/mm are observed to be essentially independent of pT for most centralities up to about pT=10 GeV/c. Analysing the differences among higher-order cumulants of elliptic flow (v2), which have different sensitivities to flow fluctuations, a measurement of the standardised skewness of the event-by-event v2 distribution P(v2) is reported and constraints on its higher moments are provided. The Elliptic Power distribution is used to parametrise P(v2), extracting its parameters from fits to cumulants. The measurements are compared to different model predictions in order to discriminate among initial-state models and to constrain the temperature dependence of the shear viscosity to entropy-density ratio.

Energy dependence of exclusive J/ψ photoproduction off protons in ultra-peripheral p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - Shreyasi Acharya; Fernando Torales Acosta; Ralf Keidel; Dagmar Adamova (2018)
The ALICE Collaboration has measured the energy dependence of exclusive photoproduction of J/ψ vector mesons off proton targets in ultra-peripheral p-Pb collisions at a centre-of-mass energy per nucleon pair sNN‾‾‾‾√=5.02 TeV. The e+e− and μ+μ− decay channels are used to measure the cross section as a function of the rapidity of the J/ψ in the range −2.5<y<2.7, corresponding to an energy in the γp centre-of-mass in the interval 40<Wγp<550 GeV. The measurements, which are consistent with a power law dependence of the exclusive J/ψ photoproduction cross section, are compared to previous results from HERA and the LHC and to several theoretical models. They are found to be compatible with previous measurements.

Event-shape engineering for the D-meson elliptic flow in mid-central Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV - Shreyasi Acharya; Fernando Torales Acosta; Ralf Keidel; Dagmar Adamova (2018)
The production yield of prompt D mesons and their elliptic flow coefficient v2 were measured with the Event-Shape Engineering (ESE) technique applied to mid-central (10-30% and 30-50% centrality classes) Pb-Pb collisions at the centre-of-mass energy per nucleon pair sNN‾‾‾‾√=5.02 TeV, with the ALICE detector at the LHC. The ESE technique allows the classification of events, belonging to the same centrality, according to the azimuthal anisotropy of soft particle production in the collision. The reported measurements give the opportunity to investigate the dynamics of charm quarks in the Quark-Gluon Plasma and provide information on their participation in the collective expansion of the medium. D mesons were reconstructed via their hadronic decays at mid-rapidity, |η|<0.8, in the transverse momentum interval 1<pT<24 GeV/c. The v2 coefficient is found to be sensitive to the event-shape selection confirming a correlation between the D-meson azimuthal anisotropy and the collective expansion of the bulk matter, while the per-event D-meson yields do not show any significant modification within the current uncertainties.

Inclusive J/ψ production at forward and backward rapidity in p-Pb collisions at sNN‾‾‾‾√ = 8.16 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
Inclusive J/ψ production is studied in p-Pb interactions at a centre-of-mass energy per nucleon-nucleon collision sNN‾‾‾‾√=8.16 TeV, using the ALICE detector at the CERN LHC. The J/ψ meson is reconstructed, via its decay to a muon pair, in the centre-of-mass rapidity intervals 2.03<ycms<3.53 and −4.46<ycms<−2.96, where positive and negative ycms refer to the p-going and Pb-going direction, respectively. The transverse momentum coverage is pT<20 GeV/c. In this paper, ycms- and pT-differential cross sections for inclusive J/ψ production are presented, and the corresponding nuclear modification factors RpPb are shown. Forward results show a suppression of the J/ψ yield with respect to pp collisions, concentrated in the region pT≲5 GeV/c. At backward rapidity no significant suppression is observed. The results are compared to previous measurements by ALICE in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV and to theoretical calculations. Finally, the ratios RFB between forward- and backward-ycms RpPb values are shown and discussed.

Inclusive J/ψ production in Xe-Xe collisions at sNN‾‾‾‾√ = 5.44 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
Inclusive J/ψ production is studied in Xe-Xe interactions at a centre-of-mass energy per nucleon pair of sNN‾‾‾‾√=5.44 TeV, using the ALICE detector at the CERN LHC. The J/ψ meson is reconstructed via its decay into a muon pair, in the centre-of-mass rapidity interval 2.5<y<4 and down to zero transverse momentum. In this Letter, the nuclear modification factors RAA for inclusive J/ψ, measured in the centrality range 0-90% as well as in the centrality intervals 0-20% and 20-90% are presented. The RAA values are compared to previously published results for Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV and to the calculation of a transport model. A good agreement is found between Xe-Xe and Pb-Pb results as well as between data and the model.

Jet fragmentation transverse momentum measurements from di-hadron correlations in s√ = 7 TeV pp and sNN‾‾‾‾√ = 5.02 TeV p-Pb collisions - Fernando Torales Acosta; Shreyasi Acharya; Ralf Keidel; Dagmar Adamova (2018)
The transverse structure of jets was studied via jet fragmentation transverse momentum (jT) distributions, obtained using two-particle correlations in proton-proton and proton-lead collisions, measured with the ALICE experiment at the LHC. The highest transverse momentum particle in each event is used as the trigger particle and the region 3<pTt<15 GeV/c is explored in this study. The measured distributions show a clear narrow Gaussian component and a wide non-Gaussian one. Based on Pythia simulations, the narrow component can be related to non-perturbative hadronization and the wide component to quantum chromodynamical splitting. The width of the narrow component shows a weak dependence on the transverse momentum of the trigger particle, in agreement with the expectation of universality of the hadronization process. On the other hand, the width of the wide component shows a rising trend suggesting increased branching for higher transverse momentum. The results obtained in pp collisions at s√ = 7 TeV and in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV are compatible within uncertainties and hence no significant cold nuclear matter effects are observed. The results are compared to previous measurements from CCOR and PHENIX as well as to Pythia 8 and Herwig 7 simulations.

Measurement of D0, D+, D∗+ and D+s production in Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
We report measurements of the production of prompt D0, D+, D∗+ and D+s mesons in Pb-Pb collisions at the centre-of-mass energy per nucleon-nucleon pair sNN‾‾‾‾√=5.02 TeV, in the centrality classes 0-10%, 30-50% and 60-80%. The D-meson production yields are measured at mid-rapidity (|y|<0.5) as a function of transverse momentum (pT). The pT intervals covered in central collisions are: 1<pT<50 Gev/c for D0, 2<pT<50 GeV/c for D+, 3<pT<50 GeV/c for D∗+, and 4<pT<16 GeV/c for D+s mesons. The nuclear modification factors (RAA) for non-strange D mesons (D0, D+, D∗+) show minimum values of about 0.2 for pT = 6-10 GeV/c in the most central collisions and are compatible within uncertainties with those measured at sNN‾‾‾‾√=2.76 TeV. For D+s mesons, the values of RAA are larger than those of non-strange D mesons, but compatible within uncertainties. In central collisions the average RAA of non-strange D mesons is compatible with that of charged particles for pT>8 GeV/c, while it is larger at lower pT. The nuclear modification factors for strange and non-strange D mesons are also compared to theoretical models with different implementations of in-medium energy loss.

Measurement of dielectron production in central Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
The first measurement of dielectron (e+e−) production in central (0−10%) Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV at the LHC is presented. The dielectron invariant-mass spectrum is compared to the expected contributions from hadron decays in the invariant-mass range 0<mee<3.5 GeV/c2. The ratio of data and the cocktail of hadronic contributions without vacuum ρ0 is measured in the invariant-mass range 0.15<mee<0.7 GeV/c2, where an excess of dielectrons is observed in other experiments, and its value is 1.40±0.28 (stat.)±0.08 (syst.)±0.27 (cocktail). The dielectron spectrum measured in the invariant mass range 0<mee<1 GeV/c2 is consistent with the predictions from two theoretical model calculations that include thermal dielectron production from both partonic and hadronic phases with in-medium broadened ρ0 meson. The fraction of direct virtual photons over inclusive virtual photons is extracted for dielectron pairs with invariant mass 0.1<mee<0.3 GeV/c2, and in the transverse-momentum intervals 1<pT,ee<2 GeV/c and 2<pT,ee<4 GeV/c. The measured fraction of virtual direct photons is consistent with the measurement of real direct photons by ALICE and with the expectations from previous dielectron measurements at RHIC within the experimental uncertainties.

Measurement of the inclusive J/ψ polarization at forward rapidity in pp collisions at s√=8 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
We report on the measurement of the inclusive J/ψ polarization parameters in pp collisions at a center of mass energy s√=8 TeV with the ALICE detector at the LHC. The analysis is based on a data sample corresponding to an integrated luminosity of 1.23 pb−1. J/ψ resonances are reconstructed in their di-muon decay channel in the rapidity interval 2.5<y<4.0 and over the transverse-momentum interval 2<pT<15 GeV/c. The three polarization parameters (λθ, λφ, λθφ) are measured as a function of pT both in the helicity and Collins-Soper reference frames. The measured J/ψ polarization parameters are found to be compatible with zero within uncertainties, contrary to expectations from all available predictions. The results are compared with the measurement in pp collisions at s√=7 TeV.

Measurements of low-pT electrons from semileptonic heavy-flavour hadron decays at mid-rapidity in pp and Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
Transverse-momentum (pT) differential yields of electrons from semileptonic heavy-flavour hadron decays have been measured in the most central (0-10%) and in semi-central (20-40%) Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV. The corresponding production cross section in pp collisions has been measured at the same energy with substantially reduced systematic uncertainties with respect to previously published results. The modification of the yield in Pb-Pb collisions with respect to the expectation from an incoherent superposition of nucleon-nucleon collisions is quantified at mid-rapidity (|y| < 0.8) in the pT interval 0.5-3 GeV/c via the nuclear modification factor, RAA. This paper extends the pT reach of the RAA measurement towards significantly lower values with respect to a previous publication. In Pb-Pb collisions the pT-differential measurements of yields at low pT are essential to investigate the scaling of heavy-flavour production with the number of binary nucleon-nucleon collisions. Heavy-quark hadronization, a collective expansion and even initial-state effects, such as the nuclear modification of the Parton Distribution Functions, are also expected to have a significant effect on the measured distribution.

Measuring KS0K± interactions using pp collisions at s=7 TeV - S. Acharya; F.T.-. Acosta; R. Keidel; D. Adamová; A. Adler; J. Adolfsson; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S.U. Ahn; et al. (Physics Letters B, 2018)
We present the first measurements of femtoscopic correlations between the K0S and K± particles in pp collisions at s√=7 TeV measured by the ALICE experiment. The observed femtoscopic correlations are consistent with final-state interactions proceeding solely via the a0(980) resonance. The extracted kaon source radius and correlation strength parameters for K0SK− are found to be equal within the experimental uncertainties to those for K0SK+. Results of the present study are compared with those from identical-kaon femtoscopic studies also performed with pp collisions at s√=7 TeV by ALICE and with a K0SK± measurement in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV. Combined with the Pb-Pb results, our pp analysis is found to be compatible with the interpretation of the a0(980) having a tetraquark structure instead of that of a diquark.

Medium modification of the shape of small-radius jets in central Pb-Pb collisions at sNN‾‾‾‾√=2.76TeV - S. Acharya; F. T.- Acosta; R. Keidel; D. Adamová; A. Adler; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. U. Ahn; et al. (Journal of High Energy Physics, 2018)
We present the measurement of a new set of jet shape observables for track-based jets in central Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV. The set of jet shapes includes the first radial moment or angularity, g; the momentum dispersion, pTD; and the difference between the leading and sub-leading constituent track transverse momentum, LeSub. These observables provide complementary information on the jet fragmentation and can constrain different aspects of the theoretical description of jet-medium interactions. The jet shapes were measured for a small resolution parameter R=0.2 and were fully corrected to particle level. The observed jet shape modifications indicate that in-medium fragmentation is harder and more collimated than vacuum fragmentation as obtained by PYTHIA calculations, which were validated with the measurements of the jet shapes in proton-proton collisions at s√=7 TeV. The comparison of the measured distributions to templates for quark and gluon-initiated jets indicates that in-medium fragmentation resembles that of quark jets in vacuum. We further argue that the observed modifications are not consistent with a totally coherent energy loss picture where the jet loses energy as a single colour charge, suggesting that the medium resolves the jet structure at the angular scales probed by our measurements (R=0.2). Furthermore, we observe that small-R jets can help to isolate purely energy loss effects from other effects that contribute to the modifications of the jet shower in medium such as the correlated background or medium response.

Multiplicity dependence of light-flavor hadron production in pp collisions at s√ = 7 TeV - Shreyasi Acharya; Fernando Torales Acosta; Ralf Keidel; Dagmar Adamova (2018)
Comprehensive results on the production of unidentified charged particles, π±, K±, K0S, K*(892)0, p, p⎯⎯⎯, φ(1020), Λ, Λ⎯⎯⎯⎯, Ξ−, Ξ⎯⎯⎯⎯+, Ω− and Ω⎯⎯⎯⎯⎯+ hadrons in proton-proton (pp) collisions at s√ = 7 TeV at midrapidity (|y|<0.5) as a function of charged-particle multiplicity density are presented. In order to avoid auto-correlation biases, the actual transverse momentum (pT) spectra of the particles under study and the event activity are measured in different rapidity windows. In the highest multiplicity class, the charged-particle density reaches about 3.5 times the value measured in inelastic collisions. While the yield of protons normalized to pions remains approximately constant as a function of multiplicity, the corresponding ratios of strange hadrons to pions show a significant enhancement that increases with increasing strangeness content. Furthermore, all identified particle to pion ratios are shown to depend solely on charged-particle multiplicity density, regardless of system type and collision energy. The evolution of the spectral shapes with multiplicity and hadron mass shows patterns that are similar to those observed in p-Pb and Pb-Pb collisions at LHC energies. The obtained pT distributions and yields are compared to expectations from QCD-based pp event generators as well as to predictions from thermal and hydrodynamic models. These comparisons indicate that traces of a collective, equilibrated system are already present in high-multiplicity pp collisions.

Neutral pion and η meson production at mid-rapidity in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
Neutral pion and η meson production in the transverse momentum range 1 < pT < 20 GeV/c have been measured at mid-rapidity by the ALICE experiment at the Large Hadron Collider (LHC) in central and semi-central Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV. These results were obtained using the photon conversion method as well as the PHOS and EMCal detectors. The results extend the upper pT reach of the previous ALICE π0 measurements from 12 GeV/c to 20 GeV/c and present the first measurement of η meson production in heavy-ion collisions at the LHC. The η/π0 ratio is similar for the two centralities and reaches at high pT a plateau value of 0.457 ± 0.013stat ± 0.018syst. A suppression of similar magnitude for π0 and η meson production is observed in Pb-Pb collisions with respect to their production in pp collisions scaled by the number of binary nucleon-nucleon collisions. We discuss the results in terms of NLO pQCD predictions and hydrodynamic models. The measurements show a stronger suppression with respect to what was observed at lower center-of-mass energies in the pT range 6 < pT < 10 GeV/c. At pT < 3 GeV/c, hadronization models describe the π0 results while for the η some tension is observed.

Neutral pion and η meson production in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
Neutral pion and η meson invariant differential yields were measured in non-single diffractive p-Pb collisions at sNN‾‾‾‾√=5.02 TeV with the ALICE experiment at the CERN LHC. The analysis combines results from three complementary photon measurements, utilizing the PHOS and EMCal calorimeters and the Photon Conversion Method. The invariant differential yields of π0 and η meson inclusive production are measured near mid-rapidity in a broad transverse momentum range of 0.3<pT<20 GeV/c and 0.7<pT<20 GeV/c, respectively. The measured η/π0 ratio increases with pT and saturates for pT>4 GeV/c at 0.483±0.015stat±0.015sys. A deviation from mT scaling is observed for pT<2 GeV/c. The measured η/π0 ratio is consistent with previous measurements from proton-nucleus and pp collisions over the full pT range. The measured η/π0 ratio at high pT also agrees within uncertainties with measurements from nucleus-nucleus collisions. The π0 and η yields in p-Pb relative to the scaled pp interpolated reference, RpPb, are presented for 0.3<pT<20 GeV/c and 0.7<pT<20 GeV/c, respectively. The results are compared with theoretical model calculations. The values of RpPb are consistent with unity for transverse momenta above 2 GeV/c. These results support the interpretation that the suppressed yield of neutral mesons measured in Pb-Pb collisions at LHC energies is due to parton energy loss in the hot QCD medium.

p-p, p-Λ and Λ-Λ correlations studied via femtoscopy in pp reactions at s√ = 7 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
We report on the first femtoscopic measurement of baryon pairs, such as p-p, p-Λ and Λ-Λ, measured by ALICE at the Large Hadron Collider (LHC) in proton-proton collisions at s√ = 7 TeV. This study demonstrates the feasibility of such measurements in pp collisions at ultrarelativistic energies. The femtoscopy method is employed to constrain the hyperon-nucleon and hyperon-hyperon interactions, which are still rather poorly understood. A new method to evaluate the influence of residual correlations induced by the decays of resonances and experimental impurities is hereby presented. The p-p, p-Λ and Λ-Λ correlation functions were fitted simultaneously with the help of a new tool developed specifically for the femtoscopy analysis in small colliding systems 'Correlation Analysis Tool using the Schrödinger Equation' (CATS). Within the assumption that in pp collisions the three particle pairs originate from a common source, its radius is found to be equal to r0=1.144±0.019 (stat) +0.069−0.012 (syst) fm. The sensitivity of the measured p-Λ correlation is tested against different scattering parameters which are defined by the interaction among the two particles, but the statistics is not sufficient yet to discriminate among different models. The measurement of the Λ-Λ correlation function constrains the phase space spanned by the effective range and scattering length of the strong interaction. Discrepancies between the measured scattering parameters and the resulting correlation functions at LHC and RHIC energies are discussed in the context of various models.

Particle identification studies with a full-size 4-GEM prototype for the ALICE TPC upgrade - M.M. Aggarwal; Z. Ahammed; R. Keidel; S. Aiola; J. Alme; T. Alt; W. Amend; A. Andronic; V. Anguelov; H. Appelshäuser; M. Arslandok; R. Averbeck; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2018)
A large Time Projection Chamber is the main device for tracking and charged-particle identification in the ALICE experiment at the CERN LHC. After the second long shutdown in 2019/20, the LHC will deliver Pb beams colliding at an interaction rate of about 50 kHz, which is about a factor of 50 above the present readout rate of the TPC. This will result in a significant improvement on the sensitivity to rare probes that are considered key observables to characterize the QCD matter created in such collisions. In order to make full use of this luminosity, the currently used gated Multi-Wire Proportional Chambers will be replaced. The upgrade relies on continuously operated readout detectors employing Gas Electron Multiplier technology to retain the performance in terms of particle identification via the measurement of the specific energy loss by ionization dE/dx. A full-size readout chamber prototype was assembled in 2014 featuring a stack of four GEM foils as an amplification stage. The performance of the prototype was evaluated in a test beam campaign at the CERN PS. The dE/dx resolution complies with both the performance of the currently operated MWPC-based readout chambers and the challenging requirements of the ALICE TPC upgrade program. Detailed simulations of the readout system are able to reproduce the data.

Production of the ρ(770)0 meson in pp and Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; J. Adolfsson (2018)
The production of the ρ(770)0 meson has been measured at mid-rapidity (|y|<0.5) in pp and centrality differential Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV with the ALICE detector at the Large Hadron Collider. The particles have been reconstructed in the ρ(770)→π+π− decay channel in the transverse momentum (pT) range 0.5−11 GeV/c. A centrality dependent suppression of the ratio of the integrated yields 2ρ(770)0/(π++π−) is observed. The ratio decreases by ∼40% from pp to central Pb-Pb collisions. A study of the pT-differential 2ρ(770)0/(π++π−) ratio reveals that the suppression occurs at low transverse momenta, pT<2 GeV/c. At higher momentum, particle ratios measured in heavy-ion and pp collisions are consistent. The observed suppression is very similar to that previously measured for the K∗(892)0/K ratio and is consistent with EPOS3 predictions that may imply that rescattering in the hadronic phase is a dominant mechanism for the observed suppression.

Prompt and non-prompt J/ψ production and nuclear modification at mid-rapidity in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; F. T. Acosta; R. Keidel; D. Adamová; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. U. Ahn; S. Aiola; et al. (The European Physical Journal C, 2018)
A measurement of beauty hadron production at mid-rapidity in proton-lead collisions at a nucleon-nucleon centre-of-mass energy sNN‾‾‾‾√=5.02 TeV is presented. The semi-inclusive decay channel of beauty hadrons into J/ψ is considered, where the J/ψ mesons are reconstructed in the dielectron decay channel at mid-rapidity down to transverse momenta of 1.3 GeV/c. The bb¯ production cross section at mid-rapidity, dσbb¯/dy, and the total cross section extrapolated over full phase space, σbb¯, are obtained. This measurement is combined with results on inclusive J/ψ production to determine the prompt J/ψ cross sections. The results in p-Pb collisions are then scaled to expectations from pp collisions at the same centre-of-mass energy to derive the nuclear modification factor RpPb, and compared to models to study possible nuclear modifications of the production induced by cold nuclear matter effects. RpPb is found to be smaller than unity at low pT for both J/ψ coming from beauty hadron decays and prompt J/ψ.

Real-time data processing in the ALICE High Level Trigger at the LHC - Shreyasi Acharya; Fernando Tolares Acosta; Ralf Keidel; Dagmar Adamova (2018)
At the Large Hadron Collider at CERN in Geneva, Switzerland, atomic nuclei are collided at ultra-relativistic energies. Many final-state particles are produced in each collision and their properties are measured by the ALICE detector. The detector signals induced by the produced particles are digitized leading to data rates that are in excess of 48 GB/s. The ALICE High Level Trigger (HLT) system pioneered the use of FPGA- and GPU-based algorithms to reconstruct charged-particle trajectories and reduce the data size in real time. The results of the reconstruction of the collision events, available online, are used for high level data quality and detector-performance monitoring and real-time time-dependent detector calibration. The online data compression techniques developed and used in the ALICE HLT have more than quadrupled the amount of data that can be stored for offline event processing.

Study of J/ψ azimuthal anisotropy at forward rapidity in Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - Shreyasi Acharya; Fernando Torales Acosta; Ralf Keidel; Dagmar Adamova (2018)
The second (v2) and third (v3) flow harmonic coefficients of J/ψ mesons are measured at forward rapidity (2.5 < y < 4.0) in Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV with the ALICE detector at the LHC. Results are obtained with the scalar product method and reported as a function of transverse momentum, pT, for various collision centralities. A positive value of J/ψ v3 is observed with 3.7σ significance. The measurements, compared to those of prompt D0 mesons and charged particles at mid-rapidity, indicate an ordering with vn(J/ψ) <vn(D0) <vn(h±) (n = 2, 3) at low and intermediate pT up to 6 GeV/c and a convergence with v2(J/ψ) ≈v2(D0) ≈v2(h±) at high pT above 6-8 GeV/c. In semi-central collisions (5-40% and 10-50% centrality intervals) at intermediate pT between 2 and 6 GeV/c, the ratio v3/v2 of J/ψ mesons is found to be significantly lower (4.6σ) with respect to that of charged particles. In addition, the comparison to the prompt D0-meson ratio in the same pT interval suggests an ordering similar to that of the v2 and v3 coefficients. The J/ψ v2 coefficient is further studied using the Event Shape Engineering technique. The obtained results are found to be compatible with the expected variations of the eccentricity of the initial-state geometry.

Suppression of Λ(1520) resonance production in central Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
The production yield of the Λ(1520) baryon resonance is measured at mid-rapidity in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV with the ALICE detector at the LHC. The measurement is performed in the Λ(1520)→pK− (and charge conjugate) hadronic decay channel as a function of the transverse momentum (pT) and collision centrality. The pT-integrated production rate of Λ(1520) relative to Λ in central collisions is suppressed by about a factor of 2 with respect to peripheral collisions. This is the first observation of the suppression of a baryonic resonance at LHC and the first evidence of Λ(1520) suppression in heavy-ion collisions. The measured Λ(1520)/Λ ratio in central collisions is smaller than the value predicted by the statistical hadronisation model calculations. The shape of the measured pT distribution and the centrality dependence of the suppression are reproduced by the EPOS3 Monte Carlo event generator. The measurement adds further support to the formation of a dense hadronic phase in the final stages of the evolution of the fireball created in heavy-ion collisions, lasting long enough to cause a significant reduction in the observable yield of short-lived resonances.

The ALICE Transition Radiation Detector: Construction, operation, and performance - S. Acharya; J. Adam; R. Keidel; D. Adamova (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2018)
The Transition Radiation Detector (TRD) was designed and built to enhance the capabilities of the ALICE detector at the Large Hadron Collider (LHC). While aimed at providing electron identification and triggering, the TRD also contributes significantly to the track reconstruction and calibration in the central barrel of ALICE. In this paper the design, construction, operation, and performance of this detector are discussed. A pion rejection factor of up to 410 is achieved at a momentum of 1 GeV/c in p-Pb collisions and the resolution at high transverse momentum improves by about 40% when including the TRD information in track reconstruction. The triggering capability is demonstrated both for jet, light nuclei, and electron selection.

Transverse momentum spectra and nuclear modification factors of charged particles in pp, p-Pb and Pb-Pb collisions at the LHC - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
We report the measured transverse momentum (pT) spectra of primary charged particles from pp, p-Pb and Pb-Pb collisions at a center-of-mass energy sNN‾‾‾‾√=5.02 TeV in the kinematic range of 0.15<pT<50 GeV/c and |η|<0.8. A significant improvement of systematic uncertainties motivated the reanalysis of data in pp and Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV, as well as in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV, which is also presented. Spectra from Pb-Pb collisions are presented in nine centrality intervals and are compared to a reference spectrum from pp collisions scaled by the number of binary nucleon-nucleon collisions. For central collisions, the pT spectra are suppressed by more than a factor of 7 around 6-7 GeV/c with a significant reduction in suppression towards higher momenta up to 30 GeV/c. The nuclear modification factor RpPb, constructed from the pp and p-Pb spectra measured at the same collision energy, is consistent with unity above 8 GeV/c. While the spectra in both pp and Pb-Pb collisions are substantially harder at sNN‾‾‾‾√=5.02 TeV compared to 2.76 TeV, the nuclear modification factors show no significant collision energy dependence. The obtained results should provide further constraints on the parton energy loss calculations to determine the transport properties of the hot and dense QCD matter.

Transverse momentum spectra and nuclear modification factors of charged particles in Xe-Xe collisions at sNN‾‾‾‾√ = 5.44 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
Transverse momentum (pT) spectra of charged particles at mid-pseudorapidity in Xe-Xe collisions at sNN‾‾‾‾√ = 5.44 TeV measured with the ALICE apparatus at the Large Hadron Collider are reported. The kinematic range 0.15<pT<50 GeV/c and |η|<0.8 is covered. Results are presented in nine classes of collision centrality in the 0-80% range. For comparison, a pp reference at the collision energy of s√ = 5.44 TeV is obtained by interpolating between existing measurements at s√ = 5.02 and 7 TeV. The nuclear modification factors in central Xe-Xe collisions and Pb-Pb collisions at a similar center-of-mass energy of sNN‾‾‾‾√ = 5.02 TeV, and in addition at 2.76 TeV, at analogous ranges of charged particle multiplicity density ⟨dNch/dη⟩ show a remarkable similarity at pT>10 GeV/c. The comparison of the measured Xe-Xe collision in the two colliding systems could provide insight on the path length dependence of medium-induced parton energy loss. The centrality dependence of the ratio of the average transverse momentum ⟨pT⟩ in Xe-Xe collisions over Pb-Pb collision at s√ = 5.02 TeV is compared to hydrodynamical model calculations.

Two particle differential transverse momentum and number density correlations in p-Pb and Pb-Pb at the LHC - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
We present measurements of two-particle differential number correlation functions R2 and transverse momentum correlation functions P2, obtained from p-Pb collisions at 5.02 TeV and Pb-Pb collisions at 2.76 TeV. The results are obtained using charged particles in the pseudorapidity range |η|< 1.0, and transverse momentum range 0.2<pT<2.0 GeV/c as a function of pair separation in pseudorapidity, |Δη|, azimuthal angle, Δφ, and for several charged-particle multiplicity classes. Measurements are carried out for like-sign and unlike-sign charged-particle pairs separately and combined to obtain charge-independent and charge-dependent correlation functions. We study the evolution of the width of the near-side peak of these correlation functions with collision centrality. Additionally, we study Fourier decompositions of the correlators in Δφ as a function of the pair separation |Δη|. Significant differences in the dependence of their harmonic coefficients on multiplicity classes are found. These differences can be exploited, in theoretical models, to obtain further insight into charged-particle production and transport in heavy-ion collisions. Moreover, an upper limit of non-flow contributions to flow coefficients vn measured in Pb-Pb collisions based on the relative strength of Fourier coefficients measured in p-Pb interactions is estimated.

WoDiCoF - A Testbed for the Evaluation of (Parallel) Covert Channel Detection Algorithms. - Ralf Keidel; Steffen Wendzel; Sebastian Zillien; Eric S. Conner; Georg Haas (J. Univers. Comput. Sci., 2018)

Λ+c production in Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV - Fernando Torales Acosta; Shreyasi Acharya; Ralf Keidel; Dagmar Adamova (2018)
A measurement of the production of prompt Λ+c baryons in Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV with the ALICE detector at the LHC is reported. The Λ+c and Λ⎯⎯⎯⎯−c were reconstructed at midrapidity (|y|<0.5) via the hadronic decay channel Λ+c→pK0S (and charge conjugate) in the transverse momentum and centrality intervals 6<pT<12 GeV/c and 0-80%. The Λ+c/D0 ratio, which is sensitive to the charm quark hadronisation mechanisms in the medium, is measured and found to be larger than the ratio measured in minimum-bias pp collisions at s√=7 TeV and in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV. In particular, the values in p-Pb and Pb-Pb collisions differ by about two standard deviations of the combined statistical and systematic uncertainties. The Λ+c/D0 ratio is also compared with model calculations including different implementations of charm quark hadronisation. The measured ratio is reproduced by models implementing a pure coalescence scenario, while adding a fragmentation contribution leads to an underestimation. The Λ+c nuclear modification factor, RAA, is also presented. The measured values of the RAA of Λ+c, Ds and non-strange D mesons are compatible within the combined statistical and systematic uncertainties. They show, however, a hint of a hierarchy (RD0AA<RDsAA<RΛ+cAA), conceivable with a contribution of recombination mechanisms to charm hadron formation in the medium.

Υ suppression at forward rapidity in Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2018)
Inclusive Υ(1S) and Υ(2S) production have been measured in Pb-Pb collisions at the centre-of-mass energy per nucleon-nucleon pair sNN‾‾‾√=5.02 TeV, using the ALICE detector at the CERN LHC. The Υ mesons are reconstructed in the centre-of-mass rapidity interval 2.5<y<4 and in the transverse-momentum range pT<15 GeV/c, via their decays to muon pairs. In this Letter, we present results on the inclusive Υ(1S) nuclear modification factor RAA as a function of collision centrality, transverse momentum and rapidity. The Υ(1S) and Υ(2S) RAA, integrated over the centrality range 0-90%, are 0.37±0.02(stat)±0.03(syst) and 0.10±0.04(stat)±0.02(syst), respectively, leading to a ratio RΥ(2S)AA/RΥ(1S)AA of 0.28±0.12(stat)±0.06(syst). The observed Υ(1S) suppression increases with the centrality of the collision and no significant variation is observed as a function of transverse momentum and rapidity.

ϕ meson production at forward rapidity in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV - S. Acharya; F.-T. Acosta; R. Keidel; D. Adamová; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. U. Ahn; S. Aiola; et al. (The European Physical Journal C, 2018)
ϕ meson measurements provide insight into strangeness production, which is one of the key observables for the hot medium formed in high-energy heavy-ion collisions. ALICE measured ϕ production through its decay in muon pairs in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV in the intermediate transverse momentum range 2<pT<5 GeV/c and in the rapidity interval 2.5<y<4. The ϕ yield was measured as a function of the transverse momentum and collision centrality. The nuclear modification factor was obtained as a function of the average number of participating nucleons. Results were compared with the ones obtained via the kaon decay channel in the same pT range at midrapidity. The values of the nuclear modification factor in the two rapidity regions are in agreement within uncertainties.

Azimuthally Differential Pion Femtoscopy in Pb-Pb Collisions at sNN=2.76 TeV - D. Adamová; M. M. Aggarwal; R. Keidel; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; S. Aiola; A. Akindinov; S. N. Alam; et al. (Physical Review Letters, 2017)
We present the first azimuthally differential measurements of the pion source size relative to the second harmonic event plane in Pb-Pb collisions at a center-of-mass energy per nucleon-nucleon pair of √sNN=2.76 TeV. The measurements have been performed in the centrality range 0%-50% and for pion pair transverse momenta 0.2<kT<0.7 GeV/c. We find that the Rside and Rout radii, which characterize the pion source size in the directions perpendicular and parallel to the pion transverse momentum, oscillate out of phase, similar to what was observed at the Relativistic Heavy Ion Collider. The final-state source eccentricity, estimated via Rside oscillations, is found to be significantly smaller than the initial-state source eccentricity, but remains positive—indicating that even after a stronger expansion in the in-plane direction, the pion source at the freeze-out is still elongated in the out-of-plane direction. The 3+1D hydrodynamic calculations are in qualitative agreement with observed centrality and transverse momentum Rside oscillations, but systematically underestimate the oscillation magnitude.

Charged-particle multiplicities in proton-proton collisions at s√ = 0.9 to 8 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (The European Physical Journal C, 2017)
A detailed study of pseudorapidity densities and multiplicity distributions of primary charged particles produced in proton-proton collisions, at s√= 0.9, 2.36, 2.76, 7 and 8 TeV, in the pseudorapidity range |η|<2, was carried out using the ALICE detector. Measurements were obtained for three event classes: inelastic, non-single diffractive and events with at least one charged particle in the pseudorapidity interval |η|<1. The use of an improved track-counting algorithm combined with ALICE's measurements of diffractive processes allows a higher precision compared to our previous publications. A KNO scaling study was performed in the pseudorapidity intervals |η|< 0.5, 1.0 and 1.5. The data are compared to other experimental results and to models as implemented in Monte Carlo event generators PHOJET and recent tunes of PYTHIA6, PYTHIA8 and EPOS. arXiv:1509.07541 [nucl-ex]

Charged-particle multiplicity distributions over a wide pseudorapidity range in proton-proton collisions at s√= 0.9, 7, and 8 TeV - S. Acharya; D. Adamová; R. Keidel; J. Adolfsson; M. M. Aggarwal; G. AglieriRinella; M. Agnello; N. Agrawal; Z. Ahammed; N. Ahmad; S. U. Ahn; S. Aiola; et al. (The European Physical Journal C, 2017)
We present the charged-particle multiplicity distributions over a wide pseudorapidity range ( −3.4<η<5.0 ) for pp collisions at s√=0.9,7 , and 8 TeV at the LHC. Results are based on information from the Silicon Pixel Detector and the Forward Multiplicity Detector of ALICE, extending the pseudorapidity coverage of the earlier publications and the high-multiplicity reach. The measurements are compared to results from the CMS experiment and to PYTHIA, PHOJET and EPOS LHC event generators, as well as IP-Glasma calculations.

Constraining the magnitude of the Chiral Magnetic Effect with Event Shape Engineering in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - S. Acharya; J. Adam; R. Keidel; D. Adamova (2017)
In ultrarelativistic heavy-ion collisions, the event-by-event variation of the elliptic flow v2 reflects fluctuations in the shape of the initial state of the system. This allows to select events with the same centrality but different initial geometry. This selection technique, Event Shape Engineering, has been used in the analysis of charge-dependent two- and three-particle correlations in Pb-Pb collisions at sNN‾‾‾√=2.76 TeV. The two-particle correlator ⟨cos(φα−φβ)⟩, calculated for different combinations of charges α and β, is almost independent of v2 (for a given centrality), while the three-particle correlator ⟨cos(φα+φβ−2Ψ2)⟩ scales almost linearly both with the event v2 and charged-particle pseudorapidity density. The charge dependence of the three-particle correlator is often interpreted as evidence for the Chiral Magnetic Effect (CME), a parity violating effect of the strong interaction. However, its measured dependence on v2 points to a large non-CME contribution to the correlator. Comparing the results with Monte Carlo calculations including a magnetic field due to the spectators, the upper limit of the CME signal contribution to the three-particle correlator in the 10-50% centrality interval is found to be 26-33% at 95% confidence level.

Constraints on jet quenching in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV measured by the event-activity dependence of semi-inclusive hadron-jet distributions - S. Acharya; D. Adamova; R. Keidel; J. Adolfsson (2017)
The ALICE Collaboration reports the measurement of semi-inclusive distributions of charged-particle jets recoiling from a high-transverse momentum trigger hadron in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV. Jets are reconstructed from charged-particle tracks using the anti-kT algorithm with resolution parameter R=0.2 and 0.4. A data-driven statistical approach is used to correct the uncorrelated background jet yield. Recoil jet distributions are reported for jet transverse momentum 15<pchT,jet<50 GeV/c and are compared in various intervals of p-Pb event activity, based on charged-particle multiplicity and zero-degree neutral energy in the forward (Pb-going) direction. The semi-inclusive observable is self-normalized and such comparisons do not require the interpretation of p-Pb event activity in terms of collision geometry, in contrast to inclusive jet observables. These measurements provide new constraints on the magnitude of jet quenching in small systems at the LHC. In p-Pb collisions with high event activity, the average medium-induced out-of-cone energy transport for jets with R=0.4 and 15<pchT,jet<50 GeV/c is measured to be less than 0.4 GeV/c at 90% confidence, which is over an order of magnitude smaller than a similar measurement for central Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV. Comparison is made to theoretical calculations of jet quenching in small systems, and to inclusive jet measurements in p-Pb collisions selected by event activity at the LHC and in d-Au collisions at RHIC.

D-meson azimuthal anisotropy in mid-central Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; D. Adamova; Ralf Keidel; J. Adolfsson (2017)
The azimuthal anisotropy coefficient v2 of prompt D0, D+, D∗+ and D+s mesons was measured in mid-central (30-50% centrality class) Pb-Pb collisions at a centre-of-mass energy per nucleon pair sNN‾‾‾‾√=5.02 TeV, with the ALICE detector at the LHC. The D mesons were reconstructed via their hadronic decays at mid-rapidity, |y|<0.8, in the transverse momentum interval 1<pT<24 GeV/c. The measured D-meson v2 has similar values as that of charged pions. The D+s v2, measured for the first time, is found to be compatible with that of non-strange D mesons. The measurements are compared with theoretical calculations of charm-quark transport in a hydrodynamically expanding medium and have the potential to constrain medium parameters.

Energy dependence of forward-rapidity J/ψ and ψ(2S) production in pp collisions at the LHC - S. Acharya; D. Adamová; R. Keidel; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; N. Ahmad; S. U. Ahn; S. Aiola; A. Akindinov; et al. (The European Physical Journal C, 2017)
We present results on transverse momentum (pT) and rapidity (y) differential production cross sections, mean transverse momentum and mean transverse momentum square of inclusive J/ψ and ψ(2S) at forward rapidity (2.5<y<4) as well as ψ(2S)-to-J/ψ cross section ratios. These quantities are measured in pp collisions at center of mass energies s√=5.02 and 13 TeV with the ALICE detector. Both charmonium states are reconstructed in the dimuon decay channel, using the muon spectrometer. A comprehensive comparison to inclusive charmonium cross sections measured at s√=2.76, 7 and 8 TeV is performed. A comparison to non-relativistic quantum chromodynamics and fixed-order next-to-leading logarithm calculations, which describe prompt and non-prompt charmonium production respectively, is also presented. A good description of the data is obtained over the full pT range, provided that both contributions are summed. In particular, it is found that for pT>15 GeV/c the non-prompt contribution reaches up to 50% of the total charmonium yield.

First measurement of jet mass in Pb-Pb and p-Pb collisions at the LHC - S. Acharya; D. Adamova; Ralf Keidel; M. M. Aggarwal (2017)
This letter presents the first measurement of jet mass in Pb-Pb and p-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV and 5.02 TeV, respectively. Both the jet energy and the jet mass are expected to be sensitive to jet quenching in the hot Quantum Chromodynamics (QCD) matter created in nuclear collisions at collider energies. Jets are reconstructed from charged particles using the anti-kT jet algorithm and resolution parameter R=0.4. The jets are measured in pseudorapidity |ηjet|<0.5 and in three intervals of transverse momentum between 60 GeV/c and 120 GeV/c. Background from the underlying Pb-Pb event is subtracted jet-by-jet using data-driven methods. Residual background fluctuations and detector effects are corrected via a two-dimensional unfolding procedure, where the jet pT and the mass are simultaneously corrected to particle level. The measurement of the jet mass in central Pb-Pb collisions is compared to the jet mass as measured in p-Pb reference collisions, to vacuum event generators, and to models including jet quenching.

First measurement of Ξ0c production in pp collisions at s√ = 7 TeV - S. Acharya; D. Adamova; R. Keidel; J. Adolfsson (2017)
The production of the charm-strange baryon Ξ0c is measured for the first time at the LHC via its semileptonic decay into e+Ξ−νe in pp collisions at s√=7 TeV with the ALICE detector. The transverse momentum (pT) differential cross section multiplied by the branching ratio is presented in the interval 1 < pT < 8 GeV/c at mid-rapidity, |y| < 0.5. The transverse momentum dependence of the Ξ0c baryon production relative to the D0 meson production is compared to predictions of event generators with various tunes of the hadronisation mechanism, which are found to underestimate the measured cross-section ratio.

Flow Dominance and Factorization of Transverse Momentum Correlations in Pb-Pb Collisions at the LHC - J. Adam; D. Adamová; R. Keidel; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; S. Aiola; A. Akindinov; et al. (Physical Review Letters, 2017)
We present the first measurement of the two-particle transverse momentum differential correlation function, P2≡⟨ΔpTΔpT⟩/⟨pT⟩2, in Pb-Pb collisions at √sNN=2.76 TeV. Results for P2 are reported as a function of the relative pseudorapidity (Δη) and azimuthal angle (Δφ) between two particles for different collision centralities. The Δϕ dependence is found to be largely independent of Δη for |Δη|≥0.9. In the 5% most central Pb-Pb collisions, the two-particle transverse momentum correlation function exhibits a clear double-hump structure around Δφ=π (i.e., on the away side), which is not observed in number correlations in the same centrality range, and thus provides an indication of the dominance of triangular flow in this collision centrality. Fourier decompositions of P2, studied as a function of the collision centrality, show that correlations at |Δη|≥0.9 can be well reproduced by a flow ansatz based on the notion that measured transverse momentum correlations are strictly determined by the collective motion of the system.

J/ψ Elliptic Flow in Pb-Pb Collisions at sNN=5.02 TeV - S. Acharya; D. Adamová; R. Keidel; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. U. Ahn; S. Aiola; A. Akindinov; et al. (Physical Review Letters, 2017)
We report a precise measurement of the J/ψ elliptic flow in Pb-Pb collisions at √sNN=5.02 TeV with the ALICE detector at the LHC. The J/ψ mesons are reconstructed at midrapidity (|y|<0.9) in the dielectron decay channel and at forward rapidity (2.5<y<4.0) in the dimuon channel, both down to zero transverse momentum. At forward rapidity, the elliptic flow v2 of the J/ψ is studied as a function of the transverse momentum and centrality. A positive v2 is observed in the transverse momentum range 2<pT<8 GeV/c in the three centrality classes studied and confirms with higher statistics our earlier results at √sNN=2.76 TeV in semicentral collisions. At midrapidity, the J/ψ v2 is investigated as a function of the transverse momentum in semicentral collisions and found to be in agreement with the measurements at forward rapidity. These results are compared to transport model calculations. The comparison supports the idea that at low pT the elliptic flow of the J/ψ originates from the thermalization of charm quarks in the deconfined medium but suggests that additional mechanisms might be missing in the models.

J/ψ production as a function of charged-particle pseudorapidity density in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - D. Adamova; M. M. Aggarwal; Ralf Keidel; G. Aglieri Rinella (2017)
We report measurements of the inclusive J/ψ yield and average transverse momentum as a function of charged-particle pseudorapidity density dNch/dη in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV with ALICE at the LHC. The observables are normalised to their corresponding averages in non-single diffractive events. An increase of the normalised J/ψ yield with normalised dNch/dη is observed at mid-rapidity and backward rapidity, similar to that found earlier in pp collisions. At forward rapidity, a saturation of the relative yield is observed for high charged-particle multiplicities. The normalised average transverse momentum at forward and backward rapidity increases with multiplicity at low multiplicities and saturates beyond moderate multiplicities. In addition, the forward-to-backward nuclear modification factor ratio is also reported, showing an increasing suppression of J/ψ production at forward rapidity with respect to backward rapidity for increasing charged-particle multiplicity.

J/ψ suppression at forward rapidity in Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Phys. Lett. B., 2017)
The inclusive J/ψ production has been studied in Pn-Pb and pp collisions at the centre-of-mass energy per nucleon pair sNN‾‾‾‾√=5.02 TeV, using the ALICE detector at the CERN LHC. The J/ψ meson is reconstructed, in the centre-of-mass rapidity interval 2.5<y<4 and in the transverse-momentum range pT<12 GeV/c, via its decay to a muon pair. In this Letter, we present results on the inclusive J/ψ cross section in pp collisions at s√=5.02 TeV and on the nuclear modification factor RAA. The latter is presented as a function of the centrality of the collision and, for central collisions, as a function of the transverse momentum pT of the J/ψ. The measured RAA values indicate a suppression of the J/ψ in nuclear collisions and are then compared to our previous results obtained in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV. The ratio of the RAA values at the two energies is also computed and compared to calculations of statistical and dynamical models. The numerical value of the ratio for central events (0-10% centrality) is 1.17±0.04(stat)±0.20(syst). In central events, as a function of pT, a slight increase of RAA with collision energy is visible in the region 2<pT<6 GeV/c. Theoretical calculations provide a good description of the measurements, within uncertainties.

K∗(892)0 and ϕ(1020) meson production at high transverse momentum in pp and Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - J. Adam; D. Adamová; R. Keidel; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; S. Aiola; A. Akindinov; et al. (Physical Review C, 2017)
The production cross sections of the prompt charmed mesons D0, D+, D∗+ and D+s were measured at mid-rapidity in proton-proton collisions at a centre-of-mass energy s√=7 TeV with the ALICE detector at the Large Hadron Collider (LHC). D mesons were reconstructed from their decays D0→K−π+, D+→K−π+π+, D∗+→D0π+, D+s→ϕπ+→K−K+π+, and their charge conjugates. With respect to previous measurements in the same rapidity region, the coverage in transverse momentum (pT) is extended and the uncertainties are reduced by a factor of about two. The accuracy on the estimated total cc⎯⎯⎯ production cross section is likewise improved. The measured pT-differential cross sections are compared with the results of three perturbative QCD calculations.

Kaon femtoscopy in Pb-Pb collisions at sNN=2.76 TeV - S. Acharya; J. Adam; R. Keidel; D. Adamová; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; N. Ahmad; S. U. Ahn; et al. (Physical Review C, 2017)
We present the results of three-dimensional femtoscopic analyses for charged and neutral kaons recorded by ALICE in Pb-Pb collisions at sNN=2.76 TeV. Femtoscopy is used to measure the space-time characteristics of particle production from the effects of quantum statistics and final-state interactions in two-particle correlations. Kaon femtoscopy is an important supplement to that of pions because it allows one to distinguish between different model scenarios working equally well for pions. In particular, we compare the measured three-dimensional kaon radii with a purely hydrodynamical calculation and a model where the hydrodynamic phase is followed by a hadronic rescattering stage. The former predicts an approximate transverse mass (mT) scaling of source radii obtained from pion and kaon correlations. This mT scaling appears to be broken in our data, which indicates the importance of the hadronic rescattering phase at LHC energies. A kT scaling of pion and kaon source radii is observed instead. The time of maximal emission of the system is estimated by using the three-dimensional femtoscopic analysis for kaons. The measured emission time is larger than that of pions. Our observation is well supported by the hydrokinetic model predictions.

Linear and non-linear flow modes in Pb-Pb collisions at sNN‾‾‾‾√= 2.76 TeV - S. Acharya; D. Adamova; Ralf Keidel; J. Adolfsson (2017)
The second and the third order anisotropic flow, V2 and V3, are mostly determined by the corresponding initial spatial anisotropy coefficients, ε2 and ε3, in the initial density distribution. In addition to their dependence on the same order initial anisotropy coefficient, higher order anisotropic flow, Vn (n>3), can also have a significant contribution from lower order initial anisotropy coefficients, which leads to mode-coupling effects. In this Letter we investigate the linear and non-linear modes in higher order anisotropic flow Vn for n=4, 5, and 6 in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV with the ALICE detector at the Large Hadron Collider. The measurements are done for particles in the pseudorapidity range |η|<0.8 and the transverse momentum range 0.2<pT<5.0 GeV/c as a function of collision centrality. The results are compared with theoretical calculations and provide important constraints on the initial conditions, including initial spatial geometry and its fluctuations, as well as the ratio of the shear viscosity to entropy density of the produced system.

Longitudinal asymmetry and its effect on pseudorapidity distributions in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - S. Acharya; J. Adam; R. Keidel; D. Adamova (2017)
First results on the longitudinal asymmetry and its effect on the pseudorapidity distributions in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV at the Large Hadron Collider are obtained with the ALICE detector. The longitudinal asymmetry arises because of an unequal number of participating nucleons from the two colliding nuclei, and is estimated for each event by measuring the energy in the forward neutron-Zero-Degree-Calorimeters (ZNs). The effect of the longitudinal asymmetry is measured on the pseudorapidity distributions of charged particles in the regions |η|<0.9, 2.8<η<5.1 and −3.7<η<−1.7 by taking the ratio of the pseudorapidity distributions from events corresponding to different regions of asymmetry. The coefficients of a polynomial fit to the ratio characterise the effect of the asymmetry. A Monte Carlo simulation using a Glauber model for the colliding nuclei is tuned to reproduce the spectrum in the ZNs and provides a relation between the measurable longitudinal asymmetry and the shift in the rapidity (y0) of the participant zone formed by the unequal number of participating nucleons. The dependence of the coefficient of the linear term in the polynomial expansion, c1, on the mean value of y0 is investigated.

Measurement of azimuthal correlations of D mesons and charged particles in pp collisions at s√=7 TeV and p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Eur. Phys. J. C, 2017)
The azimuthal correlations of D mesons and charged particles were measured with the ALICE detector in pp collisions at s√=7 TeV and p-Pb collisions at sNN‾‾‾‾√=5.02 TeV at the Large Hadron Collider. D0, D+, and D∗+ mesons with transverse momentum 3<pT<16 GeV/c and rapidity in the nucleon-nucleon centre-of-mass system |ycms|<0.5 (pp collisions) and −0.96<ycms<0.04 (p-Pb collisions) were correlated to charged particles with pT>0.3 Gev/c. The properties of the correlation peak induced by the jet containing the D meson, described in terms of the yield of charged particles in the peak and peak width, are compatible within uncertainties between the two collision systems, and described by Monte-Carlo simulations based on the PYTHIA and POWHEG event generators.

Measurement of D-meson production at mid-rapidity in pp collisions at s√=7 TeV - S. Acharya; D. Adamova; Ralf Keidel; M. M. Aggarwal (2017)
The production cross sections of the prompt charmed mesons D0, D+, D∗+ and D+s were measured at mid-rapidity in proton-proton collisions at a centre-of-mass energy s√=7 TeV with the ALICE detector at the Large Hadron Collider (LHC). D mesons were reconstructed from their decays D0→K−π+, D+→K−π+π+, D∗+→D0π+, D+s→ϕπ+→K−K+π+, and their charge conjugates. With respect to previous measurements in the same rapidity region, the coverage in transverse momentum (pT) is extended and the uncertainties are reduced by a factor of about two. The accuracy on the estimated total cc⎯⎯⎯ production cross section is likewise improved. The measured pT-differential cross sections are compared with the results of three perturbative QCD calculations.

Measurement of deuteron spectra and elliptic flow in Pb-Pb collisions at at √sNN = 2.76 TeV at the LHC - S. Acharya; D. Adamová; R. Keidel; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; N. Ahmad; S. U. Ahn; S. Aiola; et al. (The European Physical Journal C, 2017)
The transverse momentum ( pT ) spectra and elliptic flow coefficient ( v2 ) of deuterons and anti-deuterons at mid-rapidity ( |y|<0.5 ) are measured with the ALICE detector at the LHC in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV. The measurement of the pT spectra of (anti-)deuterons is done up to 8 GeV /c in 0-10% centrality class and up to 6 GeV /c in 10-20% and 20-40% centrality classes. The v2 is measured in the 0.8 < pT < 5 GeV /c interval and in six different centrality intervals (0-5, 5-10, 10-20, 20-30, 30-40 and 40-50%) using the scalar product technique. Measured π± , K± and p+ p⎯⎯⎯ transverse-momentum spectra and v2 are used to predict the deuteron pT spectra and v2 within the Blast-Wave model. The predictions are able to reproduce the v2 coefficient in the measured pT range and the transverse-momentum spectra for pT > 1.8 GeV /c within the experimental uncertainties. The measurement of the coalescence parameter B2 is performed, showing a pT dependence in contrast with the simplest coalescence model, which fails to reproduce also the measured v2 coefficient. In addition, the coalescence parameter B2 and the elliptic flow coefficient in the 20-40% centrality interval are compared with the AMPT model which is able, in its version without string melting, to reproduce the measured v2 ( pT ) and the B2 ( pT ) trend.

Measurement of Z0-boson production at large rapidities in Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; D. Adamova; R. Keidel; J. Adolfsson (2017)
The production of Z0 bosons at large rapidities in Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV is reported. Z0 candidates are reconstructed in the dimuon decay channel (Z0→μ+μ−), based on muons selected with pseudo-rapidity −4.0<η<−2.5 and pT>20 GeV/c. The invariant yield and the nuclear modification factor, RAA, are presented as a function of rapidity and collision centrality. The value of RAA for the 0-20% central Pb-Pb collisions is 0.67±0.11(stat.)±0.03(syst.)±0.06(corr. syst.), exhibiting a deviation of 2.6σ from unity. The results are well-described by calculations that include nuclear modifications of the parton distribution functions, while the predictions using vacuum PDFs deviate from data by 2.3σ in the 0-90% centrality class and by 3σ in the 0-20% central collisions.

Measuring K0SK± interactions using Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV - S. Acharya; D. Adamova; Ralf Keidel; J. Adolfsson (2017)
We present the first ever measurements of femtoscopic correlations between the K0S and K± particles. The analysis was performed on the data from Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV measured by the ALICE experiment. The observed femtoscopic correlations are consistent with final-state interactions proceeding via the a0(980) resonance. The extracted kaon source radius and correlation strength parameters for K0SK− are found to be equal within the experimental uncertainties to those for K0SK+. Comparing the results of the present study with those from published identical-kaon femtoscopic studies by ALICE, mass and coupling parameters for the a0 resonance are constrained. Our results are also compatible with the interpretation of the a0 having a tetraquark structure over that of a diquark.

Multiplicity-dependent enhancement of strange and multi-strange hadron production in proton-proton collisions at s√=7 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Nature Physics, 2017)
The yields of strange (K0S, Λ, Λ¯) and multi-strange (Ξ−, Ξ¯+, Ω−, Ω¯+) hadrons are measured at midrapidity in proton-proton (pp) collisions at s√ = 7 TeV as a function of the charged-particle multiplicity density (dNch/dη).The production rate of strange particles increases faster than that of non-strange hadrons, leading to an enhancement of strange particles relative to pions, similar to that found in nucleus-nucleus collisions as well as in proton-nucleus collisions at the LHC. This is the first observation of an enhanced production of strange particles in high-multiplicity pp collisions. The magnitude of this strangeness enhancement increases with the event activity, quantified by dNch/dη, and with hadron strangeness. It reaches almost a factor of two for the Ω at the highest multiplicity presented. No enhancement is observed for particles with no strange quark content, demonstrating that the observed effect is strangeness rather than mass related. The results are not reproduced by any of the Monte Carlo models commonly used at the LHC, suggesting that further developments are needed for a complete microscopic understanding of strangeness production and indicating the presence of a phenomenon novel in high-multiplicity pp collisions.

Production of 4He and 4He⎯ in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV at the LHC - S. Acharya; D. Adamova; R. Keidel; J. Adolfsson (2017)
Results on the production of 4He and 4He⎯ nuclei in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV in the rapidity range ∣y∣<1, using the ALICE detector, are presented in this paper. The rapidity densities corresponding to 0-10% central events are found to be dN/dy4He=(0.8±0.4 (stat)±0.3 (syst))×10−6 and dN/dy4He⎯ =(1.1±0.4 (stat)±0.2 (syst))×10−6, respectively. This is in agreement with the statistical thermal model expectation assuming the same chemical freeze-out temperature (Tchem = 156 MeV) as for light hadrons. The measured ratio of 4He⎯/4He is 1.4±0.8 (stat)±0.5 (syst).

Production of deuterons, tritons, 3He nuclei and their anti-nuclei in pp collisions at s√ = 0.9, 2.76 and 7 TeV - S. Acharya; J. Adam; R. Keidel; D. Adamova (2017)
Invariant differential yields of deuterons and anti-deuterons in pp collisions at s√ = 0.9, 2.76 and 7 TeV and the yields of tritons, 3He nuclei and their anti-nuclei at s√ = 7 TeV have been measured with the ALICE detector at the LHC. The measurements cover a wide transverse momentum (pT) range in the rapidity interval |y|<0.5, extending both the energy and the pT reach of previous measurements up to 3 GeV/c for A=2 and 6 GeV/c for A=3. The coalescence parameters of (anti-)deuterons and 3He⎯⎯⎯⎯⎯⎯⎯ nuclei exhibit an increasing trend with pT and are found to be compatible with measurements in pA collisions at low pT and lower energies. The integrated yields decrease by a factor of about 1000 for each increase of the mass number with one (anti-)nucleon. Furthermore, the deuteron-to-proton ratio is reported as a function of the average charged particle multiplicity at different center-of-mass energies.

Production of muons from heavy-flavour hadron decays in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; D. Adamová; R. Keidel; M.M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; N. Ahmad; S.U. Ahn; S. Aiola; A. Akindinov; et al. (Physics Letters B, 2017)
The production of muons from heavy-flavour hadron decays in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV was studied for 2<pT<16 GeV/c with the ALICE detector at the CERN LHC. The measurement was performed at forward (p-going direction) and backward (Pb-going direction) rapidity, in the ranges of rapidity in the center-of-mass system (cms) 2.03<ycms<3.53 and −4.46<ycms<−2.96, respectively. The production cross sections and nuclear modification factors are presented as a function of transverse momentum (pT). At forward rapidity, the nuclear modification factor is compatible with unity while at backward rapidity, in the interval 2.5<pT<3.5 GeV/c, it is above unity by more than 2σ. The ratio of the forward-to-backward production cross sections is also measured in the overlapping interval 2.96<|ycms|<3.53 and is smaller than unity by 3.7σ in 2.5<pT<3.5 GeV/c. The data are described by model calculations including cold nuclear matter effects.

Production of π0 and η mesons up to high transverse momentum in pp collisions at 2.76 TeV - S. Acharya; D. Adamová; R. Keidel; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; N. Ahmad; S. U. Ahn; S. Aiola; A. Akindinov; et al. (The European Physical Journal C, 2017)
The invariant differential cross sections for inclusive π0 and η mesons at midrapidity were measured in pp collisions at s√=2.76 TeV for transverse momenta 0.4<pT<40 GeV/c and 0.6<pT<20 GeV/c, respectively, using the ALICE detector. This large range in pT was achieved by combining various analysis techniques and different triggers involving the electromagnetic calorimeter (EMCal). In particular, a new single-cluster, shower-shape based method was developed for the identification of high-pT neutral pions, which exploits that the showers originating from their decay photons overlap in the EMCal. Above 4 GeV/c, the measured cross sections are found to exhibit a similar power-law behavior with an exponent of about 6.3. Next-to-leading-order perturbative QCD calculations differ from the measured cross sections by about 30% for the π0, and between 30-50% for the η meson, while generator-level simulations with PYTHIA 8.2 describe the data to better than 10-30%, except at pT<1 GeV/c. The new data can therefore be used to further improve the theoretical description of π0 and η meson production.

Production of Σ(1385)± and Ξ(1530)0 in p-Pb collisions at sNN−−−√=5.02 TeV - D. Adamová; M. M. Aggarwal; R. Keidel; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; S. Aiola; A. Akindinov; S. N. Alam; et al. (The European Physical Journal C, 2017)
The transverse momentum distributions of the strange and double-strange hyperon resonances (Σ(1385)±, Ξ(1530)0) produced in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV were measured in the rapidity range −0.5<yCMS<0 for event classes corresponding to different charged-particle multiplicity densities, ⟨dNch/dηlab⟩. The mean transverse momentum values are presented as a function of ⟨dNch/dηlab⟩, as well as a function of the particle masses and compared with previous results on hyperon production. The integrated yield ratios of excited to ground-state hyperons are constant as a function of ⟨dNch/dηlab⟩. The equivalent ratios to pions exhibit an increase with ⟨dNch/dηlab⟩, depending on their strangeness content.

Relative particle yield fluctuations in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV - S. Acharya; D. Adamova; R. Keidel; J. Adolfsson (2017)
First results on K/π, p/π and K/p fluctuations are obtained with the ALICE detector at the CERN LHC as a function of centrality in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV. The observable νdyn, which is defined in terms of the moments of particle multiplicity distributions, is used to quantify the magnitude of dynamical fluctuations of relative particle yields and also provides insight into the correlation between particle pairs. This study is based on a novel experimental technique, called the Identity Method, which allows one to measure the moments of multiplicity distributions in case of incomplete particle identification. The results for p/π show a change of sign in νdyn from positive to negative towards more peripheral collisions. For central collisions, the results follow the smooth trend of the data at lower energies and νdyn exhibits a change in sign for p/π and K/p.

Search for collectivity with azimuthal J/ψ-hadron correlations in high multiplicity p-Pb collisions at sNN‾‾‾‾√ = 5.02 and 8.16 TeV - S. Acharya; D. Adamova; R. Keidel; J. Adolfsson (2017)
We present a measurement of azimuthal correlations between inclusive J/ψ and charged hadrons in p-Pb collisions recorded with the ALICE detector at the CERN LHC. The J/ψ are reconstructed at forward (2.03 < y < 3.53) and backward (−4.46 < y < −2.96) rapidity via their μ+μ− decay channel, while the charged hadrons are reconstructed at mid-rapidity (|η| < 1.8). The correlations are expressed in terms of associated charged-hadron yields per J/ψ trigger. A rapidity gap of at least 1.5 units between the trigger J/ψ and the associated charged hadrons is required. Possible correlations due to collective effects are assessed by subtracting the associated per-trigger yields in the low-multiplicity collisions from those in the high-multiplicity collisions. After the subtraction, we observe a strong indication of remaining symmetric structures at Δφ ≈ 0 and Δφ ≈ π, similar to those previously found in two-particle correlations at middle and forward rapidity. The corresponding second-order Fourier coefficient (v2) in the transverse momentum interval between 3 and 6 GeV/c is found to be positive with a significance of about 5σ. The obtained results are similar to the J/ψ v2 coefficients measured in Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV, suggesting a common mechanism at the origin of the J/ψ v2.

Searches for transverse momentum dependent flow vector fluctuations in Pb-Pb and p-Pb collisions at the LHC - S. Acharya; D. Adamová; R. Keidel; J. Adolfsson; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; N. Ahmad; S. U. Ahn; S. Aiola; et al. (Journal of High Energy Physics, 2017)
The measurement of azimuthal correlations of charged particles is presented for Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV and p-Pb collisions at sNN‾‾‾‾√=5.02 TeV with the ALICE detector at the CERN Large Hadron Collider. These correlations are measured for the second, third and fourth order flow vector in the pseudorapidity region |η| < 0.8 as a function of centrality and transverse momentum pT using two observables, to search for evidence of pT-dependent flow vector fluctuations. For Pb-Pb collisions at 2.76 TeV, the measurements indicate that pT-dependent fluctuations are only present for the second order flow vector. Similar results have been found for p-Pb collisions at 5.02 TeV. These measurements are compared to hydrodynamic model calculations with event-by-event geometry fluctuations in the initial state to constrain the initial conditions and transport properties of the matter created in Pb-Pb and p-Pb collisions.

Systematic studies of correlations between different order flow harmonics in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - S. Acharya; J. Adam; Ralf Keidel; D. Adamova (2017)
The correlations between event-by-event fluctuations of anisotropic flow harmonic amplitudes have been measured in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV with the ALICE detector at the LHC. The results are reported in terms of multiparticle correlation observables dubbed Symmetric Cumulants. These observables are robust against biases originating from nonflow effects. The centrality dependence of correlations between the higher order harmonics (the quadrangular v4 and pentagonal v5 flow) and the lower order harmonics (the elliptic v2 and triangular v3 flow) is presented. The transverse momentum dependence of correlations between v3 and v2 and between v4 and v2 is also reported. The results are compared to calculations from viscous hydrodynamics and A Multi-Phase Transport (AMPT) model calculations. The comparisons to viscous hydrodynamic models demonstrate that the different order harmonic correlations respond differently to the initial conditions and the temperature dependence of the ratio of shear viscosity to entropy density (η/s). A small average value of η/s is favored independent of the specific choice of initial conditions in the models. The calculations with the AMPT initial conditions yield results closest to the measurements. Correlations between the magnitudes of v2, v3 and v4 show moderate pT dependence in mid-central collisions. Together with existing measurements of individual flow harmonics, the presented results provide further constraints on the initial conditions and the transport properties of the system produced in heavy-ion collisions.

Λ+c production in pp collisions at s√=7 TeV and in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - S. Acharya; F. T. Acosta; Ralf Keidel; D. Adamova (2017)
The pT-differential production cross section of prompt Λ+c charmed baryons was measured with the ALICE detector at the Large Hadron Collider (LHC) in pp collisions at s√=7 TeV and in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV at midrapidity. The Λ+c and Λ⎯⎯⎯⎯−c were reconstructed in the hadronic decay modes Λ+c→pK−π+, Λ+c→pK0S and in the semileptonic channel Λ+c→e+νeΛ (and charge conjugates). The measured values of the Λ+c/D0 ratio, which is sensitive to the c-quark hadronisation mechanism, and in particular to the production of baryons, are presented and are larger than those measured previously in different colliding systems, centre-of-mass energies, rapidity and pT intervals, where the Λ+c production process may differ. The results are compared with the expectations obtained from perturbative Quantum Chromodynamics calculations and Monte Carlo event generators. Neither perturbative QCD calculations nor Monte Carlo models reproduce the data, indicating that the fragmentation of heavy-flavour baryons is not well understood. The first measurement at the LHC of the Λ+c nuclear modification factor, RpPb, is also presented. The RpPb is found to be consistent with unity and with that of D mesons within the uncertainties, and consistent with a theoretical calculation that includes cold nuclear matter effects and a calculation that includes charm quark interactions with a deconfined medium.

π0 and η meson production in proton-proton collisions at s√=8 TeV - S. Acharya; J. Adam; R. Keidel; D. Adamova (2017)
An invariant differential cross section measurement of inclusive π0 and η meson production at mid-rapidity in pp collisions at s√=8 TeV was carried out by the ALICE experiment at the LHC. The spectra of neutral mesons π0 and η were measured in transverse momentum ranges of 0.3<pT<35 GeV/c and 0.5<pT<35 GeV/c, respectively. Next-to-leading order perturbative QCD calculations using fragmentation functions DSS14 for π0 and AESSS for η overestimate the cross sections of both neutral mesons, but agree with the measured η/π0 ratio within uncertainties. The results are also compared with PYTHIA8.2 predictions for which the Monash2013 tune yields the best agreement with the measured neutral meson spectra. The measurements confirm a universal behavior of the η/π0 ratio seen for NA27, PHENIX and ALICE data for pp collisions from s√=27.5 GeV to s√=8 TeV within experimental uncertainties. A relation between the π0 and η production cross sections for pp collisions at s√=8 TeV is given by mT scaling for pT>3.5 GeV/c. However, a deviation from this empirical scaling law is observed for transverse momenta below pT<3.5 GeV/c in the η/π0 ratio with a significance of 6.2σ.

Insight into particle production mechanisms via angular correlations of identified particles in pp collisions at s√=7 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2016)
Two-particle angular correlations were measured in pp collisions at s√=7 TeV. The analysis was carried out for pions, kaons, protons, and lambdas, for all particle/anti-particle combinations in the pair. Data for mesons exhibit an expected peak dominated by effects associated with mini-jets and are well reproduced by general purpose Monte Carlo generators. However, for baryon–baryon and anti-baryon–anti-baryon pairs, where both particles have the same baryon number, a near-side anti-correlation structure is observed instead of a peak. This effect is interpreted in the context of baryon production mechanisms in the fragmentation process. It currently presents a challenge to Monte Carlo models and its origin remains an open question.

Centrality dependence of the charged-particle multiplicity density at mid-rapidity in Pb-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (PHYSICAL REVIEW LETTERS, 2016)
The pseudorapidity density of charged particles (dNch/dη) at mid-rapidity in Pb-Pb collisions has been measured at a center-of-mass energy per nucleon pair of sNN‾‾‾‾√ = 5.02 TeV. It increases with centrality and reaches a value of 1943±54 in |η|<0.5 for the 5% most central collisions. A rise in dNch/dη as a function of sNN‾‾‾‾√ for the most central collisions is observed, steeper than that observed in proton-proton collisions and following the trend established by measurements at lower energy. The centrality dependence of dNch/dη as a function of the average number of participant nucleons, ⟨Npart⟩, calculated in a Glauber model, is compared with the previous measurement at lower energy. A constant factor of about 1.2 describes the increase in 2⟨Npart⟩⟨dNch/dη⟩ from sNN‾‾‾‾√ = 2.76 TeV to sNN‾‾‾‾√ = 5.02 TeV for all centrality intervals, within the measured range of 0-80% centrality. The results are also compared to models based on different mechanisms for particle production in nuclear collisions. arXiv:1512.06104 [nucl-ex]

Anisotropic Flow of Charged Particles in Pb-Pb Collisions at sNN=5.02 TeV - J. Adam; D. Adamová; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; S. Aiola; A. Akindinov; S. N. Alam; et al. (Phys. Rev. Lett., 2016)
We report the first results of elliptic (v2), triangular (v3), and quadrangular (v4) flow of charged particles in Pb-Pb collisions at a center-of-mass energy per nucleon pair of sNN=5.02 TeV with the ALICE detector at the CERN Large Hadron Collider. The measurements are performed in the central pseudorapidity region |η|<0.8 and for the transverse momentum range 0.2<pT<5 GeV/c. The anisotropic flow is measured using two-particle correlations with a pseudorapidity gap greater than one unit and with the multiparticle cumulant method. Compared to results from Pb-Pb collisions at sNN=2.76 TeV, the anisotropic flow coefficients v2, v3, and v4 are found to increase by (3.0±0.6)%, (4.3±1.4)%, and (10.2±3.8)%, respectively, in the centrality range 0%-50%. This increase can be attributed mostly to an increase of the average transverse momentum between the two energies. The measurements are found to be compatible with hydrodynamic model calculations. This comparison provides a unique opportunity to test the validity of the hydrodynamic picture and the power to further discriminate between various possibilities for the temperature dependence of shear viscosity to entropy density ratio of the produced matter in heavy-ion collisions at the highest energies.

Anomalous evolution of the near-side jet peak shape in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2016)
The measurement of two-particle angular correlations is a powerful tool to study jet quenching in a pT region inaccessible by direct jet identification. In these measurements pseudorapidity (Δη) and azimuthal (Δφ) differences are used to extract the shape of the near-side peak formed by particles associated to a higher pT trigger particle (1<pT,trig< 8 GeV/c). A combined fit of the near-side peak and long-range correlations is applied to the data allowing the extraction of the centrality evolution of the peak shape in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV. A significant broadening of the peak in the Δη direction at low pT is found from peripheral to central collisions, which vanishes above 4 GeV/c, while in the Δφ direction the peak is almost independent of centrality. For the 10% most central collisions and 1<pT,assoc< 2 GeV/c, 1<pT,trig< 3 GeV/c a novel feature is observed: a depletion develops around the centre of the peak. The results are compared to pp collisions at the same centre of mass energy and to AMPT model simulations. The comparison to the investigated models suggests that the broadening and the development of the depletion is connected to the strength of radial and longitudinal flow.

Azimuthal anisotropy of charged jet production in View the MathML sourcesNN=2.76 TeV Pb-Pb collisions - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Physics Letters B, 2016)
We present measurements of the azimuthal dependence of charged jet production in central and semi-central View the MathML sourcesNN=2.76 TeV Pb-Pb collisions with respect to the second harmonic event plane, quantified as View the MathML sourcev2ch jet. Jet finding is performed employing the anti-kTkT algorithm with a resolution parameter R=0.2R=0.2 using charged tracks from the ALICE tracking system. The contribution of the azimuthal anisotropy of the underlying event is taken into account event-by-event. The remaining (statistical) region-to-region fluctuations are removed on an ensemble basis by unfolding the jet spectra for different event plane orientations independently. Significant non-zero View the MathML sourcev2ch jet is observed in semi-central collisions (30-50% centrality) for View the MathML source20<pTch jet<90 GeV/c. The azimuthal dependence of the charged jet production is similar to the dependence observed for jets comprising both charged and neutral fragments, and compatible with measurements of the v2v2 of single charged particles at high pTpT. Good agreement between the data and predictions from JEWEL, an event generator simulating parton shower evolution in the presence of a dense QCD medium, is found in semi-central collisions.

Centrality dependence of charged jet production in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - J. Adam; D. Adamová; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; S. Aiola; A. Akindinov; S. N. Alam; et al. (Eur. Phys. J. C, 2016)
Measurements of charged jet production as a function of centrality are presented for p-Pb collisions recorded at sNN‾‾‾‾√=5.02 TeV with the ALICE detector. Centrality classes are determined via the energy deposit in neutron calorimeters at zero degree, close to the beam direction, to minimise dynamical biases of the selection. The corresponding number of participants or binary nucleon-nucleon collisions is determined based on the particle production in the Pb-going rapidity region. Jets have been reconstructed in the central rapidity region from charged particles with the anti-kT algorithm for resolution parameters R=0.2 and R=0.4 in the transverse momentum range 20 to 120 GeV/c. The reconstructed jet momentum and yields have been corrected for detector effects and underlying-event background. In the five centrality bins considered, the charged jet production in p-Pb collisions is consistent with the production expected from binary scaling from pp collisions. The ratio of jet yields reconstructed with the two different resolution parameters is also independent of the centrality selection, demonstrating the absence of major modifications of the radial jet structure in the reported centrality classes.

Centrality dependence of pion freeze-out radii in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (PHYSICAL REVIEW C, 2016)
We report on the measurement of freeze-out radii for pairs of identical-charge pions measured in Pb–Pb collisions at sNN‾‾‾‾√=2.76 TeV as a function of collision centrality and the average transverse momentum of the pair kT. Three-dimensional sizes of the system (femtoscopic radii), as well as direction-averaged one-dimensional radii are extracted. The radii decrease with kT, following a power-law behavior. This is qualitatively consistent with expectations from a collectively expanding system, produced in hydrodynamic calculations. The radii also scale linearly with ⟨dNch/dη⟩1/3. This behaviour is compared to world data on femtoscopic radii in heavy-ion collisions. While the dependence is qualitatively similar to results at smaller sNN‾‾‾‾√, a decrease in the Rout/Rside ratio is seen, which is in qualitative agreement with specific predictions from hydrodynamic models. The results provide further evidence for the production of a collective, strongly coupled system in heavy-ion collisions at the LHC.

Centrality dependence of the pseudorapidity density distribution for charged particles in Pb-Pb collisions at sNN‾‾‾‾√=5.02 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2016)
We present the charged-particle pseudorapidity density in Pb-Pb collisions at sNN‾‾‾‾√=5.02TeV in centrality classes measured by ALICE. The measurement covers a wide pseudorapidity range from −3.5 to 5, which is sufficient for reliable estimates of the total number of charged particles produced in the collisions. For the most central (0-5%) collisions we find 21400±1300 while for the most peripheral (80-90%) we find 230±38. This corresponds to an increase of (27±4)% over the results at sNN‾‾‾‾√=2.76TeV previously reported by ALICE. The energy dependence of the total number of charged particles produced in heavy-ion collisions is found to obey a modified power-law like behaviour. The charged-particle pseudorapidity density of the most central collisions is compared to model calculations — none of which fully describes the measured distribution. We also present an estimate of the rapidity density of charged particles. The width of that distribution is found to exhibit a remarkable proportionality to the beam rapidity, independent of the collision energy from the top SPS to LHC energies.

Centrality dependence of ψ(2S) suppression in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - J. Adam; D. Adamová; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; S. Aiola; A. Akindinov; S. N. Alam; et al. (Journal of High Energy Physics, 2016)
The inclusive production of the ψ(2S) charmonium state was studied as a function of centrality in p-Pb collisions at the nucleon-nucleon center of mass energy s√NN=5.02 TeV at the CERN LHC. The measurement was performed with the ALICE detector in the center of mass rapidity ranges −4.46 < ycms < −2.96 and 2.03 < ycms < 3.53, down to zero transverse momentum, by reconstructing the ψ(2S) decay to a muon pair. The ψ(2S) production cross section σψ(2S) is presented as a function of the collision centrality, which is estimated through the energy deposited in forward rapidity calorimeters. The relative strength of nuclear effects on the ψ(2S) and on the corresponding 1S charmonium state J/ψ is then studied by means of the double ratio of cross sections [σψ(2S) /σJ/ψ ]pPb /[σψ(2S) /σJ/ψ ]pp between p-Pb and pp collisions, and by the values of the nuclear modification factors for the two charmonium states. The results show a large suppression of ψ(2S) production relative to the J/ψ at backward (negative) rapidity, corresponding to the flight direction of the Pb-nucleus, while at forward (positive) rapidity the suppressions of the two states are comparable. Finally, comparisons to results from lower energy experiments and to available theoretical models are presented.

Charge-dependent flow and the search for the Chiral Magnetic Wave in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (PHYSICAL REVIEW C, 2016)
We report on measurements of a charge-dependent flow using a novel three-particle correlator with ALICE in Pb-Pb collisions at the LHC, and discuss the implications for observation of local parity violation and the Chiral Magnetic Wave (CMW) in heavy-ion collisions. Charge-dependent flow is reported for different collision centralities as a function of the event charge asymmetry. While our results are in qualitative agreement with expectations based on the CMW, the nonzero signal observed in higher harmonics correlations indicates a possible significant background contribution. We also present results on a differential correlator, where the flow of positive and negative charges is reported as a function of the mean charge of the particles and their pseudorapidity separation. We argue that this differential correlator is better suited to distinguish the differences in positive and negative charges expected due to the CMW and the background effects, such as local charge conservation coupled with strong radial and anisotropic flow. arXiv:1512.05739 [nucl-ex]

Correlated event-by-event fluctuations of flow harmonics in Pb-Pb collisions at sNN‾‾‾√=2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Phys. Rev. Lett., 2016)
We report the measurements of correlations between event-by-event fluctuations of amplitudes of anisotropic flow harmonics in nucleus-nucleus collisions, obtained for the first time using a new analysis method based on multiparticle cumulants in mixed harmonics. This novel method is robust against systematic biases originating from non-flow effects and by construction any dependence on symmetry planes is eliminated. We demonstrate that correlations of flow harmonics exhibit a better sensitivity to medium properties than the individual flow harmonics. The new measurements are performed in Pb-Pb collisions at the centre-of-mass energy per nucleon pair of sNN‾‾‾√=2.76 TeV by the ALICE experiment at the Large Hadron Collider (LHC). The centrality dependence of correlation between event-by-event fluctuations of the elliptic, v2, and quadrangular, v4, flow harmonics, as well as of anti-correlation between v2 and triangular, v3, flow harmonics are presented. The results cover two different regimes of the initial state configurations: geometry-dominated (in mid-central collisions) and fluctuation-dominated (in the most central collisions). Comparisons are made to predictions from MC-Glauber, viscous hydrodynamics, AMPT and HIJING models. Together with the existing measurements of individual flow harmonics the presented results provide further constraints on initial conditions and the transport properties of the system produced in heavy-ion collisions.

D-meson production in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV and in pp collisions at s√=7 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Phys. Rev. C, 2016)
The production cross sections of the prompt charmed mesons D0, D+, D∗+ and Ds were measured at mid-rapidity in p-Pb collisions at a centre-of-mass energy per nucleon pair sNN‾‾‾‾√=5.02 TeV with the ALICE detector at the LHC. D mesons were reconstructed from their decays D0→K−π+, D+→K−π+π+, D∗+→D0π+, D+s→ϕπ+→K−K+π+, and their charge conjugates. The pT-differential production cross sections were measured at mid-rapidity in the interval 1<pT<24 GeV/c for D0, D+ and D∗+ mesons and in 2<pT<12 GeV/c for Ds mesons, using an analysis method based on the selection of decay topologies displaced from the interaction vertex. The production cross sections of the D0, D+ and D∗+ mesons were also measured in three pT intervals as a function of the rapidity ycms in the centre-of-mass system in −1.26<ycms<0.34. In addition, the prompt D0 cross section was measured in pp collisions at s√=7 TeV and p-Pb collisions at sNN‾‾‾‾√=5.02 TeV down to pT=0 using an analysis technique that is based on the estimation and subtraction of the combinatorial background, without reconstruction of the D0 decay vertex. The nuclear modification factor RpPb(pT), defined as the ratio of the pT-differential D-meson cross section in p-Pb collisions and that in pp collisions scaled by the mass number of the Pb nucleus, was calculated for the four D-meson species and found to be compatible with unity within experimental uncertainties. The results are compared to theoretical calculations that include cold-nuclear-matter effects and to transport model calculations incorporating the interactions of charm quarks with an expanding deconfined medium.

Determination of the event collision time with the ALICE detector at the LHC - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Eur. Phys. J. Plus, 2016)
Particle identification is an important feature of the ALICE detector at the LHC. In particular, for particle identification via the time-of-flight technique, the precise determination of the event collision time represents an important ingredient of the quality of the measurement. In this paper, the different methods used for such a measurement in ALICE by means of the T0 and the TOF detectors are reviewed. Efficiencies, resolution and the improvement of the particle identification separation power of the methods used are presented for the different LHC colliding systems (pp , p-Pb and Pb-Pb) during the first period of data taking of LHC (Run 1).

Direct photon production in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Physics Letters B, 2016)
Direct photon production at mid-rapidity in Pb-Pb collisions at sNN‾‾‾√=2.76 TeV was studied in the transverse momentum range 0.9<pT<14 GeV/c. Photons were detected with the highly segmented electromagnetic calorimeter PHOS and via conversions in the ALICE detector material with the e+e− pair reconstructed in the central tracking system. The results of the two methods were combined and direct photon spectra were measured for the 0-20%, 20-40%, and 40-80% centrality classes. For all three classes, agreement was found with perturbative QCD calculations for pT≳5 GeV/c. Direct photon spectra down to pT≈1 GeV/c could be extracted for the 20-40% and 0-20% centrality classes. The significance of the direct photon signal for 0.9<pT<2.1 GeV/c is 2.6σ for the 0-20% class. The spectrum in this pT range and centrality class can be described by an exponential with an inverse slope parameter of (297±12stat±41syst) MeV. State-of-the-art models for photon production in heavy-ion collisions agree with the data within uncertainties. https://arxiv.org/abs/1509.07324 arXiv:1509.07324 [nucl-ex]

Elliptic flow of electrons from heavy-flavour hadron decays at mid-rapidity in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Journal of High Energy Physics, 2016)
The elliptic flow of electrons from heavy-flavour hadron decays at mid-rapidity (|y| < 0.7) is measured in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV with ALICE at the LHC. The particle azimuthal distribution with respect to the reaction plane can be parametrized with a Fourier expansion, where the second coefficient (v2) represents the elliptic flow. The v2 coefficient of inclusive electrons is measured in three centrality classes (0-10%, 10-20% and 20-40%) with the event plane and the scalar product methods in the transverse momentum (pT) intervals 0.5-13 GeV/c and 0.5-8 GeV/c, respectively. After subtracting the background, mainly from photon conversions and Dalitz decays of neutral mesons, a positive v2 of electrons from heavy-flavour hadron decays is observed in all centrality classes, with a maximum significance of 5.9σ in the interval 2< pT < 2.5 GeV/c in semi-central collisions (20-40%). The value of v2 decreases towards more central collisions at low and intermediate pT (0.5 < pT < 3 GeV/c). The v2 of electrons from heavy-flavour hadron decays at mid-rapidity is found to be similar to the one of muons from heavy-flavour hadron decays at forward rapidity (2.5 < y < 4). The results are described within uncertainties by model calculations including substantial elastic interactions of heavy quarks with an expanding strongly-interacting medium.

Elliptic flow of muons from heavy-flavour hadron decays at forward rapidity in Pb-Pb collisions at sNN=2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Physics Letters B, 2016)
The elliptic flow, v2, of muons from heavy-flavour hadron decays at forward rapidity (2.5<y<4) is measured in Pb–Pb collisions at sNN‾‾‾‾√=2.76 TeV with the ALICE detector at the LHC. The scalar product, two- and four-particle Q cumulants and Lee-Yang zeros methods are used. The dependence of the v2 of muons from heavy-flavour hadron decays on the collision centrality, in the range 0–40%, and on transverse momentum, pT, is studied in the interval 3<pT<10GeV/c. A positive v2 is observed with the scalar product and two-particle Q cumulants in semi-central collisions (10–20% and 20–40% centrality classes) for the pT interval from 3 to about 5 GeV/c. The v2 magnitude tends to decrease towards more central collisions and with increasing pT. It becomes compatible with zero in the interval 6<pT<10 GeV/c. The results are compared to models describing the interaction of heavy quarks and open heavy-flavour hadrons with the high-density medium formed in high-energy heavy-ion collisions. The model calculations describe the measured v2 within uncertainties.

Event shape engineering for inclusive spectra and elliptic flow in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (PHYSICAL REVIEW C, 2016)
We report on results obtained with the Event Shape Engineering technique applied to Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV. By selecting events in the same centrality interval, but with very different average flow, different initial state conditions can be studied. We find the effect of the event-shape selection on the elliptic flow coefficient v2 to be almost independent of transverse momentum pT, as expected if this effect is due to fluctuations in the initial geometry of the system. Charged hadron, pion, kaon, and proton transverse momentum distributions are found to be harder in events with higher-than-average elliptic flow, indicating an interplay between radial and elliptic flow. https://arxiv.org/abs/1507.06194

Evolution of the longitudinal and azimuthal structure of the near-side jet peak in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2016)
In two-particle angular correlation measurements, jets give rise to a near-side peak, formed by particles associated to a higher pT trigger particle. Measurements of these correlations as a function of pseudorapidity (Δη) and azimuthal (Δφ) differences are used to extract the centrality and pT dependence of the shape of the near-side peak in the pT range 1<pT< 8 GeV/c in Pb-Pb and pp collisions at sNN‾‾‾‾√ = 2.76 TeV. A combined fit of the near-side peak and long-range correlations is applied to the data and the peak shape is quantified by the variance of the distributions. While the width of the peak in the Δφ direction is almost independent of centrality, a significant broadening in the Δη direction is found from peripheral to central collisions. This feature is prominent for the low pT region and vanishes above 4 GeV/c. The widths measured in peripheral collisions are equal to those in pp in the Δφ direction and above 3 GeV/c in the Δη direction. Furthermore, for the 10% most central collisions and 1<pT,assoc< 2 GeV/c, 1<pT,trig< 3 GeV/c a departure from a Gaussian shape is found: a depletion develops around the centre of the peak. The results are compared to AMPT model simulations as well as other theoretical calculations indicating that the broadening and the development of the depletion is connected to the strength of radial and longitudinal flow.

Higher harmonic flow coefficients of identified hadrons in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Journal of High Energy Physics, 2016)
The elliptic, triangular, quadrangular and pentagonal anisotropic flow coefficients for π±, K± and p+p⎯⎯⎯ in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV were measured with the ALICE detector at the Large Hadron Collider. The results were obtained with the Scalar Product method, correlating the identified hadrons with reference particles from a different pseudorapidity region. Effects not related to the common event symmetry planes (non-flow) were estimated using correlations in pp collisions and were subtracted from the measurement. The obtained flow coefficients exhibit a clear mass ordering for transverse momentum (pT) values below ≈ 3 GeV/c. In the intermediate pT region (3<pT<6 GeV/c), particles group at an approximate level according to the number of constituent quarks, suggesting that coalescence might be the relevant particle production mechanism in this region. The results for pT<3 GeV/c are described fairly well by a hydrodynamical model (iEBE-VISHNU) that uses initial conditions generated by A Multi-Phase Transport model (AMPT) and describes the expansion of the fireball using a value of 0.08 for the ratio of shear viscosity to entropy density (η/s), coupled to a hadronic cascade model (UrQMD). Finally, expectations from AMPT alone fail to quantitatively describe the measurements for all harmonics throughout the measured transverse momentum region. However, the comparison to the AMPT model highlights the importance of the late hadronic rescattering stage to the development of the observed mass ordering at low values of pT and of coalescence as a particle production mechanism for the particle type grouping at intermediate values of pT for all harmonics.

Inclusive quarkonium production at forward rapidity in pp collisions at s√=8 TeV - J. Adam; D. Adamova; Ralf Keidel; M. Aggarwal (The European Physical Journal C, 2016)
We report on the inclusive production cross sections of J/ψ, ψ(2S), Υ(1S), Υ(2S) and Υ(3S), measured at forward rapidity with the ALICE detector in pp collisions at a center-of-mass energy s√=8 TeV. The analysis is based on data collected at the LHC and corresponds to an integrated luminosity of 1.28 pb−1. Quarkonia are reconstructed in the dimuon-decay channel. The differential production cross sections are measured as a function of the transverse momentum pT and rapidity y, over the pT ranges 0<pT<20 GeV/c for J/ψ, 0<pT<12 GeV/c for all other resonances, and for 2.5<y<4. The cross sections, integrated over pT and y, and assuming unpolarized quarkonia, are σJ/ψ=8.63±0.04±0.79 μb, σψ(2S)=1.18±0.08±0.21 μb, σΥ(1S)=68±6±7 nb, σΥ(2S)=25±5±4 nb and σΥ(3S)=9±4±1 nb, where the first uncertainty is statistical and the second one is systematic. These values agree, within at most 1.2σ, with measurements performed by the LHCb collaboration in the same rapidity range. arXiv:1509.08258 [hep-ex]

Jet-like correlations with neutral pion triggers in pp and central Pb-Pb collisions at 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Physics Letters B, 2016)
We present measurements of two-particle correlations with neutral pion trigger particles of transverse momenta 8<ptrigT<16 GeV/c and associated charged particles of 0.5<passocT<10 GeV/c versus the azimuthal angle difference Δφ at midrapidity in pp and central Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV with ALICE. The new measurements exploit associated charged hadrons down to 0.5 GeV/c, which significantly extends our previous measurement that only used charged hadrons above 3 GeV/c. After subtracting the contributions of the flow background, v2 to v5, the per-trigger yields are extracted for |Δφ|<0.7 on the near and for |Δφ−π|<1.1 on the away side. The ratio of per-trigger yields in Pb–Pb to those in pp collisions, IAA, is measured on the near and away side for the 0–10% most central Pb–Pb collisions. On the away side, the per-trigger yields in Pb–Pb are strongly suppressed to the level of IAA≈0.6 for passocT>3 GeV/c, while with decreasing momenta an enhancement develops reaching about 5 at low passocT. On the near side, an enhancement of IAA between 1.2 at the highest to 1.8 at the lowest passocT is observed. The data are compared to parton-energy-loss predictions of the JEWEL and AMPT event generators, as well as to a perturbative QCD calculation with medium-modified fragmentation functions. All calculations qualitatively describe the away-side suppression at high passocT. Only AMPT captures the enhancement at low passocT, both on the near and away side. However, it also underpredicts IAA above 5 GeV/c, in particular on the near-side.

Measurement of an excess in the yield of J/ψ at very low pT in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - J. Adam; D. Adamova; Ralf Keidel; M. Aggarwal (PHYSICAL REVIEW LETTERS, 2016)
We report on the first measurement of an excess in the yield of J/ψ at very low transverse momentum (pT<0.3 GeV/c) in peripheral hadronic Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV, performed by ALICE at the CERN LHC. Remarkably, the measured nuclear modification factor (RAA) of J/ψ in the rapidity range 2.5<y<4 reaches about 7 (2) in the pT range 0-0.3 GeV/c in the 70-90% (50-70%) centrality class. The J/ψ production cross section associated with the observed excess is obtained under the hypothesis that coherent photoproduction of J/ψ is the underlying physics mechanism. If confirmed, the observation of J/ψ coherent photoproduction in Pb-Pb collisions at impact parameters smaller than twice the nuclear radius opens new theoretical and experimental challenges and opportunities. In particular, coherent photoproduction accompanying hadronic collisions may provide insight into the dynamics of photoproduction and nuclear reactions, as well as become a novel probe of the Quark-Gluon Plasma.

Measurement of D-meson production versus multiplicity in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (JHEP, 2016)
The measurement of prompt D-meson production as a function of multiplicity in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV with the ALICE detector at the LHC is reported. D0, D+ and D∗+ mesons are reconstructed via their hadronic decay channels in the centre-of-mass rapidity range −0.96<ycms<0.04 and transverse momentum interval 1<pT<24 GeV/c. The multiplicity dependence of D-meson production is examined by either comparing yields in p-Pb collisions in different event classes, selected based on the multiplicity of produced particles or zero-degree energy, with those in pp collisions, scaled by the number of binary nucleon-nucleon collisions (nuclear modification factor); as well as by evaluating the per-event yields in p-Pb collisions in different multiplicity intervals normalised to the multiplicity-integrated ones (relative yields). The nuclear modification factors for D0, D+ and D∗+ are consistent with one another. The D-meson nuclear modification factors as a function of the zero-degree energy are consistent with unity within uncertainties in the measured pT regions and event classes. The relative D-meson yields, calculated in various pT intervals, increase as a function of the charged-particle multiplicity. The results are compared with the equivalent pp measurements at s√=7 TeV as well as with EPOS3 calculations.

Measurement of electrons from beauty-hadron decays in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV and Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2016)
The production of beauty hadrons was measured via semi-leptonic decays at mid-rapidity with the ALICE detector at the LHC in the transverse momentum interval 1<pT<8 GeV/c in minimum-bias p-Pb collisions at sNN‾‾‾‾√=5.02 TeV and in 1.3<pT<8 GeV/c in the 20% most central Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV. The pp reference spectra at s√=5.02 TeV and s√=2.76 TeV, needed for the calculation of the nuclear modification factors RpPb and RPbPb, were obtained by a pQCD-driven scaling of the cross section of electrons from beauty-hadron decays measured at s√=7 TeV. The RPbPb is about 0.7 with an uncertainty of about 30% in the interval 3<pT<6 GeV/c and 0.47 with an uncertainty of 25% in 6<pT<8 GeV/c in Pb-Pb collisions. Below pT=3 GeV/c, the RPbPb values increase with decreasing transverse momentum with systematic uncertainties of 30-45%. The RpPb is consistent with unity within systematic uncertainties of about 20% at high pT, increasing at low pT, and is well described by theoretical calculations that include cold nuclear matter effects in p-Pb collisions. The measured RpPb and these calculations indicate that cold nuclear matter effects are small at high transverse momentum also in Pb-Pb collisions. Therefore, the observed reduction of RPbPb below unity for high pT can be ascribed to an effect of the hot and dense medium formed in Pb-Pb collisions.

Measurement of electrons from heavy-flavour hadron decays in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Physics Letters B, 2016)
The production of electrons from heavy-flavour hadron decays was measured as a function of transverse momentum (pT) in minimum-bias p-Pb collisions at sNN‾‾‾‾√=5.02 TeV with ALICE at the LHC. The measurement covers the pT interval 0.5<pT<12 GeV/c and the rapidity range −1.06<ycms<0.14 in the centre-of-mass reference frame. The contribution of electrons from background sources was subtracted using an invariant mass approach. The nuclear modification factor RpPb was calculated by comparing the pT-differential invariant cross section in p-Pb collisions to a pp reference at the same centre-of-mass energy, which was obtained by interpolating measurements at s√=2.76 TeV and s√=7 TeV. The RpPb is consistent with unity within uncertainties of about 25%, which become larger for pT below 1 GeV/c. The data are described by recent model calculations that include cold nuclear matter effects.

Measurement of the production of high-pT electrons from heavy-flavour hadron decays in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Physics Letters B, 2016)
Electrons from heavy-flavour hadron decays (charm and beauty) were measured with the ALICE detector in Pb-Pb collisions at a centre-of-mass of energy sNN‾‾‾‾√=2.76 TeV. The transverse momentum (pT) differential production yields at mid-rapidity were used to calculate the nuclear modification factor RAA in the interval 3<pT<18 GeV/c. The RAA shows a strong suppression compared to binary scaling of pp collisions at the same energy (up to a factor of 4) in the 10% most central Pb-Pb collisions. There is a centrality trend of suppression, and a weaker suppression (down to a factor of 2) in semi-peripheral (50-80%) collisions is observed. The suppression of electrons in this broad pT interval indicates that both charm and beauty quarks lose energy when they traverse the hot medium formed in Pb-Pb collisions at LHC. arXiv:1609.07104 [nucl-ex]

Measurement of transverse energy at midrapidity in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Phys. Rev. C, 2016)
We report the transverse energy (ET) measured with ALICE at midrapidity in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV as a function of centrality. The transverse energy was measured using identified single particle tracks. The measurement was cross checked using the electromagnetic calorimeters and the transverse momentum distributions of identified particles previously reported by ALICE. The results are compared to theoretical models as well as to results from other experiments. The mean ET per unit pseudorapidity (η), ⟨dET/dη⟩, in 0-5% central collisions is 1737 ± 6(stat.) ± 97(sys.) GeV. We find a similar centrality dependence of the shape of ⟨dET/dη⟩ as a function of the number of participating nucleons to that seen at lower energies. The growth in ⟨dET/dη⟩ at the LHC sNN‾‾‾‾√ exceeds extrapolations of low energy data. We observe a nearly linear scaling of ⟨dET/dη⟩ with the number of quark participants. With the canonical assumption of a 1 fm/c formation time, we estimate that the energy density in 0-5% central Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV is 12.3 ± 1.0 GeV/fm3and that the energy density at the most central 80 fm2 of the collision is at least 21.5 ± 1.7 GeV/fm3. This is roughly 2.3 times that observed in 0-5% central Au-Au collisions at sNN‾‾‾‾√ = 200 GeV.

Multipion Bose-Einstein correlations in pp, p-Pb, and Pb-Pb collisions at the LHC - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (PHYSICAL REVIEW C, 2016)
Three- and four-pion Bose-Einstein correlations are presented in pp, p-Pb, and Pb-Pb collisions at the LHC. We compare our measured four-pion correlations to the expectation derived from two- and three-pion measurements. Such a comparison provides a method to search for coherent pion emission. We also present mixed-charge correlations in order to demonstrate the effectiveness of several analysis procedures such as Coulomb corrections. Same-charge four-pion correlations in pp and p-Pb appear consistent with the expectations from three-pion measurements. However, the presence of non-negligible background correlations in both systems prevent a conclusive statement. In Pb-Pb collisions, we observe a significant suppression of three- and four-pion Bose-Einstein correlations compared to expectations from two-pion measurements. There appears to be no centrality dependence of the suppression within the 0-50% centrality interval. The origin of the suppression is not clear. However, by postulating either coherent pion emission or large multibody Coulomb effects, the suppression may be explained. https://arxiv.org/abs/1512.08902

Multiplicity and transverse momentum evolution of charge-dependent correlations in pp, p-Pb, and Pb-Pb collisions at the LHC - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (The European Physical Journal C, 2016)
We report on two-particle charge-dependent correlations in pp, p-Pb, and Pb-Pb collisions as a function of the pseudorapidity and azimuthal angle difference, Δη and Δφ respectively. These correlations are studied using the balance function that probes the charge creation time and the development of collectivity in the produced system. The dependence of the balance function on the event multiplicity as well as on the trigger and associated particle transverse momentum (pT) in pp, p-Pb, and Pb-Pb collisions at sNN‾‾‾‾√=7, 5.02, and 2.76 TeV, respectively, are presented. In the low transverse momentum region, for 0.2<pT<2.0 GeV/c, the balance function becomes narrower in both Δη and Δφ directions in all three systems for events with higher multiplicity. The experimental findings favor models that either incorporate some collective behavior (e.g. AMPT) or different mechanisms that lead to effects that resemble collective behavior (e.g. PYTHIA8 with color reconnection). For higher values of transverse momenta the balance function becomes even narrower but exhibits no multiplicity dependence, indicating that the observed narrowing with increasing multiplicity at low pT is a feature of bulk particle production. https://arxiv.org/abs/1509.07255

Multiplicity dependence of charged pion, kaon, and (anti)proton production at large transverse momentum in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - Dagmar Adamova; Ralf Keidel; Jaroslav Adam; Madan Mohan Aggarwal (Physics Letters B, 2016)
The production of charged pions, kaons and (anti)protons has been measured at mid-rapidity (−0.5<y<0) in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV using the ALICE detector at the LHC. Exploiting particle identification capabilities at high transverse momentum (pT), the previously published pT spectra have been extended to include measurements up to 20 GeV/c for seven multiplicity event classes. The pT spectra for pp collisions at s√=7 TeV, needed to interpolate a pp reference spectrum, have also been extended up to 20 GeV/c to measure the nuclear modification factor (RpPb) in non-single diffractive p-Pb collisions. At intermediate transverse momentum (2<pT<10 GeV/c) the proton-to-pion ratio increases with multiplicity in p-Pb collisions, a similar effect is not present in the kaon-to-pion ratio. The pT dependent structure of such increase is qualitatively similar to those observed in pp and heavy-ion collisions. At high pT (>10 GeV/c), the particle ratios are consistent with those reported for pp and Pb-Pb collisions at the LHC energies. At intermediate pT the (anti)proton RpPb shows a Cronin-like enhancement, while pions and kaons show little or no nuclear modification. At high pT the charged pion, kaon and (anti)proton RpPb are consistent with unity within statistical and systematic uncertainties.

Particle identification in ALICE: a Bayesian approach - J. Adam; D. Adamová; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; S. Aiola; A. Akindinov; S. N. Alam; et al. (Eur. Phys. J. Plus, 2016)
We present a Bayesian approach to particle identification (PID) within the ALICE experiment. The aim is to more effectively combine the particle identification capabilities of its various detectors. After a brief explanation of the adopted methodology and formalism, the performance of the Bayesian PID approach for charged pions, kaons and protons in the central barrel of ALICE is studied. PID is performed via measurements of specific energy loss ( dE/dx ) and time of flight. PID efficiencies and misidentification probabilities are extracted and compared with Monte Carlo simulations using high-purity samples of identified particles in the decay channels K0S→π−π+ , ϕ→K−K+ , and Λ→pπ− in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV. In order to thoroughly assess the validity of the Bayesian approach, this methodology was used to obtain corrected pT spectra of pions, kaons, protons, and D0 mesons in pp collisions at s√=7 TeV. In all cases, the results using Bayesian PID were found to be consistent with previous measurements performed by ALICE using a standard PID approach. For the measurement of D0→K−π+ , it was found that a Bayesian PID approach gave a higher signal-to-background ratio and a similar or larger statistical significance when compared with standard PID selections, despite a reduced identification efficiency. Finally, we present an exploratory study of the measurement of Λ+c→pK−π+ in pp collisions at s√=7 TeV, using the Bayesian approach for the identification of its decay products.

Production of K∗ (892)0 and ϕ (1020) in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - J. Adam; D. Adamová; M. M. Aggarwal; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; S. Aiola; A. Akindinov; S. N. Alam; et al. (Eur. Phys. J. C, 2016)
The production of K∗ (892)0 and ϕ (1020) mesons has been measured in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV. K∗0 and ϕ are reconstructed via their decay into charged hadrons with the ALICE detector in the rapidity range -0.5

Pseudorapidity dependence of the anisotropic flow of charged particles in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Phys. Lett. B, 2016)
We present measurements of the elliptic (v2), triangular (v3) and quadrangular (v4) anisotropic azimuthal flow over a wide range of pseudorapidities (−3.5<η<5). The measurements are performed with Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV using the ALICE detector at the Large Hadron Collider (LHC). The flow harmonics are obtained using two- and four-particle correlations from nine different centrality intervals covering central to peripheral collisions. We find that the shape of vn(η) is largely independent of centrality for the flow harmonics n=2−4, however the higher harmonics fall off more steeply with increasing |η|. We assess the validity of extended longitudinal scaling of v2 by comparing to lower energy measurements, and find that the higher harmonic flow coefficients are proportional to the charged particle densities at larger pseudorapidities. Finally, we compare our measurements to both hydrodynamical and transport models, and find they both have challenges when it comes to describing our data.

Study of cosmic ray events with high muon multiplicity using the ALICE detector at the CERN Large Hadron Collider - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Journal of Cosmology and Astroparticle Physics, 2016)
ALICE is one of four large experiments at the CERN Large Hadron Collider near Geneva, specially designed to study particle production in ultra-relativistic heavy-ion collisions. Located 52 meters underground with 28 meters of overburden rock, it has also been used to detect muons produced by cosmic ray interactions in the upper atmosphere. In this paper, we present the multiplicity distribution of these atmospheric muons and its comparison with Monte Carlo simulations. This analysis exploits the large size and excellent tracking capability of the ALICE Time Projection Chamber. A special emphasis is given to the study of high multiplicity events containing more than 100 reconstructed muons and corresponding to a muon areal density ρμ>5.9 m−2. Similar events have been studied in previous underground experiments such as ALEPH and DELPHI at LEP. While these experiments were able to reproduce the measured muon multiplicity distribution with Monte Carlo simulations at low and intermediate multiplicities, their simulations failed to describe the frequency of the highest multiplicity events. In this work we show that the high multiplicity events observed in ALICE stem from primary cosmic rays with energies above 1016 eV and that the frequency of these events can be successfully described by assuming a heavy mass composition of primary cosmic rays in this energy range. The development of the resulting air showers was simulated using the latest version of QGSJET to model hadronic interactions. This observation places significant constraints on alternative, more exotic, production mechanisms for these events.

Transverse momentum dependence of D-meson production in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Journal of High Physics, 2016)
The production of prompt charmed mesons D0, D+ and D∗+, and their antiparticles, was measured with the ALICE detector in Pb-Pb collisions at the centre-of-mass energy per nucleon pair, sNN‾‾‾‾√, of 2.76 TeV. The production yields for rapidity |y|<0.5 are presented as a function of transverse momentum, pT, in the interval 1-36 GeV/c for the centrality class 0-10% and in the interval 1-16 GeV/c for the centrality class 30-50%. The nuclear modification factor RAA was computed using a proton-proton reference at s√=2.76 TeV, based on measurements at s√=7 TeV and on theoretical calculations. A maximum suppression by a factor of 5-6 with respect to binary-scaled pp yields is observed for the most central collisions at pT of about 10 GeV/c. A suppression by a factor of about 2-3 persists at the highest pT covered by the measurements. At low pT (1-3 GeV/c), the RAA has large uncertainties that span the range 0.35 (factor of about 3 suppression) to 1 (no suppression). In all pT intervals, the RAA is larger in the 30-50% centrality class compared to central collisions. The D-meson RAA is also compared with that of charged pions and, at large pT, charged hadrons, and with model calculations.

W and Z boson production in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - Jarroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Journal of High Energy Physics, 2016)
The W and Z boson production was measured via the muonic decay channel in proton-lead collisions at sNN‾‾‾‾√=5.02 TeV at the Large Hadron Collider with the ALICE detector. The measurement covers backward (−4.46<ycms<−2.96) and forward (2.03<ycms<3.53) rapidity regions, corresponding to Pb-going and p-going directions, respectively. The Z-boson production cross section, with dimuon invariant mass of 60<mμμ<120 GeV/c2 and muon transverse momentum (pμT) larger than 20 GeV/c, is measured. The production cross section and charge asymmetry of muons from W-boson decays with pμT>10 GeV/c are determined. The results are compared to theoretical calculations both with and without including the nuclear modification of the parton distribution functions. The W-boson production is also studied as a function of the collision centrality: the cross section of muons from W-boson decays is found to scale with the average number of binary nucleon-nucleon collisions within uncertainties.

3ΛH and 3Λ¯H¯¯¯ production in Pb-Pb collisions at sNN−−−√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
The production of the hypertriton nuclei 3ΛH and 3Λ¯H¯¯¯ has been measured for the first time in Pb-Pb collisions at sNN−−−√ = 2.76 TeV with the ALICE experiment at LHC energies. The total yield, dN/dy ×B.R.(3ΛH→3He,π−)=(3.86±0.77(stat.)±0.68(syst.))×10−5 in the 0-10% most central collisions, is consistent with the predictions from a statistical thermal model using the same temperature as for the light hadrons. The coalescence parameter B3 shows a dependence on the transverse momentum, similar to the B2 of deuterons and the B3 of 3He nuclei. The ratio of yields S3 = 3ΛH/(3He ×Λ/p) was measured to be S3 = 0.60 ± 0.13 (stat.) ± 0.21 (syst.) in 0-10% centrality events; this value is compared to different theoretical models. The measured S3 is fully compatible with thermal model predictions. The measured 3ΛH lifetime, τ=181+54−39(stat.)±33(syst.) ps is compatible within 1σ with the world average value.

Centrality dependence of high-pT D meson suppression in Pb-Pb collisions at sNN−−−√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
The nuclear modification factor, RAA, of the prompt charmed mesons D0, D+ and D∗+, and their antiparticles, was measured with the ALICE detector in Pb-Pb collisions at a centre-of-mass energy sNN−−−√=2.76 TeV in two transverse momentum intervals, 5<pT<8 GeV/c and 8<pT<16 GeV/c, and in six collision centrality classes. The RAA shows a maximum suppression of a factor of 5-6 in the 10% most central collisions. The suppression and its centrality dependence are compatible within uncertainties with those of charged pions. A comparison with the RAA of non-prompt J/ψ from B meson decays, measured by the CMS Collaboration, hints at a larger suppression of D mesons in the most central collisions.

Centrality dependence of inclusive J/ψ production in p-Pb collisions at sNN−−−√ = 5.02 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
We present a measurement of inclusive J/ψ production in p-Pb collisions at sNN−−−√ = 5.02 TeV as a function of the centrality of the collision, as estimated from the energy deposited in the Zero Degree Calorimeters. The measurement is performed with the ALICE detector down to zero transverse momentum, pT, in the backward (−4.46<ycms<−2.96) and forward (2.03<ycms<3.53) rapidity intervals in the dimuon decay channel and in the mid-rapidity region (−1.37<ycms<0.43) in the dielectron decay channel. The backward and forward rapidity intervals correspond to the Pb-going and p-going direction, respectively. The pT-differential J/ψ production cross section at backward and forward rapidity is measured for several centrality classes, together with the corresponding average pT and p2T values. The nuclear modification factor, QpPb, is presented as a function of centrality for the three rapidity intervals, and, additionally, at backward and forward rapidity, as a function of pT for several centrality classes. At mid- and forward rapidity, the J/ψ yield is suppressed up to 40% compared to that in pp interactions scaled by the number of binary collisions. The degree of suppression increases towards central p-Pb collisions at forward rapidity, and with decreasing pT of the J/ψ. At backward rapidity, the QpPb is compatible with unity within the total uncertainties, with an increasing trend from peripheral to central p-Pb collisions.

Centrality dependence of the nuclear modification factor of charged pions, kaons, and protons in Pb-Pb collisions at sNN−−−√=2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
Transverse momentum (pT) spectra of pions, kaons, and protons up to pT=20 GeV/c have been measured in Pb-Pb collisions at sNN−−−√=2.76 TeV using the ALICE detector for six different centrality classes covering 0-80%. The proton-to-pion and the kaon-to-pion ratios both show a distinct peak at pT≈3 GeV/c in central Pb-Pb collisions that decreases towards more peripheral collisions. For pT>10 GeV/c, the nuclear modification factor is found to be the same for all three particle species in each centrality interval within systematic uncertainties of 10-20%. This suggests there is no direct interplay between the energy loss in the medium and the particle species composition in the hard core of the quenched jet. For pT<10 GeV/c, the data provide important constraints for models aimed at describing the transition from soft to hard physics.

Coherent ρ0 photoproduction in ultra-peripheral Pb–Pb collisions at sNN−−−√=2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
We report the first measurement at the LHC of coherent photoproduction of ρ0 mesons in ultra-peripheral Pb-Pb collisions. The invariant mass and transverse momentum distributions for ρ0 production are studied in the π+π− decay channel at mid-rapidity. The production cross section in the rapidity range |y|<0.5 is found to be dσ/dy=425±10(stat.) +42−50(sys.) mb. Coherent ρ0 production is studied with and without requirement of nuclear breakup, and the fractional yields for various breakup scenarios are presented. The results are compared with those from lower energies and with model predictions based on the Glauber model and the color dipole model. The measured cross section is found to be inconsistent with a scaling of the γ-nucleon cross section using the Glauber model.

Coherent ψ(2S) photo-production in ultra-peripheral PbPb collisions at sNN=2.76 TeV - J. Adam; D. Adamova; Ralf Keidel; M. Aggarwal (Physics Letters B, 2015)
We have performed the first measurement of the coherent ψ(2S)ψ(2S) photo-production cross section in ultra-peripheral Pb–Pb collisions at the LHC. This charmonium excited state is reconstructed via the ψ(2S)→l+l−ψ(2S)→l+l− and ψ(2S)→J/ψπ+π−ψ(2S)→J/ψπ+π− decays, where the J/ψJ/ψ decays into two leptons. The analysis is based on an event sample corresponding to an integrated luminosity of about 22 μb−122 μb−1. The cross section for coherent ψ(2S)ψ(2S) production in the rapidity interval −0.9<y<0.9−0.9<y<0.9 is View the MathML sourcedσψ(2S)coh/dy=0.83±0.19(stat+syst) mb. The ψ(2S)ψ(2S) to J/ψJ/ψ coherent cross section ratio is View the MathML source0.34−0.07+0.08(stat+syst). The obtained results are compared to predictions from theoretical models.

Differential studies of inclusive J/ψ and ψ(2S) production at forward rapidity in Pb-Pb collisions at sNN−−−√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
The production of J/ψ and ψ(2S) was measured with the ALICE detector in Pb-Pb collisions at the LHC. The measurement was performed at forward rapidity (2.5<y<4) down to zero transverse momentum (pT) in the dimuon decay channel. Inclusive J/ψ yields were extracted in different centrality classes and the centrality dependence of the average pT is presented. The J/ψ suppression, quantified with the nuclear modification factor (RAA), was studied as a function of centrality, transverse momentum and rapidity. Comparisons with similar measurements at lower collision energy and theoretical models indicate that the J/ψ production is the result of an interplay between color screening and recombination mechanisms in a deconfined partonic medium, or at its hadronization. Results on the ψ(2S) suppression are provided via the ratio of ψ(2S) over J/ψ measured in pp and Pb-Pb collisions.

Forward-backward multiplicity correlations in pp collisions at s√=0.9, 2.76 and 7 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; M. M. Aggarwal (2015)
The strength of forward-backward (FB) multiplicity correlations is measured by the ALICE detector in proton-proton (pp) collisions at s√=0.9, 2.76 and 7 TeV. The measurement is performed in the central pseudorapidity region (|η|<0.8) for the transverse momentum pT>0.3 GeV/c. Two separate pseudorapidity windows of width (δη) ranging from 0.2 to 0.8 are chosen symmetrically around η=0. The multiplicity correlation strength (bcor) is studied as a function of the pseudorapidity gap (ηgap) between the two windows as well as the width of these windows. The correlation strength is found to decrease with increasing ηgap and shows a non-linear increase with δη. A sizable increase of the correlation strength with the collision energy, which cannot be explained exclusively by the increase of the mean multiplicity inside the windows, is observed. The correlation coefficient is also measured for multiplicities in different configurations of two azimuthal sectors selected within the symmetric FB η-windows. Two different contributions, the short-range (SR) and the long-range (LR), are observed. The energy dependence of bcor is found to be weak for the SR component while it is strong for the LR component. Moreover, the correlation coefficient is studied for particles belonging to various transverse momentum intervals chosen to have the same mean multiplicity. Both SR and LR contributions to bcor are found to increase with pT in this case. Results are compared to PYTHIA and PHOJET event generators and to a string-based phenomenological model. The observed dependencies of bcor add new constraints on phenomenological models.

Forward-central two-particle correlations in p-Pb collisions at sNN−−−√ = 5.02 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Mahan Modan Aggarwal (2015)
Two-particle angular correlations between trigger particles in the forward pseudorapidity range (2.5<|η|<4.0) and associated particles in the central range (|η|<1.0) are measured with the ALICE detector in p-Pb collisions at a nucleon-nucleon centre-of-mass energy of 5.02 TeV. The trigger particles are reconstructed using the muon spectrometer, and the associated particles by the central barrel tracking detectors. In high-multiplicity events, the double-ridge structure, previously discovered in two-particle angular correlations at midrapidity, is found to persist to the pseudorapidity ranges studied in this Letter. The second-order Fourier coefficients for muons in high-multiplicity events are extracted after jet-like correlations from low-multiplicity events have been subtracted. The coefficients are found to have a similar transverse momentum (pT) dependence in p-going (p-Pb) and Pb-going (Pb-p) configurations, with the Pb-going coefficients larger by about 16±6%, rather independent of pT within the uncertainties of the measurement. The data are compared with calculations using the AMPT model, which predicts a different pT and η dependence than observed in the data. The results are sensitive to the parent particle v2 and composition of reconstructed muon tracks, where the contribution from heavy flavour decays are expected to dominate at pT>2 GeV/c.

Inclusive, prompt and non-prompt J/ψ production at mid-rapidity in Pb-Pb collisions at sNN−−−√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
The transverse momentum (pT) dependence of the nuclear modification factor RAA and the centrality dependence of the average transverse momentum ⟨pT⟩ for inclusive J/ψ have been measured with ALICE for Pb-Pb collisions at sNN−−−√ = 2.76 TeV in the e+e− decay channel at mid-rapidity (|y|<0.8). The ⟨pT⟩ is significantly smaller than the one observed for pp collisions at the same centre-of-mass energy. Consistently, an increase of RAA is observed towards low pT. These observations might be indicative of a sizable contribution of charm quark coalescence to the J/ψ production. Additionally, the fraction of non-prompt J/ψ from beauty hadron decays, fB, has been determined in the region 1.5<pT<10 GeV/c in three centrality intervals. No significant centrality dependence of fB is observed. Finally, the RAA of non-prompt J/ψ is discussed and compared with model predictions. The nuclear modification in the region 4.5<pT<10 GeV/c is found to be stronger than predicted by most models.

Measurement of charged jet production cross sections and nuclear modification in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; M. M. Aggarwal (2015)
A measurement of dijet correlations in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV with the ALICE detector is presented. Jets are reconstructed from charged particles measured in the central tracking detectors and neutral energy deposited in the electromagnetic calorimeter. The transverse momentum of the full jet (clustered from charged and neutral constituents) and charged jet (clustered from charged particles only) is corrected event-by-event for the contribution of the underlying event, while corrections for underlying event fluctuations and finite detector resolution are applied on an inclusive basis. A projection of the dijet transverse momentum, kTy=pch+neT,jetsin(Δφdijet) with Δφdijet the azimuthal angle between a full and charged jet and pch+neT,jet the transverse momentum of the full jet, is used to study nuclear matter effects in p-Pb collisions. This observable is sensitive to the acoplanarity of dijet production and its potential modification in p-Pb collisions with respect to pp collisions. Measurements of the dijet kTy as a function of the transverse momentum of the full and recoil charged jet, and the event multiplicity are presented. No significant modification of kTy due to nuclear matter effects in p-Pb collisions with respect to the event multiplicity or a PYTHIA8 reference is observed.

Measurement of charm and beauty production at central rapidity versus charged-particle multiplicity in proton-proton collisions at s√=7 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
Prompt D meson and non-prompt J/ψ yields are studied as a function of the multiplicity of charged particles produced in inelastic proton-proton collisions at a centre-of-mass energy of s√=7 TeV. The results are reported as a ratio between yields in a given multiplicity interval normalised to the multiplicity-integrated ones (relative yields). They are shown as a function of the multiplicity of charged particles normalised to the average value for inelastic collisions (relative charged-particle multiplicity). D0, D+ and D∗+ mesons are measured in five pT intervals from 1 to 20 GeV/c and for |y|<0.5 via their hadronic decays. The D-meson relative yield is found to increase with increasing charged-particle multiplicity. For events with multiplicity six times higher than the average multiplicity of inelastic collisions, a yield enhancement of a factor about 15 relative to the multiplicity-integrated yield in inelastic collisions is observed. The yield enhancement is independent of transverse momentum within the uncertainties of the measurement. The D0-meson relative yield is also measured as a function of the relative multiplicity at forward pseudorapidity. The non-prompt J/ψ, i.e. the B hadron, contribution to the inclusive J/ψ production is measured in the di-electron decay channel at central rapidity. It is evaluated for pT>1.3 GeV/c and |y|<0.9, and extrapolated to pT>0. The fraction of non-prompt J/ψ in the inclusive J/ψ yields shows no dependence on the charged-particle multiplicity at central rapidity. Charm and beauty hadron relative yields exhibit a similar increase with increasing charged-particle multiplicity. The measurements are compared to PYTHIA 8, EPOS 3 and percolation calculations.

Measurement of D+s production and nuclear modification factor in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (Journal of High Energy Physics, 2015)
The production of prompt D+s mesons was measured for the first time in collisions of heavy nuclei with the ALICE detector at the LHC. The analysis was performed on a data sample of Pb-Pb collisions at a centre-of-mass energy per nucleon pair, sNN‾‾‾‾√, of 2.76 TeV in two different centrality classes, namely 0-10% and 20-50%. D+s mesons and their antiparticles were reconstructed at mid-rapidity from their hadronic decay channel D+s→ϕπ+, with ϕ→K−K+, in the transverse momentum intervals 4<pT<12 GeV/c and 6<pT<12 GeV/c for the 0-10% and 20-50% centrality classes, respectively. The nuclear modification factor RAA was computed by comparing the pT-differential production yields in Pb-Pb collisions to those in proton-proton (pp) collisions at the same energy. This pp reference was obtained using the cross section measured at s√=7 TeV and scaled to s√=2.76 TeV. The RAA of D+s mesons was compared to that of non-strange D mesons in the 10% most central Pb-Pb collisions. At high pT (8<pT<12 GeV/c) a suppression of the D+s-meson yield by a factor of about three, compatible within uncertainties with that of non-strange D mesons, is observed. At lower pT (4<pT<8 GeV/c) the values of the D+s-meson RAA are larger than those of non-strange D mesons, although compatible within uncertainties. The production ratios D+s/D0 and D+s+ were also measured in Pb-Pb collisions and compared to their values in proton-proton collisions. https://arxiv.org/abs/1509.07287

Measurement of dijet kT in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; M.M. Aggarwal (2015)
A measurement of dijet correlations in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV with the ALICE detector is presented. Jets are reconstructed from charged particles measured in the central tracking detectors and neutral energy deposited in the electromagnetic calorimeter. The transverse momentum of the full jet (clustered from charged and neutral constituents) and charged jet (clustered from charged particles only) is corrected event-by-event for the contribution of the underlying event, while corrections for underlying event fluctuations and finite detector resolution are applied on an inclusive basis. A projection of the dijet transverse momentum, kTy=pch+neT,jetsin(Δφdijet) with Δφdijet the azimuthal angle between a full and charged jet and pch+neT,jet the transverse momentum of the full jet, is used to study nuclear matter effects in p-Pb collisions. This observable is sensitive to the acoplanarity of dijet production and its potential modification in p-Pb collisions with respect to pp collisions. Measurements of the dijet kTy as a function of the transverse momentum of the full and recoil charged jet, and the event multiplicity are presented. No significant modification of kTy due to nuclear matter effects in p-Pb collisions with respect to the event multiplicity or a PYTHIA8 reference is observed.

Measurement of jet quenching with semi-inclusive hadron-jet distributions in central Pb-Pb collisions at sNN−−−−√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
We report the measurement of a new observable of jet quenching in central Pb-Pb collisions at sNN−−−√=2.76 TeV, based on the semi-inclusive rate of charged jets recoiling from a high transverse momentum (high-pT) charged hadron trigger. Jets are measured using collinear-safe jet reconstruction with infrared cutoff for jet constituents of 0.15 GeV/c, for jet resolution parameters R=0.2, 0.4 and 0.5. Underlying event background is corrected at the event-ensemble level, without imposing bias on the jet population. Recoil jet spectra are reported in the range 20<pchT,jet<100 GeV/c. Reference distributions for pp collisions at s√=2.76 TeV are calculated using Monte Carlo and NLO pQCD methods, which are validated by comparing with measurements in pp collisions at s√=7 TeV. The recoil jet yield in central Pb-Pb collisions is found to be suppressed relative to that in pp collisions. No significant medium-induced broadening of the intra-jet energy profile is observed within 0.5 radians relative to the recoil jet axis. The angular distribution of the recoil jet yield relative to the trigger axis is found to be similar in central Pb-Pb and pp collisions, with no significant medium-induced acoplanarity observed. Large-angle jet deflection, which may provide a direct probe of the nature of the quasi-particles in hot QCD matter, is explored.

Measurement of jet suppression in central Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; M. M. Aggarwal (2015)
The transverse momentum (pT) spectrum and nuclear modification factor (RAA) of reconstructed jets in 0-10% and 10-30% central Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV were measured. Jets were reconstructed from charged and neutral particles, utilizing the ALICE tracking detectors and Electromagnetic Calorimeter (EMCal), with the anti-kT jet algorithm with a resolution parameter of R=0.2. The jet pT spectra are reported in the pseudorapidity interval of |ηjet|<0.5 for 40<pT,jet<120 GeV/c in 0-10% and for 30<pT,jet<100 GeV/c in 10-30% collisions. Reconstructed jets were required to contain a leading charged particle with pT>5 GeV/c to suppress jets constructed from the combinatorial background in Pb-Pb collisions. The effect of the leading charged particle requirement has been studied in both pp and Pb-Pb collisions and has been shown to have negligible effects on the RAA within the uncertainties of the measurement. The nuclear modification factor is obtained by dividing the jet spectrum measured in Pb-Pb by that in pp collisions scaled by the number of independent nucleon-nucleon collisions estimated using a Glauber model. RAA is found to be 0.28±0.04 in 0-10% and 0.35±0.04 in 10-30% collisions, independent of pT,jet within the uncertainties of the measurement. The observed suppression is in fair agreement with expectations from two model calculations with different approaches to jet quenching.

Measurement of pion, kaon and proton production in proton-proton collisions at s√=7 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (The European Physics Journal C, 2015)
The measurement of primary π±, K±, p and p¯ production at mid-rapidity (|y|< 0.5) in proton-proton collisions at s√=7 TeV performed with ALICE (A Large Ion Collider Experiment) at the Large Hadron Collider (LHC) is reported. Particle identification is performed using the specific ionization energy loss and time-of-flight information, the ring-imaging Cherenkov technique and the kink-topology identification of weak decays of charged kaons. Transverse momentum spectra are measured from 0.1 up to 3 GeV/c for pions, from 0.2 up to 6 GeV/c for kaons and from 0.3 up to 6 GeV/c for protons. The measured spectra and particle ratios are compared with QCD-inspired models, tuned to reproduce also the earlier measurements performed at the LHC. Furthermore, the integrated particle yields and ratios as well as the average transverse momenta are compared with results at lower collision energies.

Multi-strange baryon production in p-Pb collisions at sNN‾‾‾‾√=5.02 - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
The multi-strange baryon yields in Pb–Pb collisions have been shown to exhibit an enhancement relative to pp reactions. In this work, Ξ and Ω production rates have been measured with the ALICE experiment as a function of transverse momentum, pT, in p-Pb collisions at a centre-of-mass energy of sNN‾‾‾‾√ = 5.02 TeV. The results cover the kinematic ranges 0.6 GeV/c<pT<7.2 GeV/c and 0.8 GeV/c<pT< 5 GeV/c, for Ξ and Ω respectively, in the common rapidity interval -0.5 <yCMS< 0. Multi-strange baryons have been identified by reconstructing their weak decays into charged particles. The pT spectra are analysed as a function of event charged-particle multiplicity, which in p-Pb collisions ranges over one order of magnitude and lies between those observed in pp and Pb-Pb collisions. The measured pT distributions are compared to the expectations from a Blast-Wave model. The parameters which describe the production of lighter hadron species also describe the hyperon spectra in high multiplicity p-Pb. The yield of hyperons relative to charged pions is studied and compared with results from pp and Pb-Pb collisions. A statistical model is employed, which describes the change in the ratios with volume using a canonical suppression mechanism, in which the small volume causes a species-dependent relative reduction of hadron production. The calculations, in which the magnitude of the effect depends on the strangeness content, show good qualitative agreement with the data.

One-dimensional pion, kaon, and proton femtoscopy in Pb-Pb collisions at sNN−−−√ =2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
The size of the particle emission region in high-energy collisions can be deduced using the femtoscopic correlations of particle pairs at low relative momentum. Such correlations arise due to quantum statistics and Coulomb and strong final state interactions. In this paper, results are presented from femtoscopic analyses of π±π±, K±K±, K0SK0S, pp, and p¯p¯ correlations from Pb-Pb collisions at sNN−−−√=2.76 TeV by the ALICE experiment at the LHC. One-dimensional radii of the system are extracted from correlation functions in terms of the invariant momentum difference of the pair. The comparison of the measured radii with the predictions from a hydrokinetic model is discussed. The pion and kaon source radii display a monotonic decrease with increasing average pair transverse mass mT which is consistent with hydrodynamic model predictions for central collisions. The kaon and proton source sizes can be reasonably described by approximate mT-scaling.

Precision measurement of the mass difference between light nuclei and anti-nuclei - J. Adam; M. M. Aggarwal; R. Keidel; D. Adamová; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; I. Ahmed; S. U. Ahn; I. Aimo; S. Aiola; et al. (Nature Physics, 2015)
The measurement of the mass differences for systems bound by the strong force has reached a very high precision with protons and anti-protons. The extension of such measurement from (anti-)baryons to (anti-)nuclei allows one to probe any difference in the interactions between nucleons and anti-nucleons encoded in the (anti-)nuclei masses. This force is a remnant of the underlying strong interaction among quarks and gluons and can be described by effective theories, but cannot yet be directly derived from quantum chromodynamics. Here we report a measurement of the difference between the ratios of the mass and charge of deuterons and anti-deuterons, and 3He and 3He⎯⎯⎯⎯⎯⎯⎯ nuclei carried out with the ALICE (A Large Ion Collider Experiment) detector in Pb-Pb collisions at a centre-of-mass energy per nucleon pair of 2.76 TeV. Our direct measurement of the mass-over-charge differences confirm CPT invariance to an unprecedented precision in the sector of light nuclei. This fundamental symmetry of nature, which exchanges particles with anti-particles, implies that all physics laws are the same under the simultaneous reversal of charge(s) (charge conjugation C), reflection of spatial coordinates (parity transformation P) and time inversion (T).

Production of inclusive Υ(1S) and Υ(2S) in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (Physics Letters B, 2015)
We report on the production of inclusive Υ(1S) and Υ(2S) in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV at the LHC. The measurement is performed with the ALICE detector at backward (−4.46<ycms<−2.96) and forward (2.03<ycms<3.53) rapidity down to zero transverse momentum. The production cross sections of the Υ(1S) and Υ(2S) are presented, as well as the nuclear modification factor and the ratio of the forward to backward yields of Υ(1S). A suppression of the inclusive Υ(1S) yield in p-Pb collisions with respect to the yield from pp collisions scaled by the number of binary nucleon-nucleon collisions is observed at forward rapidity but not at backward rapidity. The results are compared to theoretical model calculations including nuclear shadowing or partonic energy loss effects.

Production of light nuclei and anti-nuclei in pp and Pb-Pb collisions at LHC energies - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
The production of (anti-)deuteron and (anti-)3He nuclei in Pb-Pb collisions at sNN−−−√ = 2.76 TeV has been studied using the ALICE detector at the LHC. The spectra exhibit a significant hardening with increasing centrality. Combined blast-wave fits of several particles support the interpretation that this behavior is caused by an increase of radial flow. The integrated particle yields are discussed in the context of coalescence and thermal-statistical model expectations. The particle ratios, 3He/d and 3He/p, in Pb-Pb collisions are found to be in agreement with a common chemical freeze-out temperature of Tchem≈156 MeV. These ratios do not vary with centrality which is in agreement with the thermal-statistical model. In a coalescence approach, it excludes models in which nucleus production is proportional to the particle multiplicity and favors those in which it is proportional to the particle density instead. In addition, the observation of 31 anti-tritons in Pb-Pb collisions is reported. For comparison, the deuteron spectrum in pp collisions at s√=7 TeV is also presented. While the p/π ratio is similar in pp and Pb-Pb collisions, the d/p ratio in pp collisions is found to be lower by a factor of 2.2 than in Pb-Pb collisions.

Pseudorapidity and transverse-momentum distributions of charged particles in proton-proton collisions at s√ = 13 TeV - J. Adam; D. Adamova; Ralf Keidel; M. Aggarwal (Physics Letters B, 2015)
The pseudorapidity (η) and transverse-momentum (pT) distributions of charged particles produced in proton-proton collisions are measured at the centre-of-mass energy s√ = 13 TeV. The pseudorapidity distribution in |η|< 1.8 is reported for inelastic events and for events with at least one charged particle in |η|< 1. The pseudorapidity density of charged particles produced in the pseudorapidity region |η|< 0.5 is 5.31 ± 0.18 and 6.46 ± 0.19 for the two event classes, respectively. The transverse-momentum distribution of charged particles is measured in the range 0.15 < pT < 20 GeV/c and |η|< 0.8 for events with at least one charged particle in |η|< 1. The correlation between transverse momentum and particle multiplicity is also investigated by studying the evolution of the spectra with event multiplicity. The results are compared with calculations from PYTHIA and EPOS Monte Carlo generators.

Rapidity and transverse-momentum dependence of the inclusive J/ψ nuclear modification factor in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; M. M. Aggarwal (2015)
We have studied the transverse-momentum (pT) dependence of the inclusive J/ψ production in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV, in three center-of-mass rapidity (ycms) regions, down to zero pT. Results in the forward and backward rapidity ranges (2.03<ycms<3.53 and −4.46<ycms<−2.96) are obtained by studying the J/ψ decay to μ+μ−, while the mid-rapidity region (−1.37<ycms<0.43) is investigated by measuring the e+e− decay channel. The pT dependence of the J/ψ production cross section and nuclear modification factor are presented for each of the rapidity intervals, as well as the J/ψ mean pT values. Forward and mid-rapidity results show a suppression of the J/ψ yield, with respect to pp collisions, which decreases with increasing pT. At backward rapidity no significant J/ψ suppression is observed. Theoretical models including a combination of cold nuclear matter effects such as shadowing and partonic energy loss, are in fair agreement with the data, except at forward rapidity and low transverse momentum. The implications of the p-Pb results for the evaluation of cold nuclear matter effects on J/ψ production in Pb-Pb collisions are also discussed.

Search for weakly decaying Λn¯¯¯¯¯¯ and ΛΛ exotic bound states in central Pb-Pb collisions at sNN−−−√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
We present results of a search for two hypothetical strange dibaryon states, i.e. the H-dibaryon and the possible Λn¯¯¯¯ bound state. The search is performed with the ALICE detector in central (0-10%) Pb-Pb collisions at sNN−−−√=2.76 TeV, by invariant mass analysis in the decay modes Λn¯¯¯¯→d¯π+ and H-dibaryon →Λpπ−. No evidence for these bound states is observed. Upper limits are determined at 99% confidence level for a wide range of lifetimes and for the full range of branching ratios. The results are compared to thermal, coalescence and hybrid UrQMD model expectations, which describe correctly the production of other loosely bound states, like the deuteron and the hypertriton.

Two-pion femtoscopy in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; M. M. Aggarwal (2015)
We report the results of the femtoscopic analysis of pairs of identical pions measured in p-Pb collisions at sNN‾‾‾‾√=5.02 TeV. Femtoscopic radii are determined as a function of event multiplicity and pair momentum in three spatial dimensions. As in the pp collision system, the analysis is complicated by the presence of sizable background correlation structures in addition to the femtoscopic signal. The radii increase with event multiplicity and decrease with pair transverse momentum. When taken at comparable multiplicity, the radii measured in p-Pb collisions, at high multiplicity and low pair transverse momentum, are 10-20% higher than those observed in pp collisions but below those observed in A-A collisions. The results are compared to hydrodynamic predictions at large event multiplicity as well as discussed in the context of calculations based on gluon saturation.

φ-meson production at forward rapidity in p-Pb collisions at sNN−−−√ = 5.02 TeV and in pp collisions at s√ = 2.76 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2015)
The first measurement of ϕ-meson production in p-Pb collisions at a nucleon-nucleon centre-of-mass energy sNN−−−√ = 5.02 TeV has been performed with the ALICE apparatus at the LHC. The ϕ-mesons have been identified in the dimuon decay channel in the transverse momentum (pT) range 1<pT<7 GeV/c, both in the p-going (2.03<y<3.53) and the Pb-going (−4.46<y<−2.96) directions, where y stands for the rapidity in the nucleon-nucleon centre-of-mass. Differential cross sections as a function of transverse momentum and rapidity are presented. The forward-backward asymmetry for ϕ-meson production is measured for 2.96<|y|<3.53, resulting in a factor ∼0.5 with no significant pT dependence within the uncertainties. The pT dependence of the ϕ nuclear modification factor RpPb exhibits an enhancement up to a factor 1.6 at pT = 3-4 GeV/c in the Pb-going direction. The pT dependence of the ϕ-meson cross section in pp collisions at s√ = 2.76 TeV, which is used to determine a reference for the p-Pb results, is also presented here for 1<pT<5 GeV/c and 2.5<y<4.

Azimuthal anisotropy of D meson production in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
The production of the prompt charmed mesons D0, D+ and D∗+ relative to the reaction plane was measured in Pb-Pb collisions at a centre-of-mass energy per nucleon–nucleon collision of sNN‾‾‾‾√ = 2.76 TeV with the ALICE detector at the LHC. D mesons were reconstructed via their hadronic decays at central rapidity in the transverse momentum (pT) interval 2-16 Gev/c. The azimuthal anisotropy is quantified in terms of the second coefficient v2 in a Fourier expansion of the D meson azimuthal distribution, and in terms of the nuclear modification factor RAA, measured in the direction of the reaction plane and orthogonal to it. The v2 coefficient was measured with three different methods and in three centrality classes in the interval 0-50%. A positive v2 is observed in mid-central collisions (30-50% centrality class), with an mean value of 0.204+0.099−0.036(tot.unc.) in the interval 2 < pT < 6 Gev/c, which decreases towards more central collisions (10-30% and 0-10% classes). The positive v2 is also reflected in the nuclear modification factor, which shows a stronger suppression in the direction orthogonal to the reaction plane for mid-central collisions. The measurements are compared to theoretical calculations of charm quark transport and energy loss in high-density strongly-interacting matter at high temperature. The models that include substantial elastic interactions with an expanding medium provide a good description of the observed anisotropy. However, they are challenged to simultaneously describe the strong suppression of high-pT yield of D mesons in central collisions and their azimuthal anisotropy in non-central collisions.

Beauty production in pp collisions at s√ = 2.76 TeV measured via semi-electronic decays - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
The ALICE collaboration at the LHC reports measurement of the inclusive production cross section of electrons from semi-leptonic decays of beauty hadrons with rapidity |y|<0.8 and transverse momentum 1

Centrality dependence of particle production in p-Pb collisions at sNN‾‾‾‾√= 5.02 TeV - Jaroslav Adam; Dagmar Adamova; Ralf Keidel; Madan Mohan Aggarwal (2014)
We report measurements of the primary charged particle pseudorapidity density and transverse momentum distributions in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV, and investigate their correlation with experimental observables sensitive to the centrality of the collision. Centrality classes are defined using different event activity estimators, i.e. charged particle multiplicities measured in three disjunct pseudorapidity regions as well as the energy measured at beam rapidity (zero-degree). The procedures to determine the centrality, quantified by the number of participants (Npart), or the number of nucleon-nucleon binary collisions (Ncoll), are described. We show that, in contrast to Pb-Pb collisions, in p-Pb collisions large multiplicity fluctuations together with the small range of participants available, generate a dynamical bias in centrality classes based on particle multiplicity. We propose to use the zero-degree energy, which we expect not to introduce a dynamical bias, as an alternative event-centrality estimator. Based on zero-degree energy centrality classes, the Npart dependence of particle production is studied. Under the assumption that the multiplicity measured in the Pb-going rapidity region scales with the number of Pb-participants, an approximate independence of the multiplicity per participating nucleon measured at mid-rapitity of the number of participating nucleons is observed. Furthermore, at high-pT the p-Pb spectra are found to be consistent with the pp spectra scaled by Ncoll for all centrality classes. Our results represent valuable input for the study of the event activity dependence of hard probes in p-Pb collision and, hence, help to establish baselines for the interpretation of the Pb-Pb data.

Charged jet cross sections and properties in proton-proton collisions at s√ = 7 TeV - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (2014)
The differential charged jet cross sections, jet fragmentation distributions, and jet shapes are measured in minimum bias proton-proton collisions at centre-of-mass energy s√=7 TeV using the ALICE detector at the LHC. Jets are reconstructed from charged particle momenta in the mid-rapidity region using the sequential recombination kT and anti-kT as well as the SISCone jet finding algorithms with several resolution parameters in the range R=0.2 to 0.6. Differential jet production cross sections measured with the three jet finders are in agreement in the transverse momentum (pT) interval 20<pjet,chT<100 GeV/c. They are also consistent with prior measurements carried out at the LHC by the ATLAS collaboration. The jet charged particle multiplicity rises monotonically with increasing jet pT, in qualitative agreement with prior observations at lower energies. The transverse profiles of leading jets are investigated using radial momentum density distributions as well as distributions of the average radius containing 80% (⟨R80⟩) of the reconstructed jet pT. The fragmentation of leading jets with R=0.4 using scaled pT spectra of the jet constituents is studied. The measurements are compared to model calculations from event generators (PYTHIA, PHOJET, HERWIG). The measured radial density distributions and ⟨R80⟩ distributions are well described by the PYTHIA model (tune Perugia-2011). The fragmentation distributions are better described by HERWIG.

Elliptic flow of identified hadrons in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
The elliptic flow coefficient (v2) of identified particles in Pb–Pb collisions at sNN‾‾‾‾√=2.76 TeV was measured with the ALICE detector at the LHC. The results were obtained with the Scalar Product method, a two-particle correlation technique, using a pseudo-rapidity gap of |Δη|>0.9 between the identified hadron under study and the reference particles. The v2 is reported for π±, K±, K0S, p+p⎯⎯, ϕ, Λ+Λ⎯⎯⎯, Ξ−+Ξ⎯⎯⎯+ and Ω−+Ω⎯⎯⎯+ in several collision centralities. In the low transverse momentum (pT) region, pT<2GeV/c, v2(pT) exhibits a particle mass dependence consistent with elliptic flow accompanied by the transverse radial expansion of the system with a common velocity field. The experimental data for π± and K are described fairly well by hydrodynamical calculations coupled to a hadronic cascade model (VISHNU) for central collisions. However, the same calculations fail to reproduce the v2(pT) for p+p⎯⎯, ϕ, Λ+Λ⎯⎯⎯ and Ξ−+Ξ⎯⎯⎯+. For transverse momentum values larger than about 3 GeV/c, particles tend to group according to their type, i.e. mesons and baryons. However, the experimental data at the LHC exhibit deviations from the number of constituent quark (NCQ) scaling at the level of ±20% for pT>3GeV/c.

Event-by-event mean pT fluctuations in pp and Pb-Pb collisions at the LHC - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (The European Physics Journal C, 2014)
Event-by-event fluctuations of the mean transverse momentum of charged particles produced in pp collisions at s√ = 0.9, 2.76 and 7 TeV, and Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV are studied as a function of the charged-particle multiplicity using the ALICE detector at the LHC. Dynamical fluctuations indicative of correlated particle emission are observed in all systems. The results in pp collisions show little dependence on collision energy. The Monte Carlo event generators PYTHIA and PHOJET are in qualitative agreement with the data. Peripheral Pb-Pb data exhibit a similar multiplicity dependence as that observed in pp. In central Pb-Pb, the results deviate from this trend, featuring a significant reduction of the fluctuation strength. The results in Pb-Pb are in qualitative agreement with previous measurements in Au-Au at lower collision energies and with expectations from models that incorporate collective phenomena.

Exclusive J/ψ photoproduction off protons in ultra-peripheral p-Pb collisions at sNN‾‾‾‾√=5.02 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
We present the first measurement at the LHC of exclusive J/ψ photoproduction off protons, in ultra-peripheral proton-lead collisions at sNN‾‾‾‾√=5.02 TeV. Events are selected with a dimuon pair produced either in the rapidity interval, in the laboratory frame, 2.5<y<4 (p-Pb) or −3.6<y<−2.6 (Pb–p), and no other particles observed in the ALICE acceptance. The measured cross sections σ(γ+p→J/ψ+p) are 33.2 ± 2.2 (stat) ± 3.1 (syst) ± 0.7 (theo) nb in p-Pb and 284 ± 36 (stat) +27−32 (syst) ± 26 (theo) nb in Pb-p collisions. We measure this process up to about 700 GeV in the γp centre-of-mass, which is a factor of two larger than the highest energy studied at HERA. The data are consistent with a power law dependence of the J/ψ photoproduction cross section in γp energies from about 20 to 700 GeV, or equivalently, from Bjorken-x between ∼2×10−2 to ∼2×10−5, thus indicating no significant change in the gluon density behaviour of the proton between HERA and LHC energies.

Freeze-out radii extracted from three-pion cumulants in pp, p-Pb and Pb-Pb collisions at the LHC - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
In high-energy collisions, the spatio-temporal size of the particle production region can be measured using the Bose-Einstein correlations of identical bosons at low relative momentum. The source radii are typically extracted using two-pion correlations, and characterize the system at the last stage of interaction, called kinetic freeze-out. In low-multiplicity collisions, unlike in high-multiplicity collisions, two-pion correlations are substantially altered by background correlations, e.g. mini-jets. Such correlations can be suppressed using three-pion cumulant correlations. We present the first measurements of the size of the system at freeze-out extracted from three-pion cumulant correlations in pp, p-Pb and Pb-Pb collisions at the LHC with ALICE. At similar multiplicity, the invariant radii extracted in p-Pb collisions are found to be 5-15% larger than those in pp, while those in Pb-Pb are 35-55% larger than those in p-Pb. Our measurements disfavor models which incorporate substantially stronger collective expansion in p-Pb as compared to pp collisions at similar multiplicity.

Inclusive photon production at forward rapidities in proton-proton collisions at s√ = 0.9, 2.76 and 7 TeV - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (2014)
The multiplicity and pseudorapidity distributions of inclusive photons have been measured at forward rapidities (2.3<η<3.9) in proton-proton collisions at three center-of-mass energies, s√=0.9, 2.76 and 7 TeV using the ALICE detector. It is observed that the increase in the average photon multiplicity as a function of beam energy is compatible with both a logarithmic and a power-law dependence. The relative increase in average photon multiplicity produced in inelastic pp collisions at 2.76 and 7 TeV center-of-mass energies with respect to 0.9 TeV are 37.2% ± 0.3% (stat) ± 8.8% (sys) and 61.2% ± 0.3% (stat) ± 7.6% (sys), respectively. The photon multiplicity distributions for all center-of-mass energies are well described by negative binomial distributions. The multiplicity distributions are also presented in terms of KNO variables. The results are compared to model predictions, which are found in general to underestimate the data at large photon multiplicities, in particular at the highest center-of-mass energy. Limiting fragmentation behavior of photons has been explored with the data, but is not observed in the measured pseudorapidity range.

K*(892)0 and Φ(1020) production in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
The yields of the K*(892)0 and Φ(1020) resonances are measured in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV through their hadronic decays using the ALICE detector. The measurements are performed in multiple centrality intervals at mid-rapidity (|y|<0.5) in the transverse-momentum ranges 0.3 < pT < 5 GeV/c for the K*(892)0 and 0.5 < pT < 5 GeV/c for the Φ(1020). The yields of K*(892)0 are suppressed in central Pb-Pb collisions with respect to pp and peripheral Pb-Pb collisions. This suppression is discussed in a scenario in which the K*(892)0 decays during the evolution of the fireball and the decay products scatter, thus escaping detection through invariant-mass reconstruction. In contrast, the Φ(1020) meson, due to its long lifetime, decays outside the fireball. These particles are also used as probes to study the mechanisms of particle production. The shape of the pTdistribution of the Φ(1020) meson, but not its yield, is reproduced fairly well by hydrodynamical models for central Pb-Pb collisions. In central Pb-Pb collisions at low and intermediate pT, the p/Φ(1020) ratio is flat in pT, while the p/π and Φ(1020)/π ratios show a pronounced increase and have similar shapes to each other. These results indicate that the shapes of the pT distributions of these particles in central Pb-Pb collisions are determined predominantly by the particle masses and radial flow. Finally, Φ(1020) production in Pb-Pb collisions is enhanced, with respect to the yield in pp collisions and the yield of charged pions, by an amount similar to the Λ and Ξ.

Measurement of charged jet suppression n Pb-Pb collisions at sqrt(sNN)=2.76TeV - B. Abelev; J. Adam; D. Adamova; Ralf Keidel (2014)
A measurement of the transverse momentum spectra of jets in Pb-Pb collisions at sqrt(sNN)=2.76TeV is reported. Jets are reconstructed from charged particles using the anti-k_T jet algorithm with jet resolution parameters R of 0.2 and 0.3 in pseudo-rapidity |eta|<0.5. The transverse momentum p_T of charged particles is measured down to 0.15 GeV/c which gives access to the low p_T fragments of the jet. Jets found in heavy-ion collisions are corrected event-by-event for average background density and on an inclusive basis (via unfolding) for residual background fluctuations and detector effects. A strong suppression of jet production in central events with respect to peripheral events is observed. The suppression is found to be similar to the suppression of charged hadrons, which suggests that substantial energy is radiated at angles larger than the jet resolution parameter R=0.3 considered in the analysis. The fragmentation bias introduced by selecting jets with a high p_T leading particle, which rejects jets with a soft fragmentation pattern, has a similar effect on the jet yield for central and peripheral events. The ratio of jet spectra with R=0.2 and R=0.3 is found to be similar in Pb-Pb and simulated PYTHIA pp events, indicating no strong broadening of the radial jet structure in the reconstructed jets with R<0.3.

Measurement of electrons from semileptonic heavy-flavor hadron decays in pp collisions at s√ = 2.76 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
The pT-differential production cross section of electrons from semileptonic decays of heavy-flavor hadrons has been measured at mid-rapidity in proton-proton collisions at s√ = 2.76 TeV in the transverse momentum range 0.5 < pT < 12 GeV/c with the ALICE detector at the LHC. The analysis was performed using minimum bias events and events triggered by the electromagnetic calorimeter. Predictions from perturbative QCD calculations agree with the data within the theoretical and experimental uncertainties.

Measurement of prompt D-meson production in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
The pT-differential production cross sections of the prompt charmed mesons D0,D+,D∗+ and D+s and their charge conjugate in the rapidity interval -0.96 < ycms < 0.04 were measured in p-Pb collisions at a centre-of-mass energy sNN‾‾‾‾√ = 5.02 TeV with the ALICE detector at the LHC. The nuclear modification factor RpPb, quantifying the D-meson yield in p–Pb collisions relative to the yield in pp collisions scaled by the number of binary nucleon-nucleon collisions, is compatible within the 15-20% uncertainties with unity in the transverse momentum interval 1 < pT < 24 GeV/c. No significant difference among the RpPb of the four D-meson species is observed. The results are described within uncertainties by theoretical calculations that include initial-state effects. The measurement adds experimental evidence that the modification of the momentum spectrum of D mesons observed in Pb-Pb collisions with respect to pp collisions is due to strong final-state effects induced by hot partonic matter.

Measurement of quarkonium production at forward rapidity in pp collisions at s√= 7 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
The inclusive production cross sections at forward rapidity of J/ψ, ψ(2S), Υ(1S) and Υ(2S) are measured in pp collisions at s√ = 7 TeV with the ALICE detector at the LHC. The analysis is based on a data sample corresponding to an integrated luminosity of 1.35 pb−1. Quarkonia are reconstructed in the dimuon-decay channel and the signal yields are evaluated by fitting the μ+μ− invariant mass distributions. The differential production cross sections are measured as a function of the transverse momentum pT and rapidity y, over the transverse momentum range 0 < pT < 20 GeV/c for J/ψ and 0 < pT < 12 GeV/c for all other resonances and for 2.5 < y < 4. The measured cross sections integrated over pT and y, and assuming unpolarized quarkonia, are: σJ/ψ=6.69 ± 0.04 ± 0.61 μ b, σψ(2S) = 1.13 ± 0.07 ± 0.14 μb, σΥ(1S) = 54.2 ± 5.0 ± 6.7 nb and σΥ(2S)=18.4 ± 3.7 ± 2.2 nb, where the first uncertainty is statistical and the second one is systematic. These cross sections are obtained assuming unpolarized quarkonium production. The results are compared to measurements performed by other LHC experiments and to theoretical models.

Measurement of visible cross sections in proton-lead collisions at sNN‾‾‾‾√ = 5.02 TeV in van der Meer scans with the ALICE detector - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
In 2013, the Large Hadron Collider provided proton-lead and lead-proton collisions at the center-of-mass energy per nucleon pair sNN‾‾‾‾√ = 5.02 TeV. Van der Meer scans were performed for both configurations of colliding beams, and the cross section was measured for two reference processes, based on particle detection by the T0 and V0 detectors, with pseudo-rapidity coverage 4.6 < η < 4.9, -3.3 < η < -3.0 and 2.8 < η < 5.1, -3.7 < η < -1.7, respectively. Given the asymmetric detector acceptance, the cross section was measured separately for the two configurations. The measured visible cross sections are used to calculate the integrated luminosity of the proton-lead and lead-proton data samples, and to indirectly measure the cross section for a third, configuration-independent, reference process, based on neutron detection by the Zero Degree Calorimeters.

Multi-particle azimuthal correlations in p-Pb and Pb-Pb collisions at the LHC - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
Measurements of multi-particle azimuthal correlations (cumulants) for charged particles in p-Pb at sNN‾‾‾‾√=5.02 TeV and Pb-Pb at sNN‾‾‾‾√=2.76 TeV collisions are presented. They help address a question if there is evidence for global, flow-like, azimuthal correlations in the p-Pb system. Comparisons are made to measurements from the larger Pb-Pb system, where such evidence is established. In particular, the second harmonic two-particle cumulants are found to decrease with multiplicity, characteristic of a dominance of few-particle correlations in p-Pb collisions. However, when a |Δη| gap is placed to suppress such correlations, the two-particle cumulants begin to rise at high-multiplicity, indicating the presence of global azimuthal correlations. The Pb-Pb values are higher than the p-Pb values at similar multiplicities. In both systems, the second harmonic four-particle cumulants exhibit a transition from positive to negative values when the multiplicity increases. The negative values allow for a measurement of v24 to be made, which is found to be higher in Pb-Pb collisions at similar multiplicities. The second harmonic six-particle cumulants are also found to be higher in Pb-Pb collisions. In Pb-Pb collisions, we generally find v24≃v26≠0 which is indicative of a Bessel-Gaussian function for the v2 distribution. For very high-multiplicity Pb-Pb collisions, we observe that the four- and six-particle cumulants become consistent with 0. Finally, third harmonic two-particle cumulants in p-Pb and Pb-Pb are measured. These are found to be similar for overlapping multiplicities, when a |Δη|>1.4 gap is placed.

Multiplicity dependence of jet-like two-particle correlations in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
Two-particle angular correlations between unidentified charged trigger and associated particles are measured by the ALICE detector in p-Pb collisions at a nucleon-nucleon centre-of-mass energy of 5.02 TeV. The transverse-momentum range 0.7 <pT,assoc<pT,trig< 5.0 GeV/c is examined, to include correlations induced by jets originating from low momentum-transfer scatterings (minijets). The correlations expressed as associated yield per trigger particle are obtained in the pseudorapidity range |η|<0.9. The near-side long-range pseudorapidity correlations observed in high-multiplicity p-Pb collisions are subtracted from both near-side short-range and away-side correlations in order to remove the non-jet-like components. The yields in the jet-like peaks are found to be invariant with event multiplicity with the exception of events with low multiplicity. This invariance is consistent with the particles being produced via the incoherent fragmentation of multiple parton–parton scatterings, while the yield related to the previously observed ridge structures is not jet-related. The number of uncorrelated sources of particle production is found to increase linearly with multiplicity, suggesting no saturation of the number of multi-parton interactions even in the highest multiplicity p-Pb collisions. Further, the number scales in the intermediate multiplicity region with the number of binary nucleon-nucleon collisions estimated with a Glauber Monte-Carlo simulation.

Multiplicity Dependence of Pion, Kaon, Proton and Lambda Production in p-Pb Collisions at (√sNN) = 5.02 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamaova (Physics Letters B, 2014)
In this Letter, comprehensive results on π±, K±, View the MathML source, p(View the MathML source) and View the MathML source production at mid-rapidity (0<yCMS<0.5) in p-Pb collisions at View the MathML source, measured by the ALICE detector at the LHC, are reported. The transverse momentum distributions exhibit a hardening as a function of event multiplicity, which is stronger for heavier particles. This behavior is similar to what has been observed in pp and Pb-Pb collisions at the LHC. The measured pT distributions are compared to d-Au, Au-Au and Pb-Pb results at lower energy and with predictions based on QCD-inspired and hydrodynamic models.

Neutral pion production at midrapidity in pp and Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
Invariant yields of neutral pions at midrapidity in the transverse momentum range 0.6<pT<12 GeV/c measured in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV are presented for six centrality classes. The pp reference spectrum was measured in the range 0.4<pT<10 GeV/c at the same center-of-mass energy. The nuclear modification factor, RAA, shows a suppression of neutral pions in central Pb-Pb collisions by a factor of up to about 8−10 for 5≲pT≲7 GeV/c. The presented measurements are compared with results at lower center-of-mass energies and with theoretical calculations.

Performance of the ALICE Experiment at the CERN LHC - B. Abelev; A. Abramyan; Ralf Keidel; J. Adam (2014)
ALICE is the heavy-ion experiment at the CERN Large Hadron Collider. The experiment continuously took data during the first physics campaign of the machine from fall 2009 until early 2013, using proton and lead-ion beams. In this paper we describe the running environment and the data handling procedures, and discuss the performance of the ALICE detectors and analysis methods for various physics observables.

Production of charged pions, kaons and protons at large transverse momenta in pp and Pb-Pb collisions at √sNN=2.76 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
Transverse momentum spectra of Pi+/-, K+/- and p(anti-p) up to pT = 20 GeV/c at mid-rapidity, |y| < 0.8, in pp and Pb-Pb collisions at sqrt(sNN) = 2.76 TeV have been measured using the ALICE detector at the LHC. At intermediate pT (2-8 GeV/c) an enhancement of the proton-to-proton ratio, (p + anti-p)/(Pi+ + Pi-), with respect to pp collisions is observed and the ratio reaches 0.80 in central Pb-Pb collisions. The measurement of the nuclear modification factors for Pi+/-, K+/- and p(anti-p) indicates that within the systematic and statistical uncertainties they are the same at high pT (> 10 GeV/c), suggesting that the chemical composition of leading particles from jets in the medium is similar to that of vacuum jets.

Production of Σ(1385)± and Ξ(1530)0 in proton-proton collisions at s√= 7 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
The production of the strange and double-strange baryon resonances (Σ(1385)±, Ξ(1530)0) has been measured at mid-rapidity (∣∣y∣∣<0.5) in proton-proton collisions at s√ = 7 TeV with the ALICE detector at the LHC. Transverse momentum spectra for inelastic collisions are compared to QCD-inspired models, which in general underpredict the data. A search for the ϕ(1860) pentaquark, decaying in the Ξπ channel, has been carried out but no evidence is seen.

Suppression of Υ(1S) at forward rapidity in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
We report on the measurement of the inclusive Υ(1S) production in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV carried out at forward rapidity (2.5

Suppression of ψ(2S) production in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
The ALICE Collaboration has studied the inclusive production of the charmonium state ψ(2S) in proton-lead (p-Pb) collisions at the nucleon-nucleon centre of mass energy sNN‾‾‾‾√ = 5.02 TeV at the CERN LHC. The measurement was performed at forward (2.03<ycms<3.53) and backward (−4.46<ycms<−2.96) centre of mass rapidities, studying the decays into muon pairs. In this paper, we present the inclusive production cross sections σψ(2S), both integrated and as a function of the transverse momentum pT, for the two ycms domains. The results are compared to those obtained for the 1S vector state (J/ψ), by showing the ratios between the production cross sections, as well as the double ratios [σψ(2S)/σJ/ψ]pPb/[σψ(2S)/σJ/ψ]pp between p-Pb and proton-proton collisions. Finally, the nuclear modification factor for inclusive ψ(2S) is evaluated and compared to the measurement of the same quantity for J/ψ and to theoretical models including parton shadowing and coherent energy loss mechanisms. The results show a significantly larger suppression of the ψ(2S) compared to that measured for J/ψ and to models. These observations represent a clear indication for sizeable final state effects on ψ(2S) production.

Technical Design Report for the Upgrade of the ALICE Inner Tracking System - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (Journal of Physics G: Nuclear and Particle Physics, 2014)
ALICE (A Large Ion Collider Experiment) is studying the physics of strongly interacting matter, and in particular the properties of the Quark-Gluon Plasma (QGP), using proton-proton, proton-nucleus and nucleus-nucleus collisions at the CERN LHC (Large Hadron Collider). The ALICE Collaboration is preparing a major upgrade of the experimental apparatus, planned for installation in the second long LHC shutdown in the years 2018-2019. A key element of the ALICE upgrade is the construction of a new, ultra-light, high-resolution Inner Tracking System (ITS) based on monolithic CMOS pixel detectors. The primary focus of the ITS upgrade is on improving the performance for detection of heavy-flavour hadrons, and of thermal photons and low-mass di-electrons emitted by the QGP. With respect to the current detector, the new Inner Tracking System will significantly enhance the determination of the distance of closest approach to the primary vertex, the tracking efficiency at low transverse momenta, and the read-out rate capabilities. This will be obtained by seven concentric detector layers based on a 50 μm thick CMOS pixel sensor with a pixel pitch of about 30×30 μm2. This document, submitted to the LHCC (LHC experiments Committee) in September 2013, presents the design goals, a summary of the R&D activities, with focus on the technical implementation of the main detector components, and the projected detector and physics performance.

Transverse momentum dependence of inclusive primary charged-particle production in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2014)
The transverse momentum (pT) distribution of primary charged particles is measured at midrapidity in minimum-bias p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV with the ALICE detector at the LHC in the range 0.15 < pT < 50 GeV/c. The spectra are compared to the expectation based on binary collision scaling of particle production in pp collisions, leading to a nuclear modification factor consistent with unity for pT larger than 2 GeV/c. The measurement is compared to theoretical calculations and to data in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV

Two and Three-Pion Quantum Statistics Correlations in Pb-Pb Collisions at sNN‾‾‾‾√=2.76 TeV at the LHC - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (Physical Review C, 2014)
Correlations induced by quantum statistics are sensitive to the spatio-temporal extent as well as dynamics of particle emitting sources in heavy-ion collisions. In addition, such correlations can be used to search for the presence of a coherent component of pion production. Two and three-pion correlations of same and mixed-charge are measured at low relative momentum to estimate the coherent fraction of charged pions in Pb-Pb collisions at sNN‾‾‾‾√= 2.76 TeV at the LHC with ALICE. The genuine three-pion quantum statistics correlation is found to be suppressed relative to the two-pion correlation based on the assumption of fully chaotic pion emission.The suppression is observed to decrease with triplet momentum. The observed suppression at low triplet momentum may correspond to a coherent fraction in charged pion emission of 22% +- 12%.

Centrality dependence of Pi, K, p production in Pb-Pb collisions at sqrt(sNN) = 2.76 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamová (2013)
In this paper measurements are presented of Pi+, Pi-, K+, K-, p and antiproton production at mid-rapidity < 0.5, in Pb-Pb collisions at sqrt(sNN) = 2.76 TeV as a function of centrality. The measurement covers the transverse momentum pt range from 100, 200, 300 MeV/c up to 3, 3, 4.6 GeV/c, for Pi, K, and p respectively. The measured pt distributions and yields are compared to expectations based on hydrodynamic, thermal and recombination models. The spectral shapes of central collisions show a stronger radial flow than measured at lower energies, which can be described in hydrodynamic models. In peripheral collisions, the pt distributions are not well reproduced by hydrodynamic models. Ratios of integrated particle yields are found to be nearly independent of centrality. The yield of protons normalized to pions is a factor 1.5 lower than the expectation from thermal models.

Centrality dependence of the pseudorapidity density distribution for charged particles in Pb-Pb collisions at sqrt(sNN) = 2.76 TeV - E. Abbas; B. Abelev; Ralf Keidel; J. Adam (2013)
We present the first wide-range measurement of the charged-particle pseudorapidity density distribution, for different centralities (the 0-5%, 5-10%, 10-20%, and 20-30% most central events) in Pb-Pb collisions at sqrt(sNN) = 2.76 TeV at the LHC. The measurement is performed using the full coverage of the ALICE detectors, -5.0 < eta < 5.5, and employing a special analysis technique based on collisions arising from LHC 'satellite' bunches. We present the pseudorapidity density as a function of the number of participating nucleons as well as an extrapolation to the total number of produced charged particles Nch = 17165 +/- 772 for the 0-5% most central collisions). From the measured dNch/deta distribution we derive the rapidity density distribution, dNch/dy, under simple assumptions. The rapidity density distribution is found to be significantly wider than the predictions of the Landau model, which reproduce data well at RHIC energies. We assess the validity of longitudinal scaling by comparing to lower energy results from RHIC. Finally the mechanisms of the underlying particle production are discussed based on a comparison with various theoretical models.

Centrality determination of Pb-Pb collisions at sqrt(sNN) = 2.76 TeV with ALICE - B. Abelev; J. Adam; Ralf Keidel; D. Adamová (2013)
This publication describes the methods used to measure the centrality of inelastic Pb-Pb collisions at a center-of-mass energy of 2.76 TeV per colliding nucleon pair with ALICE. The centrality is a key parameter in the study of the properties of QCD matter at extreme temperature and energy density, because it is directly related to the initial overlap region of the colliding nuclei. Geometrical properties of the collision, such as the number of participating nucleons and number of binary nucleon-nucleon collisions, are deduced from a Glauber model with a sharp impact parameter selection, and shown to be consistent with those extracted from the data. The centrality determination provides a tool to compare ALICE measurements with those of other experiments and with theoretical calculations.

Centrality, rapidity and transverse momentum dependence of J/Psi suppression in Pb-Pb collisions at sqrt(sNN)=2.76TeV - B. Abelev; J. Adam; D. Adamova; Ralf Keidel (Physics Letters B, 2013)
The inclusive J/Psi nuclear modification factor Raa in Pb-Pb collisions at sqrt(sNN)=2.76TeV has been measured by ALICE as a function of centrality in the e+e- decay channel at mid-rapidity |y| < 0.8 and as a function of centrality, transverse momentum and rapidity in the u+u- decay channel at forward-rapidity 2.5 < y < 4.The J/Psi yields measured in Pb-Pb are suppressed compared to those in pp collisions scaled by the number of binary collisions.The Raa integrated over a centrality range corresponding to 90% of the inelastic Pb-Pb cross section is 0.72 +- 0.06 (stat.) +- 0.10 (syst.) at mid-rapidity and 0.57 +- 0.01 (stat.) +- 0.09 (syst.) at forward-rapidity.At low transverse momentum, significantly larger values of Raa are measured at forward-rapidity compared to measurements at lower energy.These features suggest that a contribution to the J/Psi yield originates from charm quarks (re)combination in the deconfined partonic medium.

Charge correlations using the balance function in Pb-Pb collisions at sqrts_NN = 2.76 TeV - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamová (2013)
In high-energy heavy-ion collisions, the correlations between the emitted particles can be used as a probe to gain insight into the charge creation mechanisms. In this article, we report the first results of such studies using the electric charge balance function in the relative pseudorapidity Δη and azimuthal angle Δφ in Pb-Pb collisions at sqrts_NN = 2.76 TeV with the ALICE detector at the Large Hadron Collider. The width of the balance function decreases with growing centrality (i.e. for more central collisions) in both projections. This centrality dependence is not reproduced by HIJING, while AMPT, a model which incorporates strings and parton rescattering, exhibits qualitative agreement with the measured correlations in Δφ but fails to describe the correlations in Δη. A thermal blast wave model incorporating local charge conservation and tuned to describe the p_T spectra and v_2 measurements reported by ALICE, is used to fit the centrality dependence of the width of the balance function and to extract the average separation of balancing charges at freeze-out. The comparison of our results with measurements at lower energies reveals an ordering with sqrts_NN: the balance functions become narrower with increasing energy for all centralities. This is consistent with the effect of larger radial flow at the LHC energies but also with the late stage creation scenario of balancing charges. However, the relative decrease of the balance function widths in Δη and Δφ with centrality from the highest SPS to the LHC energy exhibits only small differences. This observation cannot be interpreted solely within the framework where the majority of the charge is produced at a later stage in the evolution of the heavy-ion collision.

Charmonium and e+e- pair photoproduction at mid-rapidity in ultra-peripheral Pb-Pb collisions at sqrt(sNN) = 2.76 TeV - E. Abbas; B. Abelev; Ralf Keidel; J. Adam (The European Physical Journal C, 2013)
The ALICE Collaboration at the LHC has measured the j/psi and psi' photoproduction at mid-rapidity in ultra-peripheral Pb-Pb collisions at sqrt(sNN) = 2.76 TeV. The charmonium is identified via its leptonic decay for events where the hadronic activity is required to be minimal. The analysis is based on an event sample corresponding to an integrated luminosity of about 23 μb^-1. The cross section for coherent and incoherent j/psi production in the rapidity interval -0.9 < y < 0.9, are dσ_J/ψ^coh/dy = 2.38^+0.34_-0.24(sta+sys) mb and dσ_J/ψ^inc/dy = 0.98^+0.19_-0.17(sta+sys) mb, respectively. The results are compared to theoretical models for j/ψ production and the coherent cross section is found to be in good agreement with those models which include nuclear gluon shadowing consistent with EPS09 parametrization. In addition the cross section for the process γγ -> e+e- has been measured and found to be in agreement with the STARLIGHT Monte Carlo predictions.

Coherent J/ψ photoproduction in ultra-peripheral Pb-Pb collisions at - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamová (Physics Letters B, 2013)
The ALICE collaboration has made the first measurement at the LHC of J/Psi photoproduction in ultra-peripheral Pb-Pb-collisions at s_NN = 2.76 TeV. The J/Psi is identified via its dimuon decay in the forward rapidity region with the muon spectrometer for events where the hadronic activity is required to be minimal. The analysis is based on an event sample corresponding to an integrated luminosity of about 55 mub-1. The cross section for coherent J/Psi production in the rapidity interval -3.6 < y < -2.6 is measured to be dsigma/dy = 1.00 +/- 0.18 (stat) +0.24/-0.26 (syst) mb. The result is compared to theoretical models for coherent J/Psi production and found to be in good agreement with models which include nuclear gluon shadowing.

D meson elliptic flow in non-central Pb-Pb D meson elliptic flow in non-central Pb-Pb collisions at sqrts(s_NN) = 2.76TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamová (2013)
Azimuthally anisotropic distributions of D0, D+ and D*+ mesons were studied in the central rapidity region (|y|<0.8) in Pb-Pb collisions at a centre-of-mass energy sqrts(s_NN) = 2.76TeV per nucleon-nucleon collision, with the ALICE detector at the LHC. The second Fourier coefficient v2 (commonly denoted elliptic flow) was measured in the centrality class 30-50% as a function of the D meson transverse momentum pt, in the range 2-16GeV/c. The measured v2 of D mesons is comparable in magnitude to that of light-flavour hadrons. It is positive in the range 2 < pt < 6 GeV/c with 5.7 sigma significance, based on the combination of statistical and systematic uncertainties.

Directed flow of charged particles at mid-rapidity relative to the spectator plane in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (2013)
The directed flow of charged particles at mid-rapidity is measured in Pb-Pb collisions at sqrts_NN=2.76 TeV relative to the collision plane defined by the spectator nucleons. Both, the rapidity odd (v_1^odd) and even (v_1^even) directed flow components are reported. The v_1^odd component has a negative slope as a function of pseudorapidity similar to that observed at the highest RHIC energy, but with about a three times smaller magnitude. The v^even component is found to be non-zero and independent of pseudorapidity. Both components show little dependence on the collision centrality and change sign at transverse momenta around 1.2-1.7 GeV/c for midcentral collisions. The shape of v_1^even as a function of transverse momentum and a vanishing transverse momentum shift along the spectator deflection for v_1^even are consistent with dipole-like initial density fluctuations in the overlap zone of the nuclei.

Energy Dependence of the Transverse Momentum Distributions of Charged Particles in pp Collisions Measured by ALICE - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (2013)
Differential cross sections of charged particles in inelastic pp collisions as a function of p_T have been measured at sqrt(s) = 0.9, 2.76 and 7 TeV at the LHC. The p_T spectra are compared to NLO-pQCD calculations. Though the differential cross section for an individual sqrt(s) cannot be described by NLO-pQCD, the relative increase of cross section with sqrt(s) is in agreement with NLO-pQCD. Based on these measurements and observations, procedures are discussed to construct pp reference spectra at sqrt(s) = 2.76 and 5.02 TeV up to p_T = 50 GeV/c as required for the calculation of the nuclear modification factor in nucleus-nucleus and proton-nucleus collisions.

J/ψ production and nuclear effects in p-Pb collisions at √SNN = 5.02 TeV - B. Abelev; J. Adam; D. Adamova; Ralf Keidel (2013)
Inclusive J/psi production has been studied with the ALICE detector in p-Pb collisions at sNN‾‾‾‾√ = 5.02 TeV at the CERN LHC, in the rapidity domains 2.03 < ycms < 3.53 and −4.46 < ycms < −2.96, down to zero transverse momentum. The J/ψ measurement is performed in the Muon Spectrometer through the μ+μ− decay mode. In this Letter, the J/ψ production cross section and the nuclear modification factor RpPb for the rapidities under study are presented. While at forward rapidity a suppression of the J/ψ yield with respect to binary-scaled pp collisions is observed, in the backward region no suppression is present. The ratio of the forward and backward yields is also shown differentially in rapidity and transverse momentum. Theoretical predictions based on nuclear shadowing, as well as on models including, in addition, a contribution from partonic energy loss, are in fair agreement with the experimental results.

K0S and Λ production in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (Physics Review Letters, 2013)
The ALICE measurement of K0S and Λ production at midrapidity in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV is presented. The transverse momentum (pT) spectra are shown for several collision centrality intervals and in the pT range from 0.4 GeV/c (0.6 GeV/c for Λ) to 12 GeV/c. The pT dependence of the Λ/K0S ratios exhibits maxima in the vicinity of 3 GeV/c, and the positions of the maxima shift towards higher pT with increasing collision centrality. The magnitude of these maxima increases by almost a factor of three between most peripheral and most central Pb-Pb collisions. This baryon excess at intermediate pT is not observed in pp interactions at s√=0.9 TeV and at s√=7 TeV. Qualitatively, the baryon enhancement in heavy-ion collisions is expected from radial flow. However, the measured pT spectra above 2 GeV/c progressively decouple from hydrodynamical-model calculations. For higher values of pT, models that incorporate the influence of the medium on the fragmentation and hadronization processes describe qualitatively the pT dependence of the Λ/K0S ratio.

Long-range angular correlations of pi, K and p in p–Pb collisions at sqrt(s_NN) = 5.02 TeV - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (2013)
Angular correlations between unidentified charged trigger particles and various species of charged associated particles (unidentified particles, pions, kaons, protons and antiprotons) are measured by the ALICE detector in p-Pb collisions at a nucleon–nucleon centre-of-mass energy of 5.02 TeV in the transverse-momentum range 0.3 < p_T < 4 GeV/c. The correlations expressed as associated yield per trigger particle are obtained in the pseudorapidity range |eta_lab|<0.8. Fourier coefficients are extracted from the long-range correlations projected onto the azimuthal angle difference and studied as a function of and in intervals of event multiplicity. In high-multiplicity events, the second-order coefficient for protons, v_2^p, is observed to be smaller than that for pions, v_2^pi, up to about p_T = 2 GeV/c. To reduce correlations due to jets, the per-trigger yield measured in low-multiplicity events is subtracted from that in high-multiplicity events. A two-ridge structure is obtained for all particle species. The Fourier decomposition of this structure shows that the second-order coefficients for pions and kaons are similar. The v_2^p is found to be smaller at low p_T and larger at higher p_T than v_2^pi, with a crossing occurring at about 2 GeV. This is qualitatively similar to the elliptic-flow pattern observed in heavy-ion collisions. A mass ordering effect at low transverse momenta is consistent with expectations from hydrodynamic model calculations assuming a collectively expanding system.

Long-range angular correlations on the near and away side in p-Pb collisions at √sNN=5.02 TeV - Ralf Keidel; Betty Abelev; Jaroslav Adam; Dagmar Adamová (Physics Letters B, 2013)
Angular correlations between charged trigger and associated particles are measured by the ALICE detector in p-Pb collisions at a nucleon-nucleon centre-of-mass energy of 5.02 TeV for transverse momentum ranges within 0.5 < pT,assoc < pT,trig < 4 GeV/c. The correlations are measured over two units of pseudorapidity and full azimuthal angle in different intervals of event multiplicity, and expressed as associated yield per trigger particle. Two long-range ridge-like structures, one on the near side and one on the away side, are observed when the per-trigger yield obtained in low-multiplicity events is subtracted from the one in high-multiplicity events. The excess on the near-side is qualitatively similar to that recently reported by the CMS collaboration, while the excess on the away-side is reported for the first time. The two-ridge structure projected onto azimuthal angle is quantified with the second and third Fourier coefficients as well as by near-side and away-side yields and widths. The yields on the near side and on the away side are equal within the uncertainties for all studied event multiplicity and pT bins, and the widths show no significant evolution with event multiplicity or pT. These findings suggest that the near-side ridge is accompanied by an essentially identical away-side ridge.

Measurement of the inclusive differential jet cross section in pp collisions at 2.76 TeV - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamová (Physics Letters B, 2013)
The ALICE Collaboration at the CERN Large Hadron Collider reports the first measurement of the inclusive differential jet cross section at mid-rapidity in pp collisions at 2.76 TeV, with integrated luminosity of 13.6 nb−1. Jets are measured over the transverse momentum range 20 to 125 GeV/c and are corrected to the particle level. Calculations based on Next-to-Leading Order perturbative QCD are in good agreement with the measurements. The ratio of inclusive jet cross sections for jet radii R=0.2R=0.2 and R=0.4R=0.4 is reported, and is also well reproduced by a Next-to-Leading Order perturbative QCD calculation when hadronization effects are included.

Mid-rapidity anti-baryon to baryon ratios in pp collisions at sqrt(s) = 0.9, 2.76 and 7 TeV measured by ALICE - E. Abbas; B. Abelev; Ralf Keidel; J. Adam (2013)
The ratios of yields of anti-baryons to baryons probes the mechanisms of baryon-number transport. Results for anti-p/p, anti-Λ/Λ, anti-Ξ+/Ξ- and anti-Ω+/Ω- in pp collisions at sqrt(s) = 0.9, 2.76 and 7TeV, measured with the ALICE detector at the LHC, are reported. Within the experimental uncertainties and ranges covered by our measurement, these ratios are independent of rapidity, transverse momentum and multiplicity for all measured energies. The results are compared to expectations from event generators, such as PYTHIA and HIJING/B, that are used to model the particle production in pp collisions. The energy dependence of anti-p/p, anti-Λ/Λ, anti-Ξ+/Ξ- and anti-Ω+/Ω-, reaching values compatible with unity for sqrt(s) = 7TeV, complement the earlier anti-p/p measurement of ALICE. These dependencies can be described by exchanges with the Regge-trajectory intercept of α_j 0.5, which are suppressed with increasing rapidity interval Δ y. Any significant contribution of an exchange not suppressed at large Δ y (reached at LHC energies) is disfavoured.

Multi-strange baryon production at mid-rapidity in Pb-Pb collisions at = 2.76 TeV - Betty Abelev; Jaroslav Adam; Dagmar Adamova; Ralf Keidel (2013)
The ALICE experiment at the LHC has measured the production of Ξ- and Ω- baryons and their anti-particles in Pb-Pb collisions at sqrt(s_NN) = 2.76 TeV. The transverse momentum spectra at mid-rapidity (|y| < 0.5) for charged Ξ and Ω hyperons have been studied in the range 0.6 < pT < 8.0 GeV/c and 1.2 < pT < 7.0 GeV/c, respectively, and in several centrality intervals (from the most central 0-10% to the most peripheral 60-80% collisions). These spectra have been compared with the predictions of recent hydrodynamic models. In particular, the Kraków and EPOS models give a satisfactory description of the data, with the latter covering a wider pT range. Mid-rapidity yields, integrated over pT, have been determined. The hyperon-to-pion ratios are similar to those at RHIC: they rise smoothly with centrality up to <N_part> 150 and saturate thereafter. The enhancements (yields per participant nucleon relative to p-p collisions) increase both with the strangeness content of the baryon and with centrality, but are less pronounced than at lower energies.

Multiplicity dependence of the average transverse momentum in pp, p-Pb, and Pb-Pb collisions at the LHC - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (2013)
The average transverse momentum <pT> versus the charged-particle multiplicity Nch was measured in p-Pb collisions at a collision energy per nucleon-nucleon pair sNN‾‾‾‾√ = 5.02 TeV and in pp collisions at collision energies of s√ = 0.9, 2.76, and 7 Tev in the kinematic range 0.15 < pT < 10.0 Gev/c and |η| < 0.3 with the ALICE apparatus at the LHC. These data are compared to results in Pb-Pb collisions at sNN‾‾‾‾√ = 2.76 Tev at similar charged-particle multiplicities. In pp and p-Pb collisions, a strong increase of <pT> with Nch is observed, which is much stronger than that measured in Pb-Pb collisions. For pp collisions, this could be attributed, within a model of hadronizing strings, to multiple-parton interactions and to a final-state color reconnection mechanism. The data in p-Pb and Pb-Pb collisions cannot be described by an incoherent superposition of nucleon-nucleon collisions and pose a challenge to most of the event generators.

Multiplicity dependence of two-particle azimuthal correlations in pp collisions at the LHC - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (2013)
We present the measurements of particle pair yields per trigger particle obtained from di-hadron azimuthal correlations in pp collisions at sqrt(s) = 0.9, 2.76, and 7 TeV recorded with the ALICE detector. The yields are studied as a function of the charged particle multiplicity. Taken together with the single particle yields the pair yields provide information about parton fragmentation at low transverse momenta, as well as on the contribution of multiple parton interactions to particle production. Data are compared to calculations using the PYTHIA6, PYTHIA8, and PHOJET event generators.

Performance of the ALICE VZERO system - E. Abbas; Betty Abelev; Ralf Keidel; Jaroslav Adam (2013)
ALICE is an LHC experiment devoted to the study of strongly interacting matter in proton–proton, proton–nucleus and nucleus–nucleus collisions at ultra-relativistic energies. The ALICE VZERO system, made of two scintillator arrays at asymmetric positions, one on each side of the interaction point, plays a central role in ALICE. In addition to its core function as a trigger, the VZERO system is used to monitor LHC beam conditions, to reject beam-induced backgrounds and to measure basic physics quantities such as luminosity, particle multiplicity, centrality and event plane direction in nucleus-nucleus collisions. After describing the VZERO system, this publication presents its performance over more than four years of operation at the LHC.

Pseudorapidity Density of Charged Particles in p+Pb Collisions at Pseudorapidity Density of Charged Particles in p+Pb Collisions at √sNN=5.02 TeV - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamová (Physical review letters, 2013)
The charged-particle pseudorapidity density measured over four units of pseudorapidity in nonsingle-diffractive p Pb collisions at a center-of-mass energy per nucleon pair ?sNN=5.02??TeV is presented. The average value at midrapidity is measured to be 16.81±0.71??(syst), which corresponds to 2.14±0.17??(syst) per participating nucleon, calculated with the Glauber model. This is 16% lower than in nonsingle-diffractive pp collisions interpolated to the same collision energy and 84% higher than in d Au collisions at ?sNN=0.2??TeV. The measured pseudorapidity density in p Pb collisions is compared to model predictions and provides new constraints on the description of particle production in high-energy nuclear collisions.

Transverse Momentum Distribution and Nuclear Modification Factor of Charged Particles in p-Pb Collisions at √ sNN=5.02 TeV - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (Physical Review Letters, 2013)
The transverse momentum (pT) distribution of primary charged particles is measured in minimum bias (non-single-diffractive) p+Pb collisions at √sNN=5.02 TeV with the ALICE detector at the LHC. The pT spectra measured near central rapidity in the range 0.5<pT<20 GeV/c exhibit a weak pseudorapidity dependence. The nuclear modification factor RpPb is consistent with unity for pT above 2 GeV/c. This measurement indicates that the strong suppression of hadron production at high pT observed in Pb+Pb collisions at the LHC is not due to an initial-state effect. The measurement is compared to theoretical calculations.

𝐽/𝜓 Elliptic Flow in Pb-Pb Collisions at √𝑠𝑁⁢𝑁 =2.76 TeV - Ralf Keidel; E. Abbas; B. Abelev; J. Adam (2013)
We report on the first measurement of inclusive J/Psi elliptic flow, v2, in heavy-ion collisions at the LHC. The measurement is performed with the ALICE detector in Pb-Pb collisions at sqrt(sNN) = 2.76 TeV in the rapidity range 2.5 < y < 4.0. The dependence of the J/Psi v2 on the collision centrality and on the J/Psi transverse momentum is studied in the range 0 <= pT < 10 GeV/c. For semi-central Pb-Pb collisions at sqrt(sNN) = 2.76 TeV, an indication of non-zero v2 is observed with a maximum value of v2 = 0.116+/-0.046(stat.)+/-0.029(syst.) for J/Psi in the transverse momentum range 2 <= pT < 4 GeV/c. The elliptic flow measurement complements the previously reported ALICE results on the inclusive J/Psi nuclear modification factor and favors the scenario of a significant fraction of J/Psi production from charm quarks in a deconfined partonic phase.

Anisotropic flow of charged hadrons, pions and (anti-)protons measured at high transverse momentum in Pb-Pb collisions at =2.76 TeV. - B. Abelev; J. Adamova; Ralf Keidel; A. M. Adare (2012)
The elliptic, v2, triangular, v3, and quadrangular, v4, flow coefficients are measured for unidentified charged particles, pions and (anti-)protons in Pb-Pb collisions at =2.76 TeV with the ALICE detector at the Large Hadron Collider. Results obtained with the event plane and four-particle correlation methods are reported for the pseudo-rapidity range |η|<0.8 at different collision centralities and as a function of transverse momentum, , out to =20 GeV/c. The observed non-zero elliptic and triangular flow depends only weakly on transverse momentum for >8 GeV/c. The small dependence of the difference between elliptic flow results obtained from two- and four-particle cumulant methods suggests a common origin of flow fluctuations up to =8 GeV/c. The magnitude of the (anti-)proton elliptic and triangular flow is larger than that of pions out to at least =8 GeV/c indicating that the particle type dependence persists out to high .

Automatic tests to ensure the reliability of the ALICE DCS - Ralf Keidel; Michael Bittorf; Eric Sean Conner; Thomas Selig (Scientific Report, 2012)
The Detector Control System (DCS) for the ALICEdetectors TPC and TRD are based on the softwarecomponents: InterCom Layer (ICL)[1], FeeServer withState Engine, CommandCoder, DIM1 and PVSS2. Thissystem is performing reliable and stable during the lasttwo run periods. During this time three major softwareupdates have been shipped with far reaching changesin the code base. This was necessary to achieve performanceimprovements and fulfill feature requests.

Centrality Dependence of Charged Particle Production at Large Transverse Momentum in Pb–Pb Collisions at sNN‾‾‾‾√=2.76 TeV - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (2012)
The inclusive transverse momentum (pT) distributions of primary charged particles are measured in the pseudo-rapidity range |h| < 0.8 as a function of event centrality in Pb-Pb collisions at√sNN = 2.76 TeV with ALICE at the LHC. The data are presented in the pT range 0.15 < pT < 50 GeV/c for nine centrality intervals from70-80%to 0-5%. The Pb-Pb spectra are presented in terms of the nuclear modification factor RAA using a pp reference spectrum measured at the same collision energy. We observe that the suppression of high-pT particles strongly depends on event centrality. In central collisions (0-5%) the yield ismost suppressedwith RAA ≈0.13 at pT = 6-7 GeV/c. Above pT =7 GeV/c, there is a significant rise in the nuclear modification factor, which reaches RAA ≈ 0.4 for pT > 30 GeV/c.In peripheral collisions (70-80%), the suppression is weaker with RAA ≈ 0.7 almost independently of pT. The measured nuclear modification factors are compared to other measurements and model calculations.

Charge separation relative to the reaction plane in Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV. - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (2012)
Measurements of charge dependent azimuthal correlations with the ALICE detector at the LHC are reported for Pb-Pb collisions at s_NN = 2.76 TeV. Two- and three-particle charge-dependent azimuthal correlations in the pseudo-rapidity range |η| < 0.8 are presented as a function of the collision centrality, particle separation in pseudo-rapidity, and transverse momentum. A clear signal compatible with a charge-dependent separation relative to the reaction plane is observed, which shows little or no collision energy dependence when compared to measurements at RHIC energies. This provides a new insight for understanding the nature of the charge dependent azimuthal correlations observed at RHIC and LHC energies.

Charged kaon femtoscopic correlations in pp collisions at s√=7 TeV - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (2012)
Correlations of two charged identical kaons (Kch Kch) are measured in pp collisions at s√=7 TeV by the ALICE experiment at the Large Hadron Collider (LHC). One-dimensional Kch Kch correlation functions are constructed in three multiplicity and four transverse momentum ranges. The Kch Kch femtoscopic source parameters R and lambda are extracted. The Kch Kch correlations show a slight increase of femtoscopic radii with increasing multiplicity and a slight decrease of radii with increasing transverse momentum. These trends are similar to the ones observed for ππ and K0sK0s correlations in pp and heavy-ion collisions. However, the observed one dimensional correlation radii for charged kaons are larger at high multiplicities than those for pions in contrast to what was observed in heavy-ion collisions at RHIC.

Coherent J/ψ photoproduction in ultra-peripheral Pb-Pb collisions at sNN‾‾‾‾√=2.76 TeV. - Betty Abelev; Jaroslav Adam; Ralf Keidel; DAgmar Adamova (2012)
The ALICE collaboration has made the first measurement at the LHC of J/y photoproduction in ultra-peripheral Pb-Pb-collisions at √sNN= 2.76 TeV. The J/y is identified via its dimuon decay in the forward rapidity region with the muon spectrometer for events where the hadronic activity is required to be minimal. The analysis is based on an event sample corresponding to an integrated luminosity of about 55 mb−1. The cross section for coherent J/y production in the rapidity interval - 3.6 < y < -2.6 is measured to be ds coh J/y dy=1.00±0.18(stat)+0.24 −0.26(syst) mb. The result is compared to theoretical models for coherent J/y production and found to be in good agreement with those models which include nuclear gluon shadowing.

D+s meson production at central rapidity in proton–proton collisions at s√=7 TeV. - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (Physics Letters B, 2012)
The pT-differential inclusive production cross section of the prompt charm-strange meson D+ s in the rapidity range |y| < 0.5 was measured in proton-proton collisions at √ s = 7 TeV at the LHC using the ALICE detector. The analysis was performed on a data sample of 2.98 × 108 events collected with a minimum-bias trigger. The corresponding integrated luminosity is Lint = 4.8 nb−1. Reconstructing the decay D+ s → φπ+, with φ → K−K+, and its charge conjugate, about 480 D± s mesons were counted,after selection cuts, in the transverse momentum range 2 < pT < 12 GeV/c. The results are compared with predictions from models based on perturbative QCD. The ratios of the cross sections of four D meson species (namely D0, D+, D∗+ and D+ s ) were determined both as a function of pT and integrated over pT after extrapolating to full pT range, together with the strangeness suppression factor in charm fragmentation. The obtained values are found to be compatible within uncertainties with those measured by other experiments in e+e−, ep and pp interactions at various centre-of-mass energies.

Harmonic decomposition of two-particle angular correlations in Pb-Pb collisions at sqrt(sNN) = 2.76 TeV. - K. Aamodt; B. Abelev; Ralf Keidel; A. Abrahantes Quintana (Physics Letters B, 2012)
Angular correlations between unidentified charged trigger (t) and associated (a) particles are measured by the ALICE experiment in Pb-Pb collisions at sqrt(sNN) = 2.76 TeV for transverse momenta 0.25 < pT^t,a < 15 GeV/c, where pT^t > pT^a. The shapes of the pair correlation distributions are studied in a variety of collision centrality classes between 0 and 50% of the total hadronic cross section for particles in the pseudorapidity interval |η| < 1.0. Distributions in relative azimuth Δφ φ^t - φ^a are analyzed for |Δη| |η^t - η^a| > 0.8, and are referred to as 'long-range correlations'. Fourier components V_nΔ <cos(nΔφ)> are extracted from the long-range azimuthal correlation functions. If particle pairs are correlated to one another through their individual correlation to a common symmetry plane, then the pair anisotropy V_nΔ(pT^t, pT^a) is fully described in terms of single-particle anisotropies v_n(pT) as V_nΔ(pT^t, pT^a) = v_n(pT^t) v_n(pT^a). This expectation is tested for 1 ≤ n ≤ 5 by applying a global fit of all V_nΔ(pT^t, pT^a) to obtain the best values v_nGF(pT). It is found that for 2 ≤ n ≤ 5, the fit agrees well with data up to pT^a 3-4 GeV/c, with a trend of increasing deviation as pT^t and pT^a are increased or as collisions become more peripheral. This suggests that no pair correlation harmonic can be described over the full 0.25 < pT < 15 GeV/c range using a single v_n(pT) curve/ such a description is however approximately possible for 2 ≤ n ≤ 5 when pT^a < 4 GeV/c. For the n=1 harmonic, however, a single v_1(pT) curve is not obtained even within the reduced range pT^a < 4 GeV/c.

Heavy flavour decay muon production at forward rapidity in proton–proton collisions at (s) = 7 TeV. - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (Physics Letters B, 2012)
The production of muons from heavy flavour decays is measured at forward rapidity in proton–proton collisions at (s) = 7 TeV collected with the ALICE experiment at the LHC. The analysis is carried out on a data sample corresponding to an integrated luminosity L_int = 16.5 nb^-1. The transverse momentum and rapidity differential production cross sections of muons from heavy flavour decays are measured in the rapidity range 2.5 < y < 4, over the transverse momentum range 2 < p_t < 12 GeV/c. The results are compared to predictions based on perturbative QCD calculations.

Inclusive J/psi production in pp collisions at sqrt(s) = 2.76 TeV - B. Abelev; J. Adam; D. Adamova; A. M. Adare; Ralf Keidel (arXiv.org e-print Archiv, 2012)
The ALICE Collaboration has measured inclusive J/psi production in pp collisions at a center of mass energy sqrt(s)=2.76 TeV at the LHC. The results presented in this Letter refer to the rapidity ranges |y|<0.9 and 2.5<y<4 and have been obtained by measuring the electron and muon pair decay channels, respectively. The integrated luminosities for the two channels are L^e_int=1.1 nb^-1 and L^mu_int=19.9 nb^-1, and the corresponding signal statistics are N_J/psi^e+e-=59 +/- 11 and N_J/psi^mu+mu-=1364 +/- 53. We present dsigma_J/psi/dy for the two rapidity regions under study and, for the forward-y range, d^2sigma_J/psi/dydp_t in the transverse momentum domain 0<p_t<8 GeV/c. The results are compared with previously published results at sqrt(s)=7 TeV and with theoretical calculations.

J/ψ Polarization in pp Collisions at √s=7 TeV - B. Abelev; A. Abrahantes Quintana; Ralf Keidel; D. Adamova (Physical review letters, 2012)
The ALICE Collaboration has studied J/ψ production in pp collisions at √s=7 TeV at the LHC through its muon pair decay. The polar and azimuthal angle distributions of the decay muons were measured, and results on the J/ψ polarization parameters λθ and λϕ were obtained. The study was performed in the kinematic region 2.5<y<4, 2<pt<8 GeV/c, in the helicity and Collins-Soper reference frames. In both frames, the polarization parameters are compatible with zero, within uncertainties.

J/ψ Production as a Function of Charged Particle Multiplicity in pp Collisions at s√=7 TeV. - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (Physics Letters B, 2012)
The ALICE collaboration reports the measurement of the inclusive J/psi yield as a function of charged particle pseudorapidity density dN_ch/deta in pp collisions at sqrts = 7 TeV at the LHC. J/psi particles are detected for p_t > 0, in the rapidity interval |y| < 0.9 via decay into e+e-, and in the interval 2.5 < y < 4.0 via decay into mu+mu- pairs. An approximately linear increase of the J/psi yields normalized to their event average (dN_J/psi/dy)/<dN_J/psi/dy> with (dN_ch/deta)/<dN_ch/deta> is observed in both rapidity ranges, where dN_ch/deta is measured within |eta| < 1 and p_t > 0. In the highest multiplicity interval with <dN_ch/deta(bin)> = 24.1, corresponding to four times the minimum bias multiplicity density, an enhancement relative to the minimum bias J/psi yield by a factor of about 5 at 2.5 < y < 4 (8 at |y| < 0.9) is observed.

J/ψ production at low transverse momentum in Pb-Pb collisions at sqrt(sNN) = 2.76 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2012)
The ALICE experiment has measured the inclusive J/psi production in Pb-Pb collisions at sqrt(sNN) = 2.76 TeV down to pt = 0 in the rapidity range 2.5 < y < 4. A suppression of the inclusive J/psi yield in Pb-Pb is observed with respect to the one measured in pp collisions scaled by the number of binary nucleon-nucleon collisions. The nuclear modification factor, integrated over the 0%-80% most central collisions, is 0.545 +/- 0.032 (stat.) +/- 0.084 (syst.) and does not exhibit a significant dependence on the collision centrality. These features appear significantly different from lower energy measurements. Models including J/psi production from charm quarks in a deconfined partonic phase can describe our data.

K0s K0s correlations in pp collisions at √s = 7 TeV from the LHC ALICE experiment - Betty Abelev; Jaroslav Adam; Dagmar Adamová; Ralf Keidel (Physics letters. B, 2012)
Identical neutral kaon pair correlations are measured in √s = 7 TeV pp collisions in the ALICEexperiment. One-dimensional K0s K0s correlation functions in terms of the invariant momentum difference of kaon pairs are formed in two multiplicity and two transverse momentum ranges. The femtoscopic parameters for the radius and correlation strength of the kaon source are extracted. The fit includes quantum statistics and final-state interactions of the a0/f0 resonance. K0s K0s correlations show an increase in radius for increasing multiplicity and a slight decrease in radius for increasing transverse mass, mT, as seen in ππ correlations in pp collisions and in heavy-ion collisions. Transverse mass scaling is observed between the K0s K0s and ππ radii. Also, the first observation is made of the decay of the f2(1525) meson into the K0s K0s channel in pp collisions.

Light vector meson production in pp collisions at view the MathML source - B. Abelev; A. Abrahantes Quintana; Ralf Keidel; D. Adamova (Physics letters B, 2012)
The ALICE experiment has measured low-mass dimuon production in pp collisions at s = 7 TeV in the dimuon rapidity region 2.5<y<4. The observed dimuon mass spectrum is described as a superposition of resonance decays (η, ρ, ω, η^', φ) into muons and semi-leptonic decays of charmed mesons. The measured production cross sections for ω and φ are σ_ω (1<p_t<5 GeV/c,2.5<y<4) = 5.28 +- 0.54 (stat) +- 0.50 (syst) mb and σ_φ(1<p_t<5 GeV/c,2.5<y<4)=0.940 +- 0.084 (stat) +- 0.078 (syst) mb. The differential cross sections d^2σ/dy dp_t are extracted as a function of p_t for ω and φ. The ratio between the ρ and ω cross section is obtained. Results for the φ are compared with other measurements at the same energy and with predictions by models.

Measurement of charm production at central rapidity in proton-proton collisions at s√=7 TeV. - B. Abelev; A. Abrahantes Quintana; Ralf Keidel; D. Adamova (Journal of High Energy Physics, 2012)
The pt-differential inclusive production cross sections of the prompt charmed mesons D0, D+, and D*+ in the rapidity range |y|<0.5 were measured in proton-proton collisions at sqrt(s) = 7 TeV at the LHC using the ALICE detector. Reconstructing the decays D0->K-pi+, D+->K-pi+pi+, D*+->D0pi+, and their charge conjugates, about 8,400 D0, 2,900 D+, and 2,600 D*+ mesons with 1<pt<24 GeV/c were counted, after selection cuts, in a data sample of 3.14x10^8 events collected with a minimum-bias trigger (integrated luminosity L_int = 5/nb). The results are described within uncertainties by predictions based on perturbative QCD.

Measurement of electrons from beauty hadron decays in pp collisions at s√=7 TeV. - Jaroslav Adam; Betty Abelev; Ralf Keidel; Dagmar Adamova (2012)
The production cross section of electrons from semileptonic decays of beauty hadrons was measured at mid-rapidity (|y| < 0.8) in the transverse momentum range 1 < pt < 8 Gev/c with the ALICE experiment at the CERN LHC in pp collisions at a center of mass energy sqrts = 7 TeV using an integrated luminosity of 2.2 nb^-1. Electrons from beauty hadron decays were selected based on the displacement of the decay vertex from the collision vertex. A perturbative QCD calculation agrees with the measurement within uncertainties. The data were extrapolated to the full phase space to determine the total cross section for the production of beauty quark-antiquark pairs.

Measurement of event background fluctuations for charged particle jet reconstruction in Pb-Pb collisions at Wurzel sNN = 2.76 TeV - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (Journal of high energy physics, 2012)
The effect of event background fluctuations on charged particle jet reconstruction in Pb-Pb collisions at sqrt(s_NN) = 2.76 TeV has been measured with the ALICE experiment. The main sources of non-statistical fluctuations are characterized based purely on experimental data with an unbiased method, as well as by using single high p_t particles and simulated jets embedded into real Pb-Pb events and reconstructed with the anti-kt jet finder. The influence of a low transverse momentum cut-off on particles used in the jet reconstruction is quantified by varying the minimum track p_t between 0.15 GeV/c and 2 GeV/c. For embedded jets reconstructed from charged particles with p_t > 0.15 GeV/c, the uncertainty in the reconstructed jet transverse momentum due to the heavy-ion background is measured to be 11.3 GeV/c (standard deviation) for the 10% most central Pb-Pb collisions, slightly larger than the value of 11.0 GeV/c measured using the unbiased method. For a higher particle transverse momentum threshold of 2 GeV/c, which will generate a stronger bias towards hard fragmentation in the jet finding process, the standard deviation of the fluctuations in the reconstructed jet transverse momentum is reduced to 4.8-5.0 GeV/c for the 10% most central events. A non-Gaussian tail of the momentum uncertainty is observed and its impact on the reconstructed jet spectrum is evaluated for varying particle momentum thresholds, by folding the measured fluctuations with steeply falling spectra.

Measurement of inelastic, single- and double-diffraction cross sections in proton–proton collisions at the LHC with ALICE. - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (The European Physical Journal C, 2012)
Measurements of cross sections of inelastic and diffractive processes in proton-proton collisions at LHC energies were carried out with the ALICE detector. The fractions of diffractive processes in inelastic collisions were determined from a study of gaps in charged particle pseudorapidity distributions:for single diffraction (diffractive mass MX <200 GeV/c2) sSD=sINEL =0:210:03;0:20+0:07

Measurement of prompt and non-prompt J/ψ production cross sections at mid-rapidity in pp collisions at √s=7 TeV. - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (2012)
The ALICE experiment at the LHC has studied J/psi production at mid-rapidity in pp collisions at s = 7 TeV through its electron pair decay on a data sample corresponding to an integrated luminosity L_int = 5.6nb-1. The fraction of J/psi from the decay of long-lived beauty hadrons was determined for J/psi candidates with transverse momentum pt > 1.3 GeV/c and rapidity |y| < 0.9. The cross section for prompt J/psi mesons, i.e. directly produced J/psi and prompt decays of heavier charmonium states such as the Psi(2S) and Csi_c resonances, is sigma_prompt-J/psi(pt > 1.3 GeV/c, |y| < 0.9) = 7.2 +- 0.7(stat.) +- 1.0(syst.)+1.3-1.2 (syst.pol.) mb. The pt-differential cross section for prompt J/psi has also been measured. The cross section for the production of b-hadrons decaying to J/psi with transverse momentum greater than 1.3 GeV/c in the rapidity range |y| < 0.9 is sigma_J/psi<-h_B = 1.26 +- 0.33 (stat.) +0.23-0.28 (syst.) mb. The results are compared to QCD model predictions. The shape of the pt and y distributions of b-quarks predicted by perturbative QCD model calculations are used to extrapolate the measured cross section to derive the bb pair total cross section and dsigma/dy at midrapidity.

Multi-strange baryon production in pp collisions at √s = 7 TeV with ALICE - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (Physik Letters B, 2012)
A measurement of the multi-strange Xi- and Omega- baryons and their antiparticles by the ALICE experiment at the CERN Large Hadron Collider (LHC) is presented for inelastic proton-proton collisions at centre of mass energy of 7 TeV. The transverse momentum (pt) distributions were studied at mid-rapidity (|y| < 0.5) in the range of 0.6 < pt < 8.5 GeV/c for Xi- and Xi+ baryons, and in the range of 0.8 < pt < 5 GeV/c for Omega- and Omega+. Baryons and antibaryons were measured as separate particles and we find that the baryon to antibaryon ratio of both particle species is consistent with unity over the entire range of the measurement. The statistical precision of the current LHC data has allowed us to measure a difference between the mean pt of Xi- (Xi+) and Omega- (Omega+). Particle yields, mean pt, and the spectra in the intermediate pt range are not well described by the PYTHIA Perugia 2011 tune Monte Carlo event generator, which has been tuned to reproduce the early LHC data. The discrepancy is largest for Omega- (Omega+). This PYTHIA tune approaches the pt spectra of Xi- and Xi+ baryons below pt < 0.85 GeV/c and describes the Xi- and Xi+ spectra above pt > 6.0 GeV/c. We also illustrate the difference between the experimental data and model by comparing the corresponding ratios of (Omega-+Omega+)/(Xi-+Xi+) as a function of transverse mass.

Net-Charge Fluctuations in Pb-Pb collisions at _N - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (2012)
We report the first measurement of the net-charge fluctuations in Pb-Pb collisions at (s)_NN = 2.76 TeV, measured with the ALICE detector at the CERN Large Hadron Collider. The dynamical fluctuations per unit entropy are observed to decrease when going from peripheral to central collisions. An additional reduction in the amount of fluctuations is seen in comparison to the results from lower energies. We examine the dependence of fluctuations on the pseudo-rapidity interval, which may account for the dilution of fluctuations during the evolution of the system. We find that the ALICE data points are between the theoretically predicted values for a hadron gas and a Quark-Gluon Plasma.

Neutral pion and η meson production in proton-proton collisions at s√=0.9 TeV and s√=7 TeV. - B. Abelev; A. Abrahantes Quintana; Ralf Keidel; D. Adamova (2012)
The first measurements of the invariant differential cross sections of inclusive π0 and η meson production at mid-rapidity in proton-proton collisions at s√=0.9 TeV and s√=7 TeV are reported. The π0 measurement covers the ranges 0.4<pT<7 GeV/c and 0.3<pT<25 GeV/c for these two energies, respectively. The production of η mesons was measured at s√=7 TeV in the range 0.4<pT<15 GeV/c. Next-to-Leading Order perturbative QCD calculations, which are consistent with the π0 spectrum at s√=0.9 TeV, overestimate those of π0 and η mesons at s√=7 TeV, but agree with the measured η/π0 ratio at s√=7 TeV.

Particle-yield modification in jet-like azimuthal di-hadron correlations in Pb-Pb collisions at √sNN = 2.76 TeV. - K. Aamodt; B. Abelev; Ralf Keidel; A. Abranantes Quintana (Physical Review Letters, 2012)
The yield of charged particles associated with high-pt trigger particles (8<pt<15 GeV/c) is measured with the ALICE detector in Pb-Pb collisions at √sNN=2.76 TeV relative to proton-proton collisions at the same energy. The conditional per-trigger yields are extracted from the narrow jetlike correlation peaks in azimuthal dihadron correlations. In the 5% most central collisions, we observe that the yield of associated charged particles with transverse momenta pt>3 GeV/c on the away side drops to about 60% of that observed in pp collisions, while on the near side a moderate enhancement of 20%-30% is found.

Pion, Kaon, and Proton Production in Central Pb-Pb Collisions at √sNN=2.76 TeV - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (Physical Review Letters, 2012)
In this Letter we report the first results on π±, K±, p, and p̅ production at midrapidity (|y|<0.5) in central Pb-Pb collisions at √sNN=2.76 TeV, measured by the ALICE experiment at the LHC. The pT distributions and yields are compared to previous results at √sNN=200 GeV and expectations from hydrodynamic and thermal models. The spectral shapes indicate a strong increase of the radial flow velocity with √sNN, which in hydrodynamic models is expected as a consequence of the increasing particle density. While the K/π ratio is in line with predictions from the thermal model, the p/π ratio is found to be lower by a factor of about 1.5. This deviation from thermal model expectations is still to be understood.

Production of K∗0(892) and ϕ(1020) in pp collisions at s√=7 TeV - Ralf Keidel; Betty Abelev; Jaroslav Adam; Dagmar Adamová (The European Physics Journal C, 2012)
The production of K*(892)^0 and phi(1020) in pp collisions at sqrt(s)=7 TeV was measured by the ALICE experiment at the LHC.The yields and the transverse momentum spectra d^2N/dydpT at midrapidity |y|<0.5 in the range 0<pT<6 GeV/c for K*(892)^0 and 0.4<pT<6 GeV/c for phi(1020) are reported and compared to model predictions. Using the yield of pions, kaons, and Omega baryons measured previously by ALICE at sqrt(s)=7 TeV, the ratios K*/K^-, phi/K*, phi/K^-, phi/π^-, and (Omega + anti-Omega)/phi are presented. The values of the K*/K^-, phi/K* and phi/K^- ratios are similar to those found at lower centre-of-mass energies. In contrast, the phi/pi^- ratio, which has been observed to increase with energy, seems to saturate above 200 GeV. The (Omega + anti-Omega)/phi ratio in the pT range 1-5 GeV/c is found to be in good agreement with the prediction of the HIJING/BB v2.0 model with a strong colour field.

Production of muons from heavy flavour decays at forward rapidity in pp and Pb-Pb collisions at √sNN=2.76 TeV. - J. Adam; B. Abelev; Ralf Keidel; D. Adamova (2012)
The ALICE Collaboration has measured the inclusive production of muons from heavy flavour decays at forward rapidity, 2.5 < y < 4, in pp and Pb-Pb collisions at √ sNN = 2.76 TeV. The pt-differential inclusive cross section of muons from heavy flavour decays in pp collisions is compared to perturbative QCD calculations. The nuclear modification factor is studied as a function of pt and collision centrality. A weak suppression is measured in peripheral collisions. In the most central collisions, a suppression of a factor of about 3-4 is observed in 6 < pt < 10 GeV/c. The suppression shows no significant pt dependence.

Pseudorapidity density of charged particles p-Pb collisions at sNN‾‾‾‾√=5.02 TeV. - Betty Abelev; Jaroslav Adam; Ralf Keidel; Dagmar Adamova (2012)
The charged-particle pseudorapidity density measured over 4 units of pseudorapidity in non-singlediffractive (NSD) p-Pb collisions at a centre-of-mass energy per nucleon pair psNN= 5.02 TeV is presented. The average value at midrapidity is measured to be 16.81 0.71 (syst.), which corresponds to 2.14 0.17 (syst.) per participating nucleon. This is 16% lower than in NSD pp collisions interpolated to the same collision energy, and 84% higher than in d-Au collisions at psNN =0:2 TeV. The measured pseudorapidity density in p-Pb collisions is compared to model predictions, and provides new constraints on the description of particle production in high-energy nuclear collisions.

Transverse sphericity of primary charged particles in minimum bias proton-proton collisions at sqrt(s)=0.9, 2.76 and 7 TeV. - B. Abelev; J. Adam; Ralf Keidel; D. Adamova (2012)
Measurements of the sphericity of primary charged particles in minimum bias proton–proton collisions at sqrt(s)=0.9, 2.76 and 7 TeV with the ALICE detector at the LHC are presented. The observable is linearized to be collinear safe and is measured in the plane perpendicular to the beam direction using primary charged tracks with pT≥0.5 GeV/c in |η|≤0.8. The mean sphericity as a function of the charged particle multiplicity at mid-rapidity (Nch) is reported for events with different pT scales ('soft' and 'hard') defined by the transverse momentum of the leading particle. In addition, the mean charged particle transverse momentum versus multiplicity is presented for the different event classes, and the sphericity distributions in bins of multiplicity are presented. The data are compared with calculations of standard Monte Carlo event generators. The transverse sphericity is found to grow with multiplicity at all collision energies, with a steeper rise at low Nch, whereas the event generators show the opposite tendency. The combined study of the sphericity and the mean pT with multiplicity indicates that most of the tested event generators produce events with higher multiplicity by generating more back-to-back jets resulting in decreased sphericity (and isotropy). The PYTHIA6 generator with tune PERUGIA-2011 exhibits a noticeable improvement in describing the data, compared to the other tested generators.

Underlying Event measurements in pp collisions at sqrt s = 0.9 and 7 TeV with the ALICE experiment at the LHC - B. Abelev; A. Abrahantes Quintana; Ralf Keidel; D. Adamova (Journal of high energy physics, 2012)
We present measurements of Underlying Event observables in pp collisions at sqrt(s) = 0.9 and 7 TeV. The analysis is performed as a function of the highest charged-particle transverse momentum pT,LT in the event. Different regions are defined with respect to the azimuthal direction of the leading (highest transverse momentum) track: Toward, Transverse and Away. The Toward and Away regions collect the fragmentation products of the hardest partonic interaction. The Transverse region is expected to be most sensitive to the Underlying Event activity. The study is performed with charged particles above three different pT thresholds: 0.15, 0.5 and 1.0 GeV/c. In the Transverse region we observe an increase in the multiplicity of a factor 2-3 between the lower and higher collision energies, depending on the track pT threshold considered. Data are compared to Pythia 6.4, Pythia 8.1 and Phojet. On average, all models considered underestimate the multiplicity and summed pT in the Transverse region by about 10-30%.

Centrality dependence of the charged-particle multiplicity density at midrapidity in Pb-Pb collisions at sqrt(sNN) = 2.76 TeV. - K. Aamodt; A. Abrahantes Quintana; Ralf Keidel; D. Adamova (Physical review letters : PRL ; providing rapid publication of short reports of important fundamental research with coverage of major advances in all aspects of physics and of developments with significant consequences across subdisciplines, 2011)
The centrality dependence of the charged-particle multiplicity density at midrapidity in Pb-Pb collisions at ?sNN=2.76??TeV is presented. The charged-particle density normalized per participating nucleon pair increases by about a factor of 2 from peripheral (70%?80%) to central (0%?5%) collisions. The centrality dependence is found to be similar to that observed at lower collision energies. The data are compared with models based on different mechanisms for particle production in nuclear collisions.

Femtoscopy of pp collisions at sqrts=0.9 and 7 TeV at the LHC with two-pion Bose-Einstein correlations - K. Aamodt; A. Abrahantes Quintana; Ralf Keidel; D. Adamova (2011)
We report on the high statistics two-pion correlation functions from pp collisions at sqrts=0.9 TeV and sqrts=7 TeV, measured by the ALICE experiment at the Large Hadron Collider. The correlation functions as well as the extracted source radii scale with event multiplicity and pair momentum. When analyzed in the same multiplicity and pair transverse momentum range, the correlation is similar at the two collision energies. A three-dimensional femtoscopic analysis shows an increase of the emission zone with increasing event multiplicity as well as decreasing homogeneity lengths with increasing transverse momentum. The latter trend gets more pronounced as multiplicity increases. This suggests the development of space-momentum correlations, at least for collisions producing a high multiplicity of particles. We consider these trends in the context of previous femtoscopic studies in high-energy hadron and heavy-ion collisions, and discuss possible underlying physics mechanisms. Detailed analysis of the correlation reveals an exponential shape in the outward and longitudinal directions, while the sideward remains a Gaussian. This is interpreted as a result of a significant contribution of strongly decaying resonances to the emission region shape. Significant non-femtoscopic correlations are observed, and are argued to be the consequence of 'mini-jet'-like structures extending to low p_T. They are well reproduced by the Monte-Carlo generators and seen also in pi^+ pi^- correlations.

Further Enhancements of the Front-End-Electronics Communication Software - Ralf Keidel; Michael Bittorf; Eric Sean Conner (GSI Scientific Report 2010, 2011)
The InterComLayer (ICL) of the Front-End-Electronics communication (FeeCom) chain has been refactored and enhanced to adapt to the requirements which have arisen during daily usage by the pertinent detectors in ALICE. A major focus has been set on the implementation of a dynamic watch dog time out system, bug fixing and full support of all log channels.

Higher harmonic anisotropic flow measurements of charged particles in Pb-Pb collisions at ... = 2.76 TeV - K. Aamodt; B. Abelev; Ralf Keidel; A. Abrahantas Quintana (Physical review letters, 2011)
We report on the first measurement of the triangular v3, quadrangular v4, and pentagonal v5 charged particle flow in Pb-Pb collisions at √sNN=2.76 TeV measured with the ALICE detector at the CERN Large Hadron Collider. We show that the triangular flow can be described in terms of the initial spatial anisotropy and its fluctuations, which provides strong constraints on its origin. In the most central events, where the elliptic flow v2 and v3 have similar magnitude, a double peaked structure in the two-particle azimuthal correlations is observed, which is often interpreted as a Mach cone response to fast partons. We show that this structure can be naturally explained from the measured anisotropic flow Fourier coefficients.

Higher harmonic anisotropic flow measurements of charged particles in Pb-Pb collisions at 2.76 TeV - K. Aamodt; B. Abelev; Ralf Keidel; A. Abrahantas Quintana (2011)
We report on the first measurement of the triangular v3, quadrangular v4, and pentagonal v5 charged particle flow in Pb-Pb collisions at 2.76 TeV measured with the ALICE detector at the CERN Large Hadron Collider. We show that the triangular flow can be described in terms of the initial spatial anisotropy and its fluctuations, which provides strong constraints on its origin. In the most central events, where the elliptic flow v2 and v3 have similar magnitude, a double peaked structure in the two-particle azimuthal correlations is observed, which is often interpreted as a Mach cone response to fast partons. We show that this structure can be naturally explained from the measured anisotropic flow Fourier coefficients.

Production of pions, kaons and protons in pp collisions at sqrt(s)= 900 GeV with ALICE at the LHC. - K. Aamodt; A. Abrahantes Quintana; Ralf Keidel; D. Adamova (2011)
The production of pi+, pi-, K+, K-, p, and pbar at mid-rapidity has been measured in proton-proton collisions at sqrt(s) = 900 GeV with the ALICE detector. Particle identification is performed using the specific energy loss in the inner tracking silicon detector and the time projection chamber. In addition, time-of-flight information is used to identify hadrons at higher momenta. Finally, the distinctive kink topology of the weak decay of charged kaons is used for an alternative measurement of the kaon transverse momentum (pt) spectra. Since these various particle identification tools give the best separation capabilities over different momentum ranges, the results are combined to extract spectra from pt = 100 MeV/c to 2.5 GeV/c. The measured spectra are further compared with QCD-inspired models which yield a poor description. The total yields and the mean pt are compared with previous measurements, and the trends as a function of collision energy are discussed.

Rapidity and transverse momentum dependence of inclusive J/psi production in pp collisions at sqrt(s) = 7 TeV - K. Aamodt; A. Abrahantes Quintana; Ralf Keidel; D. Adamova (2011)

Suppression of charged particle production at large transverse momentum in central PbPb collisions at √sNN = 2.76 TeV - K. Aamodt; A. Abrahantes Quintana; Ralf Keidel; D. Adamová (Physics letters. B, 2011)
Inclusive transverse momentum spectra of primary charged particles in Pb-Pb collisions at sNN = 2.76 TeV have been measured by the ALICE Collaboration at the LHC. The data are presented for central and peripheral collisions, corresponding to 0-5% and 70-80% of the hadronic Pb-Pb cross section. The measured charged particle spectra in 08 and 03pT20 GeV/c are compared to the expectation in pp collisions at the same sNN , scaled by the number of underlying nucleon-nucleon collisions. The comparison is expressed in terms of the nuclear modification factor RAA. The result indicates only weak medium effects (RAA 0.7) in peripheral collisions. In central collisions, RAA reaches a minimum of about 0.14 at pT=6 -7GeV/c and increases significantly at larger pT. The measured suppression of high-pT particles is stronger than that observed at lower collision energies, indicating that a very dense medium is formed in central Pb-Pb collisions at the LHC.

Alignment of the ALICE inner tracking system with cosmic-ray tracks / Authors: ALICE collaboration - K. Aamodt; Ralf Keidel; Eric Sean Conner; Sebastian Bablok (Journal of instrumentation, 2010)
ALICE (A Large Ion Collider Experiment) is the LHC (Large Hadron Collider) experiment devoted to investigating the strongly interacting matter created in nucleus-nucleus collisions at the LHC energies. The ALICE ITS, Inner Tracking System, consists of six cylindrical layers of silicon detectors with three different technologies; in the outward direction: two layers of pixel detectors, two layers each of drift, and strip detectors. The number of parameters to be determined in the spatial alignment of the 2198 sensor modules of the ITS is about 13,000. The target align- ment precision is well below 10 ?m in some cases (pixels). The sources of alignment information include survey measurements, and the reconstructed tracks from cosmic rays and from proton- proton collisions. The main track-based alignment method uses the Millepede global approach. An iterative local method was developed and used as well. We present the results obtained for the ITS alignment using about 105 charged tracks from cosmic rays that have been collected during summer 2008, with the ALICE solenoidal magnet switched off.

Charged-particle multiplicity density at mid-rapidity in central Pb-Pb collisions at sqrt(sNN) = 2.76 TeV. - K. Aamodt; B. Abelev; Ralf Keidel; A. Abrahantes Quintana (2010)
The first measurement of the charged-particle multiplicity density at mid-rapidity in Pb-Pb collisions at a centre-of-mass energy per nucleon pair sqrt(sNN) = 2.76 TeV is presented. For an event sample corresponding to the most central 5% of the hadronic cross section the pseudo-rapidity density of primary charged particles at mid-rapidity is 1584 +- 4 (stat) +- 76 (sys.), which corresponds to 8.3 +- 0.4 (sys.) per participating nucleon pair. This represents an increase of about a factor 1.9 relative to pp collisions at similar collision energies, and about a factor 2.2 to central Au-Au collisions at sqrt(sNN) = 0.2 TeV. This measurement provides the first experimental constraint for models of nucleus-nucleus collisions at LHC energies.

Charged-particle multiplicity measurement in proton-proton collisions at sqrt(s) = 7 TeV with ALICE at LHC - Ralf Keidel; Eric Sean Conner; Sebastian Bablok; K. Aamodt (The European Physical Journal C, 2010)
The pseudorapidity density and multiplicity distribution of charged particles produced in proton-proton collisions at the LHC, at a centre-of-mass energy sqrt(s) = 7 TeV, were measured in the central pseudorapidity region |eta| < 1. Comparisons are made with previous measurements at sqrt(s) = 0.9 TeV and 2.36 TeV. At sqrt(s) = 7 TeV, for events with at least one charged particle in |eta| < 1, we obtain dNch/deta = 6.01 +- 0.01 (stat.) +0.20 -0.12 (syst.). This corresponds to an increase of 57.6% +- 0.4% (stat.) +3.6 -1.8% (syst.) relative to collisions at 0.9 TeV, significantly higher than calculations from commonly used models. The multiplicity distribution at 7 TeV is described fairly well by the negative binomial distribution.

Charged-particle multiplicity measurement in proton-proton collisions at and 2.36 TeV with ALICE at LHC - K. Aamodt; N. Abel; Ralf Keidel; U. Abeysekara (The European Physical Journal C, 2010)
Charged-particle production was studied in proton-proton collisions collected at the LHC with the ALICE detector at centre-of-mass energies 0.9 TeV and 2.36 TeV in the pseudorapidity range |η|<1.4. In the central region (|η|<0.5), at 0.9 TeV, we measure charged-particle pseudorapidity density for inelastic interactions, and for non-single-diffractive interactions. At 2.36 TeV, we find for inelastic, and for non-single-diffractive collisions. The relative increase in charged-particle multiplicity from the lower to higher energy is for inelastic and for non-single-diffractive interactions. This increase is consistent with that reported by the CMS collaboration for non-single-diffractive events and larger than that found by a number of commonly used models. The multiplicity distribution was measured in different pseudorapidity intervals and studied in terms of KNO variables at both energies. The results are compared to proton-antiproton data and to model predictions.

Elliptic flow of charged particles in Pb-Pb collisions at 2.76 TeV. - K. Aamodt; B. Abelev; Ralf Keidel; A. Abrahantes Quintana (2010)
We report the first measurement of charged particle elliptic flow in Pb-Pb collisions at 2.76 TeV with the ALICE detector at the CERN Large Hadron Collider. The measurement is performed in the central pseudorapidity region (|eta|<0.8) and transverse momentum range 0.2< p_t< 5.0 GeV/c. The elliptic flow signal v_2, measured using the 4-particle correlation method, averaged over transverse momentum and pseudorapidity is 0.087 +/- 0.002 (stat) +/- 0.004 (syst) in the 40-50% centrality class. The differential elliptic flow v_2(p_t) reaches a maximum of 0.2 near p_t = 3 GeV/c. Compared to RHIC Au-Au collisions at 200 GeV, the elliptic flow increases by about 30%. Some hydrodynamic model predictions which include viscous corrections are in agreement with the observed increase.

First proton–proton collisions at the LHC as observed with the ALICE detector: measurement of the charged particle pseudorapidity density at sqrt(s) = 900 GeV - K. Aamodt; Ralf Keidel; Eric Sean Conner (The European Physical Journal C, 2010)
On 23rd November 2009, during the early commissioning of the CERN Large Hadron Collider (LHC), two counter-rotating proton bunches were circulated for the first time concurrently in the machine, at the LHC injection energy of 450 GeV per beam. Although the proton intensity was very low, with only one pilot bunch per beam, and no systematic attempt was made to optimize the collision optics, all LHC experiments reported a number of collision candidates. In the ALICE experiment, the collision region was centred very well in both the longitudinal and transverse directions and 284 events were recorded in coincidence with the two passing proton bunches. The events were immediately reconstructed and analyzed both online and offline. We have used these events to measure the pseudorapidity density of charged primary particles in the central region. In the range |eta| < 0.5, we obtain dNch/deta = 3.10 +- 0.13 (stat.) +- 0.22 (syst.) for all inelastic interactions, and dNch/deta = 3.51 +- 0.15 (stat.) +- 0.25 (syst.) for non-single diffractive interactions. These results are consistent with previous measurements in proton–antiproton interactions at the same centre-of-mass energy at the CERN SppS collider. They also illustrate the excellent functioning and rapid progress of the LHC accelerator, and of both the hardware and software of the ALICE experiment, in this early start-up phase.

Midrapidity antiproton-to-proton ratio in pp collisions at s = 0.9 and 7TeV measured by the ALICE experiment - K. Aamodt; Ralf Keidel; Eric Sean Conner; Sebastian Bablok (Physiks Review Letters, 2010)
The ratio of the yields of antiprotons to protons in pp collisions has been measured by the ALICE experiment at √s=0.9 and 7 TeV during the initial running periods of the Large Hadron Collider. The measurement covers the transverse momentum interval 0.45<pt<1.05 GeV/c and rapidity |y|<0.5. The ratio is measured to be R|y|<0.5=0.957±0.006(stat)±0.014(syst) at 0.9 TeV and R|y|<0.5=0.991±0.005(stat)±0.014(syst) at 7 TeV and it is independent of both rapidity and transverse momentum. The results are consistent with the conventional model of baryon-number transport and set stringent limits on any additional contributions to baryon-number transfer over very large rapidity intervals in pp collisions.

Strange particle production in proton-proton collisions at sqrt(s) = 0.9 TeV with ALICE at the LHC - K. Aamodt; A. Abrahantes Quintana; Ralf Keidel; D. Adamova (2010)
The production of mesons containing strange quarks (K0s, phi) and both singly and doubly strange baryons (Lambda, Anti-Lambda, and Xi+Anti-Xi) are measured at central rapidity in pp collisions at s = 0.9 TeV with the ALICE experiment at the LHC. The results are obtained from the analysis of about 250 k minimum bias events recorded in 2009. Measurements of yields (dN/dy) and transverse momentum spectra at central rapidities for inelastic pp collisions are presented. For mesons, we report yields (<dN/dy>) of 0.184 ± 0.002 stat. ± 0.006 syst. for K0s and 0.021 ± 0.004 stat. ± 0.003 syst. for phi. For baryons, we find <dN/dy> = 0.048 ± 0.001 stat. ± 0.004 syst. for Lambda, 0.047 ± 0.002 stat. ± 0.005 syst. for Anti-Lambda and 0.0101 ± 0.0020 stat. ± 0.0009 syst. for Xi+Anti-Xi. The results are also compared with predictions for identified particle spectra from QCD-inspired models and provide a baseline for comparisons with both future pp measurements at higher energies and heavy-ion collisions.

The ALICE TPC, a large 3-dimensional tracking device with fast readout for ultra-high multiplicity events - J. Alme; Ralf Keidel; Sebastian Bablok (2010)
The design, construction, and commissioning of the ALICE Time-Projection Chamber (TPC) is described. It is the main device for pattern recognition, tracking, and identification of charged particles in the ALICE experiment at the CERN LHC. The TPC is cylindrical in shape with a volume close to 90 m3 and is operated in a 0.5 T solenoidal magnetic field parallel to its axis. In this paper we describe in detail the design considerations for this detector for operation in the extreme multiplicity environment of central Pb-Pb collisions at LHC energy. The implementation of the resulting requirements into hardware (field cage, read- out chambers, electronics), infrastructure (gas and cooling system, laser-calibration system), and software led to many technical innovations which are described along with a presentation of all the major components of the detector, as currently realized. We also report on the performance achieved after completion of the first round of stand-alone calibration runs and demonstrate results close to those specified in the TPC Technical Design Report.

Transverse momentum spectra of charged particles in proton-proton collisions at s = 900GeV with ALICE at the LHC - K. Aamodt; Ralf Keidel; Eric Sean Conner; Sebstian Bablok (Physics Letters B, 2010)
The inclusive charged particle transverse momentum distribution is measured in proton-proton collisions at s = 900GeV at the LHC using the ALICE detector. The measurement is performed in the central pseudorapidity region (|η|<0.8) over the transverse momentum range 0.15<p_T<10GeV/c. The correlation between transverse momentum and particle multiplicity is also studied. Results are presented for inelastic (INEL) and non-single-diffractive (NSD) events. The average transverse momentum for |η|<0.8 is <p_T>_INEL=0.483±0.001(stat.)±0.007(syst.)GeV/c and <p_T>_NSD=0.489±0.001(stat.)±0.007(syst.)GeV/c, respectively. The data exhibit a slightly larger <p_T> than measurements in wider pseudorapidity intervals. The results are compared to simulations with the Monte Carlo event generators PYTHIA and PHOJET.

Two-pion Bose-Einstein correlations in central PbPb collisions at sqrt(s_NN) = 2.76 TeV. - K. Aamodt; A. Abrahantes Quintana; Ralf Keidel; D. Adamova (2010)
The first measurement of two-pion Bose–Einstein correlations in central PbPb collisions at sNN=276 TeV at the Large Hadron Collider is presented. We observe a growing trend with energy now not only for the longitudinal and the outward but also for the sideward pion source radius. The pion homogeneity volume and the decoupling time are significantly larger than those measured at RHIC.

Two-pion Bose-Einstein correlations in pp collisions at sqrt(s)=900 GeV - K. Aamodt; Ralf Keidel; Eric Sean Conner; Sebastian Bablok (2010)
We report on the measurement of two-pion correlation functions from pp collisions at sqrt(s)=900 GeV performed by the ALICE experiment at the Large Hadron Collider. Our analysis shows an increase of the HBT radius with increasing event multiplicity, in line with other measurements done in particle- and nuclear collisions. Conversely, the strong decrease of the radius with increasing transverse momentum, as observed at RHIC and at Tevatron, is not manifest in our data.

Enhancements of the front-end-electronics communication software - Sebastian Bablok; Ralf Keidel; Eric Sean Conner (Scientific report / Gesellschaft für Schwerionenforschung, Darmstadt, 2009)
The InterComLayer (ICL) of the Front-End- Electronics communication (FeeCom) chain has been redeveloped and enhanced to adapt to the requirements which have arisen during daily usage by the pertinent detectors in ALICE. A major focus has been set on transfer performance and priority hierarchy imposed by the data transported. Transparency of the redesign to the underlying detectors has been achieved.

Front-End-Device - Application Programming Interface - Ralf Keidel; Sebastian Bablok; Eric Sean Conner (Scientific report / Gesellschaft für Schwerionenforschung, Darmstadt[Elektronische Ressource], 2009)
The Front-End-Device - Application Programming Interface (FED-API)[1] has been designed and developed to supervise and control FED with versatile programming interfaces to support different detector systems while reducing the amount of data per time unit up to a distinct level to prevent the Process Visualization System from malfunctioning.

ALICE electromagnetic calorimeter technical design report - P. Cortese; G. Dellacasa; Ralf Keidel; Sebastian Bablok (2008)
ALICE (A Large Ion Collider Experiment) at the LHC contains a wide array of detector systems for measuring hadrons, leptons, and photons. ALICE is designed to carry out comprehensive measurements of high energy nucleusnucleus collisions, in order to study QCD matter under extreme conditions and to study the phase transition between conned matter and the Quark-Gluon Plasma (QGP). Discussion of the full ALICE physics program can be found in [1, 2]. The interaction and energy loss of high energy partons in matter provides a sensitive tomographic probe of the medium generated in high energy nuclear collisions (jet quenching) [36]. Jet quenching measurements have played a key role at the Relativistic Heavy Ion Collider (RHIC) [710] and will be central to the study of nuclear collisions at the LHC. This Technical Design Report describes a large acceptance Electromagnetic Calorimeter (EMCal) that will be installed in the ALICE central detector. The EMCal enhances ALICE's capabilities for jet quenching measurements. The addition of the EMCal enables triggering on high energy jets, reduces signicantly the measurement bias for jet quenching studies, improves jet energy resolution, and augments existing ALICE capabilities to measure high momentum photons and electrons. Combined with ALICE's excellent capabilities to track and identify particles from very low pt to high pt the EMCal enables an extensive study of jet quenching at the LHC.

NewOX - extending the Online eXam system to provide automated formative evaluation of student text-based assignments - Ralf Keidel; Heinz Dreher; Eric Sean Conner; Marc Wilhelm Küster (Kassel Univ. Press, 2008)
A cheat-resistant and foolproof distributed electronic application for summative assessment of student learning outcomes has been developed and field tested ?Online eXam?(OX). Good usability experience and feedback features for the students as well as the lecturers were design goals of the implementation. The field tests showed the robustness of the system in a heterogenic PC pool environment, the ease of use and a good student learning outcome assessment ability (summative assessment) but a lack of a formative impact on the student learning efforts. The incorporation and adoption (for European needs) of a short essay assessment algorithm with a rich user interface is proposed

The ALICE experiment at the CERN LHC - K. Aamodt; Ralf Keidel (Journal of instrumentation, 2008)
ALICE (A Large Ion Collider Experiment) is a general-purpose, heavy-ion detector at the CERN LHC which focuses on QCD, the strong-interaction sector of the Standard Model. It is designed to address the physics of strongly interacting matter and the quark-gluon plasma at extreme values of energy density and temperature in nucleus-nucleus collisions. Besides running with Pb ions, the physics programme includes collisions with lighter ions, lower energy running and dedicated proton-nucleus runs. ALICE will also take data with proton beams at the top LHC energy to collect reference data for the heavy-ion programme and to address several QCD topics for which ALICE is complementary to the other LHC detectors. The ALICE detector has been built by a collaboration including currently over 1000 physicists and engineers from 105 Institutes in 30 countries. Its overall dimensions are 16 × 16 × 26 m3 with a total weight of approximately 10 000 t. The experiment consists of 18 different detector systems each with its own specific technology choice and design constraints, driven both by the physics requirements and the experimental conditions expected at LHC. The most stringent design constraint is to cope with the extreme particle multiplicity anticipated in central Pb-Pb collisions. The different subsystems were optimized to provide high-momentum resolution as well as excellent Particle Identification (PID) over a broad range in momentum, up to the highest multiplicities predicted for LHC. This will allow for comprehensive studies of hadrons, electrons, muons, and photons produced in the collision of heavy nuclei. Most detector systems are scheduled to be installed and ready for data taking by mid-2008 when the LHC is scheduled to start operation, with the exception of parts of the Photon Spectrometer (PHOS), Transition Radiation Detector (TRD) and Electro Magnetic Calorimeter (EMCal). These detectors will be completed for the high-luminosity ion run expected in 2010. This paper describes in detail the detector components as installed for the first data taking in the summer of 2008.

ALICE : physics performance report, volume II - B. Alessandro (Journal of physics. G, nuclear and particle physics, 2006)
ALICE is a general-purpose heavy-ion experiment designed to study the physics of strongly interacting matter and the quark-gluon plasma in nucleus-nucleus collisions at the LHC. It currently involves more than 900 physicists and senior engineers, from both the nuclear and high-energy physics sectors, from over 90 institutions in about 30 countries. The ALICE detector is designed to cope with the highest particle multiplicities above those anticipated for Pb-Pb collisions (dNch/dy up to 8000) and it will be operational at the start-up of the LHC. In addition to heavy systems, the ALICE Collaboration will study collisions of lower-mass ions, which are a means of varying the energy density, and protons (both pp and pA), which primarily provide reference data for the nucleus-nucleus collisions. In addition, the pp data will allow for a number of genuine pp physics studies. The detailed design of the different detector systems has been laid down in a number of Technical Design Reports issued between mid-1998 and the end of 2004. The experiment is currently under construction and will be ready for data taking with both proton and heavy-ion beams at the start-up of the LHC. Since the comprehensive information on detector and physics performance was last published in the ALICE Technical Proposal in 1996, the detector, as well as simulation, reconstruction and analysis software have undergone significant development. The Physics Performance Report (PPR) provides an updated and comprehensive summary of the performance of the various ALICE subsystems, including updates to the Technical Design Reports, as appropriate. The PPR is divided into two volumes. Volume I, published in 2004 (CERN/LHCC 2003-049, ALICE Collaboration 2004 J. Phys. G: Nucl. Part. Phys. 30 1517-1763), contains in four chapters a short theoretical overview and an extensive reference list concerning the physics topics of interest to ALICE, the experimental conditions at the LHC, a short summary and update of the subsystem designs, and a description of the offline framework and Monte Carlo event generators. The present volume, Volume II, contains the majority of the information relevant to the physics performance in proton-proton, proton-nucleus, and nucleus-nucleus collisions. Following an introductory overview, Chapter 5 describes the combined detector performance and the event reconstruction procedures, based on detailed simulations of the individual subsystems. Chapter 6 describes the analysis and physics reach for a representative sample of physics observables, from global event characteristics to hard processes.

Front-end-electronics communication software for multiple detectors in the ALICE experiment - Sebastian Bablok; Eric Sean Conner; G. Hartung; Ralf Keidel; C. Kofler; T. Krawutschke; V. Lindenstruth; D. Röhrich (Nuclear instruments and methods in physics research : A, Accelerators, spectrometers, detectors and associated equipment, 2006)
In the ALICE experiment at CERN, the Detector Control System (DCS) employs several interacting software components to accomplish its task of ensuring the correct operation and monitoring of the experiment. This paper describes the Front-End-Electronics Communication (FeeCommunication) software and its role within the DCS. The FeeCommunication software's central task is passing configuration and monitoring data between the top level DCS process control and the field devices of several detectors within ALICE. The lowest level of the FeeCommunication software runs on the DCS boards, specialized embedded systems which are in direct contact with the field devices and are physically located within the detector. The middle and upper layers run on standard PC hardware located in the counting room or other external locations. This paper focuses on the design and implementation of the FeeCommunication software and the steps that were taken to fulfill the imposed reliability and performance requirements, specifically those related to safe operation in environments exposed to radiation and magnetic fields.

The control system for the front-end electronics of the ALICE time projection chamber - M. Richter; J. Alme; S. Bablok; R. Campagnolo; U. Frankenfeld; C. G. Gutierrez; Ralf Keidel; Ch. Kofler; T. Krawutschke; D. Larsen; V. Lindenstruth; B. Mota; et al. (IEEE transactions on nuclear science : NS ; a publication of the IEEE Nuclear and Plasma Sciences Society, 2006)
The ALICE detector is a dedicated heavy-ion detector currently built at the Large Hadron Collider (LHC) at CERN. The detector control system (DCS) covers the task of controlling, configuring and monitoring the detector. One sub-system is the control system for the Front-end electronics of the time projection chamber (TPC). It controls in total 216 readout systems with 4356 Front-End Cards serving roughly 560 000 channels. The system consists of a large number of distributed nodes in a layer-structured hierarchy. The low-level node controlling the Front-end electronics is an embedded computer system, the DCS board, which provides the opportunity to run a light-weight Linux system on the card. The board interfaces to the Front-end electronics via a dedicated hardware interface and connects to the higher DCS-layers via the DIM communication framework over Ethernet. Since the experiment will be running in a radiation environment, fault tolerance, error correction and system stability in general are major concerns. Already the low level devices carry out intelligent error handling and act automatically upon several conditions. This paper presents the architecture of the system, the application of the DCS board and experiences from integration tests.

A Distributed, Heterogeneous Control System for the ALICE TPC Electronics - J. Alme; M. Richter; R. Keidel; D. Larsen; D. Rohrich; K. Ullaland; K. Roed; S. Bablok; Ch. Kofler; T. Krawutschke; T. Alt; D. Gottschalk; et al. (IEEE, 2005)
The ALICE detector is a dedicated heavy-ion detector currently built at the large hadron collider (LHC) at CERN. The detector consists of several sub-detectors each of them forming a highly complex device. The detector control system (DCS) covers the task of controlling, configuring and monitoring of the detector system. Since the experiment was running in a radiation environment, fault tolerance, error correction and system stability in general are major concerns. A system consisting of independently running layers has been designed, the functionality layers are running on a large number of nodes and sub-nodes. An autonomous single-board computer, the DCS board, has been developed which allows one to run the operating system Linux in an embedded environment and to perform tasks related to the hardware devices. Further custom hardware devices have been developed covering specific tasks and serving as sub-nodes. These devices together with standard computers in higher control layers form a distributed control system. This article focused on the concept and architecture of the DCS for the front-end electronics of the time-projection chamber (TPC) and present results and experiences from system integration tests.

Communication Software for the ALICE TPC Front-End Electronics - M. Richter; Ralf Keidel; Sebastian Bablok; Christian Kofler (2005)
The ALICE Time Projection Chamber (TPC) is read out by 4356 Front-End Cards serving roughly 560000 channels. Each channel has to be congured and monitored individually. As one part of the overall controlling of the detector this task is covered by the Detector Control System (DCS). Since fault tolerance, error correction and system stability in general are major concerns, a system consisting of independently running layers has been designed. The functionality layers are running on a large number of nodes and sub-nodes. The low-level node controlling the Front-End Electronics is an embedded computer system, the DCS board, which provides the opportunity to run a light-weight Linux system on the card. The board interfaces to the front-end electronics via a dedicated hardware interface and connects to the higher DCS-layers via the DIM communication framework over Ethernet. This article presents the structure of the communication software and the application of the DCS board.

ALICE technical design report on forward detectors: FMD, T0 and V0 - P. Cortese; R. Keidel; E. S. Conner; G. Dellacasa (2004)
The initial concept of ALICE as defined in the Technical Proposal [1] mentions a set of MicroChannel Plate (MCP) detectors as the preferred solution to providing the Level 0 trigger and multiplicity information in the forward/backward regions (|h| > 1.5). The MCP option would have been a novel and elegant way to build a forward detector system, but it was realized that it would have required substantial funds and a major R&D effort and that, the desired functionality could be achieved with existing and proved technologies based on Cherenkov radiators, scintillators, and Si-strip detectors. This led to the division into the T0, the V0 and the FMD, for convenience named the Forward Detectors (FWD). These systems provide different functionalities, but also to some extent functional overlap and complementarity, which is considered an advantage for ALICE.Since then, work on the three sub-detectors has proceeded independently, although on issues such as integration, electronics, simulations, etc. there has always been good co-operation between the relevant detectors. Therefore, recognizing the common roots and the physical proximity of the modules and anticipating even closer collaboration in the future, it was decided to submit a joint Technical Design Report on the Forward Detectors (FMD, T0 and V0 TDR).

ALICE: Physics performance report, volume I. - Ralf Keidel; Eric Sean Conner; F. Carminati; P. Foka (Journal of Physics G: Nuclear and Particle Physics, 2004)
The possibility of colliding heavy nuclei with high luminosity at the Large Hadron Collider,expected to start operating in 2007 at CERN, offers a unique opportunity to investigate the behaviour of strongly interacting matter under extreme conditions of compression and heating. This will allow unprecedented tests of our understanding of equilibration processes and equilibrium states in Quantum Chromo-Dynamics (QCD), the fundamental theory of strong interactions. In particular, equilibrium QCD predicts that a phase transition to a plasma of deconfined partons, (the Quark-Gluon Plasma, or QGP), occurs at a critical energy density which is within experimental reach. Measurements at the LHC will probe extensively the properties of the bulk partonic matter produced in nucleus-nucleus collisions. The ALICE experiment—presently under construction is the only LHC experiment designed specifically for the study of nucleus-nucleus collisions.

Charged particle production in proton, deuteron, oxygen and sulphur nucleus collisions at 200-GeV per nucleon - T. Alber; Ralf Keidel (The European Physical Journal C - Particles and Fields, 1998)
The transverse momentum and rapidity distributions of net protons and negatively charged hadrons have been measured for minimum bias proton-nucleus and deuteron-gold interactions, as well as central oxygen-gold and sulphur-nucleus collisions at 200 GeV per nucleon. The rapidity density of net protons at midrapidity in central nucleus-nucleus collisions increases both with target mass for sulphur projectiles and with the projectile mass for a gold target. The shape of the rapidity distributions of net protons forward of midrapidity for d+Au and central S+Au collisions is similar. The average rapidity loss is larger than 2 units of rapidity for reactions with the gold target. The transverse momentum spectra of net protons for all reactions can be described by a thermal distribution with ‘temperatures’ between MeV (p+S interactions) and MeV (central S+Au collisions). The multiplicity of negatively charged hadrons increases with the mass of the colliding system. The shape of the transverse momentum spectra of negatively charged hadrons changes from minimum bias p+p and p+S interactions to p+Au and central nucleus-nucleus collisions. The mean transverse momentum is almost constant in the vicinity of midrapidity and shows little variation with the target and projectile masses. The average number of produced negatively charged hadrons per participant baryon increases slightly from p+p, p+A to central S+S,Ag collisions.

Image data analysis for the NA35 streamer chamber - D. Brinkmann; Ralf Keidel (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 1995)
In the collision of relativistic heavy ions with nuclear targets at the CERN SPS up to several hundred charged particles in the momentum range of 0.1-200 GeV/c are produced. These events have been recorded on film by the NA35 streamer chamber. A computer environment for the analysis of this data was developed and became operational at the University of Frankfurt. This Frankfurt Image Processing System (FIPS) is a modular und distributed system allowing the application of image processing and image understanding techniques to digitized streamer chamber images as well as the interactive computer-assisted measurement of photographic streamer chamber pictures on traditional film projection tables. Automatic track reconstruction software has been developed which in turn utilizes a multitude of image processing and image understanding techniques. The efficiency of the pattern recognition and track reconstruction processes is greater than 95% with a very good momentum resolution dP/P = ”(0.0009P)2 + (0.0018)2. So far about 20 000 of these events have been processed. Currently approximately 50 events per day are automatically analysed.

An Investigation of intermittency in proton - gold, oxygen - gold, sulfur - gold and sulfur-sulfur interactions at 200-GeV per nucleon - J. Baechler; Ralf Keidel (Zeitschrift für Physik C Particles and Fields, 1994)
The intermittency phenomenon is investigated in proton-gold, oxygen-gold, sulphur-gold and sulphur-sulphur collisions at 200 GeV per nucleon. The data were taken with the NA 35 streamer chamber detector at the CERN SPS. The data samples are carefully corrected for double counting of tracks and for contamination from photon conversions, particle decays and secondary interactions. The analysis is carried out in terms of factorial moments, using a new definition, and of correlation integrals. Both methods show the presence of nonstatistical fluctuations (ldquointermittencyrdquo). The main conclusions are: The observation of the effect for pairs of hadrons with negative charges and its near absence for pairs of opposite charges is consistent with the assumption that Bose-Einstein correlations yield the dominant contribution. The ldquointermittencyrdquo effect is not proportional to (dn/dy)-1 which would be expected in superposition models. The measured relation between the second and third factorial moment for negative hadrons indicates that genuine 3-particle correlations are small. The predictions of a Monte Carlo simulation which is based on the Lund Fritiof model with the inclusion of Bose-Einstein correlations agree with the experimental results.

Study of particle spectra with an optically readout RICH detector in the NA35 experiment - J. Baechler; Ralf Keidel (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 1994)
The first identified particle spectra obtained with a proximity focusing RICH detector using an optical readout in the high particle density environment of heavy ion collisions at ultrarelativistic energies are presented. The rapidity and transverse momentum spectra of identified pions, kaons, and protons measured in the reaction S—Au at 200 GeV/nucleon are shown and compared with the predictions of two event generators (Fritiof and VENUS).

Charged particle spectra in central S + S collisions at 200-GeV/c per nucleon. - J. Baechler; Ralf Keidel (Physical Review Letters, 1993)
The transverse momentum and rapidity distributions of negative hadrons and participant protons have been measured for central 32S+ 32S collisions at plab=200 GeV/c per nucleon. The proton mean rapidity shift 〈Δy〉∼1.6 and mean transverse momentum 〈pT〉∼0.6 GeV/c are much higher than in pp or peripheral AA collisions and indicate an increase in the nuclear stopping power. All pT spectra exhibit similar source temperatures. Including previous results for Ks0 Λ, and Λ¯, we account for all important contributions to particle production.

Multiplicity distributions in small phase space domains in central nucleus-nucleus collisions - J. Baechler; Ralf Keidel (Zeitschrift für Physik C Particles and Fields, 1993)
Multiplicity distributions of negatively charged particles have been studied in restricted phase space intervals for central S+S, O+Au and S+Au collisions at 200 GeV/nucleon. It is shown that multiplicity distributions are well described by a negative binomial form irrespectively of the size and dimensionality of phase space domain. A clan structure analysis reveals interesting similarities between complex nuclear collisions and a simple partonic shower. The lognormal distribution agrees reasonably well with the multiplicity data in large domains, but fails in the case of small intervals. No universal scaling function was found to describe the shape of multiplicity distributions in phase space intervals of varying size

Production of charged kaons in proton - nucleus and nucleus-nucleus collisions at 200-GeV/Nucleon - J. Baechler; Ralf Keidel (Zeitschrift für Physik C Particles and Fields, 1993)
Production of charged kaons in proton-sulphur, proton-gold, sulphur-sulphur and oxygen-gold collisions at 200 GeV/nucleon has been studied in the NA35 Streamer Chamber experiment. Rapidity and transverse mass distributions as well as mean multiplicities were obtained. The results are compared with nucleon-nucleon data and with model predictions.

Fluctuations of multiplicities in rapidity windows in sulphur-sulphur collisions at 200A GeV - J. Bächler; J. Bartke; H. Białkowska; R. Bock; R. Brockmann; P. Buncic; S. I. Chase; I. Derado; V. Eckardt; J. Eschke; D. Ferenc; B. Fleischmann; et al. (Zeitschrift für Physik C Particles and Fields, 1992)
Multiplicity distributions and their second moments fornegatively charged particles produced in32S-S central and minimum bias interactions at 200A GeV are studied in various rapidity intervals. Fritiof and Venus models mostly describe the dependence of second moments on rapidity intervals in minimum bias interactions, but not in central collisions. For central collisions the behaviour of second moments might indicate enhanced multiplicity fluctuations.

Pion interferometry in ultrarelativistic nuclear collisions - D. Ferenc; Ralf Keidel (Nuclear Physics A, 1992)
Pion interferometry is the unique tool to study the space-time evolution of the systems created in the ultrarelativistic nuclear collisions. Five different data sets have been analyzed in terms of cylindrical coordinates, and all yield consistent results. We conclude that the system expands longitudinally, the decoupling proper time is not, vert, similar5 fm/c, the duration of particle emission is very short <2 fm/c, and the transverse decoupling size is 1.5 to 2 times larger than the one corresponding to the collision geometry. That gives a causally consistent space-time evolution picture.

Production of charged kaons in central S + S and O + Au collisions at 200-GeV/nucleon - Marek Kowalski; Ralf Keidel (Nuclear Physics A, 1992)
Product of charged kaons in central S + S and O + Au collisions at 200 GeV/nucleon has been studied in the NA 35 Streamer Chamber experiment. Mean multiplicities and transverse mass distributions were obtained. They were compared with nucleon-nucleon data and with model predictions.

Recent results from experiment NA35 - P. Seyboth; Ralf Keidel (Nuclear Physics A, 1992)
Enhanced strange particle production, nonstatistical multiplicity fluctuations and two- pion Bose-Einstein correlations were measured in 0, S-nucleus reactions at 60 and 200 GeV/nucleon . The results indicate significant collective effects in high-energy nucleus- nucleus collisions.

Bose Einstein correlations in ultrarelativistic heavy ion collisions - J. Baechler; Ralf Keidel (Nuclear Physics A, 1991)
Results from the analysis of Bose-Einstein correlations of negative pions produced in central collisions of S + S, S + Ag, S + Au and O + Au at 200 GeV/N in a wide rapidity range 0.5 < y < 4.0 are presented. At mid-rapidity a transverse source size significantly larger than the projectile radius is observed in central S + Ag and O + Au collisions. A strong dependence of transverse and longitudinal sizes with rapidity, rapidity density and total multiplicity is observed. For S + S and S + Au the midrapidity correlation functions can not be fitted with a Gaussian parametrization.

Charged particle multiplicities in nuclear collisions at 200-GeV/N - J. Baechler; Ralf Keidel (Zeitschrift für Physik C Particles and Fields, 1991)
Data on multiplicities of charged particles produced in proton-nucleus and nucleus-nucleus collisions at 200 GeV per nucleon are presented. It is shown that the mean multiplicity of negative particles is proportional to the mean number of nucleons participating in the collision both for nucleus-nucleus and proton-nucleus collisions. The apparent consistency of pion multiplicity data with the assumption of an incoherent superposition of nucleon-nucleon collisions is critically discussed.

Pion and proton spectra in S-32 + S collisions at 200-GeV/nucleon - J. Baechler; Ralf Keidel (Nuclear Physics A, 1991)
Rapidity spectra of pions and participant protons in S + S collisions at 200 GeV/nucleon are compared with N + N data. The average energy loss of the participating nucleons increases by 23% and is balanced by the energy of the final state particles, through a twofold increase of strange particle production and a similar enhancement, assumed for baryon-antibaryon pairs.

Proton rapidity distributions from 60-GeV/n O-16 + Au collisions - S. R. Tonse; Ralf Keidel (Nuclear Physics A, 1991)
An analysis of the proton rapidity distribution in central 160+Au collisions at 60 GeV/n measured in the NA35 streamer chamber detector at the CERN SPS is presented. The charge excess of positive particles over negative particles was measured. The rapidity distribution of the charge excess which can be associated with the primordial protons in the collision is studied in terms of the nuclear stopping power and is compared to the predictions of various models.

Strangeness enhancement in central S + S collisions at 200-GeV/nucleon - J. Baechler; Ralf Keidel (Nuclear Physics A, 1991)
Neutral strange particle production was studied in S + 5 collisions at the CERN SPS energy of 200 GeV/nucleon. The NA35 Streamer Chamber was run with both a minimum bias and a central collision trigger: data for p + S were also taken. We obtained 1 i mean multiplicities for b, x and Kz in full phase space, as well as the distributions in rapidity y and transverse momentum PT. Simi- lar data for negative hadrons and participating protons were obtained in the same experiment.

Study of the energy flow in sulphur and oxygen nucleus collisions at 60-GeV/nucleon and 200-Gev/nucleon - J. Baechler; Ralf Keidel (Zeit Zeitschrift für Physik C Particles and Fields, 1991)
We report on a systematic study of midrapidity transverse energy production and forward energy flow in interactions of 160 and 32S projectiles with S, Cu, Ag and Au targets at 60 and 200 GeV/nucleon. The vari- ation of the shape of the Er distributions with target and projectile mass can be understood from collision geometry. Average Er values determined for central col- lisions show an increasing stopping power for heavier target nuclei. A higher relative stopping is observed at 60 GeV/nucleon than at 200 GeV/nucleon. Bjorken esti- mates of the energy density reach approximately 3 GeV/fm3 in high Er events at 200 GeV/nucleon with 160 and 32Sprojectiles. The systematics of the data and the shapes of Er and pseudorapidity distributions are well described by the Lund model Fritiof.

Neutral strange particle production in sulphur sulphur and proton sulphur collisions at 200-GeV/nucleon - J. Bartke; Ralf Keidel (Zeitschrift für Physik C Particles and Fields, 1990)
The production of A, A and Ks has been stud- ied in 200 GeV/nucleon p + S and S + S collisions in the streamer chamber of the NA35 experiment at the CERN SPS. Significant enhancement of the multiplicities of all observed strange particles relative to negative hadrons was observed in central S+S collisions, as compared to p+p and p+S collisions. The latter collisions show no overall (relative) strangeness enhancement over p + p, but the rapidity distributions and hadron multiplicities indicate some secondary cascading production of A par- ticles in the p + S and p + Au collisions. The A polariza- tion in central S+ S collisions was found to be compati- ble with zero up to Pr = 2 GeV/c.

A study of K0(S), Lambda and Anti-Lambda production in 60 and 200 GeV per nucleon OAu and pAu collisions with a streamer chamber detector at the CERN SPS - A. Bamberger; Ralf Keidel (Zeitschrift für Physik C Particles and Fields, 1989)
The production of neutral strange particlesK s o , Λ and Λ has been studied in 60 and 200 GeV per nucleon OAu and pAu collisions with the streamer chamber vertex spectrometer of the NA35 experiment at the CERN-SPS accelerator. Ratios of neutral strange particle production to negatively charged particle production in selected regions of phase space were measured to be the same in OAu and pAu reactions. The rates of strange particle production in central OAu collisions are about a factor of 16 higher than in pAu collisions when compared in the same regions of phase space. If an enhancement of strange particle production in OAu collisions relative to pAu collisions is considered to be a signature for quark-gluon plasma formation, no evidence supporting it is observed. The experimental results are compared to the Lund FRITIOF model.

Large Acceptance Hadron And Photon Detector For An Investigation Of Pb Induced Reactions At The Cern Sps. - R. Keidel; A. Karabarbounis; A. Panagiotou; A. Petridis (1989)

Memorandum To The Spsc Committee Proposing The Addition Of A Downstream Tpc To The Na35 Apparatus For The 1990 Data Taking Period - R. Keidel; J. Baechler; J. Bartke; H. Bialkowska (1989)

Neutral Strange Particle Production In S S Collisions At 200-Gev/Nucleon - Marek Gazdzicki; Ralf Keidel (Nuclear Physics A, 1989)
High energy nucleus-nucleus collisions offer a unique possibi- lity to study properties of large systems containing strongly in- teracting particles at high energy densities. Such a system, crea- ted during the first stage of the collision expands, covering hundreds of fm3 and has a life-time proportional to the characte- ristic transverse dimension of the system. It is reasonable to expect that an increased volume, life time and energy density will lead to a higher level of equilibration and therefore result in a change of the final state.

Recent Results From The Na35 Collaboration At Cern - John W. Harris; Ralf Keidel (Nuclear Physics A, 1989)
Recent results from the NA35 Collaboration are presented for the reactions of 60 and 200 GeV/nucleon p and 16O, and 200 GeV/nucleon 32S with various targets ranging from S to Au. Midrapidity transverse energy distributions and forward energy flow, pperpendicular spectra and rapidity distributions of hadrons are presented. Two-pion interferometry results are discussed. Neutral strange particle yields and pperpendicular distributions are presented. Conclusions are drawn from the experimental results.

Charged Particle Multiplicities And Interaction Cross-Sections In High-Energy Nuclear Collisions - A. Bamberger; Ralf Keidel (Physics Letters B, 1988)
Inelastic cross sections at 60 and 200 GeV/nucleon are determined in a streamer chamber for 160 o n several nuclear targets. Charged particle multiplicity distributions for inelastic and central collisions are studied and compared with theoretical predic- tions. The inelastic cross sections exhibit a geometrical dependence on nuclear radii. The multiplicity data are governed by the collisiongeometry. They are consistent with a picture of superposition of independent nucleon-nucleus interactions.

Charged particle spectra in nucleus-nucleus collisions at CERN energies. - H. Strobele; A. Bamberger; R. Keidel; J. Bartke; H. Bialkowska (1988)

First Results On Strangeness Production In 60-Gev/Nucleon And 200-Gev/Nucleon Heavy Ion Reactions From The Na35 Streamer Chamber - G. Vesztergombi; Ralf Keidel (Zeitschrift für Physik C Particles and Fields, 1988)
We present the first preliminary results on A, Ks and Z production on a gold target with proton and oxygen beams in the NA35 streamer chamber.

Negative Particle Production in Nuclear Collisions at 60-GeV/Nucleon and 200-GeV/Nucleon - H. Strobele; Ralf Keidel (Zeitschrift für Physik C Particles and Fields, 1988)
The results on spectra of negative particles produced in16O+Au andp-Au collisions at 200 GeV/nucleon and16O+Au at 60 GeV/nucleon are presented. The correlations of average rapidity and average transverse momentum with event multiplicity are studied. Spectral shapes are similar for central16O+Au andp-Au collisions. The transverse momentum and rapidity distributions for central16O+Au andp-Au collisions differ strongly from corresponding distributions forp+p interactions. The FRITIOF model fails to describe the shapes of the transverse momentum distributions. The simple thermodynamical model of a single fireball does not fit the midrapidity transverse momentum distributions, and the rapidity distributions.

Pion Interferometry With Ultrarelativistic Heavy Ion Collisions From The Na35 Experiment - T. J. Humanic; Ralf Keidel (Zeitschrift für Physik C Particles and Fields, 1988)
Results from a pion interferometric analysis of the system 200 GeV/nucleon 160 + Au, central col- lisions, are reported. Both a Gaussian source model and a model based on the inside-outside cascade are used to fit to the experimental correlation function, giving transverse and longitudinal shape parameters, a freezeout time parameter, and a chaoticity parame- ter for the pion emitting source. We find a transverse source size consistent with the projectile radius except for a narrow rapidity window centered about the CM rapidity, where significantly larger transverse and lon- gitudinal sizes and a longer freezeout time are mea- sured suggesting a thermalized source. Calculation of freezeout energy densities and correlation lengths, a fit to a single-event correlation function, and compar- isons with other pion interferometry experiments are presented.

Probing The Space-Time Geometry Of Ultrarelativistic Heavy Ion Collisions - A. Bamberger; Ralf Keidel (Physics Letters B, 1988)
We report results from a pion interferometry analysis of 200 GeV/nucleon 60+Au collisions. Both a gaussian source model and a model based on the inside-outside cascade are used to fit the experimental correlation function, giving transverse and longitudinal shape parameters, a freeze-out time parameter, and a chaoticity parameter for the pion emitting source. We find a transverse source size consistent with the projectile radius except at the CM rapidity, where significantly larger transverse and longitudinal sizes and a longer freeze-out time are measured suggesting a thermalized source. Calculation of correlation lengths, and comparisons with a simple freeze-out model and other pion interferometry experiments are presented.

Results From Calorimeter And Charged Particle Measurements In O-16 And S-32 Nucleus Collisions At 200-gev And 60-gev Per Nucleon - K. Pretzl; P. Seyboth; R. Keidel; A. Bamberger (1988)

Study Of Relativistic Nucleus Nucleus Collisions : Na-35 Extension Request - A. Bamberger; J. Bartke; R. Keidel; H. Bialkowska (1988)

Study of the energy flow in16O-nucleus collisions at 60 and 200 GeV/nucleon - W. Heck; Ralf Keidel (Zeitschrift für Physik C Particles and Fields, 1988)
We report a systematic study of mid-rapidityE T production and forward energy flow in the interaction of16O projectiles on Al, Cu, Ag and Au at 60 and 200 GeV/nucleon. First results onE T production with32S projectiles are presented.

Track recognition in digitized streamer chamber pictures - Ralf Keidel; F. Pühlhofer; D. Röhrich (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 1988)
A method for recognizing particle tracks in photographic streamer chamber pictures was developed. The pictures were digitized by a high-resolution CCD camera and processed by a computer. After filtering track recognition was carried out in two steps: a “local” detection of straight track pieces in small sections of the image, followed by a “global” recognition of the complete track. All tracks were assumed to originate in a single, known interaction point and to be of circular shape. The procedure is demonstrated by means of streamer chamber data for high-energy nucleus-nucleus collisions obtained in the CERN experiment NA35.

Charged Particle Observables In O-16 Nucleus Collisions At 200-gev/nucleon And 60-gev/nucleon - S. Wenig; A. Bamberger; R. Keidel; D. Bangert (1987)

Event simulation in NA35 — Study of relativistic nucleus-nucleus collisions - A. Sandoval; A. Bamberger; Ralf Keidel; D. Bangert (Nuclear Physics A, 1987)
The NA35 experiment is a survey study of nucleus-nucleus collisions at the SPS energies of 60 to 200 GeV/A [l], [2]. It will investigate the stopping power of the nuclear medium by recording the energy/ momentum flux distrlbmions of the electromagnetic and hadronic fractions of the &al state, as well as the v- and T+ rapidity distributions. It will look for signatures of the quark - gluon plasma formation in the high energy density region created near mid-rapidity in violent head- on collisions. In this report we will describe how event simulations have been used in the pm-run stage of the experiment. For this we will describe tirst the experimental setup, then we will discuss what we have used for event generators and detector simulation pmcedures and finally we will present some of the cases in which event simulations have been used.

Multiplicity and transverse energy flux in 16O+Pb at 200 GeV per nucleon - A. Bamberger; Ralf Keidel (Physics Letters B, 1987)
First results from ultrarelativistic 16O+Pb collisions at 200 GeV/nucleon are presented. The transverse energy ET in average central collisions is ≈ 75 GeV for the interval 2.2less-than-or-equals, slantyless-than-or-equals, slant3.8. A 16-fold convolution of the inelastic p+Au transverse energy spectrum, also measured at 200 GeV, reproduces the mean ET of 16O+Pb. The amount of nuclear stopping power appears to be high.

Measurement of beauty-quark production in pp collisions at s = 13 TeV via non-prompt D mesons - S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics)

Signal shapes in multiwire proportional chamber-based TPCs - J. Alme; T. Alt; H. Appelshäuser; M. Arslandok; R. Averbeck; E. Bartsch; P. Becht; L. Bratrud; P. Braun-Munzinger; H. Buesching; H. Caines; P. Christiansen; et al. (Journal of Instrumentation)

Studying the interaction between charm and light-flavor mesons - Collaboration ALICE; S. Acharya; D. Adamová; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Physical Review D)